10-YEAR CLINICAL EVENTS AVOIDED IN DIABETIC AND CHRONIC KIDNEY DISEASE HYPERTENSION PATIENTS TREATED WITH RADIOFREQUENCY RENAL DENERVATION: PROJECTIONS BASED ON 3-YEAR DATA FROM THE GLOBAL SYMPLICITY REGISTRY - Schmieder, Roland; Cao, Khoa; Esler, Murray; Kandzari, David; Lobo, Melvin; Sharp, Andrew; Mancia, Giuseppe; Boehm, Michael; Pietzch, Jan (NEPHROLOGY DIALYSIS TRANSPLANTATION, 2022)
CRIS-Team WoS Importer:2022-07-22

12-Month Results From the Unblinded Phase of the RADIANCE-HTN SOLO Trial of Ultrasound Renal Denervation - Azizi, Michel; Daemen, Joost; Lobo, Melvin D.; Mahfoud, Felix; Sharp, Andrew S.P.; Schmieder, Roland; Wang, Yale; Saxena, Manish; Lurz, Philipp; Sayer, Jeremy; Bloch, Michael J.; Basile, Jan; et al. (Jacc-Cardiovascular Interventions, 2020)
Objectives: This study reports the 12-month results of the RADIANCE-HTN (A Study of the ReCor Medical Paradise System in Clinical Hypertension) SOLO trial following unblinding of patients at 6 months. Background: The blood pressure (BP)–lowering efficacy and safety of endovascular ultrasound renal denervation (RDN) in the absence (2 months) and presence (6 months) of antihypertensive medications were previously reported. Methods: Patients with daytime ambulatory BP ≥135/85 mm Hg after 4 weeks off medication were randomized to RDN (n = 74) or sham (n = 72) and maintained off medication for 2 months. A standardized medication escalation protocol was instituted between 2 and 5 months (blinded phase). Between 6 and 12 months (unblinded phase), patients received antihypertensive medications at physicians’ discretion. Outcomes at 12 months included medication burden, change in daytime ambulatory systolic BP (dASBP) and office or home systolic BP (SBP), visit-to-visit variability in SBP, and safety. Results: Sixty-five of 74 RDN patients and 67 of 72 sham patients had 12-month dASBP measurements. The proportion of patients on ≥2 medications (27.7% vs. 44.8%; p = 0.041), the number of medications (0 vs. 1.4; p = 0.015), and defined daily dose (1.4 vs. 2.2; p = 0.007) were less with RDN versus sham. The decrease in dASBP from baseline in the RDN group (−16.5 ± 12.9 mm Hg) remained stable at 12 months. The RDN versus sham adjusted difference at 12 months was −2.3 mm Hg (95% confidence interval [CI]: −5.9 to 1.3 mm Hg; p = 0.201) for dASBP, −6.3 mm Hg (95% CI: −11.1 to −1.5 mm Hg; p = 0.010) for office SBP, and −3.4 mm Hg (95% CI: −6.9 to 0.1 mm Hg; p = 0.062) for home SBP. Visit-to-visit variability in SBP was smaller in the RDN group. No renal artery injury was detected on computed tomographic or magnetic resonance angiography. Conclusions: Despite unblinding, the BP-lowering effect of RDN was maintained at 12 months with fewer prescribed medications compared with sham.
CRIS-Team Scopus Importer:2020-12-25
Keywords: blood pressure; hypertension; renal denervation; ultrasound; variability

1-Year outcomes of hypertension management in 13,000 outpatients under practice conditions: Prospective 3A registry - Zeymer, Uwe; Dechend, Ralf; Riemer, Thomas; Kaiser, Edelgard; Senges, Jochen; Pittrow, David; Schmieder, Roland (International Journal of Cardiology, 2014)
Current data on characteristics and outcomes of patients with high blood pressure (BP) managed under clinical practice conditions are limited.The 3A registry is an open, prospective observational cohort study in German primary care offices, with a 4:1:1 inclusion ratio to either aliskiren (ALIS), an ACE inhibitor/angiotensin receptor blocker (ACEI/ARB), or to an antihypertensive agent not affecting the renin angiotensin system (non-RAS). A nonlinear mixed regression model was used to assess BP changes during follow-up regarding different BP values at inclusion in the various groups. ClinicalTrial.gov identifier is NCT01454583. In the total cohort of 13,433 patients with 1-year follow-up results, the mean age of patients was 64.7years, 54% were men. Mean number of antihypertensive drugs was higher in the ALIS group compared to the other groups (3.0 drugs versus 2.5 in ACEI/ARB versus 1.6 in non-RAS; p<0.0001). Statistical regression analysis revealed baseline BP as the dominant covariate. After adjustment for baseline BP and 12 other confounders, no significant differences in BP reduction between the three groups were observed. The rate of major cardiac events (death, myocardial infarction, and stroke) was 1.3% in the total cohort, and did not differ across groups.ALIS at beginning of the observation was mostly used by the physicians in patients with higher BP at entry and in higher risk populations. By study end, in all groups, stringent BP lowering measures, usually with combination therapy, led to significant improvements; more than half of these at-risk patients reached the BP targets.
EVALuna2:3736

2013 ESH/ESC Practice Guidelines for the Management of Arterial Hypertension - Mancia, Giuseppe; Fagard, Robert; Narkiewicz, Krzysztof; Redon, Josep; Zanchetti, Alberto; Boehm, Michael; Christiaens, Thierry; Cifkova, Renata; De Backer, Guy; Dominiczak, Anna; Galderisi, Maurizio; Grobbee, Diederick E.; et al. (Blood Pressure, 2014)
EVALuna2:3731

2018 ESC/ESH Guidelines for the management of arterial hypertension - Williams, Bryan; Mancia, Giuseppe; Spiering, Wilko; Rosei, Enrico Agabiti; Azizi, Michel; Burnier, Michel; Clement, Denis L.; Coca, Antonio; De Simone, Giovanni; Dominiczak, Anna; Kahan, Thomas; Mahfoud, Felix; et al. (Kardiologia Polska, 2019)
EVALuna2:118632

2018 ESC/ESH Guidelines for the management of arterial hypertension: The Task Force for the management of arterial hypertension of the European Society of Cardiology and the European Society of Hypertension: The Task Force for the management of arterial hypertension of the European Society of Cardiology and the European Society of Hypertension - Williams, Bryan; Mancia, Giuseppe; Spiering, Wilko; Rosei, Enrico Agabiti; Azizi, Michel; Burnier, Michel; Clement, Denis L.; Coca, Antonio; De Simone, Giovanni; Dominiczak, Anna; Kahan, Thomas; Mahfoud, Felix; et al. (Journal of Hypertension, 2018)
: Document reviewers: Guy De Backer (ESC Review Co-ordinator) (Belgium), Anthony M. Heagerty (ESH Review Co-ordinator) (UK), Stefan Agewall (Norway), Murielle Bochud (Switzerland), Claudio Borghi (Italy), Pierre Boutouyrie (France), Jana Brguljan (Slovenia), Héctor Bueno (Spain), Enrico G. Caiani (Italy), Bo Carlberg (Sweden), Neil Chapman (UK), Renata Cifkova (Czech Republic), John G. F. Cleland (UK), Jean-Philippe Collet (France), Ioan Mircea Coman (Romania), Peter W. de Leeuw (The Netherlands), Victoria Delgado (The Netherlands), Paul Dendale (Belgium), Hans-Christoph Diener (Germany), Maria Dorobantu (Romania), Robert Fagard (Belgium), Csaba Farsang (Hungary), Marc Ferrini (France), Ian M. Graham (Ireland), Guido Grassi (Italy), Hermann Haller (Germany), F. D. Richard Hobbs (UK), Bojan Jelakovic (Croatia), Catriona Jennings (UK), Hugo A. Katus (Germany), Abraham A. Kroon (The Netherlands), Christophe Leclercq (France), Dragan Lovic (Serbia), Empar Lurbe (Spain), Athanasios J. Manolis (Greece), Theresa A. McDonagh (UK), Franz Messerli (Switzerland), Maria Lorenza Muiesan (Italy), Uwe Nixdorff (Germany), Michael Hecht Olsen (Denmark), Gianfranco Parati (Italy), Joep Perk (Sweden), Massimo Francesco Piepoli (Italy), Jorge Polonia (Portugal), Piotr Ponikowski (Poland), Dimitrios J. Richter (Greece), Stefano F. Rimoldi (Switzerland), Marco Roffi (Switzerland), Naveed Sattar (UK), Petar M. Seferovic (Serbia), Iain A. Simpson (UK), Miguel Sousa-Uva (Portugal), Alice V. Stanton (Ireland), Philippe van de Borne (Belgium), Panos Vardas (Greece), Massimo Volpe (Italy), Sven Wassmann (Germany), Stephan Windecker (Switzerland), Jose Luis Zamorano (Spain).The disclosure forms of all experts involved in the development of these Guidelines are available on the ESC website www.escardio.org/guidelines.
EVALuna2:35229

23Na magnetic resonance imaging-determined tissue sodium in healthy subjects and hypertensive patients - Kopp, Christoph; Linz, Peter; Dahlmann, Anke; Hammon, Matthias; Jantsch, Jonathan; Mueller, Dominik N.; Schmieder, Roland; Cavallaro, Alexander Josef; Eckardt, Kai-Uwe; Uder, Michael; Luft, Friedrich C.; Titze, Jens (Hypertension, 2013)
High dietary salt intake is associated with hypertension; the prevalence of salt-sensitive hypertension increases with age. We hypothesized that tissue Na might accumulate in hypertensive patients and that aging might be accompanied by Na deposition in tissue. We implemented Na magnetic resonance imaging to measure Na content of soft tissues in vivo earlier, but had not studied essential hypertension. We report on a cohort of 56 healthy control men and women, and 57 men and women with essential hypertension. The ages ranged from 22 to 90 years. Na magnetic resonance imaging measurements were made at the level of the calf. We observed age-dependent increases in Na content in muscle in men, whereas muscle Na content did not change with age in women. We estimated water content with conventional MRI and found no age-related increases in muscle water in men, despite remarkable Na accumulation, indicating water-free Na storage in muscle. With increasing age, there was Na deposition in the skin in both women and men; however, skin Na content remained lower in women. Similarly, this sex difference was found in skin water content, which was lower in women than in men. In contrast to muscle, increasing Na content was paralleled with increasing skin water content. When controlled for age, we found that patients with refractory hypertension had increased tissue Na content, compared with normotensive controls. These observations suggest that Na magnetic resonance imaging could have utility in assessing the role of tissue Na storage for cardiovascular morbidity and mortality in longitudinal studies. © 2013 American Heart Association, Inc.
CRIS-Team Scopus Importer:2023-03-08
Keywords: aging; gender difference; hypertension; salt; sodium MRI

3D-Visualization of Neurovascular Compression at the Ventrolateral Medulla in Patients with Arterial Hypertension - Manava, Panagiota; Naraghi, Ramin; Schmieder, Roland; Fahlbusch, Rudolf; Dörfler, Arnd; Lell, Michael M.; Buchfelder, Michael; Hastreiter, Peter (Clinical Neuroradiology, 2020)
Purpose: Controversy exists on the association of arterial hypertension (HTN) and neurovascular compression (NVC) at the ventrolateral medulla (VLM). No standardized and reproducible technique has been introduced yet for detection of NVC in HTN. This study aimed to generate, analyze and compare different results of exact reproducible anatomical 3D-representations of the VLM in patients with HTN, based on magnetic resonance imaging (MRI). Methods: A 3T scanner provided MRI (T2-constructive interference in steady state (CISS) high resolution imaging and three-dimensional Time-of-flight (3D-TOF) angiography) from the posterior fossa of 44 patients with clinical treatment-resistant HTN. Image processing consists of segmentation of the CISS data, registration and fusion of the CISS and TOF data and visualization. For each patient two 3D-visualizations (before and after fusion) were obtained. The reproduction quality of the vessels, flow-related signal variability and pulsation artifacts were analyzed and compared, using a ranking score. Results: Integrating vascular information from TOF into CISS data reduced artifacts in 3D-visualizations of exclusively processed CISS data. The quality of 3D-visualization of the vessels near the brain stem was significantly improved (p = 0.004). The results were reproducible and reliable. The quality of the 3D-presentations of neurovascular relationships at the VLM improved significantly (p < 0.001). Conclusion: The 3D-visualization of fused image data provides an excellent overview of the relationship between cranial nerves and vessels at the VLM and simplifies the detection of NVC in HTN. It provides a powerful tool for future clinical and scientific research. Although microvascular decompression (MVD) in treatment resistant HTN is not a standard procedure, it can be discussed in selected patients with intractable severe HTN.
CRIS-Team Scopus Importer:2020-06-05
Keywords: Cranial nerves; Image fusion; Image processing; MRI; Posterior fossa; Vascular compression disorders

Accuracy of Cuff-Measured Blood Pressure: Systematic Reviews and Meta-Analyses - Picone, Dean S.; Schultz, Martin G.; Otahal, Petr; Aakhus, Svend; Al-Jumaily, Ahmed M.; Black, J. Andrew; Bos, Willem J.; Chambers, John B.; Chen, Chen-Huan; Cheng, Hao-Min; Cremer, Antoine; Davies, Justin E.; et al. (Journal of the American College of Cardiology, 2017)
Hypertension (HTN) is the single greatest cardiovascular risk factor worldwide. HTN management is usually guided by brachial cuff blood pressure (BP), but questions have been raised regarding accuracy.This comprehensive analysis determined the accuracy of cuff BP and the consequent effect on BP classification compared with intra-arterial BP reference standards.Three individual participant data meta-analyses were conducted among studies (from the 1950s to 2016) that measured intra-arterial aortic BP, intra-arterial brachial BP, and cuff BP.A total of 74 studies with 3,073 participants were included. Intra-arterial brachial systolic blood pressure (SBP) was higher than aortic values (8.0 mm Hg; 95% confidence interval [CI]: 5.9 to 10.1 mm Hg; p < 0.0001) and intra-arterial brachial diastolic BP was lower than aortic values (-1.0 mm Hg; 95% CI: -2.0 to -0.1 mm Hg; p = 0.038). Cuff BP underestimated intra-arterial brachial SBP (-5.7 mm Hg; 95% CI: -8.0 to -3.5 mm Hg; p < 0.0001) but overestimated intra-arterial diastolic BP (5.5 mm Hg; 95% CI: 3.5 to 7.5 mm Hg; p < 0.0001). Cuff and intra-arterial aortic SBP showed a small mean difference (0.3 mm Hg; 95% CI: -1.5 to 2.1 mm Hg; p = 0.77) but poor agreement (mean absolute difference 8.0 mm Hg; 95% CI: 7.1 to 8.9 mm Hg). Concordance between BP classification using the Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure cuff BP (normal, pre-HTN, and HTN stages 1 and 2) compared with intra-arterial brachial BP was 60%, 50%, 53%, and 80%, and using intra-arterial aortic BP was 79%, 57%, 52%, and 76%, respectively. Using revised intra-arterial thresholds based on cuff BP percentile rank, concordance between BP classification using cuff BP compared with intra-arterial brachial BP was 71%, 66%, 52%, and 76%, and using intra-arterial aortic BP was 74%, 61%, 56%, and 65%, respectively.Cuff BP has variable accuracy for measuring either brachial or aortic intra-arterial BP, and this adversely influences correct BP classification. These findings indicate that stronger accuracy standards for BP devices may improve cardiovascular risk management.
EVALuna2:3961

Achieved blood pressure and cardiovascular outcomes in high-risk patients: results from ONTARGET and TRANSCEND trials - Boehm, Michael; Schumacher, Helmut; Teo, Koon K.; Lonn, Eva M.; Mahfoud, Felix; Mann, Johannes F. E.; Mancia, Giuseppe; Redon, Josep; Schmieder, Roland; Sliwa, Karen; Weber, Michael A.; Williams, Bryan; et al. (Lancet, 2017)
Studies have challenged the appropriateness of accepted blood pressure targets. We hypothesised that different levels of low blood pressure are associated with benefit for some, but harm for other outcomes.In this analysis, we assessed the previously reported outcome data from high-risk patients aged 55 years or older with a history of cardiovascular disease, 70% of whom had hypertension, from the ONTARGET and TRANSCEND trials investigating ramipril, telmisartan, and their combination, with a median follow-up of 56 months. Detailed descriptions of randomisation and intervention have already been reported. We analysed the associations between mean blood pressure achieved on treatment; prerandomisation baseline blood pressure; or time-updated blood pressure (last on treatment value before an event) on the composite outcome of cardiovascular death, myocardial infarction, stroke, and hospital admission for heart failure; the components of the composite outcome; and all-cause death. Analysis was done by Cox regression analysis, ANOVA, and ?(2). These trials were registered with ClinicalTrials.gov, number NCT00153101.Recruitment for ONTARGET took place between Dec 1, 2001, and July 31, 2008. TRANSCEND took place between Nov 1, 2001, and May 30, 2004. 30 937 patients were recruited from 733 centres in 40 countries and followed up for a median of 56 months. In ONTARGET, 25 127 patients known to be tolerant to angiotensin-converting-enzyme (ACE)-inhibitors were randomly assigned after a run-in period to oral ramipril 10 mg/day (n=8407), telmisartan 80 mg/day (n=8386), or the combination of both (n=8334). In TRANSCEND, 5810 patients who were intolerant to ACE-inhibitors were randomly assigned to oral telmisartan 80 mg/day (n=2903) or placebo (n=2907). Baseline systolic blood pressure (SBP) 140 mm Hg or higher was associated with greater incidence of all outcomes compared with 120 mm Hg to less than 140 mm Hg. By contrast, a baseline diastolic blood pressure (DBP) less than 70 mm Hg was associated with the highest risk for most outcomes compared with all DBP categories 70 mm Hg or more. In 4052 patients with SBP less than 120 mm Hg on treatment, the risk of the composite cardiovascular outcome (adjusted hazard ratio [HR] 1·14, 95% CI 1·03-1·26), cardiovascular death (1·29, 1·12-1·49), and all deaths (1·28, 1·15-1·42) were increased compared with those in whom SBP was 120-140 mm Hg during treatment (HR 1 for all outcomes, n=16099). No harm or benefit was observed for myocardial infarction, stroke, or hospital admission for heart failure. Mean achieved SBP more accurately predicted outcomes than baseline or time-updated SBP, and was associated with the lowest risk at approximately 130 mm Hg, and at 110-120 mm Hg risk increased for the combined outcome, cardiovascular death, and all-cause death except stroke. A mean DBP less than 70 mm Hg (n=5352) during treatment was associated with greater risk of the composite primary outcome (HR 1·31, 95% CI 1·20-1·42), myocardial infarction (1·55, 1·33-1·80), hospital admission for heart failure (1·59, 1·36-1·86) and all-cause death (1·16, 1·06-1·28) than a DBP 70-80 mm Hg (14 305). A pretreatment and mean on-treatment DBP of about 75 mm Hg was associated with the lowest risk.Mean achieved SBP less than 120 mm Hg during treatment was associated with increased risk of cardiovascular outcomes except for myocardial infarction and stroke. Similar patterns were observed for DBP less than 70 mm Hg, plus increased risk for myocardial infarction and hospital admission for heart failure. Very low blood pressure achieved on treatment was associated with increased risks of several cardiovascular disease events. These data suggest that the lowest blood pressure possible is not necessarily the optimal target for high-risk patients, although it is not possible to rule out some effect of reverse causality.Boehringer Ingelheim.
EVALuna2:3947

Achieved diastolic blood pressure and pulse pressure at target systolic blood pressure (120-140 mmHg) and cardiovascular outcomes in high-risk patients: results from ONTARGET and TRANSCEND trials - Boehm, Michael; Schumacher, Helmut; Teo, Koon K.; Lonn, Eva; Mahfoud, Felix; Mann, Johannes F. E.; Mancia, Giuseppe; Redon, Josep; Schmieder, Roland; Weber, Michael; Sliwa, Karen; Williams, Bryan; et al. (European Heart Journal, 2018)
Aims: Current guidelines of hypertensive management recommend upper limits for systolic (SBP) and diastolic blood pressure (DBP). J-curve associations of BP with risk exist for some outcomes suggesting that lower limits of DBP goals may also apply. We examined the association between mean attained DBP and cardiovascular (CV) outcomes in patients who achieved an on-treatment SBP in the range of 120 to <140 mmHg in the Ongoing Telmisartan Alone and in Combination with Ramipril Global Endpoint Trial (ONTARGET) and Telmisartan Randomized AssessmeNt Study in ACE iNtolerant participants with cardiovascular Disease (TRANSCEND) trials on patients with high CV risk. This SBP range was associated with the lowest CV risk. Methods: We analysed the outcome data from patients age 55 years or older with CV disease from the ONTARGET and TRANSCEND trials that randomized high-risk patients to ramipril, telmisartan, and the combination. In patients with controlled SBP (on-treatment 120 to <140 mmHg), the composite outcome of CV death, myocardial infarction, stroke and hospital admission for heart failure, the components thereof, and all-cause mortality were analysed according to mean on-treatment DBP as categorical (<70, 70 to <80, 80 to <90, and ≥90 mmHg) and continuous variable as well as the change of DBP according to baseline DBP. Pulse pressure (PP) was related to outcomes as a continuous variable. Results: In 16 099 of 31 546 patients, mean achieved SBP was 120 to <140 mmHg. The nominally lowest risk for all outcomes was observed at an achieved DBP of 70 to <80 mmHg. A higher achieved DBP was associated with a higher risk for the outcomes of stroke and of hospitalization for heart failure (≥80 mmHg) and myocardial infarction (≥90 mmHg). A lower achieved DBP (<70 mmHg) was associated with a higher risk for the primary outcome [hazard ratio (HR) 1.29, 95% confidence interval (95% CI) 1.15-1.45; P < 0.0001], myocardial infarction HR 1.54 (95% CI 1.26-1.88, P < 0.0001) and hospitalization for heart failure HR 1.81 (95% CI 1.47-2.24, P < 0.0001) and all-cause death (HR 1.19, 95% CI 1.04-1.35; P < 0.0001) while there was no signal for stroke and CV death compared to DBP 70 to <80 mmHg. A decrease of DBP was associated with lower risk when baseline DBP was >80 mmHg. The associations to outcomes were similar when patients were divided to SBP 120 to <130 mmHg or 130 to <140 mmHg for DBP or PP. Conclusion: Compared to a DBP of 70 to <80 mmHg, lower and higher DBP was associated with a higher risk in patients achieving a SBP of 120 to <140 mmHg. Associations of DBP and PP to risk were similar notably at controlled SBP. These data suggest at optimal achieved SBP, risk is still defined by low or high DBP. These findings support guidelines which take DBP at optimal SBP control into consideration.
EVALuna2:34232

Achievement of individualized treatment targets in patients with comorbid type-2 diabetes and hypertension: 6 months results of the DIALOGUE registry - Schmieder, Roland; Gitt, Anselm K.; Koch, Cornelia; Bramlage, Peter; Ouarrak, Taoufik; Tschoepe, Diethelm (BMC Endocrine Disorders, 2015)
Patients with type-2 diabetes mellitus (T2DM) and hypertension have increased risk of cardiovascular disease (CVD). We studied individualized treatment targets and their achievement in clinical practice.DIALOGUE is a prospective, multi-center registry in patients with both T2DM and hypertension.Patients (n = 6,586) had a baseline fasting glucose (8.5 ± 2.8 mmol/l), postprandial glucose (10.9 ± 3.4 mmol/l), and HbA1c (7.8 ± 2.1%) levels indicated poor glycemic control. Baseline systolic and diastolic BP were 140.3 ± 15.7 and 82.6 ± 9.5, respectively. Patients were categorized by HbA1c treatment goals: <=6.5% (strict), >6.5 to <=7.0% (medium), and >7.0 to <=7.5% (loose). When considering systolic BP (SBP) targets (<=130 mmHg [strict], >130 to <=135 mmHg [medium], and >135 to <=140 mmHg [loose]), patients with strict SBP treatment goals displayed similar characteristics to those with strict HbA1c targets. Although approximately 70% of patients received both strict HbA1c and SBP targeting, overall treatment goals remained unmet in all HbA1c target groups at the 6-month follow-up. SBP targets were not reached in the strict and medium groups, but were achieved in the loose treatment group. Specific predictors for choosing loose SBP or HbA1c treatment goals were identified, including SBP/HbA1c levels and various comorbidities.Individualized glucose and BP targets were selected by treating physicians based on patient characteristics and overall comorbidity. While treatment goals were not consistently met using various antidiabetic and antihypertensive therapies, our analyses indicated that the strictly targeted patient populations maintained lower overall HbA1c and SBP levels at 6 months.
EVALuna2:3759

Acute change in glomerular filtration rate with inhibition of the renin-angiotensin system does not predict subsequent renal and cardiovascular outcomes - Clase, Catherine M.; Barzilay, Joshua; Gao, Peggy; Smyth, Andrew; Schmieder, Roland; Tobe, Sheldon; Teo, Koon K.; Yusuf, Salim; Mann, Johannes (Kidney International, 2017)
Initiation of blockade of the renin-angiotensin system may cause an acute decrease in glomerular filtration rate (GFR): the prognostic significance of this is unknown. We did a post hoc analysis of patients with, or at risk for, vascular disease, in two randomized controlled trials: Ongoing Telmisartan Alone and in combination with Ramipril Global Endpoint Trial (ONTARGET) and the Telmisartan Randomized AssessmeNt Study in ACE iNtolerant participants with cardiovascular Disease (TRANSCEND), whose median follow-up was 56 months. In 9340 patients new to renin-angiotensin system blockade, who were then randomized to renin-angiotensin system blockade, a fall in GFR of 15% or more at 2 weeks after starting renin-angiotensin system blockade was seen in 1480 participants (16%), with persistence at 8 weeks in 700 (7%). Both acute increases and decreases in GFR after initiation of renin-angiotensin system blockade were associated with tendencies, mostly not statistically significant, to increased risk of cardiovascular outcomes, which occurred in 1280 participants, and of microalbuminuria, which occurred in 864. Analyses of creatinine-based outcomes were suggestive of regression to the mean. In more than 3000 patients randomized in TRANSCEND to telmisartan or placebo, there was no interaction between acute change in GFR and renal or cardiovascular benefit from telmisartan. Thus, both increases and decreases in GFR on initiation of renin-angiotensin system blockade are common, and may be weakly associated with increased risk of cardiovascular and renal outcomes. Changes do not predict increased benefit from therapy.
EVALuna2:3927

Adherence to Antihypertensive Medication in Treatment-Resistant Hypertension Undergoing Renal Denervation - Schmieder, Roland; Ott, Christian; Schmid, Andrea; Friedrich, Stefanie; Kistner, Iris; Ditting, Tilmann; Veelken, Roland; Uder, Michael; Toennes, Stefan W. (Journal of the American Heart Association, 2016)
Adherence to medication has been repeatedly proposed to represent a major cause of treatment-resistant hypertension (TRH); however, treatment decisions such as treating TRH with renal denervation depend on accurate judgment of adherence. We carefully analyzed adherence rates to medication before and after renal denervation and its effect on blood pressure (BP) control.Eighty patients with TRH were included in 2 prospective observational studies that assessed the difference of potential antihypertensive and nephroprotective effects of renal denervation. To compare prescribed with actual medication intake (representing a measure of adherence), we analyzed urine samples collected at baseline and at 6 months after renal denervation for antihypertensive compounds or metabolites (by liquid chromatography-mass spectrometry). In addition to office BP, 24-hour ambulatory BP and central hemodynamics (central systolic pressure, central pulse pressure) were assessed. Informed consent for analyses of urine metabolites was obtained from 79 of 80 patients. Actual intake of all antihypertensive drugs was detected at baseline and at 6 months after renal denervation in 44 (56%) and 52 (66%) patients, respectively; 1 drug was missing in 22 (28%) and 17 (22%) patients, respectively, and >=2 drugs were missing in 13 (16%) and 10 (13%) patients, respectively. At baseline, 24-hour ambulatory BP (P=0.049) and central systolic BP (P=0.012) were higher in nonadherent patients. Adherence did not significantly change overall (McNemar-Bowker test, P=0.362). An increase in adherence was observed in 21 patients, and a decrease was observed in 11 patients. The decrease in 24-hour ambulatory BP was not different in those with stable adherence 6 months after renal denervation (n=41, -7±13 mm Hg) compared with those with increased adherence (n=21, -10±13 mm Hg) and decreased adherence (n=11, -7±14 mm Hg) (P>0.20). Our study is limited by the relatively small sample size and potentially by the specific health environment of our university center (Northern Bavaria, Germany).Nonadherence to medication among patients with TRH was relatively low: ?1 of 6 patients with TRH did not take >=2 of the prescribed drugs. Adherence pattern did not change significantly after renal denervation and had no impact on the overall observed BP changes, supporting the concept that renal denervation is an effective treatment in patients with TRH.URL: https://www.clinicaltrials.gov. Unique identifiers: NCT00888433, NCT01442883 and NCT01687725.
EVALuna2:3842

A European Renal Association (ERA) synopsis for nephrology practice of the 2023 European Society of Hypertension (ESH) Guidelines for the Management of Arterial Hypertension - Sarafidis, Pantelis; Schmieder, Roland; Burnier, Michel; Persu, Alexandre; Januszewicz, Andrzej; Halimi, Jean Michel; Arici, Mustafa; Ortiz, Alberto; Wanner, Christoph; Mancia, Giuseppe; Kreutz, Reinhold (Nephrology Dialysis Transplantation, 2024)
In June 2023, the European Society of Hypertension (ESH) presented and published the new 2023 ESH Guidelines for the Management of Arterial Hypertension, a document that was endorsed by the European Renal Association (ERA). Following the evolution of evidence in recent years, several novel recommendations relevant to the management of hypertension in patients with chronic kidney disease (CKD) appeared in these Guidelines. These include recommendations for target office blood pressure (BP) <130/80 mmHg in most and against target office BP <120/70 mmHg in all patients with CKD; recommendations for use of spironolactone or chlorthalidone for patients with resistant hypertension with estimated glomerular filtration rate (eGFR) higher or lower than 30 mL/min/1.73 m2, respectively; use of a sodium-glucose cotransporter 2 inhibitor for patients with CKD and estimated eGFR ≥20 mL/min/1.73 m2; use of finerenone for patients with CKD, type 2 diabetes mellitus, albuminuria, eGFR ≥25 mL/min/1.73 m2 and serum potassium <5.0 mmol/L; and revascularization in patients with atherosclerotic renovascular disease and secondary hypertension or high-risk phenotypes if stenosis ≥70% is present. The present report is a synopsis of sections of the ESH Guidelines that are relevant to the daily clinical practice of nephrologists, prepared by experts from ESH and ERA. The sections summarized are those referring to the role of CKD in hypertension staging and cardiovascular risk stratification, the evaluation of hypertension-mediated kidney damage and the overall management of hypertension in patients with CKD.
CRIS-Team Scopus Importer:2024-06-14
Keywords: albuminuria; blood pressure; chronic kidney disease; hypertension; hypertensive kidney disease

Afferent neurons of the kidney with impaired firing pattern in inflammation – role of sodium currents? - Lale, Nena; Ditting, Tilmann; Hilgers, Karl Friedrich; Linz, Peter; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Rodionova, Kristina (Pflügers Archiv: European Journal of Physiology, 2023)
Peripheral neurons with renal afferents exhibit a predominantly tonic firing pattern of higher frequency that is reduced to low frequencies (phasic firing pattern) in renal inflammation. We wanted to test the hypothesis that the reduction in firing activity during inflammation is due to high-activity tonic neurons switching from higher to low frequencies depending on altered sodium currents. We identified and cultivated afferent sensory neurons with renal projections from the dorsal root ganglia (Th11-L2). Cultivated neurons were incubated with the chemokine CXCL1 (1,5 nmol/ml) for 12 h. We characterized neurons as “tonic,” i.e., sustained action potential (AP) firing, or “phasic,” i.e., < 5 APs upon stimulation in the current clamp. Their membrane currents were investigated in a voltage clamp. Data analyzed: renal vs. non-renal and tonic vs. phasic neurons. Renal afferent neurons exposed to CXCL1 showed a decrease in tonic firing pattern (CXCL1: 35,6% vs. control: 57%, P < 0.05). Na+ and K+ currents were not different between control renal and non-renal DRG neurons. Phasic neurons exhibited higher Na+ and K+ currents than tonic resulting in shorter APs (3.7 ± 0.3 vs. 6.1 ± 0.6 ms, P < 0.01). In neurons incubated with CXCL1, Na+ and K+ peak current density increased in phasic (Na+: − 969 ± 47 vs. − 758 ± 47 nA/pF, P < 0.01; K+: 707 ± 22 vs. 558 ± 31 nA/pF, P < 0.01), but were unchanged in tonic neurons. Phasic neurons exposed to CXCL1 showed a broader range of Na+ currents ([− 365– − 1429 nA] vs. [− 412– − 4273 nA]; P < 0.05) similar to tonic neurons. After CXCL1 exposure, significant changes in phasic neurons were observed in sodium activation/inactivation as well as a wider distribution of Na+ currents characteristic of tonic neurons. These findings indicate a subgroup of tonic neurons besides mere tonic or phasic neurons exists able to exhibit a phasic activity pattern under pathological conditions.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Chemokine; Firing pattern; Phasic; Renal afferent nerve; Sodium currents; Tonic; Voltage-gated sodium channels

AFFERENT PEPTIDERGIC NERVE FIBERS - IMPORTANCE FOR THE SALT METABOLISM BEYOND THE KIDNEYS? - Ditting, Tilmann; Rodionova, Kristina; Reeh, Peter; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Ott, Christianroland; Veelken, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Afferent renal innervation in anti-Thy1.1 nephritis in rats - Rodionova, Kristina; Veelken, Roland; Hilgers, Karl Friedrich; Paulus, Eva Maria; Linz, Peter; Fischer, Michael J.M.; Schenker, Martina; Reeh, Peter; Tiegs, Gisa; Ott, Christian; Schmieder, Roland; Schiffer, Mario; et al. (American Journal of Physiology-Renal Physiology, 2020)
Afferent renal nerves exhibit a dual function controlling central sympathetic outflow via afferent electrical activity and influencing intrarenal immunological processes by releasing peptides such as calcitonin gene-related peptide (CGRP). We tested the hypothesis that increased afferent and efferent renal nerve activity occur with augmented release of CGRP in anti-Thy1.1 nephritis, in which enhanced CGRP release exacerbates inflammation. Nephritis was induced in Sprague-Dawley rats by intravenous injection of OX-7 antibody (1.75 mg/kg), and animals were investigated neurophysiologically, electrophysiologically, and pathomorphologically 6 days later. Nephritic rats exhibited proteinuria (169.3 ± 10.2 mg/24 h) with increased efferent renal nerve activity (14.7 ± 0.9 bursts/s vs. control 11.5 ± 0.9 bursts/s, n = 11, P < 0.05). However, afferent renal nerve activity (in spikes/s) decreased in nephritis (8.0 ± 1.8 Hz vs. control 27.4 ± 4.1 Hz, n = 11, P < 0.05). In patch-clamp recordings, neurons with renal afferents from nephritic rats showed a lower frequency of high activity following electrical stimulation (43.4% vs. 66.4% in controls, P < 0.05). In vitro assays showed that renal tissue from nephritic rats exhibited increased CGRP release via spontaneous (14 ± 3 pg/mL vs. 6.8 ± 2.8 pg/ml in controls, n = 7, P < 0.05) and stimulated mechanisms. In nephritic animals, marked infiltration of macrophages in the interstitium (26 ± 4 cells/mm2) and glomeruli (3.7 ± 0.6 cells/glomerular cross-section) occurred. Pretreatment with the CGRP receptor antagonist CGRP8-37 reduced proteinuria, infiltration, and proliferation. In nephritic rats, it can be speculated that afferent renal nerves lose their ability to properly control efferent sympathetic nerve activity while influencing renal inflammation through increased CGRP release.
CRIS-Team Scopus Importer:2020-11-13
Keywords: afferent renal neerves; calcitonin gene-related peptide; renal inflammation; renal innervation; sympathetic innervation

AFFERENT RENAL NERVE PATHWAYS IN RATS - RESPONSIVENESS TO HIGH SALT INTAKE - Rodionova, Kristina; Ditting, Tilmann; Fahrmeier, Franziska; Ott, Chirstian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

A guide for easy- and difficult-to-treat hypertension - Schmieder, Roland; Volpe, Massimo; Waeber, Bernard; Ruilope, Luis M. (International Journal of Cardiology, 2014)
Although the blood pressure (BP) of many patients can be controlled using standard combinations, treatment of hypertension frequently represents a clinical challenge to the primary care physician. This article will review best practices for managing patients with easy- and difficult-to-treat hypertension, including preferred antihypertensive combinations, optimizing adherence and persistence, recognizing white-coat hypertension, and intensifying therapy for treatment-resistant patients. Each physician must decide based on his or her own level of experience at what point a patient becomes too challenging and would benefit from referral to a hypertension specialist for more intensive management and to complete the exclusion of secondary forms of arterial hypertension. With intensive pharmacotherapy, many patients with difficult-to-treat hypertension can achieve BP control. If it fails, interventional strategies (e.g., renal denervation) are a valid option to get BP controlled.
EVALuna2:3680

Alcohol-mediated renal denervation in patients with hypertension in the absence of antihypertensive medications - Pathak, Atul; Rudolph, Ulrike M.; Saxena, Manish; Zeller, Thomas; Müller-Ehmsen, Jochen; Lipsic, Erik; Schmieder, Roland; Sievert, Horst; Halbach, Marcel; Sharif, Faisal; Parise, Helen; Fischell, Tim A.; et al. (EuroIntervention, 2023)
BACKGROUND: Ultrasound and radiofrequency renal denervation (RDN) have been shown to safely lower blood pressure (BP) in hypertension. AIMS: The TARGET BP OFF-MED trial investigated the efficacy and safety of alcohol-mediated renal denervation (RDN) in the absence of antihypertensive medications. METHODS: This randomised, blinded, sham-controlled trial was conducted in 25 centres in Europe and the USA. Patients with a 24-hour systolic BP of 135-170 mmHg, an office systolic BP 140-180 mmHg and diastolic BP ≥90 mmHg on 0-2 antihypertensive medications were enrolled. The primary efficacy endpoint was the change in mean 24-hour systolic BP at 8 weeks. Safety endpoints included major adverse events up to 30 days. RESULTS: A total of 106 patients were randomised; the baseline mean office BP following medication washout was 159.4/100.4±10.9/7.0 mmHg (RDN) and 160.1/98.3±11.0/6.1 mmHg (sham), respectively. At 8 weeks post-procedure, the mean (±standard deviation) 24-hour systolic BP change was â2.9±7.4 mmHg (p=0.009) versus â1.4±8.6 mmHg (p=0.25) in the RDN and sham groups, respectively (mean between-group difference: 1.5 mmHg; p=0.27). There were no differences in safety events between groups. After 12 months of blinded follow-up, with medication escalation, patients achieved similar office systolic BP (RDN: 147.9±18.5 mmHg; sham: 147.8±15.1 mmHg; p=0.68) with a significantly lower medication burden in the RDN group (mean daily defined dose: 1.5±1.5 vs 2.3±1.7; p=0.017). CONCLUSIONS: In this trial, alcohol-mediated RDN was delivered safely but was not associated with significant BP differences between groups. Medication burden was lower in the RDN group up to 12 months.
CRIS-Team Scopus Importer:2023-09-29

Alcohol-Mediated Renal Denervation Using the Peregrine System Infusion Catheter for Treatment of Hypertension - Mahfoud, Felix; Renkin, Jean; Sievert, Horst; Bertog, Stefan; Ewen, Sebastian; Böhm, Michael; Lengelé, Jean Philippe; Wojakowski, Wojciech; Schmieder, Roland; van der Giet, Markus; Parise, Helen; Haratani, Nicole; et al. (Jacc-Cardiovascular Interventions, 2020)
Objectives: The aim of this multicenter, open-label trial was to evaluate the safety and efficacy of alcohol-mediated renal denervation using a novel catheter system (the Peregrine System Infusion Catheter) for the infusion of dehydrated alcohol as a neurolytic agent into the renal periarterial space. Background: The number of hypertensive patients with uncontrolled blood pressure (BP) remains unacceptably low. The renal sympathetic nervous system has been identified as an attractive therapeutic target. Methods: Forty-five patients with uncontrolled hypertension on ≥3 antihypertensive medications underwent bilateral renal denervation using the Peregrine Catheter with 0.6 ml alcohol infused per renal artery. Results: All patients were treated as intended. Mean 24-h ambulatory BP reduction at 6 months versus baseline was −11 mm Hg (95% confidence interval [CI]: −15 to −7 mm Hg) for systolic BP and −7 mm Hg (95% CI: −9 to −4 mm Hg) for diastolic BP (p < 0.001 for both). Office systolic BP was reduced by −18/−10 mm Hg (95% CI: −25 to −12/−13 to −6 mm Hg) at 6 months. Antihypertensive medications were reduced in 23% and increased in 5% of patients at 6 months. Adherence to the antihypertensive regimen remained stable over time. The primary safety endpoint, defined as the absence of periprocedural major vascular complications, major bleeding, acute kidney injury, or death within 1 month, was met in 96% of patients (95% CI: 85% to 99%). Two patients had major adverse events of periprocedural access-site pseudoaneurysms, with major bleeding in one. There were no deaths or instances of myocardial infarction, stroke, transient ischemic attack, or renal artery stenosis. Transient microleaks were noted in 42% and 49% of the left and right main renal arteries, respectively. There were 2 cases of minor vessel dissection that resolved without treatment. Conclusions: Primary results from this trial suggest that alcohol-mediated renal denervation using the Peregrine Catheter safely reduces blood pressure and as such may represent a novel approach for the treatment of hypertension.
CRIS-Team Scopus Importer:2020-02-18
Keywords: alcohol; catheter; hypertension; neurolysis; renal denervation

Alcohol-mediated renal sympathetic neurolysis for the treatment of hypertension: The Peregrine™ infusion catheter - Bertog, Stefan; Sharma, Alok; Mahfoud, Felix; Pathak, Atul; Schmieder, Roland; Sievert, Kolja; Papademetriou, Vasilios; Weber, Michael A.; Haratani, Nicole; Lobo, Melvin D.; Saxena, Manish; Kandzari, David E.; et al. (Cardiovascular Revascularization Medicine, 2020)
Renal sympathetic denervation using conventional non-irrigated radiofrequency catheters has potential technical shortcomings, including limited penetration depth and incomplete circumferential nerve damage, potentially impacting therapeutic efficacy. Against this background, second generation multi-electrode, radiofrequency and ultrasound renal denervation systems have been developed to provide more consistent circumferential nerve ablation. Irrigated catheters may allow deeper penetration while minimizing arterial injury. In this context, catheter-based chemical denervation, with selective infusion of alcohol, a potent neurolytic agent, into the perivascular space, may minimize endothelial, intimal and medial injury while providing circumferential neurolysis. Animal studies demonstrate pronounced renal norepinephrine level reductions and consistent renal nerve injury after perivascular alcohol infusion using the Peregrine Catheter. Early clinical studies demonstrated significant blood pressure reductions and a reasonable safety profile. Randomized sham-controlled trials (NCT03503773, NCT02910414) are underway to examine whether the aforementioned theoretical advantages of alcohol-medicated denervation with the Peregrine System™ Kit translate into clinical benefits.
CRIS-Team Scopus Importer:2020-12-18
Keywords: Alcohol-mediated neurolysis; Chemical neurolysis; Hypertension; Renal denervation; Sympathetic nervous system

Aldosterone antagonists and renal denervation: friends or foes? - Mahfoud, Felix; Ruilope, Luis M.; Bohm, Michael; Schmieder, Roland (Hypertension, 2015)
EVALuna2:3735

A multinational clinical approach to assessing the effectiveness of catheter-based ultrasound renal denervation: The RADIANCE-HTN and REQUIRE clinical study designs - Mauri, Laura; Kario, Kazuomi; Basile, Jan; Daemen, Joost; Davies, Justin; Kirtane, Ajay J.; Mahfoud, Felix; Schmieder, Roland; Weber, Michael; Nanto, Shinsuke; Azizi, Michel (American Heart Journal, 2018)
Catheter-based renal denervation is a new approach to treat hypertension via modulation of the renal sympathetic nerves. Although nonrandomized and small, open-label randomized studies resulted in significant reductions in office blood pressure 6months after renal denervation with monopolar radiofrequency catheters, the first prospective, randomized, sham-controlled study (Symplicity HTN-3) failed to meet its blood pressure efficacy end point. New clinical trials with new catheters have since been designed to address the limitations of earlier studies. Accordingly, the RADIANCE-HTN and REQUIRE studies are multicenter, blinded, randomized, sham-controlled trials designed to assess the blood pressure-lowering efficacy of the ultrasound-based renal denervation system (Paradise) in patients with established hypertension either on or off antihypertensive medications, is designed to evaluate patients in 2 cohorts-SOLO and TRIO, in the United States and Europe. The SOLO cohort includes patients with essential hypertension, at low cardiovascular risk, and either controlled on 1 to 2 antihypertensive medications or uncontrolled on 0 to 2 antihypertensive medications. Patients undergo a 4-week medication washout period before randomization to renal denervation (treatment) or renal angiogram (sham). The TRIO cohort includes patients with hypertension resistant to at least 3 antihypertensive drugs including a diuretic. Patients will be stabilized on a single-pill, triple-antihypertensive-drug combination for 4weeks before randomization to treatment or sham. Reduction in daytime ambulatory systolic blood pressure (primary end point) will be assessed at 2months in both cohorts. A predefined medication escalation protocol, as needed for blood pressure control, is implemented between 2 and 6months in both cohorts by a study staff member blinded to the randomization process. At 6months, daytime ambulatory blood pressure and antihypertensive treatment score will be assessed. REQUIRE is designed to evaluate patients with resistant hypertension on standard of care medication in Japan and Korea. Reduction in 24-hour ambulatory systolic blood pressure will be assessed at 3months (primary end point). Both studies are enrolling patients, and their results are expected in 2018.
EVALuna2:4042

Angiotensin pathways under therapy with empagliflozin in patients with chronic heart failure - Bosch, Agnes; Poglitsch, Marko; Kannenkeril, Dennis; Kolwelter, Julie; Striepe, Kristina; Ott, Christian; Rauh, Manfred; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (ESC Heart Failure, 2023)
Aims: Large outcome studies demonstrated a reduction of heart failure hospitalization or cardiovascular death in patients with chronic heart failure (CHF). The renin–angiotensin system (RAS) is a key player in fluid and sodium regulation. The classic angiotensin-converting enzyme–angiotensin II–angiotensin-1 receptor axis (Ang I–ACE–Ang II receptor axis) is predominantly angiotensin II (Ang-II) induced and promotes vasoconstriction. In contrast, the angiotensin-converting-enzyme-2–angiotensin-(1-7)–Mas axis (Mas-axis) is mediated by the metabolites angiotensin-1-7 (Ang-(1-7)) and angtiotensin-1-5 (Ang-(1-5)) and exerts cardioprotective effects. Methods: We previously investigated the effect of empagliflozin on the systemic haemodynamic in patients with stable CHF (NYHA II–III) in a randomized placebo-controlled clinical trial ‘Analysing the Effect of Empagliflozin on Reduction of Tissue Sodium Content in Patients With Chronic Heart Failure (ELSI)’. In a post hoc analysis, we now analysed whether empagliflozin has an effect on the RAS by measuring detailed RAS profiles (LC-MS/MS-based approach) in 72 patients from ELSI. We compared RAS parameters after 1-month and 3-months treatment with empagliflozin or placebo to baseline. The secondary goal was to analyse whether the effect of empagliflozin on RAS parameters was dependent on angiotensin-receptor-blocking (ARB) or angiotensin-converting-enzyme-inhibitor (ACEI) co-medication. Results: Empagliflozin medication induced a significant rise in Ang-II [68.5 pmol/L (21.3–324.2) vs. 131.5 pmol/L (34.9–564.0), P = 0.001], angiotensin-I (Ang-I) [78.7 pmol/L (21.5–236.6) vs. 125.9 pmol/L (52.6–512.9), P < 0.001], Ang-(1-7) [3.0 pmol/L (3.0–15.0) vs. 10.1 pmol/L (3.0–31.3), P = 0.006], and Ang-(1-5) [5.4 pmol/L (2.0–22.9) vs. 9.9 pmol/L (2.8–36.4), P = 0.004], which was not observed in the placebo group (baseline to 3-months treatment). A significant rise in Ang-II (206.4 pmol/L (64.2–750.6) vs. 568.2 pmol/L (164.7–1616.4), P = 0.001), Ang-(1-7) (3.0 pmol/L (3.0–14.1) vs. 15.0 pmol/L (3.0–31.3), P = 0.017), and Ang-(1-5) [12.2 pmol/L (3.8–46.6) vs. 36.4 pmol/L (11.1–90.7), P = 0.001] under empagliflozin treatment was only seen in the subgroup of patients with ARB co-medication, whereas no change of Ang-II (16.7 pmol/L (2.0–60.8) vs. 26.4 pmol/L (10.7–63.4), P = 0.469), Ang-(1-7) (6.6 pmol/L (3.0–20.7) vs. 10.5 pmol/L (3.0–50.5), P = 0.221), and Ang-(1-5) (2.7 pmol/L (2.0–8.4) vs. 2.8 pmol/L (2.0–6.9), P = 0.851) was observed in patients with empagliflozin that were on ACEI co-medication (baseline to 3-months treatment). Conclusions: Our data indicate that empagliflozin might lead to an activation of both the Ang I–ACE–Ang II receptor axis and the Mas-axis pathway. Activation of the Ang I–ACE–Ang II receptor axis and the protective Mas-axis pathway after initiating treatment with empagliflozin was only seen in patients with ARB co-medication, in contrast to co-medication with ACEI.
CRIS-Team Scopus Importer:2023-02-24
Keywords: Angiotensin profiles; Cardioprotective effects; Chronic heart failure; Empagliflozin; Renin–angiotensin system

ANGIOTENSIN PROFILES IN PATIENTS WITH HYPERTENSION AND TYPE 2 DIABETES WITH COMBINATION THERAPY OF EMPAGLIFLOZIN AND LINAGLIPTIN VERSUS METFORMIN AND INSULIN GLARGINE - Bosch, Agnes; Poglitsch, Marko; Kannenkeril, Dennis; Ott, Christian; Pietschner, Robert; Striepe, Kristina; Schiffer, Mario; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2022)
CRIS-Team WoS Importer:2022-07-29

ANGIOTENSIN PROFILES IN PATIENTS WITH HYPERTENSION AND TYPE 2 DIABETES WITH COMBINATION THERAPY OF EMPAGLIFLOZIN AND LINAGLIPTIN VERSUS METFORMIN AND INSULIN GLARGINE - Bosch, Agnes; Poglitsch, Marko; Kannenkeril, Dennis; Ott, Christian; Pietschner, Robert; Striepe, Kristina; Schiffer, Mario; Schmieder, Roland (Journal of Hypertension, 2022)
OBJECTIVE: The renin-angiotensin system (RAS) plays a key role in the physiological regulation of blood pressure. Patients with type-2-diabetes-mellitus (T2DM) and hypertension are known to have increased RAS activity. However, the precise role of RAS activation after SGLT2-inhibitor therapy is unknown. The classic RAS comprises the ACE-AngII-AT1R-axis (classic-axis) that promotes vasoconstriction. The Angiotensin-converting-enzyme-2-angiotensin-(1-7)-Mas axis (Mas-axis) with its components Angiotensin-(1-7) (Ang-1-7) and Angiotensin-(1-5) (Ang-1-5) is an endogenous negative regulatory pathway of the classic-axis, which can reduce its harmful effects. DESIGN AND METHOD: Angiotensin profiles were determined in 55 patients with hypertension and T2DM from our double blind, randomized, placebo controlled clinical trial "Effects of Empagliflozin+Linagliptin (E+L) vs Metformin+Insulin Glargine (M+I) on Renal and Vascular Changes in Type 2 Diabetes'' (ELMI) at baseline and three months after application of either E+L or M+I. An LC-MS/MS based approach was used to simultaneously quantify individual angiotensin metabolites (Attoquant Diagnostics, Vienna, Austria). RESULTS: In the E+L group medication induced a rise in Ang-I, Ang-(1-7) and a trend to a rise in Ang-II between baseline and treatment, which was not present in the M+I group (table).Comparison between the E+L and M+I group revealed that change between baseline and treatment was significantly different for Ang I (p = 0.002) and Ang-(1-7) (p = 0.002) between the groups. No difference in change between baseline and treatment was found for Ang II (p = 0.182) and Ang-(1-5) (p = 0.224) between the E+L and M+I group. CONCLUSIONS: In patients with hypertension and T2DM three months of therapy with E+L led to a rise of classic and protective components of the RAS, which was not present in the M+I group. The biological consequence of this complex RAS activation remains to be elucidated.
CRIS-Team Scopus Importer:2022-09-09

Angiotensin profiles in patients with type 2 diabetes and combination therapy of empagliflozin and linagliptin versus metformin and insulin glargine - Bosch, Agnes; Poglitsch, M.; Kannenkeril, Dennis; Ott, Christian; Striepe, Kristina; Schmieder, Roland (DIABETOLOGIA, 2021)
CRIS-Team WoS Importer:2021-10-01

ANNOYANCE DUE TO NOISE TRIGGERS VASCULAR CHANGES IN THE RENAL HEMODYNAMIC - Bosch, Agnes; Kannenkeril, Dennis; Ott, Christian; Harazny, Joanna M.; Striepe, Kristina; Karg, Marina V.; Jung, Susanne; Kolwelter, Julie; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

A novel, proof-of-concept radiofrequency renal denervation strategy to improve procedural efficiency: 12-month results from the SPYRAL DYSTAL pilot study - Sharp, Andrew S.P.; Kandzari, David E.; Townsend, Raymond R.; Kario, Kazuomi; Mahfoud, Felix; Weber, Michael A.; Schmieder, Roland; Tsioufis, Konstantinos; Böhm, Michael; Choi, James W.; Liu, Minglei; DeBruin, Vanessa; et al. (Cardiovascular Revascularization Medicine, 2024)
Background: Catheter-based renal sympathetic denervation (RDN) reduced blood pressure (BP) in multiple randomized sham-controlled trials of patients with uncontrolled hypertension (HTN). We tested proof-of-concept for a more selective treatment strategy, exclusively targeting these areas to improve the efficiency of the procedure. Methods: The SPYRAL DYSTAL Pilot study was designed to mirror the SPYRAL HTN-OFF MED Pivotal study, enabling comparison with a propensity score adjusted active-control group. Patients were antihypertensive medication-free for one month before undergoing BP assessment. Those with office BP of 150–180/>90 mmHg and with an ambulatory systolic BP of 140–170 mmHg were selected to undergo open label treatment, delivering energy only to the distal main renal arteries and first order branches. Patients from DYSTAL were compared with patients who underwent maximized RF RDN treatment in the prior randomized OFF MED trial at 3 months. After 3 months, patients resumed antihypertensive medications as indicated. Safety and efficacy outcomes were assessed post hoc through 12 months. Results: The SPYRAL DYSTAL Pilot study treated 56 HTN patients. Baseline office systolic BP (OSBP) and 24-h ambulatory systolic BP (ASBP) were similar between DYSTAL and OFF MED patient groups. The number of ablations (32.3 ± 8.0 vs 46.6 ± 15.3, p < 0.001), procedure time (67 ± 21 min vs 99 ± 36 min; p < 0.001), and contrast volume (173 ± 77 cc vs 208 ± 96 cc; p = 0.014) were significantly lower with the simplified treatment strategy. OSBP and ASBP changes compared with baseline were −9.0 and −1.4 mmHg at 3 months, −20.3 and −13.9 mmHg at 6 months, and −20.3 and −16.6 mmHg at 12 months, respectively. During the medication up-titration phase, BP reductions among DYSTAL patients were similar to reductions observed in OFF MED through 12 months, with comparable number of drugs (1.4 and 1.5 medications, respectively (P=NS)). Two adverse events related to guidewire placement were reported. Conclusion: In this pilot study, focusing ablation treatment on the distal main and proximal branch renal arteries was performed, resulting in fewer RF lesions, and reduced contrast volume and procedure time. Whether BP reductions are similar between a selective vs. maximized RDN approach requires further prospective study.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Renal denervation; Uncontrolled hypertension

Aortic stiffness is not only associated with structural but also functional parameters of retinal microcirculation - Dąbrowska, Edyta; Harazny, Joanna M.; Miszkowska-Nagórna, Eliza; Stefański, Adrian; Graff, Beata; Kunicka, Katarzyna; Świerblewska, Ewa; Rojek, Agnieszka; Szyndler, Anna; Gąsecki, Dariusz; Wolf, Jacek; Gruchała, Marcin; et al. (Microvascular Research, 2020)
Objective: The aim of the study was to test the hypothesis that alterations in large arteries are associated with microvascular remodelling and decreased retinal capillary blood flow. Methods: The study group comprised of 88 patients with essential hypertension and 32 healthy controls. Retinal microcirculation was evaluated by scanning laser Doppler flowmetry. Macrovascular changes were assessed on the basis of arterial stiffness measurement (carotid-femoral pulse wave velocity), its hemodynamic consequences (central pulse pressure, augmentation pressure, augmentation index) and intima media thickness of common carotid artery. Results: Pulse wave velocity was inversely correlated to mean retinal capillary blood flow in hypertensive patients (R = −0.32, p < 0.01). This relationship remained significant in multivariate regression analysis after adjustment for age, sex, central systolic blood pressure (BP) and body mass index (β = −31.27, p < 0.001). Lumen diameter (LD) of retinal arterioles was significantly smaller in hypertensive then normotensive subjects (79.4 vs. 83.8, p = 0.03). Central and brachial systolic, diastolic and mean BPs were significantly correlated with LD and outer diameter of retinal arterioles. The relationship between LD and central BPs remained significant in multivariate analysis (β = −0.15, p = 0.03 for cSBP; β = −0.22, p = 0.04 for cDBP; β = −0.21, p = 0.03 for cMBP). Moreover, in a subgroup with cardiac damage central and brachial pulse pressure were positively associated with retinal wall thickness, wall cross sectional area, and wall to lumen ratio. Conclusion: In conclusion, the study provides a strong evidence that microcirculation is coupled with macrocirculation not only in terms of structural but also functional parameters.
CRIS-Team Scopus Importer:2020-01-21
Keywords: Aortic stiffness; Microcirculation; Pulse wave velocity; Scanning laser Doppler flowmetry

AORTIC STIFFNESS IS NOT ONLY ASSOCIATED WITH STRUCTURAL BUT ALSO WITH FUNCTIONAL PARAMETERS OF MICROCIRCULATION - Dabrowska, E.; Harazny, J. M.; Miszkowska-Nagorna, E.; Stefanski, A.; Graff, B.; Szyndler, A.; Kunicka, K.; Swierblewska, E.; Rojek, A.; Gasecki, D.; Schmieder, Roland; Laurent, S.; et al. (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-20

APPLICATION OF A CENTRAL ILIAC ARTERIOVENOUS COUPLER DEVICE IN SEVERE TREATMENT-RESISTANT ARTERIAL HYPERTENSION: A FOUR-YEAR FOLLOW-UP - Jung, Susan; Ott, Christian; Karg, M.; Bosch, A.; Schmid, M.; Schlundt, Christian; Achenbach, Stephan; Schmieder, Roland (2018)
EVALuna2:35985

Application of a central iliac arteriovenous coupler device in severe treatment-resistant hypertension: a 3.5-year follow-up - Jung, Susanne; Ott, Christian; Karg, Marina V.; Bosch, Agnes; Schmid, Michael; Schlundt, Christian; Achenbach, Stephan; Schmieder, Roland (Journal of Hypertension, 2018)
OBJECTIVE: In patients with resistant hypertension, percutaneous placement of an iliac arteriovenous coupler device leads to a reduction of blood pressure (BP) via decreased total vascular resistance and improved arterial compliance. However, long-term efficacy and safety need to be further explored. We report on the first case of 3.5-year follow-up in a patient who underwent implantation of an iliac arteriovenous coupler device. RESULTS: A patient with resistant hypertension was admitted to hospital. Despite treatment with six anti-hypertensive drugs, his BP was poorly controlled. Previously, he had undergone renal denervation, which did not cause a significant BP decrease. Therefore, an arteriovenous coupler device was implanted, leading to an immediate and significant BP decrease. The patient was discharged with an office BP of 122/71 mmHg. After 3 months, there was a sustained BP decrease (-14/9 mmHg), whereas later, it was fluctuant (office BP: 147-173/85-95 mmHg, ABPM: 153-166/81-94 mmHg) probably due to medication non-adherence confirmed by a urinary toxicological screening test. Follow-up right heart catheterization showed changes in hemodynamic parameters related to volume congestion, which were accompanied by progressive dyspnea and weight gain. This was controlled by an optimized diuretic therapy. Additionally, an invasive closure maneuver was performed, leading to an immediate BP increase after closure and a similar decrease after re-opening of the anastomosis, verifying its proper long-term function. CONCLUSION: The implantation of an iliac arteriovenous coupler device appears to be a promising and effective method to decrease BP and therefore reduce cardiovascular risk in patients with severe, treatment-resistant hypertension.
EVALuna2:34505

Application of win ratio methodology in the Global SYMPLICITY Registry for patients with atrial fibrillation or obstructive sleep apnea - Mahfoud, F.; Mancia, G.; Ukena, C.; Schmieder, Roland; Narkiewicz, K.; Ruilope, L.; Schlaich, M.; Williams, B.; Fahy, M.; Boehm, M. (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

A randomised study of the impact of the SGLT2 inhibitor dapagliflozin on microvascular and macrovascular circulation - Ott, Christian; Jumar, Agnes; Striepe, Kristina; Friedrich, Stefanie; Karg, Margarete; Bramlage, Peter; Schmieder, Roland (Cardiovascular Diabetology, 2017)
The sodium-glucose cotransporter 2 inhibitor, dapagliflozin, has been shown to improve diabetic control and reduce blood pressure in patients with type 2 diabetes mellitus. Its effects on micro- and macrovascular structure and function have not yet been reported.This was a prospective, single-centre, placebo-controlled, double-blind, randomised crossover phase IIIb study conducted between March 2014 and February 2015. After a 4-week run-in/washout phase, patients (N = 59) received 6 weeks of either dapagliflozin 10 mg or placebo once daily. They then underwent a 1-week washout before crossing over to the other treatment. Changes in retinal capillary flow (RCF) and arteriole remodelling were evaluated using scanning laser Doppler flowmetry, while micro- and macrovascular parameters in the systemic circulation were assessed using pulse wave analysis.Six weeks of dapagliflozin treatment resulted in improvements in diabetes control, including blood glucose and insulin resistance, and reduced office and 24-h ambulatory blood pressure values. RCF decreased from 324 AU at baseline to 308 AU after treatment with dapagliflozin (p = 0.028), while there was little difference after the placebo (318 AU; p = 0.334). Furthermore, the arteriole remodelling that was seen after the placebo phase was not evident after the dapagliflozin phase. Central systolic and diastolic blood pressure values were significantly lower after 6 weeks of dapagliflozin, by 3.0 and 2.2 mmHg, respectively (p = 0.035 and 0.020, respectively vs. baseline).Six weeks of dapagliflozin treatment resulted in numerous beneficial effects. In addition to achieving superior diabetes control and blood pressure, parameters associated with the early stages of vascular remodelling were also improved. Trial registration http://www.clinicaltrials.gov (NCT02383238).
EVALuna2:3943

Arterial Hyper- and Hypotension associated with psychiatric medications: a risk assessment based on the summaries of product characteristics (SmPCs) - Freudenmann, Roland W.; Freudenmann, Ninja; Zurowski, Bartosz; Schönfeldt-Lecuona, Carlos; Maier, Ludwig; Schmieder, Roland; Lange-Asschenfeldt, Christian; Gahr, Maximilian (Deutsche Medizinische Wochenschrift, 2017)
Introduction Psychiatric medications are well-known triggers of clinically relevant blood pressure changes. Therefore, we aimed at creating ranking lists for their risk of causing arterial hyper- or hypotension. Methods We analyzed 784 Summaries of Product characteristics (SmPCs, available online from "Rote Liste" or "Gelbe Liste" websites) from 105 psychiatric medications registered in adult psychiatry in Germany and extracted the standardized reported risks of increasing or decreasing arterial blood pressure. Results According to the SmPCs, atomoxetine had the highest risk of arterial hypertension ("very frequent", > 10 %), and another 15 substances followed in the category "frequent" (> 1 %): duloxetine, milnacipran, venlafaxine, bupropion, citalopram, tranylcypromine (particularly with certain diets), reboxetine, methylphenidate, clozapine, paliperidone, risperidone, buprenorphine+naloxone, memantine, galantamine, and rivastigmine. Conversely, 7 substances, namely amitriptyline, tranylcypromine, chlorprothixen, flupentixol, levomepromazine, olanzapine and trimipramine had the highest reported risk of low blood pressure ("very frequent"), and another 25 substances had the risk "frequent". No risk of hypertension or hypotension was documented for many other substances. Incidentally, we observed that the reported effects on blood pressure for single substances (e. g. citalopram) markedly differed between the SmPCs from different manufacturers, rendering a clear risk assessment impossible for many medications. Discussion According to the German SmPc, many psychiatric medications are associated with the risk of arterial hypertension and, even more so, hypotension. We hardly observed substance group effects, such as high blood pressure with noradrenergic antidepressants. Commonly used tables summarising secondary causes of arterial hypertension should be revised in terms of psychiatric medications. Our rank orders of risk may aid choosing the best psychiatric medications in patients with known hypertension or at risk for syncope, as well as when blood pressure changes occur under psychiatric pharmacotherapy. A definitive risk assessment however requires controlled studies.
EVALuna2:3942

Arteriovenous fistula thrombosis is associated with increased all-cause and cardiovascular mortar in haemodialysis patients from the AURORA trial - Girerd, Sophie; Girerd, Nicolas; Frimat, Luc; Holdaas, Hallvard; Jardine, Alan G.; Schmieder, Roland; Fellstrom, Bengt; Settembre, Nicla; Malikov, Sergei; Rossignol, Patrick; Zannad, Faiez (Clinical Kidney Journal, 2020)
Background. The impact of arteriovenous fistula (AVF) or graft (AVG) thrombosis on mortality has been sparsely studied. This study investigated the association between AVF/AVG thrombosis and all-cause and cardiovascular mortality.
CRIS-Team WoS Importer:2020-05-02

Assessment of Hypertension-Mediated Organ Damage - OTT, Christian; Schmieder, Roland (Elsevier, 2023)
The individual impact of arterial hypertension on several hypertension-mediated organ damages (HMODs) varies widely. This chapter mainly addresses HMODs with arterial hypertension being the most important attributable risk factor. HMOD can be detected in an early subclinical (asymptomatic) stage, but once HMOD, even intermediate, has developed, these conditions are by far overwriting any risk prediction from the cardiovascular (CV) risk factor scores. Hence, the specific impact of HMOD is particular in (younger and middle-aged) patients with a probable reclassification of their individual risk estimation. A variety of techniques are available nowadays to diagnose HMOD of the brain, heart, eyes, kidneys, and vasculature in different organs, but with differences in sensitivity and specificity as well as applicability is limited depending on the availability of the various techniques and the reimbursement strategy of the national health care systems. The clinical importance of HMOD is also underlined by the fact that regression of HMOD is clinically a useful tool for evaluation of the efficacy of (more aggressive and immediate) antihypertensive treatment in individual patients. Therefore this chapter also emphasizes the consequences of HMOD regression by antihypertensive treatment, and attempts to establish whether or not changes of HMOD have related prognostic significance.
CRIS-Team Scopus Importer:2023-11-24
Keywords: blood pressure; brain; eye; heart; hypertension-mediated organ damage (HMOD); kidney; vasculature

Association between exercise frequency with renal and cardiovascular outcomes in diabetic and non-diabetic individuals at high cardiovascular risk - Boehm, Michael; Schumacher, Helmut; Werner, Christian; Teo, Koon K.; Lonn, Eva M.; Mahfoud, Felix; Speer, Thimoteus; Mancia, Giuseppe; Redon, Josep; Schmieder, Roland; Sliwa, Karen; Marx, Nikolaus; et al. (Cardiovascular Diabetology, 2022)
Background: Guidelines recommend physical activity to reduce cardiovascular (CV) events. The association between physical activity and progression of chronic kidney disease (CKD) with and without diabetes is unknown. We assessed the association of self-reported physical activity with renal and CV outcomes in high-risk patients aged ≥ 55 years over a median follow-up of 56 months in post-hoc analysis of a previously randomized trial program. Methods: Analyses were done with Cox regression analysis, mixed models for repeated measures, ANOVA and χ2-test. 31,312 patients, among them 19,664 with and 11,648 without diabetes were analyzed. Results: Physical activity was inversely associated with renal outcomes (doubling of creatinine, end-stage kidney disease (ESRD)) and CV outcomes (CV death, myocardial infarction, stroke, heart failure hospitalization). Moderate activity (at least 2 times/week to every day) was associated with lower risk of renal outcomes and lower incidence of new albuminuria (p < 0.0001 for both) compared to lower exercise levels. Similar results were observed for those with and without diabetes without interaction for renal outcomes (p = 0.097–0.27). Physical activity was associated with reduced eGFR decline with a moderate association between activity and diabetes status (p = 0.05). Conclusions: Moderate physical activity was associated with improved kidney outcomes with a threshold at two sessions per week. The association of physical activity with renal outcomes did not meaningfully differ with or without diabetes but absolute benefit of activity was even greater in people with diabetes. Thus, risks were similar between those with diabetes undertaking high physical activity and those without diabetes but low physical activity. Clinical trial registration: http://clinicaltrials.gov.uniqueidentifier:NCT00153101.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Cardiovascular outcomes; Physical activity; Renal outcomes; Secondary prevention

Association of Noise Annoyance with Measured Renal Hemodynamic Changes - Kannenkeril, Dennis; Jung, Susanne; Ott, Christian; Striepe, Kristina; Kolwelter, Julie; Schmieder, Roland; Bosch, Agnes (Kidney & Blood Pressure Research, 2021)
Background: Chronic mental stress is recognized as a modifiable risk factor for cardiovascular disease. The aim of this study was to demonstrate that noise annoyance-induced stress is associated with changes in renal hemodynamics. Methods: Renal hemodynamic parameters were measured using steady-state input clearance with infusion of para-aminohippuric acid and inulin in individuals with normal, high normal, and elevated blood pressure. All individuals ranked subjective annoyance due to noise in everyday life on a 7-grade Likert scale. The median of all rankings was used as a cutoff point to divide the group into noise-annoyed and non-noise-annoyed individuals. Different renal hemodynamic parameters were calculated based on the Gomez equation. Results: Noise-annoyed individuals (n = 58) showed lower renal plasma flow (599 +/- 106 vs. 663 +/- 124 mL/min, p = 0.009), lower renal blood flow (1,068 +/- 203 vs. 1,172 +/- 225 mL/min, p = 0.047), higher filtration fraction (22.7 +/- 3.3 vs. 21.3 +/- 3.0, p = 0.012), higher renal vascular resistance (88.9 +/- 25.6 vs. 75.8 +/- 22.9 mm Hg/[mL/min], p = 0.002), and higher resistance of afferent arteriole (2,439.5 +/- 1,253.4 vs. 1,849.9 +/- 1,242.0 dyn s(-1) cm(-5), p = 0.001) compared to non-noise-annoyed individuals (n = 55). There was no difference in measured glomerular filtration rate (133 +/- 11.8 vs. 138 +/- 15 mL/min, p = 0.181), resistance of efferent arteriole (2,419.4 +/- 472.2 vs. 2,245.8 +/- 370.3 dyn s(-1) cm(-5), p = 0.060), and intraglomerular pressure (64.0 +/- 3.1 vs. 64.6 +/- 3.5 mm Hg, p = 0.298) between the groups. After adjusting for age, renal plasma flow, renal blood flow, and renal vascular resistance remained significantly different between the groups, with a trend in increased afferent arteriolar resistance and filtration fraction. Conclusion: In this study, noise annoyance was associated with reduced renal perfusion attributed to increased renal vascular resistance predominantly at the afferent site. Long-term consequences of this renal hemodynamic pattern due to noise annoyance need to be investigated.
CRIS-Team WoS Importer:2021-05-14

Atherosclerotic renovascular disease: a clinical practice document by the European Renal Best Practice (ERBP) board of the European Renal Association (ERA) and the Working Group Hypertension and the Kidney of the European Society of Hypertension (ESH) - Sarafidis, Pantelis A.; Theodorakopoulou, Marieta; Ortiz, Alberto; Fernandez-Fernandez, Beatriz; Nistor, Ionut; Schmieder, Roland; Arici, Mustafa; Saratzis, Athanasios; Van Der Niepen, Patricia; Halimi, Jean Michel; Kreutz, Reinhold; Januszewicz, Andrzej; et al. (Nephrology Dialysis Transplantation, 2023)
Atherosclerotic renovascular disease (ARVD) is the most common type of renal artery stenosis. It represents a common health problem with clinical presentations relevant to many medical specialties and carries a high risk for future cardiovascular and renal events, as well as overall mortality. The available evidence regarding the management of ARVD is conflicting. Randomized controlled trials failed to demonstrate superiority of percutaneous transluminal renal artery angioplasty (PTRA) with or without stenting in addition to standard medical therapy compared with medical therapy alone in lowering blood pressure levels or preventing adverse renal and cardiovascular outcomes in patients with ARVD, but they carried several limitations and met important criticism. Observational studies showed that PTRA is associated with future cardiorenal benefits in patients presenting with high-risk ARVD phenotypes (i.e. flash pulmonary oedema, resistant hypertension or rapid loss of kidney function). This clinical practice document, prepared by experts from the European Renal Best Practice (ERBP) board of the European Renal Association (ERA) and from the Working Group on Hypertension and the Kidney of the European Society of Hypertension (ESH), summarizes current knowledge in epidemiology, pathophysiology and diagnostic assessment of ARVD and presents, following a systematic literature review, key evidence relevant to treatment, with an aim to support clinicians in decision making and everyday management of patients with this condition.
CRIS-Team Scopus Importer:2023-12-15
Keywords: angioplasty; atherosclerotic renovascular disease; epidemiology; renal artery stenosis; revascularization

AT II Receptor Blockade and Renal Denervation: Different Interventions with Comparable Renal Effects? - Rodionova, Kristina; Hindermann, Martin; Hilgers, Karl Friedrich; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Ditting, Tilmann (Kidney & Blood Pressure Research, 2021)
Background: Angiotensin II (Ang II) and the renal sympathetic nervous system exert a strong influence on renal sodium and water excretion. We tested the hypothesis that already low doses of an Ang II inhibitor (candesartan) will result in similar effects on tubular sodium and water reabsorption in congestive heart failure (CHF) as seen after renal denervation (DNX). Methods: Measurement of arterial blood pressure, heart rate (HR), renal sympathetic nerve activity (RSNA), glomerular filtration rate (GFR), renal plasma flow (RPF), urine volume, and urinary sodium. To assess neural control of volume homeostasis, 21 days after the induction of CHF via myocardial infarction rats underwent volume expansion (0.9% NaCL; 10% body weight) to decrease RSNA. CHF rat and controls with or without DNX or pretreated with the Ang II type-1 receptor antagonist candesartan (0.5 ug i.v.) were studied. Results: CHF rats excreted only 68 + 10.2% of the volume load (10% body weight) in 90 min. CHF rats pretreated with candesartan or after DNX excreted from 92 to 103% like controls. Decreases of RSNA induced by volume expansion were impaired in CHF rats but unaffected by candesartan pointing to an intrarenal drug effect. GFR and RPF were not significantly different in controls or CHF. Conclusion: The prominent function of increased RSNA - retaining salt and water - could no longer be observed after renal Ang II receptor blockade in CHF rats.
CRIS-Team WoS Importer:2021-06-11
Keywords: Renal sympathetic innervation; Angiotensin II; Congestive heart failure; Renal nerve ablation; Renal function

Attenuation of Splanchnic Autotransfusion Following Noninvasive Ultrasound Renal Denervation: A Novel Marker of Procedural Success - Saxena, Manish; Shour, Tariq; Shah, Mussadiq; Wolff, Christopher B.; Julu, Peter O.O.; Kapil, Vikas; Collier, David J.; Ng, Fu Liang; Gupta, Ajay; Balawon, Armida; Pheby, Jane; Zak, Anne; et al. (Journal of the American Heart Association, 2018)
BACKGROUND: Renal denervation has no validated marker of procedural success. We hypothesized that successful renal denervation would reduce renal sympathetic nerve signaling demonstrated by attenuation of α-1-adrenoceptor-mediated autotransfusion during the Valsalva maneuver. METHODS AND RESULTS: In this substudy of the Wave IV Study: Phase II Randomized Sham Controlled Study of Renal Denervation for Subjects With Uncontrolled Hypertension, we enrolled 23 subjects with resistant hypertension. They were randomized either to bilateral renal denervation using therapeutic levels of ultrasound energy (n=12) or sham application of diagnostic ultrasound (n=11). Within-group changes in autonomic parameters, office and ambulatory blood pressure were compared between baseline and 6 months in a double-blind manner. There was significant office blood pressure reduction in both treatment (16.1±27.3 mm Hg, P<0.05) and sham groups (27.9±15.0 mm Hg, P<0.01) because of which the study was discontinued prematurely. However, during the late phase II (Iii) of Valsalva maneuver, renal denervation resulted in substantial and significant reduction in mean arterial pressure (21.8±25.2 mm Hg, P<0.05) with no significant changes in the sham group. Moreover, there were significant reductions in heart rate in the actively treated group at rest (6.0±11.5 beats per minute, P<0.05) and during postural changes (supine 7.2±8.4 beats per minute, P<0.05, sit up 12.7±16.7 beats per minute, P<0.05), which were not observed in the sham group. CONCLUSIONS: Blood pressure reduction per se is not necessarily a marker of successful renal nerve ablation. Reduction in splanchnic autotransfusion following renal denervation has not been previously demonstrated and denotes attenuation of (renal) sympathetic efferent activity and could serve as a marker of procedural success. CLINICAL TRIAL REGISTRATION: URL: https://www.clinicaltrials.gov. Unique identifier: NCT02029885.
EVALuna2:34506

Azilsartan compared to ACE inhibitors in anti-hypertensive therapy: one-year outcomes of the observational EARLY registry - Gitt, Anselm K.; Bramlage, Peter; Potthoff, Sebastian A.; Baumgart, Peter; Mahfoud, Felix; Buhck, Hartmut; Ehmen, Martina; Ouarrak, Taoufik; Senges, Jochen; Schmieder, Roland (Bmc Cardiovascular Disorders, 2016)
Azilsartan medoxomil (AZL-M), has been demonstrated to be more effective than the other sartans currently in use; however, there is insufficient information available comparing it with ACE-inhibitors. Therefore, we aimed to compare the efficacy, safety, and tolerability of AZL-M with that of ACE-inhibitors in a real life clinical setting.The EARLY registry is a prospective, observational, national, multicentre registry with a follow-up period of 12 months. There were two principal objectives: 1) documentation of the achievement of target BP values set according to recent national and international guidelines, and 2) description of the safety profile of AZL-M.A total of 3 849 patients with essential arterial hypertension were recruited from primary care offices in Germany. Patients who initiated monotherapy at baseline comprising either AZL-M or an ACE-inhibitor were included at a ratio of seven to three. Results demonstrated that a blood pressure target of <140/90 mmHg was achieved by a significantly greater proportion of patients in the AZL-M group (61.1 %) compared with the ACE-inhibitor group (56.4 %; p < 0.05; OR, 1.21; 95 % CI, 1.03-1.42), with this finding maintained after adjusting for differences in baseline characteristics. AZL-M appeared to have an equivalent safety profile to the ACE-inhibitors, with a similar incidence of adverse events in the two patient groups (p = 0.73).These data add to the results of previous randomized controlled clinical trials suggesting that, compared with other agents that target the renin-angiotensin system, AZL-M provides statistically significant albeit small improvements in blood pressure control.
EVALuna2:3841

Basal nitric oxide activity is an independent determinant of arteriolar structure in the human retinal circulation - Ritt, Martin; Harazny, Joanna M.; Ott, Christian; Raff, Ulrike; Schneider, Markus; Michelson, Georg; Schmieder, Roland (Journal of Hypertension, 2011)
Experimental data indicate that nitric oxide might play a role in structure and remodeling of peripheral small arteries and arterioles. We hypothesized that retinal arteriolar structure is modulated by basal nitric oxide activity.The study cohort comprised 97 male untreated patients with normal and elevated blood pressure but without clinical evidence for cardiovascular disease. The changes of retinal capillary blood flow (RCF) to nitric oxide synthase inhibitor N-monomethyl-L-arginine (L-NMMA), that reflects basal nitric oxide activity of retinal vasculature, and to flicker light, that in part nitric oxide dependently provokes retinal vasodilatation, and parameters of retinal arteriolar structure, for example wall-to-lumen ratio (WLR), were assessed noninvasively and in vivo by scanning laser Doppler flowmetry.Participants were stratified according to the median WLR of retinal arterioles into two groups. In the group with WLR above the median RCF in response to infusion of L-NMMA decreased to a smaller extent (-3.82 ± 26 vs. -26.0 ± 45 arbitrary units and -0.83 ± 8.4 vs. -5.88 ± 11%, P = 0.004 and P = 0.015; respectively), whereas RCF in response to flicker light did not differ significantly compared to the counter group (22.2 ± 56 vs. 39.8 ± 51 arbitrary units and 7.42 ± 15 vs. 11.9 ± 14%, P = 0.112 and P = 0.149). In the whole study cohort WLR of retinal arterioles was related with the decrease of RCF to L-NMMA infusion [when expressed in absolute terms (r = 0.252, P = 0.013) and in percentage change (r = 0.213, P = 0.036)] and inversely related with the change of RCF to flicker light [when expressed in absolute terms (r = -0.203, P = 0.048) but not clearly when expressed in percentage change (r = -0.161, P = 0.120)]. Adjustment for major cardiovascular risk factors and changes of systemic hemodynamics in response to L-NMMA infusion revealed an independent relationship between WLR of retinal arterioles and percentage change of RCF to L-NMMA infusion (ß = 0.300, P = 0.007).Basal nitric oxide activity emerged as an independent determinant of arteriolar remodeling in the human retinal circulation in vivo.
EVALuna2:3475

Baseline Characteristics and Prescription Patterns of Standard Drugs in Patients with Angiographically Determined Coronary Artery Disease and Renal Failure (CAD-REF Registry) - Reinecke, Holger; Breithardt, Guenter; Engelbertz, Christiane; Schmieder, Roland; Fobker, Manfred; Pinnschmidt, Hans O.; Schmitz, Boris; Bruland, Philipp; Wegscheider, Karl; Pavenstaedt, Hermann; Brand, Eva (PLoS ONE, 2016)
Chronic kidney disease (CKD) is strongly associated with coronary artery disease (CAD). We established a prospective observational nationwide multicenter registry to evaluate current treatment and outcomes in patients with both CKD and angiographically documented CAD.In 32 cardiological centers 3,352 CAD patients with >=50% stenosis in at least one coronary artery were enrolled and classified according to their estimated glomerular filtration rate and proteinuria into one of five stages of CKD or as a control group.2,723 (81.2%) consecutively enrolled patients suffered from CKD. Compared to controls, CKD patients had a higher prevalence of diabetes, hypertension, peripheral artery diseases, heart failure, and valvular heart disease (each p<0.001). Myocardial infarctions (p = 0.02), coronary bypass grafting, valve replacements and pacemaker implantations had been recorded more frequently (each p<0.001). With advanced CKD, the number of diseased coronary vessels and the proportion of patients with reduced left ventricular ejection fraction (LVEF) increased significantly (both p<0.001). Percutaneous coronary interventions were performed less frequently (p<0.001) while coronary bypass grafting was recommended more often (p = 0.04) with advanced CKD. With regard to standard drugs in CAD treatment, prescriptions were higher in our registry than in previous reports, but beta-blockers (p = 0.008), and angiotensin-converting-enzyme inhibitors and/or angiotensin-receptor blockers (p<0.001) were given less often in higher CKD stages. In contrast, in the subgroup of patients with moderately to severely reduced LVEF the prescription rates did not differ between CKD stages. In-hospital mortality increased stepwise with each CKD stage (p = 0.02).In line with other studies comprising CKD cohorts, patients' morbidity and in-hospital mortality increased with the degree of renal impairment. Although cardiologists' drug prescription rates in CAD-REF were higher than in previous studies, they were still lower especially in advanced CKD stages compared to cohorts treated by nephrologists.
EVALuna2:3832

Benefits and Risks of Aliskiren Treatment in Patients With Type 2 Diabetes: Analyses of the 3A Registry - Kistner, Iris; Zeymer, Uwe; Dechend, Ralf; Hagedorn, Ina; Riemer, Thomas; Bramlage, Peter; Pittrow, David; Senges, Jochen; Schmieder, Roland (Journal of Clinical Hypertension, 2016)
The authors sought to retrospectively analyze the real-world evidence on aliskiren in diabetic patients with or without concomitant renin-angiotensin system (RAS) blocker use based on the Registry for Ambulant Therapy With RAS Inhibitors in Hypertension Patients in Germany (3A). Of 14,986 patients included, 3772 patients had diabetes and 28.5% received aliskiren, 14.3% received angiotensin-converting enzyme (ACE) inhibitors/angiotensin receptor blockers (ARBs), 35.4% received aliskiren plus an ACE inhibitor/ARB, and 10.5% received other drugs. Ambulatory blood pressure (BP) monitoring (baseline BP 148±15.8/84.0±10.9 mm Hg) revealed stronger diastolic BP reduction for aliskiren plus ACE inhibitor/ARB than aliskiren alone in the low (2.8±0.5 vs 0.6±0.6; P=.004) and intermediate (5.9±0.5 vs 4.5±0.5; P=.04) baseline BP groups. There was a lesser ambulatory BP reduction observed for patients receiving non-RAS in the high baseline category for both systolic (12.5±1.8 vs 17.1±1.0; P=.02) and diastolic (6.9±1.0 vs 9.8±0.6; P=.01) BP. In patients with hypertension and type 2 diabetes, aliskiren was beneficial in lowering BP, with no observed increases in major adverse effects compared with RAS-blocking therapy alone.
EVALuna2:3853

Blood pressure and Cardiorenal Outcomes With Finerenone in Chronic Kidney Disease in Type 2 Diabetes - Ruilope, Luis M.; Agarwal, Rajiv; Anker, Stefan D.; Filippatos, Gerasimos; Pitt, Bertram; Rossing, Peter; Sarafidis, Pantelis; Schmieder, Roland; Joseph, Amer; Rethemeier, Nicole; Nowack, Christina; Bakris, George L. (Hypertension, 2022)
BACKGROUND: Chronic kidney disease is frequently associated with hypertension and poorly controlled blood pressure can lead to chronic kidney disease progression. Finerenone, a nonsteroidal mineralocorticoid receptor antagonist, significantly improves cardiorenal outcomes in patients with chronic kidney disease and type 2 diabetes. This analysis explored the relationship between office systolic blood pressure (SBP) and cardiorenal outcomes with finerenone in FIDELIO-DKD trial (Finerenone in Reducing Kidney Failure and Disease Progression in Diabetic Kidney Disease).
CRIS-Team WoS Importer:2022-11-18

Blood pressure and LDL-cholesterol targets for prevention of recurrent strokes and cognitive decline in the hypertensive patient: design of the European Society of Hypertension-Chinese Hypertension League Stroke in Hypertension Optimal Treatment randomize - Zanchetti, Alberto; Liu, Lisheng; Mancia, Giuseppe; Parati, Gianfranco; Grassi, Guido; Stramba-Badiale, Marco; Silani, Vincenzo; Bilo, Grzegorz; Corrao, Giovanni; Zambon, Antonella; Scotti, Lorenza; Zhang, Xinhua; et al. (Journal of Hypertension, 2014)
The SBP values to be achieved by antihypertensive therapy in order to maximize reduction of cardiovascular outcomes are unknown; neither is it clear whether in patients with a previous cardiovascular event, the optimal values are lower than in the low-to-moderate risk hypertensive patients, or a more cautious blood pressure (BP) reduction should be obtained. Because of the uncertainty whether 'the lower the better' or the 'J-curve' hypothesis is correct, the European Society of Hypertension and the Chinese Hypertension League have promoted a randomized trial comparing antihypertensive treatment strategies aiming at three different SBP targets in hypertensive patients with a recent stroke or transient ischaemic attack. As the optimal level of low-density lipoprotein cholesterol (LDL-C) level is also unknown in these patients, LDL-C-lowering has been included in the design.The European Society of Hypertension-Chinese Hypertension League Stroke in Hypertension Optimal Treatment trial is a prospective multinational, randomized trial with a 3 × 2 factorial design comparing: three different SBP targets (1, <145-135; 2, <135-125; 3, <125 mmHg); two different LDL-C targets (target A, 2.8-1.8; target B, <1.8 mmol/l). The trial is to be conducted on 7500 patients aged at least 65 years (2500 in Europe, 5000 in China) with hypertension and a stroke or transient ischaemic attack 1-6 months before randomization. Antihypertensive and statin treatments will be initiated or modified using suitable registered agents chosen by the investigators, in order to maintain patients within the randomized SBP and LDL-C windows. All patients will be followed up every 3 months for BP and every 6 months for LDL-C. Ambulatory BP will be measured yearly.Primary outcome is time to stroke (fatal and non-fatal). Important secondary outcomes are: time to first major cardiovascular event; cognitive decline (Montreal Cognitive Assessment) and dementia. All major outcomes will be adjudicated by committees blind to randomized allocation. A Data and Safety Monitoring Board has open access to data and can recommend trial interruption for safety.It has been calculated that 925 patients would reach the primary outcome after a mean 4-year follow-up, and this should provide at least 80% power to detect a 25% stroke difference between SBP targets and a 20% difference between LDL-C targets.
EVALuna2:3699

Blood pressure and low-density lipoprotein-cholesterol lowering for prevention of strokes and cognitive decline: a review of available trial evidence - Zanchetti, Alberto; Liu, Lisheng; Mancia, Giuseppe; Parati, Gianfranco; Grassi, Guido; Stramba-Badiale, Marco; Silani, Vincenzo; Bilo, Grzegorz; Corrao, Giovanni; Zambon, Antonella; Scotti, Lorenza; Zhang, Xinhua; et al. (Journal of Hypertension, 2014)
It is well established by a large number of randomized controlled trials that lowering blood pressure (BP) and low-density lipoprotein cholesterol (LDL-C) by drugs are powerful means to reduce stroke incidence, but the optimal BP and LDL-C levels to be achieved are largely uncertain. Concerning BP targets, two hypotheses are being confronted: first, the lower the BP, the better the treatment outcome, and second, the hypothesis that too low BP values are accompanied by a lower benefit and even higher risk. It is also unknown whether BP lowering and LDL-C lowering have additive beneficial effects for the primary and secondary prevention of stroke, and whether these treatments can prevent cognitive decline after stroke.A review of existing data from randomized controlled trials confirms that solid evidence on optimal BP and LDL-C targets is missing, possible interactions between BP and LDL-C lowering treatments have never been directly investigated, and evidence in favour of a beneficial effect of BP or LDL-C lowering on cognitive decline is, at best, very weak.A new, large randomized controlled trial is needed to determine the optimal level of BP and LDL-C for the prevention of recurrent stroke and cognitive decline.
EVALuna2:3698

Blood Pressure Pattern and Target Organ Damage in Patients With Chronic Kidney Disease - Scheppach, Johannes B.; Raff, Ulrike; Toncar, Sebastian; Ritter, Christian; Klink, Thorsten; Stoerk, Stefan; Wanner, Christoph; Schlieper, Georg; Saritas, Turgay; Reinartz, Sebastian D.; Floege, Juergen; Janka, Rolf Matthias; et al. (Hypertension, 2018)
In patients with chronic kidney disease, data on blood pressure (BP) pattern and its association with target organ damage, which indicates elevated cardiovascular risk, are sparse. In 305 treated hypertensive chronic kidney disease patients, we assessed BP pattern, left ventricular mass (magnetic resonance imaging), intima-media thickness (ultrasound), 24-hour-pulse wave velocity and 24-hour-central augmentation index (Mobil-O-Graph). Controlled hypertension (normal office and ambulatory BP) was found in 41% and sustained uncontrolled hypertension (elevated office and ambulatory BP) in 30% of patients. Misclassification of BP status occurred in 29%: white coat uncontrolled hypertension (elevated office but normal ambulatory BP) was detected in 11% and masked uncontrolled hypertension (normal office but elevated ambulatory BP) in 18% of patients. Left ventricular mass was increased in white coat uncontrolled hypertension (+11.2 g), masked uncontrolled hypertension (+9.4 g), and sustained uncontrolled hypertension (+16.6 g) compared with controlled hypertension. Intima-media thickness was similar across all 4 BP groups. Twenty-four hour-pulse wave velocity and 24-hour-central augmentation index were increased in masked uncontrolled hypertension (+0.5 m/sec and +2.5%) and sustained uncontrolled hypertension (+0.5 m/sec and +2.9%) compared with controlled hypertension. In conclusion, based on office BP measurements, misclassification of true BP status occurred in almost one-third of chronic kidney disease patients. Both types of misclassification (white coat uncontrolled hypertension and masked uncontrolled hypertension) were associated with parameters of target organ damage. Ambulatory BP monitoring should be used routinely to identify chronic kidney disease patients at high cardiovascular risk.
EVALuna2:34688

Blood pressure profile, sympathetic nervous system activity, and subclinical target organ damage in patients with polycythemia vera - Jóźwik-Plebanek, Katarzyna; Dobrowolski, Piotr; Lewandowski, Jacek; Narkiewicz, Krzysztof; Sikorska, Anna; Siński, Maciej; Eisenhofer, Graeme; Schmieder, Roland; Januszewicz, Magdalena; Windyga, Jerzy; Prejbisz, Aleksander; Januszewicz, Andrzej (Polish Archives of Internal Medicine, 2020)
INTRODUCTION: Polycythemia vera (PV) is a rare myeloproliferative disease associated with an increased prevalence of hypertension and increased risk of cardiovascular complications. However, the precise mechanisms leading to the elevation of blood pressure (BP) and secondary target organ damage remain poorly understood. OBJECTIVES: The study aimed to evaluate BP profile, assess the activity of the sympathetic nervous system and the renin-angiotensin system, and provide a comprehensive assessment of subclinical target organ damage in patients with PV. PATIENTS AND METHODS: Twenty consecutive patients with newly diagnosed PV and 20 control subjects were included. The following were assessed: BP, levels of catecholamines, urinary and plasma O-methylated catecholamine metabolites, concentrations of aldosterone and renin. We also assessed microneurography sympathetic nervous system activity (MSNA) and baroreflex control of heart rate as well as subclinical target organ damage. RESULTS: At similar levels of BP, BP variability was decreased in the PV group (mean [SD] 24-hour systolic BP, 9 [3] vs 12 [3] mm Hg; P = 0.003). Patients with PV had lower norepinephrine excretion (mean [SD], 16.54 [6.32] vs 25.46 [12.88] μg/d; P = 0.03) as well as decreased MSNA as assessed by microneurography compared with controls (mean [SD] MSNA, 30.7 [8.7] bursts/min vs 38.7 [5.4] bursts/min; P = 0.007 and MSNA 51.8 [11] bursts/100 beats vs 61.1 [11.3] bursts/100 heart beats; P = 0.04). Baroreflex control of HR was unaltered in the PV group. Increased hemoglobin levels and red blood cell count correlated with decreased retinal capillary flow in patients with PV. CONCLUSIONS: Patients with PV, characterized by high hemoglobin concentrations and hematocrit levels had lower sympathetic nervous activity and decreased BP variability as compared with controls. There was no relationship between hemoglobin plasma concentration, hematocrit level, and target organ damage.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Blood pressure profile; Organ damage; Polycythemia vera

Blood pressure reduction after renal denervation in patients with or without chronic kidney disease - Günes-Altan, Merve; Schmid, Axel; Ott, Christian; Bosch, Agnes; Pietschner, Robert; Schiffer, Mario; Uder, Michael; Schmieder, Roland; Kannenkeril, Dennis (Clinical Kidney Journal, 2024)
Background. Renal denervation (RDN) has emerged as an adjacent option for the treatment of hypertension. This analysis of the Erlanger registry aimed to compare the blood pressure (BP)-lowering effects and safety of RDN in patients with and without chronic kidney disease (CKD). Methods. In this single-center retrospective analysis, 47 patients with and 127 without CKD underwent radiofrequency-, ultrasound- or alcohol-infusion-based RDN. Office and 24-h ambulatory BP and estimated glomerular filtration rate (eGFR) were measured at baseline, and after 6 and 12 months. Results. A total of 174 patients with a mean age of 59.0 ± 10 years were followed up for 12 months. At baseline, mean eGFR was 55.8 ± 21 mL/min/1.73 m2 in patients with CKD and 87.3 ± 13 mL/min/1.73 m2 in patients without CKD. There was no significant eGFR decline in either of the groups during 12 months of follow-up. In patients without CKD, office systolic and diastolic BP were reduced by –15.3 ± 17.5/–7.9 ± 10.8 mmHg 6 months after RDN and by –16.1 ± 18.2/–7.7 ± 9.6 mmHg 12 months after RDN. In patients with CKD, office systolic and diastolic BP were reduced by –10.7 ± 24.0/–5.8 ± 13.2 mmHg 6 months after RDN and by –15.1 ± 24.9/–5.9 ± 12.9 mmHg 12 months after RDN. Accordingly, in patients without CKD, 24-h ambulatory systolic and diastolic BP were reduced by –7.2 ± 15.8/–4.9 ± 8.8 mmHg 6 months after RDN and by –9.0 ± 17.0/–6.2 ± 9.8 mmHg 12 months after RDN. In patients with CKD, 24-h systolic and diastolic BP were reduced by –7.4 ± 12.9/–4.2 ± 9.9 mmHg 6 months after RDN and by –8.0 ± 14.0/–3.6 ± 9.6 mmHg 12 months after RDN. There was no difference in the reduction of office and 24-h ambulatory BP between the two groups at any time point (all P > .2). Similar results have been found for the 6 months data. With exception of rare local adverse events, we did not observe any safety signals. Conclusion. According to our single-center experience, we observed a similar reduction in 24-h, day and night-time ambulatory BP as well as in-office BP in patients with and without CKD at any time point up to 12 months. We conclude that RDN is an effective and safe treatment option for patients with hypertension and CKD.
CRIS-Team Scopus Importer:2024-01-26
Keywords: blood pressure; chronic kidney disease; hypertension; post-hoc analysis; renal denervation

BLOOD PRESSURE REDUCTION AFTER RENAL DENERVATION IN PATIENTS WITH OR WITHOUT CHRONIC KIDNEY DISEASE: THE ERLANGER EXPERIENCE - Schmid, Axel; Ott, Christian; Bosch, Agnes; Schiffer, Mario; Uder, Michael; Schmieder, Roland; Kannenkeril, Dennis (JOURNAL OF HYPERTENSION, 2023)
CRIS-Team WoS Importer:2023-03-17

Blood pressure reduction in higher cardiovascular risk patients in the Global SYMPLICITY Registry - Rodriguez, O.; Mahfoud, F.; Schmieder, Roland; Schlaich, M.; Narkiewicz, K.; Ruilope, L.; Williams, B.; Fahy, M.; Mancia, G.; Boehm, M. (European Heart Journal, 2022)
CRIS-Team WoS Importer:2023-03-03

CAN WE IDENTIFY GLOMERULAR HYPERFILTRATION IN PATIENTS WITH TYPE 2 DIABETES BY CLINICAL PARAMETERS? - Kolwelter, Julie; Striepe, Kristina; Kannenkeril, Dennis; Jung, Susanne; Bosch, Agnes; Ott, Christian; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Cardiac effects of hypertension - Schmieder, Roland; Nitschmann, S. (Internist, 2015)
EVALuna2:3766

Cardiovascular and health cost impacts of cuff blood pressure underestimation and overestimation of invasive aortic systolic blood pressure - Fonseca, Ricardo; Palmer, Andrew J.; Picone, Dean S.; Cox, Ingrid A.; Schultz, Martin G.; Black, J. Andrew; Bos, Willem J.W.; Cheng, Hao Min; Chen, Chen Huan; Cremer, Antoine; Dwyer, Nathan; Hughes, Alun D.; et al. (Journal of Hypertension, 2023)
OBJECTIVE: Hypertension management is directed by cuff blood pressure (BP), but this may be inaccurate, potentially influencing cardiovascular disease (CVD) events and health costs. This study aimed to determine the impact on CVD events and related costs of the differences between cuff and invasive SBP. METHODS: Microsimulations based on Markov modelling over one year were used to determine the differences in the number of CVD events (myocardial infarction or coronary death, stroke, atrial fibrillation or heart failure) predicted by Framingham risk and total CVD health costs based on cuff SBP compared with invasive (aortic) SBP. Modelling was based on international consortium data from 1678 participants undergoing cardiac catheterization and 30 separate studies. Cuff underestimation and overestimation were defined as cuff SBP less than invasive SBP and cuff SBP greater than invasive SBP, respectively. RESULTS: The proportion of people with cuff SBP underestimation versus overestimation progressively increased as SBP increased. This reached a maximum ratio of 16 : 1 in people with hypertension grades II and III. Both the number of CVD events missed (predominantly stroke, coronary death and myocardial infarction) and associated health costs increased stepwise across levels of SBP control, as cuff SBP underestimation increased. The maximum number of CVD events potentially missed (11.8/1000 patients) and highest costs (241 300 USD/1000 patients) were seen in people with hypertension grades II and III and with at least 15 mmHg of cuff SBP underestimation. CONCLUSION: Cuff SBP underestimation can result in potentially preventable CVD events being missed and major increases in health costs. These issues could be remedied with improved cuff SBP accuracy.
CRIS-Team Scopus Importer:2023-09-08

Cardiovascular outcomes and achieved blood pressure in patients with and without diabetes at high cardiovascular risk - Böhm, Michael; Schumacher, Helmut; Teo, Koon K.; Lonn, Eva M.; Mahfoud, Felix; Mann, Johannes; Mancia, Giuseppe; Redon, Josep; Schmieder, Roland; Marx, Nikolaus; Sliwa, Karen; Weber, Michael A.; et al. (European Heart Journal, 2019)
AIMS: Studies have shown a non-linear relationship between systolic blood pressure (SBP) and diastolic blood pressure (DBP) and outcomes, with increased risk observed at both low and high blood pressure (BP) levels. We hypothesized that the BP-risk association is different in individuals with and without diabetes at high cardiovascular risk. METHODS AND RESULTS: We identified patients with (N = 11 487) or without diabetes (N = 19 450), from 30 937 patients, from 133 centres in 44 countries with a median follow-up of 56 months in the ONTARGET/TRANSCEND studies. Patients had a prior history of stroke, myocardial infarction (MI), peripheral artery disease, or were high-risk diabetics. Patients in ONTARGET had been randomized to ramipril 10 mg daily, telmisartan 80 mg daily, or the combination of both. Patients in TRANSCEND were ACE intolerant and randomized to telmisartan 80 mg daily or matching placebo. We analysed the association of mean achieved in-trial SBP and DBP with the composite outcome of cardiovascular death, MI, stroke and hospitalization for congestive heart failure (CHF), the components of the composite, and all-cause death. Data were analysed by Cox regression and restricted cubic splines, adjusting for risk markers including treatment allocation and accompanying cardiovascular treatments. In patients with diabetes, event rates were higher across the whole spectrum of SBP and DBP compared with those without diabetes (P < 0.0001 for the primary composite outcome, P < 0.01 for all other endpoints). Mean achieved in-trial SBP ≥160 mmHg was associated with increased risk for the primary outcome [diabetes/no diabetes: adjusted hazard ratio (HR) 2.31 (1.93-2.76)/1.66 (1.36-2.02) compared with non-diabetics with SBP 120 to <140 mmHg], with similar findings for all other endpoints in patients with diabetes, and for MI and stroke in patients without diabetes. In-trial SBP <120 mmHg was associated with increased risk for the combined outcome in patients with diabetes [HR 1.53 (1.27-1.85)], and for cardiovascular death and all-cause death in all patients. In-trial DBP ≥90 mmHg was associated with increased risk for the primary outcome [diabetes/no diabetes: HR 2.32 (1.91-2.82)/1.61 (1.35-1.93) compared with non-diabetics with DBP 70 to <80 mmHg], with similar findings for all other endpoints, but not for CHF hospitalizations in patients without diabetes. In-trial DBP <70 mmHg was associated with increased risk for the combined outcome in all patients [diabetes/no diabetes: HR 1.77 (1.51-2.06)/1.30 (1.16-1.46)], and also for all other endpoints except stroke. CONCLUSION: High on treatment BP levels (≥160 or ≥90 mmHg) are associated with increased risk of cardiovascular outcomes and death. Also low levels (<120 or <70 mmHg) are associated with increased cardiovascular outcomes (except stroke) and death. Patients with diabetes have consistently higher risks over the whole BP range, indicating that achieving optimal BP goals is most impactful in this group. These data favour guidelines taking lower BP boundaries into consideration, in particular in diabetes. CLINICAL TRIAL REGISTRATION: http://clinicaltrials.gov.Unique identifier: NCT00153101.
EVALuna2:118635

Cardiovascular outcomes, bleeding risk, and achieved blood pressure in patients on long-term anticoagulation with the thrombin antagonist dabigatran or warfarin: Data from the RE-LY trial - Böhm, Michael; Brueckmann, Martina; Eikelboom, John W.; Ezekowitz, Michael; Fräßdorf, Mandy; Hijazi, Ziad; Hohnloser, Stefan H.; Mahfoud, Felix; Schmieder, Roland; Schumacher, Helmut; Wallentin, Lars; Yusuf, Salim (European Heart Journal, 2020)
Aims A J-shaped association of cardiovascular events to achieved systolic (SBP) and diastolic (DBP) blood pressure was shown in high-risk patients. This association on oral anticoagulation is unknown. This analysis from RELY assessed the risks of death, stroke or systemic emboli, and bleeding according to mean achieved SBP and DBP in atrial fibrillation on oral anticoagulation. Methods RE-LY patients were followed for 2 years and recruited between 22 December 2005 until 15 December 2007. and results 18.113 patients were randomized in 951 centres in 54 countries and 18,107 patients with complete blood pressure (BP) data were analysed with a median follow-up of 2.0 years and a complete follow-up in 99.9%. The association between achieved mean SBP and DBP on all-cause death, stroke and systemic embolic events (SSE), major, and any bleeding were explored. On treatment, SBP >140 mmHg and <120 mmHg was associated with all-cause death compared with SBP 120-130 mmHg (reference). For SSE, risk was unchanged at SBP <110 mmHg but increased at 140-160 mmHg (adjusted hazard ratio (HR) 1.81; 1.40-2.33) and SBP >_160 mmHg (HR 3.35; 2.09-5.36). Major bleeding events were also increased at <110 mmHg and at 110 to <120 mmHg. Interestingly, there was no increased risk of major bleeding at SBP >130 mmHg. Similar patterns were observed for DBP with an increased risk at <70 mmHg (HR 1.55; 1.35-1.78) and >90 mmHg (HR 1.88; 1.43-2.46) for all-cause death compared to 70 to <80 mmHg (reference). Risk for any bleeding was increased at low DBP <70 mmHg (HR 1.46; 1.37-1.56) at DBP 80 to <90 mmHg (HR 1.13; 1.06-1.31) without increased risk at higher achieved DBP. Dabigatran 150 mg twice daily showed an advantage in all patients for all-cause death and SSE and there was an advantage for 110 mg dabigatran twice daily for major bleeding and any bleeding irrespective of SBP or DBP achieved. Similar results were obtained for baseline BP, time-updated BP, and BP as time-varying covariate. Conclusion Low achieved SBP associates with increased risk of death, SSE, and bleeding in patients with atrial fibrillation on oral anticoagulation. Major bleeding events did not occur at higher BP. Low BP might identify high-risk patients not only for death but also for high bleeding risks.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Anticoagulation; Atrial fibrillation; Bleeding; Blood pressure; Hypertension; Novel anticoagulants; Stroke; Systemic embolism

Cardiovascular outcomes in patients at high cardiovascular risk with previous myocardial infarction or stroke - Boehm, Michael; Schumacher, Helmut; Teo, Koon K.; Lonn, Eva M.; Lauder, Lucas; Mancia, Giuseppe; Redon, Josep; Schmieder, Roland; Sliwa, Karen; Marx, Nikolaus; Weber, Michael A.; Williams, Bryan; et al. (Journal of Hypertension, 2021)
Background: Guidelines recommend to start blood pressure (BP)-lowering drugs also according to cardiovascular risk including history of cardiovascular events. We hypothesized that in patients with a history of myocardial infarction (MI), stroke, both or none of those, the index events predict the next event and have different SBP risk associations to different cardiovascular outcomes. Design and measurements: In this pooled posthoc, nonprespecified analysis, we assessed outcome data from high-risk patients aged 55 years or older with a history of cardiovascular events or proven cardiovascular disease, randomized to the Ongoing Telmisartan Alone and in Combination with Ramipril Global Endpoint Trial and to Telmisartan Randomized Assessment Study in ACE Intolerant Subjects with Cardiovascular Disease Trial investigating telmisartan, ramipril and their combination with a median follow-up of 56 months. Standardized office BP was measured every 6 months. Associations of mean achieved BP on treatment were investigated on MI, stroke and cardiovascular death. We identified patients with previous MI (N = 13 487), stroke (N = 4985), both (N = 1509) or none (N = 10 956) of these index events. Analyses were done by Cox regression, analysis of variance and Chi(2)-test. 30 937 patients with complete data were enrolled between 1 December 2001 and 31 July 2003, and followed until 31 July 2008. Data of both trials were pooled as the outcomes were similar. Results: Patients with MI as index event had a higher risk to experience a second MI [hazard ratio 1.42 (confidence interval (CI) 1.20-1.69), P < 0.0001] compared with patients with no events but no increased risk for a stroke as a next event [hazard ratio 0.95 (CI 0.73-1.23), n.s.]. The risk was roughly doubled when they had both, MI and stroke before [hazard ratio 2.07 (CI 1.58-2.71), P < 0.0001]. Patients with a stroke history had a roughly three-fold higher likelihood to experience a second stroke [hazard ratio 2.89 (CI 2.37-3.53) P < 0.0001] but not MI [hazard ratio 1.07 (CI 0.88-1.32), n.s.]. Both types of index events increased roughly three-fold the risk of a second stroke compared with no previous events. The SBP-risk relationship was not meaningfully altered by the event history. After MI and stroke the risk for subsequent events and cardiovascular death was increased over the whole SBP spectrum. A J-shape relationship between BP and outcome was only observed for cardiovascular death. Conclusion: Previous MI and previous stroke are associated with increased risk for the same event in the future, independent of achieved SBP. Thus, secondary prevention may also be chosen according to the event history of patients.
CRIS-Team WoS Importer:2021-07-23

Cardiovascular Risk Reduction After Renal Denervation According to Time in Therapeutic Systolic Blood Pressure Range - Mahfoud, Felix; Mancia, Giuseppe; Schmieder, Roland; Ruilope, Luis; Narkiewicz, Krzysztof; Schlaich, Markus; Williams, Bryan; Ribichini, Flavio; Weil, Joachim; Kao, Hsien Li; Rodriguez-Leor, Oriol; Noory, Elias; et al. (Journal of the American College of Cardiology, 2022)
Background: Renal denervation (RDN) has been shown to lower blood pressure (BP), but its effects on cardiovascular events have only been preliminarily evaluated. Time in therapeutic range (TTR) of BP is associated with cardiovascular events. Objectives: This study sought to assess the impact of catheter-based RDN on TTR and its association with cardiovascular outcomes in the GSR (Global SYMPLICITY Registry). Methods: Patients with uncontrolled hypertension were enrolled and treated with radiofrequency RDN. Office and ambulatory systolic blood pressure (OSBP and ASBP) were measured at 3, 6, 12, 24, and 36 months postprocedure and used to derive TTR. TTR through 6 months was assessed as a predictor of cardiovascular events from 6 to 36 months using a Cox proportional hazard regression model. Results: As of March 1, 2022, 3,077 patients were enrolled: 42.2% were female; mean age was 60.5 ± 12.2 years; baseline OSBP was 165.6 ± 24.8 mm Hg; and baseline ASBP was 154.3 ± 18.7 mm Hg. Patients were prescribed 4.9 ± 1.7 antihypertensive medications at baseline and 4.8 ± 1.9 at 36 months. At 36 months, mean changes were −16.7 ± 28.4 and −9.0 ± 20.2 mm Hg for OSBP and ASBP, respectively. TTR through 6 months was 30.6%. A 10% increase in TTR after RDN through 6 months was associated with significant risk reductions from 6 to 36 months of 15% for major adverse cardiovascular events (P < 0.001), 11% cardiovascular death (P = 0.010), 15% myocardial infarction (P = 0.023), and 23% stroke (P < 0.001). Conclusions: There were sustained BP reductions and higher TTR through 36 months after RDN. A 10% increase in TTR through 6 months was associated with significant risk reductions in major cardiovascular events from 6 to 36 months. (Global SYMPLICITY Registry [GSR] DEFINE; NCT01534299)
CRIS-Team Scopus Importer:2022-11-11
Keywords: cardiovascular death; hypertension; myocardial infarction; risk reduction; stroke

Catheter-based alcohol-mediated renal denervation for the treatment of uncontrolled hypertension: design of two sham-controlled, randomized, blinded trials in the absence (TARGET BP OFF-MED) and presence (TARGET BP I) of antihypertensive medications - Mahfoud, Felix; Weber, Michael; Schmieder, Roland; Lobo, Melvin D.; Blankestijn, Peter J.; Persu, Alexandre; Fischell, Tim A.; Parise, Helen; Pathak, Atul; Kandzari, David E. (American Heart Journal, 2021)
Background: Arterial hypertension is a common and life-threatening condition and poses a large global health burden. Device-based treatments have been developed as adjunctive or alternative therapy, to be used with or without antihypertensive medication for treating uncontrolled hypertension. The safety and feasibility of chemical renal denervation (RDN) using the Peregrine Catheter and alcohol were demonstrated in a first-in-man and open-label clinical trials, prompting the initiation of the ongoing TARGET BP OFF-MED and TARGET BP I trials. Design: The TARGET BP trials are randomized, blinded, sham-controlled trials designed to assess the safety and efficacy of alcohol-mediated RDN for the treatment of uncontrolled hypertension in the absence of antihypertensive medications (TARGET BP OFF-MED) or in addition to prescribed antihypertensive medications (TARGET BP I). Subjects with confirmed uncontrolled hypertension and suitable renal artery anatomy are randomized (1:1) to receive either RDN using the Peregrine Kit with alcohol (0.6 mL per renal artery) infused through the Peregrine Catheter or diagnostic renal angiography only (sham procedure). TARGET BP OFF-MED completed enrollment and randomized 96 subjects. TARGET BP I will randomize approximately 300 subjects and will transition to an open-label safety cohort of approximately 300 subjects receiving RDN once the primary efficacy endpoint of the Randomized Controlled Trial (RCT) cohort has been met. Primary endpoints are change in mean 24-hour ambulatory systolic blood pressure from baseline to 8 weeks (TARGET BP OFF-MED) and 3 months (TARGET BP I) post-procedure. Conclusion: The TARGET BP trials are the first large-scale, international, randomized trials aimed to investigate the safety and BP lowering efficacy of a novel RDN method, with perivascular alcohol delivery using the Peregrine Kit.
CRIS-Team Scopus Importer:2021-07-23

Catheter-based renal denervation for treatment of patients with treatment-resistant hypertension: 36 month results from the SYMPLICITY HTN-2 randomized clinical trial - Esler, Murray D.; Boehm, Michael; Sievert, Horst; Rump, Christian L.; Schmieder, Roland; Krum, Henry; Mahfoud, Felix; Schlaich, Markus P. (European Heart Journal, 2014)
The aim of this study was to determine long-term results of renal artery denervation for treatment of treatment-resistant hypertension in the SYMPLICITY HTN-2 study.SYMPLICITY HTN-2 randomized 106 subjects with treatment-resistant hypertension to renal denervation or medical therapy alone. At 6 months, 37 control subjects crossed over to renal denervation. Office blood pressure measurements, antihypertensive medication use, and safety events were followed every 6 months through 3 years.Follow-up was available at 36 months in 40 of 52 subjects in the initial renal denervation group and at 30 months in 30 of 37 subjects who crossed over and received renal denervation at 6 months. Baseline blood pressure was 184 ± 19/99 ± 16 mmHg in all treated subjects. At 30-month post-procedure, systolic blood pressure decreased 34 mmHg (95% CI: -40, -27, P < 0.01) and diastolic blood pressure decreased 13 mmHg (95% CI: -16, -10, P < 0.01). The systolic and diastolic blood pressure reduction at 36 months for the initial renal denervation group was -33 mmHg (95% CI: -40, -25, P < 0.01) and -14 mmHg (95% CI: -17, -10, P < 0.01), respectively. Procedural complications included one haematoma, and one renal artery dissection before energy delivery that was treated successfully. Later complications included two cases of acute renal failure, which fully resolved, 15 hypertensive events requiring hospitalization, and three deaths.Renal denervation resulted in sustained lowering of blood pressure at 3 years in a selected population of subjects with severe, treatment-resistant hypertension without serious safety concerns.NCT00888433.
EVALuna2:3697

Catheter-based renal denervation in patients with uncontrolled hypertension in the absence of antihypertensive medications (SPYRAL HTN-OFF MED): a randomised, sham-controlled, proof-of-concept trial - Townsend, Raymond R.; Mahfoud, Felix; Kandzari, David E.; Kario, Kazuomi; Pocock, Stuart; Weber, Michael A.; Ewen, Sebastian; Tsioufis, Konstantinos; Tousoulis, Dimitrios; Sharp, Andrew S.P.; Watkinson, Anthony F.; Schmieder, Roland; et al. (Lancet, 2017)
Previous randomised renal denervation studies did not show consistent efficacy in reducing blood pressure. The objective of our study was to evaluate the effect of renal denervation on blood pressure in the absence of antihypertensive medications.SPYRAL HTN-OFF MED was a multicentre, international, single-blind, randomised, sham-controlled, proof-of-concept trial. Patients were enrolled at 21 centres in the USA, Europe, Japan, and Australia. Eligible patients were drug-naive or discontinued their antihypertensive medications. Patients with an office systolic blood pressure (SBP) of 150 mm Hg or greater and less than 180 mm Hg, office diastolic blood pressure (DBP) of 90 mm Hg or greater, and a mean 24-h ambulatory SBP of 140 mm Hg or greater and less than 170 mm Hg at second screening underwent renal angiography and were randomly assigned to renal denervation or sham control. Patients, caregivers, and those assessing blood pressure were blinded to randomisation assignments. The primary endpoint, change in 24-h blood pressure at 3 months, was compared between groups. Drug surveillance was done to ensure patient compliance with absence of antihypertensive medication. The primary analysis was done in the intention-to-treat population. Safety events were assessed at 3 months. This study is registered with ClinicalTrials.gov, number NCT02439749.Between June 25, 2015, and Jan 30, 2017, 353 patients were screened. 80 patients were randomly assigned to renal denervation (n=38) or sham control (n=42) and followed up for 3 months. Office and 24-h ambulatory blood pressure decreased significantly from baseline to 3 months in the renal denervation group: 24-h SBP -5·5 mm Hg (95% CI -9·1 to -2·0; p=0·0031), 24-h DBP -4·8 mm Hg (-7·0 to -2·6; p<0·0001), office SBP -10·0 mm Hg (-15·1 to -4·9; p=0·0004), and office DBP -5·3 mm Hg (-7·8 to -2·7; p=0·0002). No significant changes were seen in the sham-control group: 24-h SBP -0·5 mm Hg (95% CI -3·9 to 2·9; p=0·7644), 24-h DBP -0·4 mm Hg (-2·2 to 1·4; p=0·6448), office SBP -2·3 mm Hg (-6·1 to 1·6; p=0·2381), and office DBP -0·3 mm Hg (-2·9 to 2·2; p=0·8052). The mean difference between the groups favoured renal denervation for 3-month change in both office and 24-h blood pressure from baseline: 24-h SBP -5·0 mm Hg (95% CI -9·9 to -0·2; p=0·0414), 24-h DBP -4·4 mm Hg (-7·2 to -1·6; p=0·0024), office SBP -7·7 mm Hg (-14·0 to -1·5; p=0·0155), and office DBP -4·9 mm Hg (-8·5 to -1·4; p=0·0077). Baseline-adjusted analyses showed similar findings. There were no major adverse events in either group.Results from SPYRAL HTN-OFF MED provide biological proof of principle for the blood-pressure-lowering efficacy of renal denervation.Medtronic.
EVALuna2:3814

Central arteriovenous anastomosis and hypertension - Authors' reply - Lobo, Melvin D.; Sobotka, Paul A.; Dolan, Eamon; Witkowski, Adam; Schmieder, Roland (Lancet, 2015)
EVALuna2:3831

Central arteriovenous anastomosis for the treatment of patients with uncontrolled hypertension (the ROX CONTROL HTN study): a randomised controlled trial - Lobo, Melvin D.; Sobotka, Paul A.; Stanton, Alice; Cockcroft, John R.; Sulke, Neil; Dolan, Eamon; Van Der Giet, Markus; Hoyer, Joachim; Furniss, Stephen S.; Foran, John P.; Witkowski, Adam; Januszewicz, Andrzej; et al. (Lancet, 2015)
Hypertension contributes to cardiovascular morbidity and mortality. We assessed the safety and efficacy of a central iliac arteriovenous anastomosis to alter the mechanical arterial properties and reduce blood pressure in patients with uncontrolled hypertension.We enrolled patients in this open-label, multicentre, prospective, randomised, controlled trial between October, 2012, and April, 2014. Eligible patients had baseline office systolic blood pressure of 140 mm Hg or higher and average daytime ambulatory blood pressure of 135 mm Hg or higher systolic and 85 mm Hg or higher diastolic despite antihypertensive treatment. Patients were randomly allocated in a 1:1 ratio to undergo implantation of an arteriovenous coupler device plus current pharmaceutical treatment or to maintain current treatment alone (control). The primary endpoint was mean change from baseline in office and 24 h ambulatory systolic blood pressure at 6 months. Analysis was by modified intention to treat (all patients remaining in follow-up at 6 months). This trial is registered with ClinicalTrials.gov, number NCT01642498.83 (43%) of 195 patients screened were assigned arteriovenous coupler therapy (n=44) or normal care (n=39). Mean office systolic blood pressure reduced by 26·9 (SD 23·9) mm Hg in the arteriovenous coupler group (p<0·0001) and by 3·7 (21·2) mm Hg in the control group (p=0·31). Mean systolic 24 h ambulatory blood pressure reduced by 13·5 (18·8) mm Hg (p<0·0001) in arteriovenous coupler recipients and by 0·5 (15·8) mm Hg (p=0·86) in controls. Implantation of the arteriovenous coupler was associated with late ipsilateral venous stenosis in 12 (29%) of 42 patients and was treatable with venoplasty or stenting.Arteriovenous anastomosis was associated with significantly reduced blood pressure and hypertensive complications. This approach might be a useful adjunctive therapy for patients with uncontrolled hypertension.ROX Medical.
EVALuna2:3769

Central arteriovenous anastomosis to treat resistant hypertension - Kapil, Vikas; Sobotka, Paul A.; Lobo, Mel D.; Schmieder, Roland (Current Opinion in Nephrology and Hypertension, 2017)
Novel, interventional treatments have emerged in the last decade for the treatment of resistant hypertension. This review focuses on a unique device that creates a fixed calibre, central iliac arteriovenous anastomosis that is significantly different in haemodynamic and safety profile from traditional haemodialysis fistulae. The background, physiology, and clinical data to date will be presented.The single, randomized, controlled clinical trial using the ROX coupler in patients with resistant hypertension demonstrated substantial reductions in both office and ambulatory blood pressure to 12-month postimplantation. There was a common, but manageable, adverse effect of upstream iliac venous stenosis causing ipsilateral lower limb oedema. There were no renal safety concerns. The mechanism of action is proposed to be mechanical by provision of a low-pressure parallel circuit attached to the high-pressure arterial system though detailed physiological evaluation is currently lacking.Preliminary data using the ROX coupler to form a central arteriovenous anastomosis are very encouraging. Concerns regarding the lack of sham control are to some extent mitigated by immediate on table blood pressure reduction with opening of the coupler and will be further addressed in the ongoing pivotal, sham-controlled ROX CONTROL Hypertension2 study which should provide further robust information regarding efficacy and safety.
EVALuna2:4031

Central Iliac Arteriovenous Anastomosis for Uncontrolled Hypertension: One-Year Results From the ROX CONTROL HTN Trial - Lobo, Melvin D.; Ott, Christian; Sobotka, Paul A.; Saxena, Manish; Stanton, Alice; Cockcroft, John R.; Sulke, Neil; Dolan, Eamon; Van Der Giet, Markus; Hoyer, Joachim; Furniss, Stephen S.; Foran, John P.; et al. (Hypertension, 2017)
Creation of a central iliac arteriovenous anastomosis using a novel nitinol coupler device results in an immediate, significant reduction of blood pressure (BP). We present efficacy and safety findings at 12 months post-coupler insertion. This open-label, multicenter, prospective, randomized trial enrolled patients with a baseline office systolic BP >=140 mm Hg and average daytime ambulatory BP >=135/85 mm Hg. Subjects were randomly allocated to coupler implantation and continuing previous pharmacotherapy or to maintain previous treatment alone. At 12 months, 39 patients who had coupler therapy were included in the intention-to-treat analysis. Office-based systolic BP reduced by 25.1±23.3 mm Hg (baseline, 174±18 mm Hg; P<0.0001) post-coupler placement, and office diastolic BP reduced by 20.8±13.3 mm Hg (baseline, 100±13 mm Hg; P<0.0001). Mean 24-hour ambulatory BP reduced by 12.6±17.4/15.3±9.7 mm Hg (P<0.0001 for both). In a prespecified subset of patients who failed to respond adequately to prior renal denervation, coupler therapy led to highly significant reduction in office systolic/diastolic BP (30.7/24.1 mm Hg) and significant reduction in 24-hour ambulatory systolic/diastolic BP (12.4/14.4 mm Hg) at 12 months (n=9). After coupler therapy, 14 patients (33%) developed ipsilateral venous stenosis; all were treated successfully with venous stenting. These findings confirm the importance of arterial mechanics in the pathophysiology of hypertension and support the clinical use of a central iliac arteriovenous anastomosis.URL: http://www.clinicaltrials.gov. Unique identifier: NCT01642498.
EVALuna2:4029

Central pulse pressure is an independent determinant of vascular remodeling in the retinal circulation - Ott, Christian; Raff, Ulrike; Harazny, Joanna M.; Michelson, Georg; Schmieder, Roland (Hypertension, 2013)
Pulse pressure has been recognized as a risk factor for stroke. Moreover, it was shown that central pulse pressure relates more strongly to vascular disease and outcome than (peripheral) brachial pulse pressure. Because vascular remodeling in the retinal circulation mirrors the 1 in the cerebral circulation and represents an easy, noninvasive possibility to assess microvascular changes in humans, we analyzed the impact of central pulse pressure on retinal vascular structure in humans. The study cohort comprised 135 nondiabetic patients across a wide range of blood pressure values. Parameter of retinal arteriolar remodeling (wall-to-lumen ratio) was assessed noninvasively and in vivo by scanning laser Doppler flowmetry. Central pulse pressure and augmentation index normalized to a heart rate of 75 beats per minute were assessed by pulse wave analysis. Central pulse pressure correlated with wall-to-lumen ratio (r=0.302; P<0.001), central augmentation index normalized to a heart rate of 75 beats per minute correlated with wall-to-lumen ratio (r=0.190; P=0.028), and in accordance pulse pressure amplification (peripheral pulse pressure/central pulse pressure) was negatively correlated with wall-to-lumen ratio (r=-0.223; P=0.009). In contrast, central mean arterial pressure was not correlated with wall-to-lumen ratio (r=0.110; P=0.203). Multiple regression analysis revealed an independent relationship between wall-to-lumen ratio and central pulse pressure (?=0.277; P=0.009), but not with other classical cardiovascular risk factors. Thus, central pulse pressure, indicative of changes in large conduit arteries is an independent determinant of vascular remodeling in small retinal arterioles. Such a relationship indicates a coupling and crosstalk between the microvascular and macrovascular changes attributable to hypertension.
EVALuna2:3610

Central pulse pressure predicts BP reduction after renal denervation in patients with treatment-resistant hypertension - Ott, Christian; Schmid, Axel; Toennes, Stefan W.; Ditting, Tilmann; Veelken, Roland; Uder, Michael; Schmieder, Roland (EuroIntervention, 2015)
Enhanced vascular ageing is associated with elevated central pulse pressure (cPP), an independent predictor of cardiovascular (CV) events. Although antihypertensive treatment strategies are effective, high residual CV risk remains indicative of advanced and largely irreversible vascular damage. Renal denervation (RDN) has been shown to reduce blood pressure (BP) to various extents in patients with treatment-resistant hypertension (TRH). We hypothesised that cPP predicts BP reduction after RDN.Sixty-three patients with true TRH underwent catheter-based RDN using the Symplicity Flex(TM) catheter and were followed for six months. At baseline, cPP was assessed by pulse wave analysis (SphygmoCor(TM)). Patients were stratified according to their median cPP (55 mmHg), and called "low cPP" (below the median) or "high cPP" (above the median). Office BP reduction six months after RDN was greater (-22±19/-13±11 vs. -12±20/-5±13 mmHg, p=0.038/0.014) and 24-hr ambulatory blood pressure (ABP) reduction tended to be greater (-11±13/-8±10 vs. -3±18/-4±10 mmHg, p=0.070/0.112) in patients with low cPP compared to those with high cPP. Only cPP (?=0.687, p=0.001) and baseline systolic BP (?=-0.564, p<0.001) were independent determinants of office systolic BP reduction after RDN.Our data suggest that cPP, indicative of the degree of large arterial stiffening, may be helpful to identify responders to RDN.
EVALuna2:3764

Change of renal function after short-term use of cardioprotective agents in patients with type 2 diabetes is not accurately assessed by the change of estimated glomerular filtration rate: an observational study - Kolwelter, Julie; Striepe, Kristina; Bosch, Agnes; Kannenkeril, Dennis; Ott, Christian; Schiffer, Mario; Schmieder, Roland (Diabetology & Metabolic Syndrome, 2022)
Background After initiating cardioprotective agents, a fall of estimated glomerular filtration rate (eGFR) has been reported in several studies. Our goal was to evaluate the accuracy of change of Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) eGFR in patients with type 2 diabetes (T2D) after short-term pharmacological intervention with angiotensin-converting enzyme inhibitor, angiotensin-receptor blocker, gliptin or sodium-glucose cotransporter-2 inhibitor. Methods We analyzed 190 patients with T2D in the early stage of the disease, having no overt renal impairment by CKD-EPI equation. In each patient, we measured GFR (mGFR) by applying the constant infusion input clearance technique with sinistrin (Inutest; Fresenius, Linz, Austria) at baseline and after short-term (4-12 weeks) pharmacological intervention with cardioprotective agents (ramipril, telmisartan, linagliptin, metformin, empagliflozin) that potentially lead to an alteration of renal function. Simultaneously, a standardized analysis of serum creatinine was performed and eGFR was estimated by the CKD-EPI equation. Results Average mGFR was 111 +/- 20 ml/min/1.73m(2), whereas eGFR was lower with 93 +/- 13 ml/min/1.73m(2). The ratio eGFR/mGFR in relation to mGFR was almost curvilinear, showing an underestimation of renal function by eGFR in the upper normal range. At baseline only 80 patients (42%) lay within +/- 10% of mGFR and the concordance correlation coefficient (CCC) was extremely low (- 0.07). After short-term pharmacological intervention changes in eGFR and mGFR correlated with each other (r = 0.286, p < 0.001). For example, for a given mGFR of 111 ml/min/1.73m(2), a change of mGFR by +/- 10% corresponded to +/- 11 ml/min/1.73m(2), but the confidence interval of eGFR was 25 ml/min/1.73m(2). The CCC was low (0.22). Conclusion The agreement between eGFR by CKD-EPI and mGFR is modest and the change of renal function after short-term pharmacological intervention is not accurately and precisely reflected by the change of eGFR in patients with T2D in the early stage of their disease.
CRIS-Team WoS Importer:2022-08-05

Changes in 24-Hour Patterns of Blood Pressure in Hypertension Following Renal Denervation Therapy - Kario, Kazuomi; Weber, Michael A.; Mahfoud, Felix; Kandzari, David E.; Schmieder, Roland; Kirtane, Ajay J.; Boehm, Michael; Hettrick, Douglas A.; Townsend, Raymond R.; Tsioufis, Konstantinos P. (Hypertension, 2019)
CRIS-Team WoS Importer:2019-08-23

Changes in blood pressure after crossover to ultrasound renal denervation in patients initially treated with sham in the RADIANCE-HTN SOLO trial - Mahfoud, Felix; Bloch, Michael J.; Azizi, Michel; Wang, Yale; Schmieder, Roland; Lobo, Melvin D.; Sharp, Andrew S. P.; Daemen, Joost; Basile, Jan; Weber, Michael A.; Scicli, Andrea P.; Mcclure, Candace K.; et al. (EuroIntervention, 2021)
Background: The multicentre, randomised, sham-controlled RADIANCE-HTN SOLO trial reported the blood pressure (BP)-lowering efficacy and safety of ultrasound renal denervation (RDN) in the absence (2 months) and presence (6 and 12 months) of antihypertensive medications in patients with mild-to-moderate hypertension.
CRIS-Team WoS Importer:2022-01-07

Changes in Plasma Renin Activity After Renal Artery Sympathetic Denervation - Mahfoud, Felix; Townsend, Raymond R.; Kandzari, David E.; Kario, Kazuomi; Schmieder, Roland; Tsioufis, Konstantinos; Pocock, Stuart; David, Shukri; Patel, Kiritkumar; Rao, Anjani; Walton, Antony; Bloom, Jason E.; et al. (Journal of the American College of Cardiology, 2021)
Background: The renin-angiotensin-aldosterone system plays a key role in blood pressure (BP) regulation and is the target of several antihypertensive medications. Renal denervation (RDN) is thought to interrupt the sympathetic-mediated neurohormonal pathway as part of its mechanism of action to reduce BP. Objectives: The purpose of this study was to evaluate plasma renin activity (PRA) and aldosterone before and after RDN and to assess whether these baseline neuroendocrine markers predict response to RDN. Methods: Analyses were conducted in patients with confirmed absence of antihypertensive medication. Aldosterone and PRA levels were compared at baseline and 3 months post-procedure for RDN and sham control groups. Patients in the SPYRAL HTN-OFF MED Pivotal trial were separated into 2 groups, those with baseline PRA ≥0.65 ng/ml/h (n = 110) versus <0.65 ng/ml/h (n = 116). Follow-up treatment differences between RDN and sham control groups were adjusted for baseline values using multivariable linear regression models. Results: Baseline PRA was similar between RDN and control groups (1.0 ± 1.1 ng/ml/h vs. 1.1 ± 1.1 ng/ml/h; p = 0.37). Change in PRA at 3 months from baseline was significantly greater for RDN compared with control subjects (−0.2 ± 1.0 ng/ml/h; p = 0.019 vs. 0.1 ± 0.9 ng/ml/h; p = 0.14), p = 0.001 for RDN versus control subjects, and similar differences were seen for aldosterone: RDN compared with control subjects (−1.2 ± 6.4 ng/dl; p = 0.04 vs. 0.4 ± 5.4 ng/dl; p = 0.40), p = 0.011. Treatment differences at 3 months in 24-h and office systolic blood pressure (SBP) for RDN versus control patients were significantly greater for patients with baseline PRA ≥0.65 ng/ml/h versus <0.65 ng/ml/h, despite similar baseline BP. Differences in office SBP changes according to baseline PRA were also observed earlier at 2 weeks post-RDN. Conclusions: Plasma renin activity and aldosterone levels for RDN patients were significantly reduced at 3 months when compared with baseline as well as when compared with sham control. Higher baseline PRA levels were associated with a significantly greater reduction in office and 24-h SBP. (SPYRAL PIVOTAL - SPYRAL HTN-OFF MED Study; NCT02439749)
CRIS-Team Scopus Importer:2021-06-11
Keywords: aldosterone; hypertension; plasma renin activity; renal denervation

Changes in Stroke Volume After Renal Denervation: Insight From Cardiac Magnetic Resonance Imaging - Lurz, Philip; Kresoja, Karl Patrik; Rommel, Karl Philipp; von Roeder, Maximilian; Besler, Christian; Lücke, Christian; Gutberlet, Matthias; Schmieder, Roland; Mahfoud, Felix; Thiele, Holger; Desch, Steffen; Fengler, Karl (Hypertension, 2020)
Recent trial results support catheter-based renal denervation (RDN) for treatment of hypertension, while the exact mechanisms causing blood pressure to fall remain incompletely understood. Cardiac magnetic resonance imaging was used to assess the effects of RDN on cardiac function in patients with hypertension undergoing RDN and compared with sham treatment. Cardiac magnetic resonance imaging was used to assess stroke volume index, cardiac index, heart rate, systemic vascular resistance index, and stroke work index from aortic flow measurements. Patients with resistant hypertension from a randomized, sham-controlled RDN trial underwent cardiac magnetic resonance imaging before RDN and at follow-up (randomized cohort). Results were then validated in a cohort of patients with resistant hypertension undergoing RDN and cardiac magnetic resonance imaging (validation cohort). In total, 162 patients were included 52 patients in the randomized trial (27 shams) and 110 patients in the validation cohort. In the randomized cohort, stroke volume index was reduced by 4.7±9.8 mL/m2 in the RDN cohort and remained unchanged in the sham cohort (P=0.008 for between-group comparison), while cardiac index and stroke work index tended to be reduced in RDN patients but not in sham patients (-0.10±5.9 versus 0.17±0.51 L/min per m2 and -7.1±12.5 versus -1.4±10.4 g/m2, P=0.08 for both). In contrast, systemic vascular resistance index and heart rate remained unchanged after RDN. In the validation cohort, reduction of stroke volume index was confirmed, and cardiac index and stroke work index were also reduced significantly, whereas systemic vascular resistance index and heart rate remained unchanged at follow-up. In this study of patients with resistant hypertension, RDN resulted in a reduction of stroke volume when compared with sham.
CRIS-Team Scopus Importer:2020-03-17
Keywords: blood pressure; hemodynamics; magnetic resonance imaging; renal denervation; stroke volume

Chronic Kidney Disease - Diagnosis and Treatment - Galle, J.; Schmieder, Roland; Weinreich, T. (Diabetes Stoffwechsel und Herz, 2021)
Around five to eight million people in Germany are affected by chronic kidney disease (CKD), with incidence and prevalence continuing to rise and a high number of unknown cases. CKD is defined as persistent kidney damage associated with declining kidney function. Hypertension, diabetes, and obesity accelerate the process, resulting in increased risk of cardiovascular disease and mortality. CKD is diagnosed in screening tests (urine test or blood test) and imaging techniques for determining overall kidney function, and then classified into stages to enable appropriate therapy. This review article aims to summarise current knowledge on CKD and place it into a clinical context focusing on CKD classification, diagnosis, complications, essential current treatment options, and recommendations on when general practitioners should refer patients to a nephrologist.
CRIS-Team WoS Importer:2022-02-11

Circadian rhythm and day to day variability of serum potassium concentration: a pilot study - Schmidt, Stefan; Ditting, T.; Deutsch, Birgit; Schutte, R.; Friedrich, S.; Kistner, I.; Ott, Christian; Raff, U.; Veelken, Roland; Schmieder, Roland (Journal of Nephrology, 2015)
Hyperkalemia is a common and life-threatening complication frequently seen in patients with acute kidney injury, end-stage renal disease and chronic heart failure. Cardiac arrest and ventricular fibrillation are possible consequences. Biosensors are currently being developed to measure serum potassium under ambulatory conditions and trigger an alarm if the potassium concentration exceeds normal limits. Only few studies exist on the circadian rhythm of potassium; and its dependence on age and kidney function is less clear.Our observational monocentric exploratory study included 30 subjects of which 15 had impaired renal function (RF) (GFR <60 ml/min/1.73 m(2)). Subjects were further categorized into three age groups: 18-39 years (N normal RF = 5, N impaired RF = 4), 40-59 years (N normal RF = 5, N impaired RF = 6), 60-80 years (N normal RF = 5, N impaired RF = 5). Serum potassium levels were measured every 2 h during a 24 h period and repeated once after 2, 4, or 6 days.In the 15 subjects with normal RF, the lowest mean potassium level (3.96 ± 0.14 mmol/l) was observed at 9 p.m. and the greatest (4.23 ± 0.23 mmol/l) at 1 p.m. In patients with impaired RF the lowest mean potassium level (4.20 ± 0.32 mmol/l) was observed at 9 p.m. and the highest (4.57 ± 0.46 mmol/l) at 3 p.m. The range between the mean of minimum and maximum was greater in patients with impaired RF (0.71 ± 0.45 mmol/l) than in subjects with normal RF (0.53 ± 0.14 mmol/l) [p < 0.001]. No difference in the circadian rhythm was found between the first and second examination.Our results indicate that patients with normal and impaired RF have comparable circadian patterns of serum potassium concentrations, but higher fluctuations in patients with impaired RF. These results have clinical relevance for developing an automatic biosensor to measure the potassium concentration in blood under ambulatory conditions in patients at high risk for potassium fluctuations.
EVALuna2:3700

CLINICAL EVENT REDUCTIONS IN HIGH-RISK HYPERTENSION PATIENTS TREATED WITH RENAL DENERVATION: 10-YEAR PROJECTIONS BASED ON 3-YEAR FOLLOW-UP FROM THE GLOBAL SYMPLICITY REGISTRY - Esler, Murray; Cao, Khoa; Lobo, Melvin; Sharp, Andrew S. P.; Kandzari, David E.; Mancia, Giuseppe; Bohm, Michael; Schmieder, Roland; Pietzch, Jan B. (JOURNAL OF HYPERTENSION, 2022)
CRIS-Team WoS Importer:2023-02-17

CLINICAL EVENT REDUCTIONS IN HIGH-RISK HYPERTENSION PATIENTS TREATED WITH RENAL DENERVATION: 10-YEAR PROJECTIONS BASED ON 3-YEAR FOLLOW-UP FROM THE GLOBAL SYMPLICITY REGISTRY - Esler, Murray; Cao, Khoa; Lobo, Melvin; Sharp, Andrew S.P.; Kandzari, David E.; Mancia, Giuseppe; Böhm, Michael; Schmieder, Roland; Pietzch, Jan B. (Journal of Hypertension, 2022)
OBJECTIVE: Clinical event rates over 3 years have been published for patients with uncontrolled hypertension treated with radiofrequency renal denervation (RDN) in the Global SYMPLICITY Registry (GSR). We estimated 10-year clinical event reductions following RDN vs. a simulated control group without RDN, for two high-risk subgroups and the full GSR cohort. DESIGN AND METHOD: A Markov model was used to compare projected 10-year clinical events [stroke, myocardial infarction (MI), cardiovascular death (CVD), heart failure (HF), all-cause death (ACD), and a composite of major adverse cardiac events (MACE, calculated as sum of stroke, MI, and CVD)] for RDN patients vs. a hypothetical control for the high atherosclerotic vascular disease risk (ASCVD) subgroup (n = 737; 69 ± 8 years), the type-2 diabetes mellitus (T2DM) subgroup (n = 1,007; 64 ± 10 years), and for all GSR patients (n = 2,651; 61 ± 12 years). The simulated control assumed maintenance of baseline office systolic blood pressure (oSBP) over time. The model was calibrated to 3-year stroke and MI events reported in the GSR and used published meta-regression data to calculate risk reduction based on cohort-specific changes in oSBP from baseline. Relative risks (RRs), events avoided, and numbers needed to treat (NNTs) were calculated at 3 and 10 years, along with the ratio of 10- vs. 3-year projected events avoided. RESULTS: 10-year MACE events were 35.8% vs. 48.5% (-12.7%, RR = 0.74) for RDN vs. control for all GSR patients, 37.8% vs. 52.4% (-14.6%, RR = 0.72) for the high ASCVD risk cohort, and 40.5% vs. 54.0% (-13.5%, RR = 0.75) for the T2DM cohort. Across all three cohorts, events avoided were highest for stroke and lowest for MI. 10-year NNTs for MACE were comparable between the three cohorts, estimated between 7 to 8. The ratio of model-projected MACE at 10- vs. 3-years was 5.20, 5.46, and 5.03 for the full GSR, high ASCVD risk, and T2DM cohorts, respectively. CONCLUSIONS: Model-based projections based on 3- year events observed in the GSR suggest meaningful event reductions after treatment with radiofrequency RDN at 10 years that might be up to 5-times higher than the projected events avoided at 3 years under the assumption of maintained treatment effect versus baseline.
CRIS-Team Scopus Importer:2022-09-09

Clinical event reductions in high-risk patients after renal denervation projected from the global SYMPLICITY registry - Schmieder, Roland; Mahfoud, Felix; Mancia, Giuseppe; Narkiewicz, Krzysztof; Ruilope, Luis; Hutton, David; Cao, Khoa; Hettrick, Douglas A.; Fahy, Martin; Schlaich, Markus P.; Bohm, Michael; Pietzsch, Jan B. (European Heart Journal - Quality of Care and Clinical Outcomes, 2022)
Aims Renal denervation has been shown to lower blood pressure in sham-controlled trials and represents a device-based treatment option for hypertension. We sought to project clinical event reductions after radiofrequency renal denervation using a novel modelling approach. Methods and results The Global SYMPLICITY Registry is a global, prospective all-comer registry to evaluate safety and efficacy after renal denervation. For this analysis, change in office systolic blood pressure from baseline was calculated from reported follow-up in the Global SYMPLICITY Registry. Relative risks for death and other cardiovascular events as well as numbers needed to treat for event avoidance were obtained for the respective blood pressure reductions based on previously reported meta-regression analyses for the full cohort and high-risk subgroups including type 2 diabetes, chronic kidney disease, resistant hypertension, and high basal cardiovascular risk. Average baseline office systolic blood pressure and reduction estimates for the full cohort (N = 2651) were 166 +/- 25 and -14.8 +/- 0.4 mmHg, respectively. Mean reductions in blood pressure ranged from -11.0–21.8 mmHg for the studied high-risk subgroups. Projected relative risks ranged from 0.57 for stroke in the resistant hypertension cohort to 0.92 for death in the diabetes cohort. Significant absolute reductions in major adverse cardiovascular events over 3 years compared with the projected control (8.6 +/- 0.7% observed vs. 11.7 +/- 0.9% for projected control; P < 0.01) were primarily due to reduced stroke incidence. The robustness of findings was confirmed in sensitivity and scenario analyses. Conclusion Model-based projections suggest radiofrequency renal denervation for patients with uncontrolled hypertension adds considerable clinical benefit across a spectrum of different cohort characteristics.
CRIS-Team WoS Importer:2022-10-21

Clinical impact of patient adherence to a fixed-dose combination of olmesartan, amlodipine and hydrochlorothiazide - Bramlage, Peter; Ketelhut, Reinhard; Fronk, Eva-Maria; Wolf, Wolf-Peter; Smolnik, Ruediger; Zemmrich, Claudia; Schmieder, Roland (Clinical Drug Investigation, 2014)
Recent findings from randomized clinical trials indicate an improved patient adherence and blood pressure (BP) control by using fixed-dose combinations (FDCs) in the treatment of hypertension. The aim of the present study was to verify those data in a large real-world sample of hypertensive patients and to cross-check adherence evaluation performed by physicians and patients self-assessment.A European multi-center, prospective, 24-week, non-interventional study was conducted including 14,979 patients with essential hypertension and new treatment with olmesartan, amlodipine and hydrochlorothiazide as an FDC. Patients' adherence was measured using the Morisky Medication Adherence Scale (MMAS-8) and a non-standardized questionnaire was used by physicians and patients for self-assessment.The mean age of the patients was 63.9 ± 11.78 years and 46.5 % were women. One or more cardiovascular risk factors were present in 71.9 % of patients and 94.7 % had been treated for hypertension before study entry. Mean adherence to medication by MMAS-8 improved from 6.0 to 6.9 at study end. Corresponding improvements of adherence were seen on physicians' and patients' self-assessments throughout the study. Mean decrease of systolic/diastolic BP was 26.4/12.8 mmHg without a relevant difference between the MMAS-8 adherence levels. BP target achievement improved from 55.3 to 67.7 % in patients with low versus high adherence. The overall rate of patients with adverse drug reactions was very low (1.76 %) but more frequent in patients with low adherence.Our data confirm previous clinical trial data on the improvement of medication adherence by switching antihypertensive combination therapy to an FDC and a subsequent improvement in BP target achievement. An observed trend toward a reduction in adverse drug reactions needs to be further investigated in clinical trials.
EVALuna2:3678

Clinical Trial Design Principles and Outcomes Definitions for Device-Based Therapies for Hypertension: A Consensus Document From the Hypertension Academic Research Consortium - Kandzari, David E.; Mahfoud, Felix; Weber, Michael A.; Townsend, Raymond; Parati, Gianfranco; Fisher, Naomi D. L.; Lobo, Melvin D.; Bloch, Michael; Bohm, Michael; Sharp, Andrew S. P.; Schmieder, Roland; Azizi, Michel; et al. (Circulation, 2022)
The clinical implications of hypertension in addition to a high prevalence of both uncontrolled blood pressure and medication nonadherence promote interest in developing device-based approaches to hypertension treatment. The expansion of device-based therapies and ongoing clinical trials underscores the need for consistency in trial design, conduct, and definitions of clinical study elements to permit trial comparability and data poolability. Standardizing methods of blood pressure assessment, effectiveness measures beyond blood pressure alone, and safety outcomes are paramount. The Hypertension Academic Research Consortium (HARC) document represents an integration of evolving evidence and consensus opinion among leading experts in cardiovascular medicine and hypertension research with regulatory perspectives on clinical trial design and methodology. The HARC document integrates the collective information among device-based therapies for hypertension to better address existing challenges and identify unmet needs for technologies proposed to treat the world's leading cause of death and disability. Consistent with the Academic Research Consortium charter, this document proposes pragmatic consensus clinical design principles and outcomes definitions for studies aimed at evaluating device-based hypertension therapies.
CRIS-Team WoS Importer:2022-03-25

Cocoa Flavanol Cardiovascular Effects Beyond Blood Pressure Reduction - Jumar, Agnes; Schmieder, Roland (Journal of Clinical Hypertension, 2016)
The protective cardiovascular (CV) effect of cocoa flavanol has been a target of many recent clinical prospective and retrospective investigations. Epidemiological data in different patient cohorts revealed an association between higher intake of flavanol-rich foods and decreased incidence of CV events, especially stroke and myocardial infarction. Cocoa flavanol has been shown to reduce systolic (2.8 mm Hg) and diastolic (2.2 mm Hg) office blood pressure (BP). Greater BP reduction has been found in hypertensive patients and people younger than 50 years. Cocoa flavanol intake exerts beneficial effects on pathophysiologic mechanisms of hypertension-related organ damage, such as improved endothelial function, anti-inflammatory potency, inhibition of platelet activation, and increased vasodilatory capacity. Recent clinical trials have focused on establishing a potential link between epidemiology and pathophysiology of flavanol and identified possible mechanisms for prevention of end-organ damage in patients at CV risk. This review summarizes the available data on the antihypertensive effects of cocoa flavanol beyond BP-BP lowering lowering effects, accentuates subgroup-specific protective actions of cocoa according to patients' different CV risk profile, and outlines potential cocoa flavanol-associated clinical implications.
EVALuna2:3801

Combination of empagliflozin and linagliptin improves blood pressure and vascular function in type 2 diabetes - Jung, Susanne; Bosch, Agnes; Kannenkeril, Dennis; Karg, Marina V.; Striepe, Kristina; Bramlage, Peter; Ott, Christian; Schmieder, Roland; Jung, Susanne (European Heart Journal - Cardiovascular Pharmacotherapy, 2020)
AIMS: Preserved vascular function represents a key prognostic factor in type 2 diabetes mellitus (T2DM), but data on vascular parameters in this patient cohort are scarce. Patients with T2DM often need more than one drug to achieve optimal glucose control. The aim of this study was to analyse the efficacy of two combination therapies on vascular function in subjects with T2DM. METHODS AND RESULTS: This prospective, randomized study included 97 subjects with T2DM. Subjects were randomized to either the combination therapy empagliflozin (E) 10 mg with linagliptin (L) 5 mg once daily or metformin (M) 850 or 1000 mg twice daily with insulin glargine (I) once daily. At baseline and after 12 weeks, subjects had peripheral office and 24-h ambulatory blood pressure (BP) measurement and underwent vascular assessment by pulse wave analysis under office and ambulatory conditions. Office, 24-h ambulatory and central BP as well as pulse pressure (PP) decreased after 12 weeks of treatment with E + L, whereas no change was observed in M + I. There were greater decreases in 24-h ambulatory peripheral systolic (between-group difference: -5.2 ± 1.5 mmHg, P = 0.004), diastolic BP (-1.9 ± 1.0 mmHg, P = 0.036), and PP (-3.3 ± 1.0 mmHg, P = 0.007) in E + L than M + I. Central office systolic BP (-5.56 ± 1.9 mmHg, P = 0.009), forward pressure height of the pulse wave (-2.0 ± 0.9 mmHg, P = 0.028), 24-h ambulatory central systolic (-3.6 ± 1.4 mmHg, P = 0.045), diastolic BP (-1.95 ± 1.1 mmHg, P = 0.041), and 24-h pulse wave velocity (-0.14 ± 0.05m/s, P = 0.043) were reduced to a greater extent with E + L. CONCLUSION: Beyond the effects on glycaemic control, the combination therapy of E + L significantly improved central BP and vascular function compared with the classic combination of M + I. CLINICALTRIALS.GOV: NCT02752113.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Blood pressure; Central haemodynamics; Empagliflozin; Linagliptin; T2DM; Vascular function

Combined therapy of empagliflozin and linagliptin is superior to metformin and insulin glargine in improving blood pressure and vascular function in type 2 diabetes - Jung, Susanne; Bosch, Agnes; Kannenkeril, Dennis; Karg, M.; Striepe, Kristina; Bramlage, P.; Ott, Christian; Schmieder, Roland (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Comeback of Renal Denervation As Treatment Option in Patients with Hypertension - Jung, Susan; Schmieder, Roland (Aktuelle Kardiologie, 2019)
The effectiveness of renal denervation to reduce blood pressure has been controversially discussed. After a few uncontrolled pilot studies had shown promising results with respect to the effectiveness of this method, the results of the Symplicity HTN-3 study were discouraging: no significant difference in blood pressure reduction between denervation and sham group could be observed. The results of three sham-controlled studies were finally able to prove the effectiveness of renal denervation: in comparison to sham-procedure, a significant office and 24-h ambulatory blood pressure reduction could be achieved. The findings obtained from these studies provide interesting future perspectives with respect to the application of the technique in other diseases and patients that profit most from renal denervation.
CRIS-Team WoS Importer:2019-10-29

Comments on the consensus paper on renal denervation of the working group on hypertension of the European Society of Cardiology (ESC) and the European Association of Percutaneous Cardiovascular Interventions (EAPCI) Kommentar zum Konsensuspapier zur renalen Denervation der Arbeitsgruppe Hypertonie der European Society of Cardiology (ESC) und der European Association of Percutaneous Cardiovascular Interventions (EAPCI) - Halbach, Marcel; Boer, Jana; Böhm, Michael; Busch, Sonia; Dörr, Oliver; Elsässer, Albrecht; Erbel, Christian; Galle, Jan Christoph; Kintscher, Ulrich; Limbourg, Florian P.; Reuter, Hannes; Rump, Lars C.; et al. (Die Kardiologie, 2023)
Since the publication of the ESC/ESH guidelines on arterial hypertension in 2018, several sham-controlled, high-quality trials on renal denervation have been published, which demonstrated the safety and efficacy of renal denervation. Therefore, renal denervation is an additional therapeutic option for patients with uncontrolled resistant hypertension, whereby the latter should be confirmed by ambulatory blood pressure monitoring. Renal denervation may also be applied in selected patients with drug intolerances. Decision making should take patient preferences after comprehensive information and the individual cardiovascular risk into account. A multidisciplinary hypertension team should establish the indications for renal denervation and perform the treatment. Interventionalists must be experienced in performing renal interventions and receive a special training for renal denervation. In Germany, renal denervation should be performed by specialized centers, which fulfill personal, spatial and technical criteria as defined by the national societies [23].
CRIS-Team Scopus Importer:2023-07-14
Keywords: Interventional treatment; Nonadherence; Patient selection; Renal artery; Resistant hypertension

Comments on the guidelines (2018) of the European Society of Cardiology (ESC) and the European Society of Hypertension (ESH) on themanagement of arterial hypertension - Mahfoud, F.; Boehm, M.; Bongarth, C. M.; Bosch, R.; Schmieder, Roland; Schunkert, H.; Stellbrink, C.; Trenkwalder, P.; Vonend, O.; Weil, J.; Kreutz, R. (Der Kardiologe, 2019)
Arterial hypertension represents one of the most frequent chronic diseases that can lead to complications, such as stroke, dementia, heart attack, heart failure and renal failure. By 2025 the number of hypertensive patients will increase to approximately 1.6 billion people worldwide. The new guidelines of the European Society of Cardiology (ESC) and the European Society of Hypertension (ESH) on the management of arterial hypertension replace the guidelines of the ESC/ESH from 2013. The 2018 guidelines of the ESC/ESH were adopted by the German Cardiac Society and the German Hypertension League. In these comments national characteristics are worked out and the essential new aspects of the guidelines are critically discussed. These include, for example, the definition of hypertension, the importance of out of office blood pressure measurements, revised blood pressure targets, the modified algorithm for drug treatment and the relevance of device-based hypertension treatments. Important aspects for the management of hypertensive emergencies are also presented.
CRIS-Team WoS Importer:2019-03-08

Comments on the guidelines (2018) of the European Society of Cardiology (ESC) and the European Society of Hypertension (ESH) on the management of arterial hypertension [Kommentar zu den Leitlinien (2018) der Europäischen Gesellschaft für Kardiologie (ESC) und der Europäischen Gesellschaft für Hypertonie (ESH) für das Management der arteriellen Hypertonie] - Mahfoud, F.; Boehm, M.; Bongarth, C. M.; Bosch, R.; Schmieder, Roland; Schunkert, H.; Stellbrink, C.; Trenkwalder, P.; Vonend, O.; Weil, J.; Kreutz, R. (Internist, 2019)
Arterial hypertension represents one of the most frequent chronic diseases that can lead to complications, such as stroke, dementia, heart attack, heart failure and renal failure. By 2025 the number of hypertensive patients will increase to approximately 1.6 billion people worldwide. The new guidelines of the European Society of Cardiology (ESC) and the European Society of Hypertension (ESH) on the management of arterial hypertension replace the guidelines of the ESC/ESH from 2013. The 2018 guidelines of the ESC/ESH were adopted by the German Cardiac Society and the German Hypertension League. In these comments national characteristics are worked out and the essential new aspects of the guidelines are critically discussed. These include, for example, the definition of hypertension, the importance of out of office blood pressure measurements, revised blood pressure targets, the modified algorithm for drug treatment and the relevance of device-based hypertension treatments. Important aspects for the management of hypertensive emergencies are also presented.
CRIS-Team Scopus Importer:2019-05-07
Keywords: Device-based hypertension treatment; Fixed combination; Guidelines; Hypertension; Hypertensive emergencies; Target blood pressure

Comparison of Early Retinal Microvascular Changes and Microalbuminuria as Indicators for Increased Cardioascular Risk - Huchzermeyer, Cord; Schaller, Barbara; Schmid, Kathrin; Schmieder, Roland; Michelson, Georg (Klinische Monatsblätter für Augenheilkunde, 2011)
Prevention of cardiovascular disease is an important goal in clinical medicine and public health. In the process, the diagnosis of early end-organ damage is a priority beside the treatment of classic cardiovascular risk factors. To achieve this, the ophthalmoscopic examination of the retinal vessels plays a prominent role. Alternatively, the quantification of low quantities of albumin in the urine (microalbuminuria) allows the detection of early vascular damage in the kidney. The question is addressed as to whether these two methods are interchangeable or are rather complementary.We examined 226 members of the staff of the University Hospital Erlangen who volunteered to participate in a preventive campaign. A comprehensive history was taken, and height, weight and blood pressure were measured. Analysis of serum lipids and determination of the urinary albumin/creatinine ratio were performed. Fotos of the central fundus were taken with a non-mydriatic camera and analysed by an experienced ophthalmologist in a standardised fashion. The risk for cardiovascular mortality within the next ten years was estimated from age, sex, blood pressure and serum cholesterol using the euroSCORE tables for Germany.There was no signficant correlation between the arteriovenous ratio of the retinal vessels and the urinary albumin/creatinine ratio. Neither parameter correlated with the euroSCORE Germany. Arteriovenous crossings and focal narrowing of the retinal vessels were associated signficantly with an elevated euroSCORE risk.In large population-based studies, the arteriovenous ratio and the urinary albumin/creatinine ratio have been confirmed as markers of cardiovascular risk. In our study, there was no correlation between these two parameters. Thus, they seem to present independent risk markers. The presence of arteriovenous crossings and focal narrowing seems to be linked more closely to the classic cardiovascular risk factors from which the euroSCORE is calculated. The ophathlmolscopic examination of retinal vessels and the analysis of urinary albumin/creatinine ratio seem to complement rather than replace each other.
EVALuna2:3434

Complex reinnervation pattern after unilateral renal denervation in rats - Rodionova, Kristina; Fiedler, Christian; Günther, Franziska; Grouzmann, Eric; Neuhuber, Winfried; Fischer, Michael; Ott, Christian; Linz, Peter; Freisinger, Wolfgang; Heinlein, Sonja; Schmidt, Stefan; Schmieder, Roland; et al. (American Journal of Physiology-Regulatory Integrative and Comparative Physiology, 2016)
Renal denervation (DNX) is a treatment for resistant arterial hypertension. Efferent sympathetic nerves regrow, but reinnervation by renal afferent nerves has only recently been shown in the renal pelvis of rats after unilateral DNX. We examined intrarenal perivascular afferent and sympathetic efferent nerves after unilateral surgical DNX. Tyrosine hydroxylase (TH), CGRP, and smooth muscle actin were identified in kidney sections from 12 Sprague-Dawley rats, to distinguish afferents, efferents, and vasculature. DNX kidneys and nondenervated kidneys were examined 1, 4, and 12 wk after DNX. Tissue levels of CGRP and norepinephrine (NE) were measured with ELISA and mass spectrometry, respectively. DNX decreased TH and CGRP labeling by 90% and 95%, respectively (P < 0.05) within 1 wk. After 12 wk TH and CGRP labeling returned to baseline with a shift toward afferent innervation (P < 0.05). Nondenervated kidneys showed a doubling of both labels within 12 wk (P < 0.05). CGRP content decreased by 72% [3.2 ± 0.3 vs. 0.9 ± 0.2 ng/gkidney; P < 0.05] and NA by 78% [1.1 ± 0.1 vs. 0.2 ± 0.1 pmol/mgkidney; P < 0.05] 1 wk after DNX. After 12 wk, CGRP, but not NE, content in DNX kidneys was fully recovered, with no changes in the nondenervated kidneys. The use of phenol in the DNX procedure did not influence this result. We found morphological reinnervation and transmitter recovery of afferents within 12 wk after DNX. Despite morphological evidence of sympathetic regrowth, NE content did not fully recover. These results suggest a long-term net surplus of afferent influence on the DNX kidney may be contributing to the blood pressure lowering effect of DNX.
EVALuna2:3840

Confounding Factors in Renal Denervation Trials Revisiting Old and Identifying New Challenges in Trial Design of Device Therapies for Hypertension - Kandzari, David E.; Mahfoud, Felix; Bhatt, Deepak L.; Boehm, Michael; Weber, Michael A.; Townsend, Raymond R.; Hettrick, Douglas A.; Schmieder, Roland; Tsioufis, Konstantinos; Kario, Kazuomi (Hypertension, 2020)
Recent randomized sham-controlled trials have demonstrated significant blood pressure reductions following renal denervation (RDN) in patients with hypertension, both in the presence and absence of antihypertensive therapy. These new data encouraged us to revisit previously published insights into potential clinical trial confounding factors that informed the design and conduct of forthcoming trials. Initially identified confounders related to procedural technique, medication variability, and selected patient subgroups have been addressed in contemporary trial design. Regarding procedural method and technology, blood pressure reductions may be improved by ensuring circumferential lesion creation in the distal renal arteries and branch vessels. Safety of the RDN procedure has been demonstrated in multiple independent meta-analyses including thousands of treated patients with low reported rates of renal vessel complications and maintenance of renal function. However, a newer generation of RDN trials has also introduced insights related to medication adherence, patient selection, and the definition of treatment response. Evolving evidence indicates that RDN therapy may be considered in higher risk populations of uncontrolled hypertension regardless of ethnicity and in patients expressing a strong preference for a nondrug therapy option. Despite advances in procedural technique and clinical trial conduct, inconsistent antihypertensive-drug adherence behavior remains perhaps the most critical clinical trial design issue for device-based hypertension therapies. As the balance in clinical equipoise increasingly favors RDN, justification of sham-controlled trial designs will be revisited, and novel study designs may be required to evaluate the safety and efficacy of novel devices and procedures intended to address the escalating prevalence of poorly controlled hypertension.
CRIS-Team WoS Importer:2020-10-23

Continuation of the ESH-CHL-SHOT trial after publication of the SPRINT: rationale for further study on blood pressure targets of antihypertensive treatment after stroke - Zanchetti, Alberto; Liu, Lisheng; Mancia, Giuseppe; Parati, Gianfranco; Grassi, Guido; Stramba-Badiale, Marco; Silani, Vincenzo; Bilo, Grzegorz; Corrao, Giovanni; Zambon, Antonella; Scotti, Lorenza; Zhang, Xinhua; et al. (Journal of Hypertension, 2016)
EVALuna2:3833

COPEPTIN AS A RESEARCH MARKER IN CARDIOVASCULAR DISEASE - Bosch, Agnes; Ott, C.; Schmid, Andrea; Kannenkeril, Dennis; Karg, M.; Ditting, T.; Veelken, Roland; Uder, Michael; Schmieder, Roland (2018)
EVALuna2:202963

COPEPTIN LEVELS IN PATIENTS WITH TREATMENT RESISTANT HYPERTENSION BEFORE AND AFTER RENAL DENERVATION - Jumar, A.; Ott, Christian; Schmid, Axel; Kannenkeril, Dennis; Ditting, T.; Veelken, Roland; Uder, Michael; Schmieder, Roland (2017)
EVALuna2:36267

Copeptin levels in patients with treatment resistant hypertension before and six months after renal denervation - Bosch, Agnes; Schmid, Axel; Ott, Christian; Kannenkeril, Dennis; Karg, Marina V.; Ditting, Tilmann; Veelken, Roland; Uder, Michael; Schmieder, Roland (American Journal of Hypertension, 2019)
BACKGROUND: Copeptin, the C-terminal peptide of pro-vasopressin, is released from the neurohypophysis and reflects the activity of the hormone arginine vasopressin in patients with hypertension. Elevated copeptin levels are associated with increased cardiovascular and all-cause mortality. The aim of this study is to compare copeptin levels in patients with treatment resistant hypertension (TRH) before and 6 months after renal denervation (RDN). METHODS: Copeptin was measured in 34 patients with TRH and 30 patients with primary hypertension stage 1 or 2 (HT). In addition, copeptin levels were measured in patients with TRH at 6 month follow-up visit after RDN. RDN was performed by an experienced interventionalist applying at least four ablations longitudinally and rotationally within the lengths of each renal artery to cover a full four quadrant ablation. RESULTS: In patients with TRH 24h ambulatory blood pressure (BP) decreased from 154±15/ 87±12 mmHg to 146±13/ 83±7.9 mmHg after RDN (systolic: p=0.001, diastolic: p=0.034). There was no significant change in copeptin levels in these 34 patients with TRH before versus six months after RDN (median 8.4 [interquartile range 3.6-14] vs 8.5 [4.5-13] pmol/l, p=0.334). Patients with TRH had higher copeptin levels (p=0.024) than patients with HT (24h ambulatory BP: 142±11/ 91±8.3 mmHg, copeptin: 4.2 [2.8-6.3] pmol/l). CONCLUSION: Patients with TRH showed 2 fold higher copeptin levels than patients with HT. RDN did not lead to any change of copeptin levels in patients with TRH 6 months after procedure despite significant fall in BP.
EVALuna2:210911

Correction to: Cost Effectiveness of Endovascular Ultrasound Renal Denervation in Patients with Resistant Hypertension (PharmacoEconomics - Open, (2024), 10.1007/s41669-024-00472-z) - Taylor, Rod S.; Bentley, Anthony; Metcalfe, Kaylie; Lobo, Melvin D.; Kirtane, Ajay J.; Azizi, Michel; Clark, Christopher; Murphy, Kieran; Boer, Jennifer H.; van Keep, Marjolijn; Ta, An Thu; Barman, Neil C.; et al. (PharmacoEconomics - Open, 2024)
In this article, the columns of Tables 2 and 3 have been incorrectly labelled: 'uRDN' and 'uRDN plus SoC'. They should read: ‘uRDN plus SoC’ and 'SoC alone’. The original article has been corrected.
CRIS-Team Scopus Importer:2024-05-17

Correction to: Percutaneous Creation of a Central Iliac Arteriovenous Anastomosis for the Treatment of Arterial Hypertension - Bertog, Stefan C.; Sobotka, Nathan A.; Sobotka, Paul A.; Lobo, Melvin D.; Sievert, Kolja; Vaskelyte, Laura; Sievert, Horst; Schmieder, Roland (Current Hypertension Reports, 2018)
In the March 2018 issue of Current Hypertension Reports, the second author's name Nathan A. Sobotka was inadvertently left out of the byline. Also, the author names were changed from initials to spelled out. The corrected author list is given above. The original article has been corrected.
EVALuna2:34236

Correction to: Rationale and design of two randomized sham‑controlled of catheter‑based renal denervation in subjects with uncontrolled hypertension in the absence (SPYRAL HTN‑OFF MED Pivotal) and presence (SPYRAL HTN‑ON MED Expansion) of antihypertensive medications: a novel approach using Bayesian design (Clinical Research in Cardiology, (2020), 109, 3, (289-302), 10.1007/s00392-020-01595-z) - Böhm, Michael; Townsend, Raymond R.; Kario, Kazuomi; Kandzari, David; Mahfoud, Felix; Weber, Michael A.; Schmieder, Roland; Tsioufis, Konstantinos; Hickey, Graeme L.; Fahy, Martin; DeBruin, Vanessa; Brar, Sandeep; et al. (Clinical Research in Cardiology, 2020)
The original version of this article unfortunately contained a mistake. The sentence within the section “Bayesian design and prespecified interim analyses” should read: Due to a Bayesian power prior approach being used, a non-standard parameterization for the ANCOVA model is used to allow for informative prior distributions to be placed separately on the RDN and control arm effects: (Formula presented.).
CRIS-Team Scopus Importer:2020-04-21

COST-EFFECTIVENESS ANALYSIS OF NEXT GENERATION RENAL DENERVATION THERAPY DEVICES: THRESHOLD ANALYSIS AND PROJECTIONS OF THE SPYRAL HTN-ON MED TRIAL FOR GERMANY - Pietzsch, J. B.; Geisler, B. P.; Schmieder, Roland (VALUE IN HEALTH, 2018)
CRIS-Team WoS Importer:2019-03-15

Cost-effectiveness of catheter-based radiofrequency renal denervation for the treatment of uncontrolled hypertension: an analysis for the UK based on recent clinical evidence - Sharp, Andrew S.P.; Cao, Khoa N.; Esler, Murray D.; Kandzari, David E.; Lobo, Melvin D.; Schmieder, Roland; Pietzsch, Jan B. (European Heart Journal - Quality of Care and Clinical Outcomes, 2024)
Aims Catheter-based radiofrequency renal denervation (RF RDN) has recently been approved for clinical use in the European Society of Hypertension guidelines and by the US Food and Drug Administration. This study evaluated the lifetime cost-effectiveness of RF RDN using contemporary evidence. ............................................................................................................................................................................................ Methods and A decision–analytic model based on multivariate risk equations projected clinical events, quality-adjusted life years results (QALYs), and costs. The model consisted of seven health states: hypertension alone, myocardial infarction (MI), other symptomatic coronary artery disease, stroke, heart failure (HF), end-stage renal disease, and death. Risk reduction associated with changes in office systolic blood pressure (oSBP) was estimated based on a published meta-regression of hypertension trials. The base case effect size of −4.9 mmHg oSBP (observed vs. sham control) was taken from the SPYRAL HTN-ON MED trial of 337 patients. Costs were based on National Health Service England data. The incremental cost-effectiveness ratio (ICER) was evaluated against the UK National Institute for Health and Care Excellence (NICE) cost-effectiveness threshold of £20 000–30 000 per QALY gained. Extensive scenario and sensitivity analyses were conducted, including the ON-MED subgroup on three medications and pooled effect sizes. RF RDN resulted in a relative risk reduction in clinical events over 10 years (0.80 for stroke, 0.88 for MI, 0.72 for HF), with an increase in health benefit over a patient’s lifetime, adding 0.35 QALYs at a cost of £4763, giving an ICER of £13 482 per QALY gained. Findings were robust across tested scenarios. ............................................................................................................................................................................................ Conclusion Catheter-based radiofrequency RDN can be a cost-effective strategy for uncontrolled hypertension in the UK, with an ICER substantially below the NICE cost-effectiveness threshold.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Cost–benefit analysis; Denervation; England; Hypertension; Radio frequency ablation

Cost Effectiveness of Endovascular Ultrasound Renal Denervation in Patients with Resistant Hypertension - Taylor, Rod S.; Bentley, Anthony; Metcalfe, Kaylie; Lobo, Melvin D.; Kirtane, Ajay J.; Azizi, Michel; Clark, Christopher; Murphy, Kieran; Boer, Jennifer H.; van Keep, Marjolijn; Ta, An Thu; Barman, Neil C.; et al. (PharmacoEconomics - Open, 2024)
Background: Resistant hypertension (rHTN) is defined as blood pressure (BP) of ≥ 140/90 mmHg despite treatment with at least three antihypertensive medications, including a diuretic. Endovascular ultrasound renal denervation (uRDN) aims to control BP alongside conventional BP treatment with antihypertensive medication. This analysis assesses the cost effectiveness of the addition of the Paradise uRDN System compared with standard of care alone in patients with rHTN from the perspective of the United Kingdom (UK) health care system. Methods: Using RADIANCE-HTN TRIO trial data, we developed a state-transition model. Baseline risk was calculated using Framingham and Prospective Cardiovascular Münster (PROCAM) risk equations to estimate the long-term cardiovascular risks in patients treated with the Paradise uRDN System, based on the observed systolic BP (SBP) reduction following uRDN. Relative risks sourced from a meta-analysis of randomised controlled trials were then used to project cardiovascular events in patients with baseline SBP (‘control’ patients); utility and mortality inputs and costs were derived from UK data. Costs and outcomes were discounted at 3.5% per annum. Modelled outcomes were validated against trial meta-analyses and the QRISK3 algorithm and real-world evidence of RDN effectiveness. One-way and probabilistic sensitivity analyses were conducted to assess the uncertainty surrounding the model inputs and sensitivity of the model results to changes in parameter inputs. Results were reported as incremental cost-effectiveness ratios (ICERs). Results: A mean reduction in office SBP of 8.5 mmHg with uRDN resulted in an average improvement in both absolute life-years (LYs) and quality-adjusted life-years (QALYs) gained compared with standard of care alone (0.73 LYs and 0.67 QALYs). The overall base-case ICER with uRDN was estimated at £5600 (€6500) per QALY gained (95% confidence interval £5463–£5739 [€6341–€6661]); modelling demonstrated > 99% probability that the ICER is below the £20,000–£30,000 (€23,214–€34,821) per QALYs gained willingness-to-pay threshold in the UK. Results were consistent across sensitivity analyses and validation checks. Conclusions: Endovascular ultrasound RDN with the Paradise system offers patients with rHTN, clinicians, and healthcare systems a cost-effective treatment option alongside antihypertensive medication.
CRIS-Team Scopus Importer:2024-02-09

Cost of poor adherence to anti-hypertensive therapy in five European countries - Mennini, F. S.; Marcellusi, Andrea; Von Der Schulenburg, J. M. Graf; Gray, A.; Levy, P.; Sciattella, P.; Soro, M.; Staffiero, G.; Zeidler, J.; Maggioni, A.; Schmieder, Roland (European Journal of Health Economics, 2015)
The financial burden for EU health systems associated with cardiovascular disease (CV) has been estimated to be nearly <euro>110 billion in 2006, corresponding to 10 % of total healthcare expenditure across EU or a mean <euro>223 annual cost per capita. The main purpose of this study is to estimate the costs related to hypertension and the economic impact of increasing adherence to anti-hypertensive therapy in five European countries (Italy, Germany, France, Spain and England). A probabilistic prevalence-based decision tree model was developed to estimate the direct costs of CV related to hypertension (CV defined as: stroke, heart attack, heart failure) in five European countries. Our model considered adherence to hypertension treatment as a main driver of blood pressure (BP) control (BP < 140/90 mmHg). Relative risk of CV, based on controlled or uncontrolled BP group, was estimated from the Framingham Heart Study and national review data. Prevalence and cost data were estimated from national literature reviews. A national payer (NP) perspective for 10 years was considered. Probabilistic sensitivity analysis was performed in order to evaluate uncertainty around the results (given as 95 % confidence intervals). The model estimated a total of 8.6 million (1.4 in Italy, 3.3 in Germany, 1.2 in Spain, 1.8 in France and 0.9 in England) CV events related to hypertension over the 10-year time horizon. Increasing the adherence rate to anti-hypertensive therapy to 70 % (baseline value is different for each country) would lead to 82,235 fewer CV events (24,058 in Italy, 7,870 in Germany, 18,870 in Spain, 24,855 in France and 6,553 in England). From the NP perspective, the direct cost associated with hypertension was estimated to be <euro>51.3 billion (8.1 in Italy, 17.1 in Germany, 12.2 in Spain, 8.8 in France and 5.0 in England). Increasing adherence to anti-hypertensive therapy to 70 % would save a total of <euro>332 million (CI 95 %: <euro>319-346 million) from the NPs perspective. This study is the first attempt to estimate the economic impact of non-adherence amongst patients with diagnosed hypertension in Europe, using data from five European countries (Italy, France, Germany, Spain and England).</euro></euro></euro></euro></euro>
EVALuna2:3753

Criteria of the German Cardiac Society (DGK), the German Hypertension League DHL (R)/German Society for Hypertension and Prevention and the German Society for Nephrology (DGfN) on certification of renal denervation centers (RDZ)-Update - Mahfoud, Felix; Galle, Jan; Schunkert, Heribert; Schmieder, Roland; Rump, Lars C.; Limbourg, Florian P.; Van Der Giet, Markus; Elsaesser, Albrecht; Kintscher, Ulrich; Boehm, Michael; Weil, Joachim (Der Kardiologe, 2021)
Arterial hypertension is highly prevalent and remains the most common modifiable risk factor for cardiovascular morbidity and mortality worldwide. In the development and progression of uncontrolled hypertension an increased sympathetic nerve activity has been identified as a main contributor. Catheter-based renal denervation was developed to selectively modulate renal sympathetic activity. Recently, several randomized sham-controlled trials have proven the efficacy and safety of renal denervation in patients with uncontrolled hypertension. Hence, one may expect renal denervation to be used as part of clinical practice some time soon. This paper aims to define national criteria for centers who wish to perform renal denervation procedures and to optimize care pathways for patients with uncontrolled hypertension. Centers may apply for certification once they fulfill all criteria.
CRIS-Team WoS Importer:2021-07-30

Current status of nephroprotection in diabetology Aktueller Stand der Nephroprotektion in der Diabetologie - Schmieder, Roland; Striepe, Kristina (Die Diabetologie, 2024)
Type 2 diabetes (T2DM) is the most common cause of chronic kidney disease (CKD), with about 40% of patients with T2DM developing CKD. The possibilities for nephroprotection have significantly expanded recently. In addition to the well-known nephroprotective effects of renin–angiotensin system inhibitors, there are additional evidence-based treatment options to reduce the progression of CKD, and possibly prevent it in some cases. In addition to antihypertensive, antihyperglycemic and lipid-lowering therapies, sodium–glucose cotransporter 2 (SGLT2) inhibitors, glucagon-like peptide‑1 (GLP-1) receptor agonists and nonsteroidal mineralocorticoid receptor antagonists are now well established in national and international guidelines for treating CKD in T2DM. Holistic, individualized, and early treatment is important for patients with T2DM and CKD.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Diabetes mellitus; type 2; Diabetic nephropathies; Guideline; Kidney protection; Mineralocorticoid receptor antagonists

Daytime systolic ambulatory blood pressure with a two-step switch from candesartan to olmesartan monotherapy and the fixed-dose combination of olmesartan/amlodipine in patients with uncontrolled essential hypertension (SEVICONTROL-2) - Bramlage, Peter; Zemmrich, Claudia; Gansz, Andrea; Sturm, Claus-Dieter; Fimmers, Rolf; Nadal, Jennifer; Schmieder, Roland; Schrader, Joachim; Lueders, Stephan (Journal of Clinical Hypertension, 2014)
The objective of this study was to investigate the efficacy of the fixed-dose combination olmesartan/amlodipine 40/10 mg in patients with moderate essential hypertension not controlled on candesartan 32 mg. This was a prospective, single-arm, phase IV study. The primary endpoint was the change in mean daytime systolic blood pressure (BP). A total of 77 of 89 screened patients started candesartan 32 mg, 62 olmesartan 40 mg, and 57 olmesartan 40 mg/amlodipine 10 mg. Mean daytime systolic BP was reduced by 9.8±15.2 mm Hg (P<.001) vs candesartan monotherapy. Office BP reduction was 9.2±18.8/5.0±8.9 mm Hg (P<0.001). Treatment goals (<140/90 mm Hg for office and <135/85 mm Hg for ambulatory BP) were achieved in 58.2% and 78.4% of patients, respectively. There was one drug-related adverse event (edema) and no serious adverse events. Patients of Caucasian ethnicity with moderate essential hypertension uncontrolled on candesartan experienced a further drop in BP using olmesartan and amlodipine.
EVALuna2:3682

Dependency of flow-mediated vasodilatation from basal nitric oxide activity - Kannenkeril, Dennis; Bosch, Agnes; Kolwelter, Julie; Jung, Susanne; Striepe, Kristina; Ott, Christian; Delles, Christian; Schmieder, Roland (Clinical Physiology and Functional Imaging, 2021)
Background: Flow-mediated vasodilatation (FMD) has become one of the most widely assessed parameters to analyse endothelial and vascular function in cardiovascular medicine. The degree of contribution of nitric oxide (NO) to FMD is inconclusive and varies widely depending on the device used. In this study, we used a semi-automatic ultrasound device to analyse to what extent basal NO activity contributes to FMD of the brachial artery. Methods: FMD was assessed with the UNEX EF device in a cross-over single blinded randomized study at baseline and then during infusion of either a NO-synthase-inhibitor (NG-monomethyl-L-arginine (L-NMMA)) or saline. The analysis was repeated after 1 week with the alternative infusion of L-NMMA or saline. All measurements were analysed both automatically and by a technician manually. Results: In total, 25 healthy men subjects completed the study. Diastolic blood pressure and heart rate significantly changed during infusion of L-NMMA. Infusion of L-NMMA reduced FMD significantly (−37%, p = 0.002). Saline solution had no effect on FMD (+14%, p = 0.392). Change in FMD was significantly different between the groups (ΔFMDL-NMMA vs. ΔFMDsaline, p = 0.032). There was a statistically significant correlation between automatically analysed results and those obtained by an experienced technician (FMDsaline: r = 0.822, p < 0.001; FMDL-NMMA: r = 0.645, p = 0.007). Conclusion: The influence of NO on FMD is approximately 40% if assessed using the UNEX EF. Prior to use FMD as a marker of endothelial dysfunction, we should explore different methods including various duration of forearm ischaemia to increase NO dependency of FMD.
CRIS-Team Scopus Importer:2021-04-02
Keywords: basal nitric oxide activity; flow-mediated vasodilatation; UNEX EF

DETAILED ANALYSIS OF VASCULAR STIFFNESS IN PATIENTS WITH CHRONIC HEART FAILURE - Pietschner, Robert; Kolwelter, Julie; Bosch, Agnes; Striepe, Kristina; Kannenkeril, Dennis; Ott, Christan; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2022)
CRIS-Team WoS Importer:2022-07-29

DETAILED ANALYSIS OF VASCULAR STIFFNESS IN PATIENTS WITH CHRONIC HEART FAILURE - Pietschner, Robert; Kolwelter, Julie; Bosch, Agnes; Striepe, Kristina; Kannenkeril, Dennis; Ott, Christan; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (Journal of Hypertension, 2022)
OBJECTIVE: Risk factors for chronic heart failure (CHF) lead as well to vascular stiffness of the large arteries, increasing thereby the afterload imposed on the left ventricle and deteriorating the clinical condition of CHF. The aim of this project was twofold: to compare vascular stiffness of patients with CHF (CHF+) to those without CHF (CHF-) and to analyse whether vascular stiffness is related to the severity of CHF. DESIGN AND METHOD: In this cross-sectional project a total of 223 patients were included (CHF+: n = 105, CHF-: n = 118). Patients in an euvolaemic state with a reduced left ventricular ejection fraction (LVEF) were included in the CHF+ group. The measurement of the pulse wave velocity (PWV), the most accepted vascular stiffness parameter, and the recording of the arterial pulse wave were performed using the SphygmoCor TM XCEL System under resting conditions. Under ambulatory conditions, blood pressure (BP) and vascular stiffness parameters were assessed by a validated device (Mobil-O-Graph, I.E.M.) over 24 hours. Additionally, blood and spot urine samples were used to measure laboratory markers, in particular NT-pro-BNP. RESULTS: Vascular stiffness parameters between the CHF+ and the CHF- group differed for resting central SBP (CHF+: 116.66 ± 15.18 mmHg, CHF-: 122.83 ± 15.87 mmHg, p = 0.004) and central augmentation index (CHF+: 21.24 ± 11.76 %, CHF-: 13.69 ± 11.49 %, p = <0.001) as well as for ambulatory central SBP (CHF+: 114.46 ± 15.35 mmHg, CHF-: 120.69 ± 13.97 mmHg, p = 0.007) and PWV (CHF+: 9.39 ± 1.56 m/s, CHF-: 8.19 ± 1.65 m/s, p = <0.001). In patients with CHF, greater levels of NT-pro-BNP were related to a higher central SBP (r = 0.292, p = 0.005), higher PWV (r = 0.340, p = <0.001) and a trend to higher central PP (r = 0.198, p = 0.058), after full adjustment for CHF risk factors and gender. In accordance, higher levels of NT-pro-BNP were related to a higher ambulatory peripheral PP (r = 0.322, p = 0.002) and total peripheral resistance (r = 0.227, p = 0.041). CONCLUSIONS: In patients with stable CHF we observed a worse vascular stiffness and function, compared to patients with no CHF. The extent of vascular stiffness and dysfunction was related to the severity of CHF.
CRIS-Team Scopus Importer:2022-09-09

Detection of Changes in Renal Blood Flow Using Arterial Spin Labeling MRI - Kannenkeril, Dennis; Janka, Rolf Matthias; Bosch, Agnes; Jung, Susanne; Kolwelter, Julie; Striepe, Kristina; Ott, Christian; Martirosian, Petros; Schiffer, Mario; Uder, Michael; Schmieder, Roland (American Journal of Nephrology, 2021)
Background: Alteration in kidney perfusion is an early marker of renal damage. The purpose of this study was to evaluate if changes in renal blood flow (RBF) could be detected using MRI with arterial spin labeling (ASL) technique. Methods: RBF as assessed by cortical (CRBF), medullary, and total renal blood flow (TRBF) were measured by MRI with arterial spin labeling (ASL-MRI) using flow-sensitive alternating inversion recovery true fast imaging with steady-state precession sequence. In 11 normotensive healthy individuals (NT) and 11 hypertensive patients (HT), RBF was measured at baseline and after both feet were covered with cold ice packs (cold pressor test) that activates the sympathetic nervous system. In another experiment, RBF was measured in 10 patients with CKD before and after a pharmacological intervention. We compared RBF measurements between the 3 study populations. Results: A significant reduction in CRBF (p = 0.042) and a trend in TRBF (p = 0.053) were observed in response to the activation of the sympathetic nervous system. A trend toward reduction of CRBF (p = 0.051) and TRBF (p = 0.059) has been detected after pharmacological intervention. TRBF was significantly lower in patients with HT and CKD patients compared to NT individuals (NT vs. HT, p = 0.014; NT vs. CKD, p = 0.004). TRBF was lower in patients with CKD compared to HT (p = 0.047). Conclusion: Our data indicate that both acute and short-term changes in RBF could be detected using ASL-MRI. We were able to detect differences in RBF between healthy and diseased individuals by needing only small sample size per group. Thus, ASL-MRI offers an advantage in conducting clinical trials compared to other technologies.
CRIS-Team Scopus Importer:2021-04-02
Keywords: ASL-MRI; Cold pressor test; Renal blood flow

DETECTION OF CHANGES IN RENAL BLOOD FLOW USING ARTERIAL SPIN LABELING MRI - Kannenkeril, Dennis; Janka, Rolf Matthias; Bosch, Agnes; Jung, Susanne; Kolwelter, Julie; Striepe, Kristina; Ott, Christian; Martirosian, Petros; Schiffer, Mario; Uder, Michael; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Determinants of arterial stiffness in patients with type 2 diabetes mellitus: a cross sectional analysis - Staef, Mawadah; Ott, Christian; Kannenkeril, Dennis; Striepe, Kristina; Schiffer, Mario; Schmieder, Roland; Bosch, Agnes (Scientific Reports, 2023)
In patients with type 2 diabetes mellitus (T2DM) arterial stiffness is associated with increased cardiovascular and total mortality. Little is known about determinants of arterial stiffness in clinical routine. Identification of potential determinants of arterial stiffness will help to address treatment targets for patients in the early state of T2DM. This is a cross-sectional analysis of arterial stiffness in 266 patients in the early stage of T2DM who did not have cardiovascular or renal complications. Parameters of arterial stiffness such as central systolic blood pressure (cSBP), central pulse pressure (cPP) and pulse wave velocity (PWV) were measured with the SphygmoCor System (AtCor Medical). We investigated the influence of parameters of glucose metabolism, lipid status, body constitution, blood pressure (BP) and inflammation on the stiffness parameters using multivariate regression analysis. The study cohort consisted of male and female patients aged 61 ± 8 years with mean diabetes duration of 6.4 ± 5.1 years, mean HbA1c 7.1 ± 0.9%, mean cSBP 121 ± 12 mmHg, mean cPP 44 ± 10 mmHg and mean PWV 8.9 ± 1.8 m/s. Multiple regression analysis identified waist circumference (WC) (beta = 0.411, p = 0.026), LDL-cholesterol (beta = 0.106, p = 0.006), systolic office BP (beta = 0.936, p < 0.001) and diabetes duration (beta = 0.233, p = 0.043) as potential determinants of cSBP. cPP was determined by sex (beta = 0.330, p = 0.008), age (beta = 0.383, p < 0.001), systolic office BP (beta = 0.370, p < 0.001) and diabetes duration (beta = 0.231, p = 0.028) whereas for PWV the following determinants could be identified: age (beta = 0.405, p < 0.001), systolic office BP (beta = 0.421, p < 0.001) and diabetes duration (beta = 0.073, p = 0.038). In addition to the known parameters age, sex and systolic office BP serum LDL-cholesterol, WC and diabetes duration have been identified as determinants of arterial stiffness in patients with T2DM. Treatment of patients in the early stage of T2DM should focus on these clinical parameters to prevent progression of arterial stiffness and as a consequence reduce cardiovascular mortality. Trial registration: The patients included in the analysis participated in one of the following clinical trials NCT02752113 (registered 26.4.2016), NCT02383238 (09.03.2015), NCT02471963 (15.06.2015), NCT01319357 (21.03.2011) (http://www.clinicaltrials.gov).
CRIS-Team Scopus Importer:2023-06-30

Diagnosis and treatment of arterial hypertension 2021 - Ott, Christian; Schmieder, Roland (Kidney International, 2021)
In the last 4 years, several evidence-based, national, and international guidelines on the management of arterial hypertension have been published, mostly with concordant recommendations, but in some aspects with discordant opinions. This in-depth review takes these guidelines into account but also addresses several new data of interest. Although being somewhat obvious and simple, accurate blood pressure (BP) measurement with validated devices is the cornerstone of the diagnosis of hypertension, but out-of-office BP measurements are of crucial importance as well. Simplified antihypertensive drug treatment such as single-pill combinations enhances the adherence to medication and speeds up the process of getting into the BP target range, a goal not so far adequately respected. Recommended (single-pill) combination therapy includes diuretics as part of the first step of antihypertensive therapy, and updated analysis does not provide evidence to exclude diuretics from this first step because of the recently discussed potential risk of increasing cancer incidence. Target BP goals need to be individualized, according to comorbidities, hypertension-mediated organ damage, coexistence of cardiovascular risk factors (including age), frailty in older patients, and individual tolerability. There are also concordant recommendations in the guidelines that an office BP between 120 and 140 mm Hg systolic and between 70 and 80 mm Hg diastolic should be achieved. The BP target of Kidney Disease: Improving Global Outcomes for hypertensive patients with chronic kidney disease are not applicable for clinical practice because they heavily rely on 1 study that used a study-specific, nontransferable BP measurement technique and excluded the most common cause of chronic kidney disease, namely, diabetic nephropathy. Actual data even from a prospective trial on chronotherapy have to be disregarded, and antihypertensive medication should not be routinely dosed at bedtime. Rigorously conducted trials justify the revival of renal denervation for treatment of (at least, but not only) uncontrolled and treatment-resistant hypertension.
CRIS-Team Scopus Importer:2021-12-17
Keywords: ambulatory blood pressure measurement; arterial hypertension; blood pressure; guideline; renal denervation; SPRINT

Diagnosis and treatment of resistant hypertension - Waeber, Bernard; Volpe, Massimo; Ruilope, Luis M.; Schmieder, Roland (Blood Pressure, 2014)
Abstract Hypertension resistant to lifestyle interventions and antihypertensive medications is a common problem encountered by physicians in everyday practice. It is most often defined as a blood pressure remaining >= 140/90 mmHg despite the regular intake of at least three drugs lowering blood pressure by different mechanisms, one of them being a diuretic. It now appears justified to include, unless contraindicated or not tolerated, a blocker of the renin-angiotensin system and a calcium channel blocker in this drug regimen, not only to gain antihypertensive efficacy, but also to prevent or regress target organ damage and delay the development of cardiorenal complications. A non-negligible fraction of treatment-resistant hypertension have normal "out of office" blood pressures. Ambulatory blood pressure monitoring and/or home blood pressure recording should therefore be routinely performed to identify patients with true resistant hypertension, i.e. patients who are more likely to benefit from treatment intensification.
EVALuna2:3672

Dialysis and ultrafiltration therapy in patients with cardio-renal syndrome: recommendations of the working group "heart-kidney" of the German Cardiac Society and the German Society of Nephrology - Schwenger, V.; Remppis, B. A.; Westenfeld, R.; Weinreich, T.; Brunkhorst, R.; Schieren, G.; Krumme, B.; Haller, H.; Schmieder, Roland; Schlieper, G.; Frye, B.; Hoppe, U. C.; et al. (Deutsche Medizinische Wochenschrift, 2014)
Renal failure is common in patients with severe heart failure. This complex pathophysiological interaction has been classified as cardio-renal syndrome. In these patients hydropic decompensation is the main cause of hospitalization. In patients with refractory heart failure, characterized by diuretic resistance and congestion due to volume overload, ultrafiltration has to be considered. In acute decompensated heart failure with worsening of renal function, extracorporeal ultrafiltration is the preferred treatment modality. On the other hand, patients suffering from chronic decompensated heart failure, particularly patients with ascites, will profit from the treatment specific advantages of peritoneal ultrafiltration. Prerequisite for an optimized care of patients with cardio-renal syndrome is the close collaboration among intensive care doctors, cardiologists and nephrologists.
EVALuna2:3705

Difference in renal parenchymal perfusion after renal denervation comparing treated vs. non-treated arteries - Schmieder, R. S.; Schmid, Axel; Janka, Rolf Matthias; Schmieder, Roland; Ott, Christian; Uder, Michael (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

Differences in patient and physician perspectives on pharmaceutical therapy and renal denervation for the management of hypertension - Schmieder, Roland; Kandzari, David E.; Wang, Tzung Dau; Lee, Ying Hsiang; Lazarus, Gabriel; Pathak, Atul (Journal of Hypertension, 2021)
OBJECTIVE: To study patient and physician attitudes to pharmaceutical therapy and renal denervation for the management of hypertension. METHODS: Data were analyzed from 19 market research studies in Western Europe and the United States conducted between 2010 and 2019 to obtain quantitative and qualitative perspectives. The analysis incorporated insights from 2768 patients and the experiences of 1902 physicians either actively performing or interested to perform device procedures, or hypertension specialists who would refer patients for a device-based intervention. RESULTS: Referring cardiologists and proceduralists were more likely to recommend the renal denervation procedure to patients with higher BP levels and a greater number of antihypertensive medications. Physicians perceived patient reluctance towards a procedure as an important obstacle to recommending renal denervation as a treatment option for uncontrolled hypertension. Patient interest in the renal denervation procedure did not correlate with BP severity (P = NS), and the highest preference for the procedure was in patients diagnosed with hypertension but not receiving treatment (P < 0.001). Patients who perceived high BP as a major problem (P = 0.029) and those who experienced side effects attributed to their BP medications (P = 0.006) had a higher preference for renal denervation. CONCLUSION: Patients with hypertension often regard the choice of renal denervation to lower BP differently from physicians. A considerable proportion of hypertensive patients, especially those not taking medications, may prefer a device-based approach to reduce their BP.
CRIS-Team Scopus Importer:2020-12-11

DIFFERENT FORMS OF AFFERENT NERVE INPUT IN CARDIAC AND RENAL DISEASE IN RATS? - Rodionova, Kristina; Ditting, Tilmann; Pickny, Lisa; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

DIFFERENT RESPONSE PATTERN TO AIRCRAFT NOISE EXPOSURE IN RENAL VERSUS SYSTEMIC HEMODYNAMIC - Bosch, Agnes; Ott, C.; Kannenkeril, Dennis; Harazny, J. M.; Striepe, Kristina; Karg, M.; Dienemann, T.; Jung, Susan; Schmieder, Roland (2018)
EVALuna2:202964

Disparate effects of the combined therapy of empagliflozin and linagliptin versus metformin and insulin glargine on renal haemodynamics in type 2 diabetes - Ott, Christian; Jung, Susan; Kannenkeril, Dennis; Striepe, Kristina; Bosch, Agnes; Korn, M.; Bramlage, P.; Schmieder, Roland (DIABETOLOGIA, 2019)
CRIS-Team WoS Importer:2019-10-11

DISPARATE NITRIC OXIDE ACTIVITY OF THE RETINAL CIRCULATION IN HYPERTENSIVE VS TYPE 2 DIABETES-PATIENTS - Kannenkeril, Dennis; Jung, Susan; Harazny, J. M.; Bosch, Agnes; Ott, Christian; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-20

Disproportional decrease in office blood pressure compared with 24-hour ambulatory blood pressure with antihypertensive treatment: dependency on pretreatment blood pressure levels - Schmieder, Roland; Schmidt, Stefan; Riemer, Thomas; Dechend, Ralf; Hagedorn, Ina; Senges, Jochen; Messerli, Franz H.; Zeymer, Uwe (Hypertension, 2014)
The long-term relationship between 24-hour ambulatory blood pressure (ABP) and office BP in patients on therapy is not well documented. From a registry we included all patients in whom antihypertensive therapy needed to be uptitrated. Drug treatment included the direct renin inhibitor aliskiren or an angiotensin-converting enzyme inhibitor/angiotensin receptor blocker or drugs not blocking the renin-angiotensin system, alone or on top of an existing drug regimen. In all patients, office BP and 24-hour ABP were obtained at baseline and after 1 year with validated devices. In the study population of 2722 patients, there was a good correlation between the change in office BP and 24-hour ABP (systolic: r=0.39; P<0.001; diastolic: r=0.34; P<0.001). However, the numeric decrease in office BP did not correspond to the decrease in ABP in a 1:1 fashion, for example, a decrease of 10, 20, and 30 mm Hg corresponded to a decrease of ?7.2, 10.5, and 13.9 mm Hg in systolic ABP, respectively. The disproportionally greater decrease in systolic office BP compared with ABP was dependent on the level of the pretreatment BP, which was consistently higher for office BP than ABP. The white coat effect (difference between office BP and ABP) was on average 10/5 mm Hg lower 1 year after intensifying treatment and the magnitude of that was also dependent on pretreatment BP. There was a disproportionally greater decrease in systolic office BP than in ABP, which for both office BP and ABP seemed to depend on the pretreatment BP level.
EVALuna2:3733

Does renal artery supply indicate treatment success of renal denervation? - Schmid, Axel; Ditting, Tilmann; Sobotka, Paul A.; Veelken, Roland; Schmieder, Roland; Uder, Michael; Ott, Christian (Cardiovascular and Interventional Radiology, 2013)
Purpose: Renal denervation (RDN) emerged as an innovative interventional antihypertensive therapy. With the exception of pretreatment blood pressure (BP) level, no other clear predictor for treatment efficacy is yet known. We analyzed whether the presence of multiple renal arteries has an impact on BP reduction after RDN. Methods: Fifty-three patients with treatment-resistant hypertension (office BP ≥ 140/90 mmHg and 24-h ambulatory BP monitoring (≥130/80 mmHg) underwent bilateral catheter-based RDN. Patients were stratified into one-vessel (OV) (both sides) and at least multivessel (MV) supply at one side. Both groups were treated on one vessel at each side; in case of multiple arteries, only the dominant artery was treated on each side. Results: Baseline clinical characteristics (including BP, age, and estimated glomerular filtration rate) did not differ between patients with OV (n = 32) and MV (n = 21). Office BP was significantly reduced in both groups at 3 months (systolic: OV -15 ± 23 vs. MV -16 ± 20 mmHg; diastolic: OV -10 ± 12 vs. MV -8 ± 11 mmHg, both p = NS) as well as 6 months (systolic: OV -18 ± 18 vs. MV -17 ± 22 mmHg; diastolic: OV -10 ± 10 vs. -10 ± 12 mmHg, both p = NS) after RDN. There was no difference in responder rate (rate of patients with office systolic BP reduction of at least 10 mmHg after 6 months) between the groups. Conclusion: In patients with multiple renal arteries, RDN of one renal artery - namely, the dominant one - is sufficient to induce BP reduction in treatment-resistant hypertension. © 2013 Springer Science+Business Media New York and the Cardiovascular and Interventional Radiological Society of Europe (CIRSE).
CRIS-Team Scopus Importer:2023-03-08
Keywords: Ablation; Artery; Endovascular treatment; Hypertension; Kidney/renal; Radiofrequency ablation

Durability of blood pressure reduction after ultrasound renal denervation: three-year follow-up of the treatment arm of the randomised RADIANCE-HTN SOLO trial - Rader, Florian; Kirtane, Ajay J.; Wang, Yale; Daemen, Joost; Lurz, Philipp; Sayer, Jeremy; Saxena, Manish; Levy, Terry; Scicli, Andrea P.; Thackeray, Lisa; Azizi, Michel; Weber, Michael A.; et al. (EuroIntervention, 2022)
Background: While the blood pressure (BP)-lowering effect of renal denervation (RDN) has been established, long-term durability is a key prerequisite for a broader clinical implementation. Aims: Our aims were to assess the long-term durability of the office BP (OBP)-lowering efficacy, antihypertensive medication (AHM) use, and safety of ultrasound RDN (uRDN). Methods: Four weeks after withdrawal of AHM, patients with untreated daytime ambulatory BP ≥135/85 mmHg and <170/105 mmHg were randomised to uRDN (n=74) or sham (n=72) in the RADIANCE-HTN SOLO trial. Initiation of AHM was encouraged for home BP >135/85 mmHg following primary endpoint ascertainment at 2 months. Patients and physicians were unblinded at 6 months. Results: Fifty-one of 74 patients (age: 53.9±11 years; 67% men) originally randomised to uRDN completed the 36-month follow-up. Initial screening OBP upon study entry was 145/92±14/10 mmHg on a mean of 1.2 AHM (range: 0-2.0). Baseline OBP after AHM washout was 154/99±13/8 mmHg. At 36 months, patients were on an average of 1.3 AHM (range: 0-3.0) with 8 patients on no AHM. OBP decreased by 18/11±15/9 mmHg from baseline to 36 months (p<0.001 for both). Overall, OBP control (<140/90 mmHg) improved from 29.4% at screening to 45.1% at 36 months (p=0.059). For patients uncontrolled at screening (n=36), systolic OBP decreased by 10.8 mmHg (p<0.001) at 36 months on similar AHM (p=0.158). Conclusions: The safety and effectiveness of uRDN was durable to 36 months, with reduced OBP and improved OBP control despite a similar starting medication burden. No new uRDN-related long-term safety concerns were identified.
CRIS-Team Scopus Importer:2022-11-25
Keywords: clinical research; clinical trials; renal sympathetic denervation

Early Signs of End-Organ Damage in Retinal Arterioles in Patients with Type 2 Diabetes Compared to Hypertensive Patients - Jumar, Agnes; Ott, Christian; Kistner, Iris; Friedrich, Stefanie; Michelson, Georg; Harazny, Joanna M.; Schmieder, Roland (Microcirculation, 2016)
Eutrophic and hypertrophic remodeling are major vascular hallmarks for hypertension and diabetes-associated microvascular end-organ damage in peripheral arterioles. The aim of this study is to compare retinal arterioles of diabetic, hypertensive, and healthy individuals.Retinal parameters were assessed in 99 patients with T2DM, 158 hypertensive, and 149 healthy individuals. WT and CA of retinal arterioles (80-140 ?m) were measured noninvasively and in vivo by scanning laser Doppler flowmetry (Heidelberg Engineering, Germany).After adjustment for values differing between the groups (age, BMI, gender, HDL cholesterol and serum creatinine, systolic office BP), patients with T2DM showed no significant difference in WT (14.2 ± 3), and CA (4199 ± 1107) in comparison with hypertensive patients (WT = 13.3 ± 4, p = 0.18, CA = 3862 ± 1546, p = 0.10) and healthy individuals (WT = 13.1 ± 3, p = 0.55, CA = 3864 ± 1216, p = 0.86). However, the subgroup of patients with diabetes duration of more than 60 months showed greater WT (14.9 ± 4, p = 0.04) and CA (4557 ± 1137, p = 0.02) than the hypertensive group and greater WT (p = 0.04) and CA (p = 0.03) than the healthy group, which is consistent with hypertrophic remodeling.In the early stage of T2DM no hypertrophic remodeling was seen in retinal arterioles. However, hypertrophic remodeling was found in diabetic patients with more than 60 months duration of disease.
EVALuna2:3870

Early vascular damage in retinal microcirculation in arterial hypertension: the Czech post-MONICA study - Cífková, Renata; Harazny, Joanna; Bruthans, Jan; Wohlfahrt, Peter; Krajčoviechová, Alena Hrubeš; Lánská, Věra; Gelžinský, Július; Mateřánková, Markéta; Mareš, Štěpán; Filipovský, Jan; Mayer, Otto; Schmieder, Roland (Journal of Hypertension, 2024)
Retinal microcirculation reflects retinal perfusion abnormalities and retinal arterial structural changes at relatively early stages of various cardiovascular diseases. Wall-to-lumen ratio (WLR) may represent the earliest step in hypertension-mediated organ damage.Our objective was to compare functional and structural parameters of retinal microcirculation in a randomly selected urban population sample, in hypertensive and normotensive individuals. DESIGN AND METHOD: A total of 398 randomly selected individuals from an urban population aged 25-65 years, residing in Pilsen, Czech Republic, were screened for major cardiovascular risk factors. Retinal microcirculation was assessed using scanning laser Doppler flowmetry, with data evaluable in 343 patients. Complete data were available for 342 individuals divided into four groups based on blood pressure and control status of hypertension: normotensive individuals ( n = 213), treated controlled hypertensive individuals ( n = 30), treated uncontrolled hypertensive individuals ( n = 26), and newly detected/untreated hypertensive individuals ( n = 73). RESULTS: There was a tendency to higher wall thickness in treated but uncontrolled hypertensive patients (compared to normotensive and treated controlled hypertensive individuals). WLR was significantly increased in treated but uncontrolled hypertensive patients as well as in individuals with newly detected thus untreated hypertension or in patients with known but untreated hypertension. There was no difference in WLR in treated, controlled hypertensive patients compared with normotensive individuals. CONCLUSION: Our results show that an increased WLR, reflecting early vascular damage, was found in newly detected individuals with hypertension and in untreated hypertensive patients, reflecting early hypertension-mediated vascular damage. Early initiation of hypertension treatment may be warranted.
CRIS-Team Scopus Importer:2024-02-16

Early vascular parameters in the micro- and macrocirculation in type 2 diabetes - Kannenkeril, Dennis; Bosch, Agnes; Harazny, Joanna; Karg, Marina; Jung, Susan; Ott, Christian; Schmieder, Roland (Cardiovascular Diabetology, 2018)
BACKGROUND: Diabetes converts from a metabolic disorder into a predominantly vascular disease, once its duration extends over several years or/and when additional cardiovascular risk factors such as hypertension coexist. In a cross-sectional analysis we analyzed various vascular parameters in the renal, retinal and systemic circulation, with the goal to identify which vascular parameter of early organ damage is the earliest that can be clinically detected. METHODS: In 111 patients with type 2 diabetes (T2DM) (off any anti-diabetic medication for at least 4 weeks) and 54 subjects without T2DM we compared various parameters of early vascular remodeling in the same patient: urinary albumin creatinine ratio ([UACR], early morning spot urine) and estimated glomerular filtration rate (eGFR), retinal capillary flow (RCF) and intercapillary distance (ICD) as parameters of capillary rarefaction, wall-to-lumen ratio (WLR) of the retinal arterioles [all assessed by Scanning Laser Doppler Flowmetry], and central systolic pressure (cSBP) and central pulse pressure (cPP) [measured by pulse wave analysis, Syphygmocor] both reflecting vascular stiffness of large arteries. RESULTS: Compared to subjects without T2DM, patients with T2DM (diabetes duration: median 48 months, interquartile range 24-88 months) were older (59.8 ± 7.3 vs 43.4 ± 12.9 years, p < 0.001), more females (33.3 vs 20.4%, p < 0.001), but 24-h systolic and diastolic blood pressure did not differ between the two groups. The analysis adjusted for age, gender and cardiovascular risk factors revealed that ICD (23.9 ± 5.1 vs 20.8 ± 3.5 µm, p value = 0.001) and cPP (41.8 ± 11.7 vs 34.8 ± 10.6 mmHg, p value < 0.001) were significantly higher and eGFR (91.7 ± 9.9 vs 95.9 ± 17.3 ml/min/1.73 m2, p value < 0.001) was significantly lower in patients with T2DM than in subjects without T2DM. CONCLUSION: These data suggest that at similar blood pressure capillary rarefaction in the retinal circulation (ICD), decreased eGFR in the renal circulation and increased central pulse pressure (cPP) of large arteries are earlier detectable than other vascular remodeling parameters of the micro- (WLR, RCF, UACR) and macrocirculation (cSBP) in patients with T2DM. Trial registration Trial registration number: NCT02471963, Date of registration: June 15, 2015, retrospectively registered; Trial registration number: NCT01319357, Date of registration: March 21, 2011, retrospectively registered; Trial registration number: NCT02383238, Date of registration: March 9, 2015, retrospectively registered; Trial registration number: NCT00152698, Date of registration: September 9, 2005, prospectively registered; Trial registration number: NCT00136188, Date of registration: August 26, 2005, prospectively registered.
EVALuna2:35230

Editorial comment: Renal denervation COMMENT - Schmieder, Roland; Bosch, Agnes (Hypertension Research, 2021)
CRIS-Team WoS Importer:2021-12-24

Effect of Alcohol-Mediated Renal Denervation on Blood Pressure in the Presence of Antihypertensive Medications: Primary Results From the TARGET BP I Randomized Clinical Trial - Kandzari, David E.; Weber, Michael A.; Pathak, Atul; Zidar, James P.; Saxena, Manish; David, Shukri W.; Schmieder, Roland; Janas, Adam J.; Langer, Christopher; Persu, Alexandre; Mendelsohn, Farrell O.; Ameloot, Koen; et al. (Circulation, 2024)
BACKGROUND: Renal denervation (RDN) has demonstrated clinically relevant reductions in blood pressure (BP) among individuals with uncontrolled hypertension despite lifestyle intervention and medications. The safety and effectiveness of alcohol-mediated RDN have not been formally studied in this indication. METHODS: TARGET BP I is a prospective, international, sham-controlled, randomized, patient- and assessor-blinded trial investigating the safety and efficacy of alcohol-mediated RDN. Patients with office systolic BP (SBP) ≥150 and ≤180 mm Hg, office diastolic BP ≥90 mm Hg, and mean 24-hour ambulatory SBP ≥135 and ≤170 mm Hg despite prescription of 2 to 5 antihypertensive medications were enrolled. The primary end point was the baseline-adjusted change in mean 24-hour ambulatory SBP 3 months after the procedure. Secondary end points included mean between-group differences in office and ambulatory BP at additional time points. RESULTS: Among 301 patients randomized 1:1 to RDN or sham control, RDN was associated with a significant reduction in 24-hour ambulatory SBP at 3 months (mean±SD, -10.0±14.2 mm Hg versus -6.8±12.1 mm Hg; treatment difference, -3.2 mm Hg [95% CI, -6.3 to 0.0]; P=0.0487). Subgroup analysis of the primary end point revealed no significant interaction across predefined subgroups. At 3 months, the mean change in office SBP was -12.7±18.3 and -9.7±17.3 mm Hg (difference, -3.0 [95% CI, -7.0 to 1.0]; P=0.173) for RDN and sham, respectively. No significant differences in ambulatory or office diastolic BP were observed. Adverse safety events through 6 months were uncommon, with one instance of accessory renal artery dissection in the RDN group (0.7%). No significant between-group differences in medication changes or patient adherence were identified. CONCLUSIONS: Alcohol-mediated RDN was associated with a modest but statistically significant reduction in 24-hour ambulatory SBP compared with sham control. No significant differences between groups in office BP or 6-month major adverse events were observed.
CRIS-Team Scopus Importer:2024-06-21
Keywords: alcohols; antihypertensive agents; denervation; hypertension

Effect of aliskiren on vascular remodelling in small retinal circulation - Jumar, Agnes; Ott, Christian; Kistner, Iris; Friedrich, Stefanie; Schmidt, Stefan; Harazny, Joanna M.; Schmieder, Roland (Journal of Hypertension, 2015)
In hypertension, changes in small arterial structure are characterized by an increased wall-to-lumen ratio (WLR). These adaptive processes are modulated by the rennin-angiotensin system. It is unclear whether direct renin inhibitors exert protective effects on small arteries in hypertensive patients.In this double-blind, randomized, placebo-controlled study (http://www.clinicaltrials.gov: NCT01318395), 114 patients with primary hypertension were randomized to additional therapy with either placebo or aliskiren 300 mg for 8 weeks after 4 weeks of standardized open-label treatment with valsartan 320 mg (run-in phase). Parameter of arteriolar remodelling was WLR of retinal arterioles (80 - 140 ?m) assessed noninvasively and in vivo by scanning laser Doppler flowmetry (Heidelberg Engineering, Germany). In addition, pulse wave analysis (SphygmoCor, AtCor Medical, Australia) and pulse pressure (PP) amplification were determined.In the whole study population, no clear effect of additional therapy with aliskiren on vascular parameters was documented. When analyses were restricted to patients with vascular remodelling, defined by a median of WLR more than 0.3326 (n = 57), WLR was reduced after 8 weeks by the treatment with aliskiren compared with placebo (-0.044 ± 0.07 versus 0.0043 ± 0.07, P = 0.015). Consistently, after 8 weeks of on-top treatment with aliskiren, there was an improvement of PP amplification compared with placebo (0.025 ± 0.07 versus -0.034 ± 0.08, P = 0.013), indicative of less stiff arteries in the peripheral circulation.Thus, our data indicate that treatment with aliskiren, given on top of valsartan therapy, improves altered vascular remodelling in hypertensive patients.
EVALuna2:3799

Effect of Arteriovenous Anastomosis on Blood Pressure Reduction in Patients With Isolated Systolic Hypertension Compared With Combined Hypertension - Ott, Christian; Lobo, Melvin D.; Sobotka, Paul A.; Mahfoud, Felix; Stanton, Alice; Cockcroft, John; Sulke, Neil; Dolan, Eamon; Van Der Giet, Markus; Hoyer, Joachim; Furniss, Stephen S.; Foran, John P.; et al. (Journal of the American Heart Association, 2016)
Options for interventional therapy to lower blood pressure (BP) in patients with treatment-resistant hypertension include renal denervation and the creation of an arteriovenous anastomosis using the ROX coupler. It has been shown that BP response after renal denervation is greater in patients with combined hypertension (CH) than in patients with isolated systolic hypertension (ISH). We analyzed the effect of ROX coupler implantation in patients with CH as compared with ISH.The randomized, controlled, prospective ROX Control Hypertension Study included patients with true treatment-resistant hypertension (office systolic BP >=140 mm Hg, average daytime ambulatory BP >=135/85 mm Hg, and treatment with >=3 antihypertensive drugs including a diuretic). In a post hoc analysis, we stratified patients with CH (n=31) and ISH (n=11). Baseline office systolic BP (177±18 mm Hg versus 169±17 mm Hg, P=0.163) and 24-hour ambulatory systolic BP (159±16 mm Hg versus 154±11 mm Hg, P=0.463) did not differ between patients with CH and those with ISH. ROX coupler implementation resulted in a significant reduction in office systolic BP (CH: -29±21 mm Hg versus ISH: -22±31 mm Hg, P=0.445) and 24-hour ambulatory systolic BP (CH: -14±20 mm Hg versus ISH: -13±15 mm Hg, P=0.672), without significant differences between the two groups. The responder rate (office systolic BP reduction >=10 mm Hg) after 6 months was not different (CH: 81% versus ISH: 82%, P=0.932).Our data suggest that creation of an arteriovenous anastomosis using the ROX coupler system leads to a similar reduction of office and 24-hour ambulatory systolic BP in patients with combined and isolated systolic hypertension.URL: http://www.clinicaltrials.gov. Unique identifier: NCT01642498.
EVALuna2:3926

Effect of a single pill concept on clinical and pharmacoeconomic outcomes in cardiovascular diseases - Weisser, Burkhard; Wassmann, Sven; Predel, Hans Georg; Schmieder, Roland; Gillessen, Anton; Wilke, Thomas; Blettenberg, Jörg; Randerath, Olaf; Mevius, Antje; Böhm, Michael (European Heart Journal - Cardiovascular Pharmacotherapy, 2024)
Aims: Our study aimed to assess whether a single pill concept (SPC) is superior to a multi-pill concept (MPC) in reducing cardiovascular (CV) events, all-cause death, and costs in CV patients. Method and results: Anonymized medical claims data covering 2012-2018, including patients with hypertension, dyslipidaemia, and CV diseases who started a drug therapy either as SPC or identical MPC were analysed after 1:1-propensity score matching. Hospitalizations with predefined CV events, all-cause mortality, and costs were studied in 25 311 patients with SPC and 25 311 patients with MPC using incidence rate ratios (IRRs) and non-parametric tests for continuous variables. IRRs were significantly lower for SPC: stroke (IRR = 0.77; 95% CI 0.67-0.88; P < 0.001), transitory ischaemic attack (IRR = 0.61; 95% CI 0.48-0.78; P < 0.001), myocardial infarction (IRR = 0.76; 95% CI 0.63-0.90; P = 0.0016), coronary artery disease (IRR = 0.66; 95% CI 0.57-0.77; P < 0.001), heart failure (IRR = 0.59; 95% CI 0.54-0.64; P < 0.001), acute renal failure (IRR = 0.54; 95% CI 0.56-0.64; P < 0.001), all cause hospitalization (IRR = 0.72; 95% CI 0.71-0.74; P < 0.001), CV hospitalization (IRR = 0.63; 95% CI 0.57-0.69; P < 0.001), and all-cause mortality (IRR = 0.62; 95% CI 0.57-0.68; P < 0.001). Mean time to first events and time to death were also in favour of SPC. Mean total costs were 4708€ for SPC vs. 5.669€ for MPC, respectively (mean ratio 0.830, P < 0.001). Conclusion: SPC is associated with lower incidence rates of CV events, time to CV events, and all-cause death, and is superior regarding pharmacoeconomic parameters and should therefore become standard of care to improve outcomes and reduce healthcare costs.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Adherence; Arterial hypertension; Cardiovascular disorders; Cardiovascular outcomes; Dyslipidemia; Single pill concept

Effect of empagliflozin on ketone bodies in patients with stable chronic heart failure - Pietschner, Robert; Kolwelter, Julie; Bosch, Agnes; Striepe, Kristina; Jung, Susan; Kannenkeril, Dennis; Ott, C.; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (Cardiovascular Diabetology, 2021)
Background: Recent studies indicated that sodium glucose cotransporter (SGLT)2 inhibition increases levels of ketone bodies in the blood in patients with type 1 and 2 diabetes. Other studies suggested that in patients with chronic heart failure (CHF), increased myocardial oxygen demand can be provided by ketone bodies as a fuel substrate. Experimental studies reported that ketone bodies, specifically beta-hydroxybutyrate (β-OHB) may increase blood pressure (BP) by impairing endothelium-dependant relaxation, thereby leading to increased vascular stiffness. In our study we assessed whether the SGLT 2 inhibition with empagliflozin increases ketone bodies in patients with stable CHF and whether such an increase impairs BP and vascular function. Methods: In a prospective, double blind, placebo controlled, parallel-group single centre study 75 patients with CHF (left ventricular ejection fraction 39.0 ± 8.2%) were randomised (2:1) to the SGLT-2 inhibitor empagliflozin 10 mg orally once daily or to placebo, 72 patients completed the study. After a run-in phase we evaluated at baseline BP by 24 h ambulatory blood pressure (ABP) monitoring, vascular stiffness parameters by the SphygmoCor system (AtCor Medical, Sydney, NSW, Australia) and fasting metabolic parameters, including β-OHB by an enzymatic assay (Beckman Coulter DxC 700 AU). The same measurements were repeated 12 weeks after treatment. In 19 of the 72 patients serum levels of β-OHB were beneath the lower border of our assay (< 0.05 mmol/l) therefore being excluded from the subsequent analysis. Results: In patients with stable CHF, treatment with empagliflozin (n = 36) was followed by an increase of β-OHB by 33.39% (p = 0.017), reduction in 24 h systolic (p = 0.038) and diastolic (p = 0.085) ABP, weight loss (p = 0.003) and decrease of central systolic BP (p = 0.008) and central pulse pressure (p = 0.008). The increase in β-OHB was related to an attenuated decrease of empagliflozin-induced 24 h systolic (r = 0.321, p = 0.069) and diastolic (r = 0.516, p = 0.002) ABP and less reduction of central systolic BP (r = 0.470, p = 0.009) and central pulse pressure (r = 0.391, p = 0.033). No significant changes were seen in any of these parameters after 12 weeks of treatment in the placebo group (n = 17). Conclusion: In patients with stable CHF ketone bodies as assessed by β-OHB increased after treatment with empagliflozin. This increase led to an attenuation of the beneficial effects of empagliflozin on BP and vascular parameters. Trial registration The study was registered at http://www.clinicaltrials.gov (NCT03128528).
CRIS-Team Scopus Importer:2021-11-19

Effect of Finerenone on Albuminuria in Patients With Diabetic Nephropathy: A Randomized Clinical Trial - Bakris, George L.; Agarwal, Rajiv; Chan, Juliana C.; Cooper, Mark E.; Gansevoort, Ron T.; Haller, Hermann; Remuzzi, Giuseppe; Rossing, Peter; Schmieder, Roland; Nowack, Christina; Kolkhof, Peter; Joseph, Amer; et al. (Journal of the American Medical Association, 2015)
Steroidal mineralocorticoid receptor antagonists, when added to a renin-angiotensin system blocker, further reduce proteinuria in patients with chronic kidney disease but may be underused because of a high risk of adverse events.To evaluate the safety and efficacy of different oral doses of the nonsteroidal mineralocorticoid receptor antagonist finerenone, given for 90 days to patients with diabetes and high or very high albuminuria who are receiving an angiotensin-converting enzyme inhibitor or an angiotensin receptor blocker.Randomized, double-blind, placebo-controlled, parallel-group study conducted at 148 sites in 23 countries. Patients were recruited from June 2013 to February 2014 and the study was completed in August 2014. Of 1501 screened patients, 823 were randomized and 821 received study drug.Participants were randomly assigned to receive oral, once-daily finerenone (1.25 mg/d, n = 96; 2.5 mg/d, n = 92; 5 mg/d, n = 100; 7.5 mg/d, n = 97; 10 mg/d, n = 98; 15 mg/d, n = 125; and 25 mg/d, n = 119) or matching placebo (n = 94) for 90 days.The primary outcome was the ratio of the urinary albumin-creatinine ratio (UACR) at day 90 vs at baseline. Safety end points were changes from baseline in serum potassium and estimated glomerular filtration rate.The mean age of the participants was 64.2 years; 78% were male. At baseline, 36.7% of patients treated had very high albuminuria (UACR >=300 mg/g) and 40.0% had an estimated glomerular filtration rate of 60 mL/min/1.73 m2 or lower. Finerenone demonstrated a dose-dependent reduction in UACR. The primary outcome, the placebo-corrected mean ratio of the UACR at day 90 relative to baseline, was reduced in the finerenone 7.5-, 10-, 15-, and 20-mg/d groups (for 7.5 mg/d, 0.79 [90% CI, 0.68-0.91; P = .004]; for 10 mg/d, 0.76 [90% CI, 0.65-0.88; P = .001]; for 15 mg/d, 0.67 [90% CI, 0.58-0.77; P<.001]; for 20 mg/d, 0.62 [90% CI, 0.54-0.72; P < .001]). The prespecified secondary outcome of hyperkalemia leading to discontinuation was not observed in the placebo and finerenone 10-mg/d groups; incidences in the finerenone 7.5-, 15-, and 20-mg/d groups were 2.1%, 3.2%, and 1.7%, respectively. There were no differences in the incidence of the prespecified secondary outcome of an estimated glomerular filtration rate decrease of 30% or more or in incidences of adverse events and serious adverse events between the placebo and finerenone groups.Among patients with diabetic nephropathy, most receiving an angiotensin-converting enzyme inhibitor or an angiotensin receptor blocker, the addition of finerenone compared with placebo resulted in improvement in the urinary albumin-creatinine ratio. Further trials are needed to compare finerenone with other active medications.clinicaltrials.gov Identifier: NCT1874431.
EVALuna2:3796

Effect of finerenone on ambulatory blood pressure in chronic kidney disease in type 2 diabetes - Agarwal, Rajiv; Ruilope, Luis M.; Ruiz-Hurtado, Gema; Haller, Hermann; Schmieder, Roland; Anker, Stefan D.; Filippatos, Gerasimos; Pitt, Bertram; Rossing, Peter; Lambelet, Marc; Nowack, Christina; Kolkhof, Peter; et al. (Journal of Hypertension, 2023)
OBJECTIVE: Finerenone is a selective nonsteroidal mineralocorticoid receptor antagonist with a short half-life. Its effects on cardiorenal outcomes were thought to be mediated primarily via nonhemodynamic pathways, but office blood pressure (BP) measurements were insufficient to fully assess hemodynamic effects. This analysis assessed the effects of finerenone on 24-h ambulatory BP in patients with chronic kidney disease and type 2 diabetes. METHODS: ARTS-DN (NCT01874431) was a phase 2b trial that randomized 823 patients with type 2 diabetes and chronic kidney disease, with urine albumin-to-creatinine ratio ≥30 mg/g and estimated glomerular filtration rate of 30-90 ml/min per 1.73 m2 to placebo or finerenone (1.25-20 mg once daily in the morning) administered over 90 days. Ambulatory BP monitoring (ABPM) over 24 h was performed in a subset of 240 patients at screening, Day 60, and Day 90. RESULTS: Placebo-adjusted change in 24-h ABPM systolic BP (SBP) at Day 90 was -8.3 mmHg (95% confidence interval [CI], -16.6 to 0.1) for finerenone 10 mg (n = 27), -11.2 mmHg (95% CI, -18.8 to -3.6) for finerenone 15 mg (n = 34), and -9.9 mmHg (95% CI, -17.7 to -2.0) for finerenone 20 mg (n = 31). Mean daytime and night-time SBP recordings were similarly reduced and finerenone did not increase the incidence of SBP dipping. Finerenone produced a persistent reduction in SBP over the entire 24-h interval. CONCLUSIONS: Finerenone reduced 24-h, daytime, and night-time SBP. Despite a short half-life, changes in BP were persistent over 24 h with once-daily dosing in the morning.
CRIS-Team Scopus Importer:2023-01-06

Effect of Heart Rate on the Outcome of Renal Denervation in Patients With Uncontrolled Hypertension - Böhm, Michael; Tsioufis, Konstantinos; Kandzari, David E.; Kario, Kazuomi; Weber, Michael A.; Schmieder, Roland; Townsend, Raymond R.; Kulenthiran, Saarraaken; Ukena, Christian; Pocock, Stuart; Ewen, Sebastian; Weil, Joachim; et al. (Journal of the American College of Cardiology, 2021)
Background: Sham-controlled trials demonstrated safety and efficacy of renal denervation (RDN) to lower blood pressure (BP). Association of baseline heart rate with BP reduction after RDN is incompletely understood. Objectives: The purpose of this analysis was to evaluate the impact of baseline heart rate on BP reduction without antihypertensive medications in the SPYRAL HTN-OFF MED (Global Clinical Study of Renal Denervation With the Symplicity Spyral Multi-electrode Renal Denervation System in Patients With Uncontrolled Hypertension in the Absence of Antihypertensive Medications) Pivotal trial. Methods: Patients removed from any antihypertensive medications were enrolled with office systolic blood pressure (SBP) ≥150 and <180 mm Hg and randomized 1:1 to RDN or sham control. Patients were separated according to baseline office heart rate <70 or ≥70 beats/min. BP changes from baseline to 3 months between treatment arms were adjusted for baseline SBP using analysis of covariance. Results: Scatter plots of 3-month changes in 24-hour and office SBP illustrate a wide range of changes in SBP for different baseline heart rates. Treatment difference at 3 months between RDN and sham control with baseline office heart rate ≥70 beats/min for 24-hour SBP was −6.2 mm Hg (95% CI: −9.0 to −3.5 mm Hg) (P < 0.001) and for baseline office heart rate <70 beats/min it was −0.1 mm Hg (−3.8 to 3.6 mm Hg) (P = 0.97) with an interaction P value of 0.008. Results were similar for changes in office, daytime, and nighttime SBP at 3 months, with a greater reduction in SBP with baseline office heart rate ≥70 beats/min. Conclusions: Reduction in mean office, 24-hour, daytime, and nighttime SBP for RDN at 3 months was greater with baseline office heart rate ≥70 than <70 beats/min, suggesting an association between baseline heart rate and BP reduction after RDN. (SPYRAL PIVOTAL—SPYRAL HTN-OFF MED Study; NCT02439749)
CRIS-Team Scopus Importer:2021-09-03
Keywords: blood pressure; heart rate; hypertension; renal denervation; sympathetic activation

Effect of Radiofrequency Renal Denervation on Blood Pressure in the Presence of Antihypertensive Drugs: 6-Month Primary Results From the SPYRAL HTN-ON Med Expansion Randomized Trial - Kandzari, David E.; Townsend, Raymond R.; Kario, Kazuomi; Mahfoud, Felix; Weber, Michael A.; Schmieder, Roland; Pocock, Stuart; Tsioufis, Konstantinos; Brar, Sandeep; Debruin, Vanessa; Fahy, Martin; Boehm, Michael (CIRCULATION, 2022)
CRIS-Team WoS Importer:2023-03-17

EFFECT OF RENAL DENERVATION IN ATTENUATING THE MORNING SURGE IN BLOOD PRESSURE: FINDINGS FROM THE SPYRAL HTN-ON MED TRIAL - Kario, K.; Boehm, M.; Townsend, R.; Mahfoud, F.; Weber, M.; Pocock, S.; Tsioufi, C.; Schmieder, Roland; Fahy, M.; Kandzari, D. (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-10

Effect of renal denervation in attenuating the stress of morning surge in blood pressure: post-hoc analysis from the SPYRAL HTN-ON MED trial - Kario, Kazuomi; Weber, Michael A.; Böhm, Michael; Townsend, Raymond R.; Mahfoud, Felix; Schmieder, Roland; Tsioufis, Konstantinos; Cohen, Sidney A.; Fahy, Martin; Kandzari, David E. (Clinical Research in Cardiology, 2020)
Background: Catheter-based renal denervation (RDN) reduces blood pressure (BP) throughout the 24-h period, as reported in several randomized sham-controlled trials. Reduction of BP in the early morning hours is especially important due to increased cardiovascular risks during that time. Objective: In this report, we examine the impact of RDN on systolic BP (SBP) and diastolic BP (DBP) during the critical morning surge period in a post-hoc analysis of patients in the SPYRAL HTN-ON MED trial. Methods and results: Ambulatory BP measurements were collected at baseline and 6 months for treatment and control patient groups over 24-h periods. Average morning BP surge is the difference between average morning BP and average nighttime BP, and the morning surge slope reflects the rate of change of BP from nighttime to morning. Mean morning DBP surge slopes were significantly lower for RDN vs. control groups at 6 months (1.1 vs. 3.6 mmHg/h; p = 0.029). In the RDN group, morning DBP surge slopes were significantly lower at 6 months compared to baseline (1.1 vs. 4.1 mmHg/h; p = 0.006). Similar patterns were observed for mean morning SBP surge slope but did not reach statistical significance. Conclusions: This decrease in the morning DBP surge slope, an index of the sympathetically-mediated morning BP surge, thus indicates a drop in late morning BP relative to early morning/nocturnal BP in the RDN group. Thus, RDN appears effective in attenuating the slope of morning surge in DBP that might indicate possible benefits in a high-risk hypertensive population. Clinical trial registration: https://www.clinicaltrials.gov (NCT02439775), registered May 12, 2015.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Blood pressure; Hypertension; Morning surge; Renal denervation

Effect of SGLT2 inhibition on ketone bodies in patients with stable chronic heart failure - Pietschner, Robert; Kolwelter, Julie; Bosch, Agnes; Kannenkeril, Dennis; Ott, C.; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (DIABETOLOGIA, 2021)
CRIS-Team WoS Importer:2021-10-01

Effects of cardiovascular single pill combinations compared with identical multi-pill therapies on healthcare cost and utilization in Germany - Wilke, Thomas; Weisser, Burkhard; Predel, Hans-Georg; Schmieder, Roland; Wassmann, Sven; Gillessen, Anton; Blettenberg, Joerg; Maywald, Ulf; Randerath, Olaf; Mueller, Sabrina; Boehm, Michael (Journal of Comparative Effectiveness Research, 2022)
Aim: This study assessed whether a single pill combination (SPC) is associated with lower direct healthcare costs. Materials & methods: Anonymized claims data of patients >= 18 years treated with drugs for cardiovascular (CV)-related diseases either as a single pill combination or multi-pill combination (follow-up to 1 year) were evaluated. After propensity score matching, 59,336 out of 1,369,840 patients were analyzed. Results: In all cohorts, patients receiving a single pill combination had a lower frequency of general practitioner and specialist visits. The patients also had a significantly lower ratio of all-cause hospitalization days and number of CV-related prescriptions as well as all-cause prescriptions (with one exception) compared with those receiving a multi-pill combination. Conclusion: Direct CV-related costs were significantly lower in four out of seven comparisons, with a trend toward lower costs in the other three comparisons.
CRIS-Team WoS Importer:2022-04-08

Effects of Catheter-Based Renal Denervation in Hypertension: A Systematic Review and Meta-Analysis - Vukadinovic, Davor; Lauder, Lucas; Kandzari, David E.; Bhatt, Deepak L.; Kirtane, Ajay J.; Edelman, Elazer R.; Schmieder, Roland; Azizi, Michel; Böhm, Michael; Mahfoud, Felix (Circulation, 2024)
BACKGROUND: Several sham-controlled trials have investigated the efficacy and safety of catheter-based renal denervation (RDN) with mixed outcomes. We aimed to perform a comprehensive meta-analysis of all randomized, sham-controlled trials investigating RDN with first- and second-generation devices in hypertension. METHODS: We searched MEDLINE and the Cochrane Library for eligible trials. Outcomes included both efficacy (24-hour and office systolic [SBP] and diastolic blood pressure [DBP]) and safety (all-cause death, vascular complication, renal artery stenosis >70%, hypertensive crisis) of RDN. We performed a study-level, pairwise, random-effects meta-analysis of the summary data. RESULTS: Ten trials comprising 2478 patients with hypertension while being either off or on treatment were included. Compared with sham, RDN reduced 24-hour and office systolic blood pressure by 4.4 mm Hg (95% CI, 2.7 to 6.1; P<0.00001) and 6.6 mm Hg (95% CI, 3.6 to 9.7; P<0.0001), respectively. The 24-hour and office diastolic blood pressure paralleled these findings (-2.6 mm Hg [95% CI, -3.6 to -1.5]; P<0.00001; -3.5 mm Hg [95% CI, -5.4 to -1.6]; P=0.0003). There was no difference in 24-hour and office systolic blood pressure reduction between trials with and without concomitant antihypertensive medication (P for interaction, 0.62 and 0.73, respectively). There was no relevant difference in vascular complications (odds ratio, 1.69 [95% CI, 0.57 to 5.0]; P=0.34), renal artery stenosis (odds ratio, 1.50 [95% CI, 0.06 to 36.97]; P=0.80), hypertensive crisis (odds ratio, 0.65 [95% CI, 0.30 to 1.38]; P=0.26), and all-cause death (odds ratio, 1.76 [95% CI, 0.34 to 9.20]; P=0.50) between RDN and sham groups. Change of renal function based on estimated glomerular filtration rate was comparable between groups (P for interaction, 0.84). There was significant heterogeneity between trials. CONCLUSIONS: RDN safely reduces ambulatory and office systolic blood pressure/diastolic blood pressure versus a sham procedure in the presence and absence of antihypertensive medication.
CRIS-Team Scopus Importer:2024-10-18
Keywords: arterial hypertension; meta-analysis; renal denervation

EFFECTS OF FINERENONE ON CARDIORENAL OUTCOMES IN BLOOD PRESSURE SUBGROUPS IN PATIENTS WITH CKD AND T2D - Ruilope, Luis; Agarwal, Rajiv; Anker, Stefan D.; Filippatos, Gerasimos; Pitt, Bertram; Rossing, Peter; Sarafidis, Pantelis; Schmieder, Roland; Joseph, Amer; Mentenich, Nicole; Nowack, Christina; Bakris, George (NEPHROLOGY DIALYSIS TRANSPLANTATION, 2021)
CRIS-Team WoS Importer:2021-12-03

Effects of folic acid on renal endothelial function in patients with diabetic nephropathy: results from a randomized trial - Schneider, Markus P.; Schneidert, Andreas; Jumar, Agnes; Kistner, Iris; Ott, Christian; Schmieder, Roland (Clinical Science, 2014)
Endothelial dysfunction has been shown to promote podocyte injury and albuminuria in diabetes, highlighting the importance of the interaction between renal endothelial cells and podocytes. Folic acid (FA) improves nitric oxide synthase (NOS) function and reduces progression of diabetic nephropathy in animal models. We tested whether high-dose FA treatment improves renal endothelial function and albuminuria in human subjects with incipient diabetic nephropathy. Following a double-blind, randomized, cross-over design, 28 patients with Type 2 diabetes and albuminuria were allocated to 4 weeks' treatment with placebo and high-dose FA (5 mg/day). Renal nitric oxide (NO) production determined as the response of renal plasma flow (RPF) to NOS inhibition with NG-monomethyl-L-arginine (L-NMMA) (4.25 mg/kg intravenously), renal oxidant stress as response of RPF to vitamin C infusion (3 mg/kg) and albuminuria were determined after each treatment phase. Neither the reduction in RPF to L-NMMA nor the increase in RPF to vitamin C infusion differed between treatment phases (?RPF to L-NMMA: -74±71 ml/min per m2 during placebo compared with -63±56 ml/min per m2 during FA, P=0.57; ?RPF to vitamin C: +93±118 ml/min per m2 compared with +94±108 ml/min per m2; P=0.70). In line with the lack of effect on the renal endothelium, albuminuria was not affected by FA treatment (110±179 mg/day during placebo compared with 87±146 mg/day during FA; P=0.12). High-dose FA treatment does not improve renal endothelial function and fails to reduce albuminuria in human subjects with diabetic nephropathy. Novel treatment options for oxidant stress and endothelial dysfunction in patients with diabetes are urgently needed.
EVALuna2:3679

Effects of linagliptin on renal endothelial function in patients with type 2 diabetes: a randomised clinical trial - Ott, Christian; Kistner, Iris; Keller, Mirjam; Friedrich, Stefanie; Willam, Carsten; Bramlage, Peter; Schmieder, Roland (Diabetologia, 2016)
Endothelial dysfunction predicts cardiovascular damage and renal involvement. Animal experiments and human studies indicate an increased nitric oxide (NO) activity and endothelial NO synthase (NOS) expression in the early stage of type 2 diabetes. The aim of the study was to assess the effect of linagliptin on the endothelial function of the renal vasculature.In this randomised, double-blind, parallel-group, investigator-initiated trial, 62 patients with type 2 diabetes were randomly assigned (by computer-generated random code) to receive linagliptin 5 mg (n = 30) or placebo (n = 32) for 4 weeks. The primary objective was to assess endothelial function of the renal vasculature, by constant-infusion input-clearance and urinary albumin/creatinine ratio (UACR), both before and after blockade of NOS with N (G)-monomethyl-L-arginine (L-NMMA).Treatment with linagliptin for 4 weeks reduced fasting, postprandial blood glucose and HbA1c, although not significantly; no change occurred with placebo. Renal plasma flow (RPF) did not change after linagliptin or placebo. After 4 weeks the absolute change in RPF due to L-NMMA was smaller in the linagliptin group than in the placebo group (-46.8 ± 34 vs -65.1 ± 36 ml/min, p = 0.045), indicating a lower basal NO activity after treatment with linagliptin. Consistently, the response of UACR to L-NMMA increased in the placebo group (p = 0.059) but not in the linagliptin group (p = 0.276), pointing to an upregulation of NO activity in the placebo group. No clinically meaningful safety concerns were evident.Our data suggest that treatment with the dipeptidyl peptidase-4 inhibitor linagliptin for 4 weeks prevented the impairment of renal endothelial function due to hyperglycaemia in type 2 diabetes.ClinicalTrials.gov NCT01835678 FUNDING: : This study was funded by Boehringer Ingelheim.
EVALuna2:3903

EFFECTS OF NEUROGENIC CGRP ON RENAL AFFERENT PEPTIDERGIC NEURONS - Veelken, Roland; Raschke, Giulia; Ditting, Tilmann; Ott, Christian; Schmieder, Roland; Amann, Kerstin Ute; Rodionova, Kristina (2018)
EVALuna2:204843

EFFECTS OF RENAL DENERVATION IN PATIENTS WITH VERSUS WITHOUT CHRONIC KIDNEY DISEASE: UPDATED DATA FROM THE GLOBAL SYMPLICITY REGISTRY WITH FOLLOW-UP OF 3 YEARS - Ott, Christian; Mahfoud, F.; Mancia, G.; Narkiewicz, K.; Ruilope, L. M.; Schlaich, M. P.; Williams, B.; Boehm, M.; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-20

Effects of renal denervation on blood pressure in hypertensive patients with end-stage renal disease: a single centre experience - Ott, Christian; Schmid, Axel; Ditting, Tilmann; Veelken, Roland; Uder, Michael; Schmieder, Roland (Clinical and Experimental Nephrology, 2019)
Background: Sympathetic nerve activity is a hallmark of hypertension in end-stage renal disease (ESRD). An initial proof-of-concept study implies that renal denervation (RDN) is feasible and safe in RDN, but overall data are limited. Methods: In this single-centre prospective pilot study six patients with ESRD and treatment resistant hypertension were consecutively included. Ambulatory blood pressure (ABP) was measured before and 6 months after RDN (Symplictiy Flex™, Medtronic Inc., Santa Rosa, CA). Moreover, haemodialysis parameters which may affect BP reduction were monitored closely. Results: In all patients bilateral RDN was successful done, without documentation of peri- or postprocedural complications. There was a significant reduction in 24-h ABP by 20 ± 17/15 ± 12 mmHg 6 months after RDN (systolic: 163 ± 16 versus 143 ± 9 mmHg, p = 0.043; diastolic: 96 ± 9 versus 81 ± 15 mmHg, p = 0.043), with similar results for day-, and nighttime values, respectively. Antihypertensive medication was kept stable as well as there was no change in haemodialysis parameters during follow-up. In addition, ultrafiltration/week (1.4 ± 1.4 versus 2.2 ± 1.4 l, p = 0.08) as well as hematocrit (measured at baseline and 6 months after RDN) (33.7 ± 4.3 versus 33.1 ± 3.9%, p = 0.715) revealed no change in volume status. Conclusion: Our single-centre pilot study not only supports current data on renal safety of RDN even in small arteries of patients with ESRD, but also enhances the knowledge towards an effective ABP reduction in this type of hypertensive patients.
CRIS-Team Scopus Importer:2019-05-07
Keywords: End-stage renal disease; Renal denervation; Treatment resistant hypertension

EFFECTS OF RENAL DENERVATION ON BLOOD PRESSURE IN PATIENTS WITH END-STAGE RENAL DISEASE: A SINGLE CENTER EXPERIENCE - Ott, C.; Schmid, Axel; Ditting, T.; Veelken, Roland; Uder, Michael; Schmieder, Roland (2018)
EVALuna2:202966

Effects of renal denervation on kidney function and long-term outcomes: 3-year follow-up from the Global SYMPLICITY Registry - Mahfoud, Felix; Böhm, Michael; Schmieder, Roland; Narkiewicz, Krzysztof; Ewen, Sebastian; Ruilope, Luis; Schlaich, Markus; Williams, Bryan; Fahy, Martin; Mancia, Giuseppe (European Heart Journal, 2019)
AIMS: Several studies and registries have demonstrated sustained reductions in blood pressure (BP) after renal denervation (RDN). The long-term safety and efficacy after RDN in real-world patients with uncontrolled hypertension, however, remains unknown. The objective of this study was to assess the long-term safety and efficacy of RDN, including its effects on renal function. METHODS AND RESULTS: The Global SYMPLICITY Registry is a prospective, open-label registry conducted at 196 active sites worldwide in hypertensive patients receiving RDN treatment. Among 2237 patients enrolled and treated with the SYMPLICITY Flex catheter, 1742 were eligible for follow-up at 3 years. Baseline office and 24-h ambulatory systolic BP (SBP) were 166 ± 25 and 154 ± 18 mmHg, respectively. SBP reduction after RDN was sustained over 3 years, including decreases in both office (-16.5 ± 28.6 mmHg, P < 0.001) and 24-h ambulatory SBP (-8.0 ± 20.0 mmHg; P < 0.001). Twenty-one percent of patients had a baseline estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m2. Between baseline and 3 years, renal function declined by 7.1 mL/min/1.73 m2 in patients without chronic kidney disease (CKD; eGFR ≥60 mL/min/1.73 m2; baseline eGFR 87 ± 17 mL/min/1.73 m2) and by 3.7 mL/min/1.73 m2 in patients with CKD (eGFR <60 mL/min/1.73 m2; baseline eGFR 47 ± 11 mL/min/1.73 m2). No long-term safety concerns were observed following the RDN procedure. CONCLUSION: Long-term data from the Global SYMPLICITY Registry representing the largest available cohort of hypertensive patients receiving RDN in a real-world clinical setting demonstrate both the safety and efficacy of the procedure with significant and sustained office and ambulatory BP reductions out to 3 years.
CRIS-Team Scopus Importer:2019-11-15
Keywords: Ambulatory blood pressure monitoring; Denervation; Hypertension; Renal function; SYMPLICITY

Effects of Renal Denervation vs Sham in Resistant Hypertension After Medication Escalation Prespecified Analysis at 6 Months of the RADIANCE-HTN TRIO Randomized Clinical Trial - Azizi, Michel; Mahfoud, Felix; Weber, Michael A.; Sharp, Andrew S. P.; Schmieder, Roland; Lurz, Philipp; Lobo, Melvin D.; Fisher, Naomi D. L.; Daemen, Joost; Bloch, Michael J.; Basile, Jan; Sanghvi, Kintur; et al. (JAMA Cardiology, 2022)
IMPORTANCE Although early trials of endovascular renal denervation (RDN) for patients with resistant hypertension (RHTN) reported inconsistent results, ultrasound RDN (uRDN) was found to decrease blood pressure (BP) vs sham at 2 months in patients with RHTN taking stable background medications in the Study of the ReCor Medical Paradise System in Clinical Hypertension (RADIANCE-HTN TRIO) trial.
CRIS-Team WoS Importer:2022-12-02

Effects of renal sympathetic denervation on urinary sodium excretion in patients with resistant hypertension - Poss, Janine; Ewen, Sebastian; Schmieder, Roland; Muhler, Sonja; Vonend, Oliver; Ott, Christian; Linz, Dominik; Geisel, Juergen; Rump, Lars C.; Schlaich, Markus; Boehm, Michael; Mahfoud, Felix (Clinical Research in Cardiology, 2015)
Sympathetic overactivity increases sodium retention and contributes to the pathophysiology of hypertension. Renal sympathetic denervation lowers blood pressure and reduces sympathetic activity in certain patients with resistant hypertension.This study aimed to assess the effect of renal denervation on urinary sodium excretion. 24-h urinary sodium excretion was estimated at baseline and after 6 months using the Kawasaki formula in 137 patients with resistant hypertension undergoing renal denervation. Sodium excretion was adjusted for cystatin C GFR and fractional sodium excretion was assessed. Mean office systolic blood pressure at baseline was 171 ± 2 mmHg despite an intake of 5.2 ± 0.1 antihypertensive drugs. Six months after renal denervation, systolic and diastolic BP decreased by 18 ± 2 mmHg (p < 0.0001) and 10 ± 1 mmHg (p < 0.001). 90 patients (65.7 %) had SBP reductions >=10 mmHg (responders). After 6 months, 24-h UNa increased by 13 % compared to baseline (236 ± 9 vs. 268 ± 9 mmol/day, p < 0.003). This increase was most pronounced in patients with less response in BP. These findings were paralleled by a significant increase in fractional sodium excretion (1.19 ± 0.11 vs. 1.64 ± 0.14 %, p < 0.0001) and were observed independently of the intake of antihypertensive drugs affecting sodium balance, such as mineralocorticoid receptor antagonists or diuretics.RDN lowered BP and increased estimated UNa and fractional sodium excretion in patients with resistant hypertension independently of renal function and antihypertensive therapy.
EVALuna2:3761

Effects of saxagliptin on early microvascular changes in patients with type 2 diabetes - Ott, Christian; Raff, Ulrike; Schmidt, Stefan; Kistner, Iris; Friedrich, Stefanie; Bramlage, Peter; Harazny, Joanna M.; Schmieder, Roland (Cardiovascular Diabetology, 2014)
Patients with diabetes mellitus are at increased risk for microvascular complications. Early changes in microcirculation are characterized by hyperperfusion (e.g. in the retina and kidney) and increased pulse wave reflection leading to increased aortic pressure. We investigated the effects of the DPP-4-inhibitor saxagliptin on early retinal microvascular changes.In this double-blind, controlled, cross-over trial 50 patients (without clinical signs of microvascular alterations) with type-2 diabetes (mean duration of 4 years) were randomized to receive placebo or 5 mg saxagliptin for 6 weeks. Retinal arteriolar structure and retinal capillary flow (RCF) at baseline and during flicker-light exposure was assessed by scanning laser Doppler flowmetry. Central hemodynamics were assessed by pulse wave analysis.Postprandial blood glucose (9.27 ± 0.4 versus 10.1 ± 0.4 mmol/L; p = 0.001) and HbA1c (6.84 ± 0.15 (51 ± 1.6) versus 7.10 ± 0.17% (54 ± 1.9 mmol/mol); p < 0.001) were significantly reduced with saxagliptin treatment compared to placebo. RCF was significantly reduced after treatment with saxagliptin (288 ± 13.2 versus 314 ± 14.1 AU; p = 0.033). This was most pronounced in a subgroup of patients (n = 32) with a fall in postprandial blood glucose (280 ± 12.1 versus 314 ± 16.6 AU; p = 0.011). No significant changes in RCF were seen during flicker-light exposure between placebo and saxagliptin, but the vasodilatory capacity increased two-fold with saxagliptin treatment. Central augmentation pressure tended to be lower after treatment with saxagliptin (p = 0.094), and central systolic blood pressure was significantly reduced (119 ± 2.3 versus 124 ± 2.3 mmHg; p = 0.038).Our data suggest that treatment with saxagliptin for 6 weeks normalizes retinal capillary flow and improves central hemodynamics in type-2 diabetes.The study was registered at (ID: NCT01319357).
EVALuna2:3676

Effects of semaglutide with and without concomitant SGLT2 inhibitor use in participants with type 2 diabetes and chronic kidney disease in the FLOW trial - Mann, Johannes F.E.; Rossing, Peter; Bakris, George; Belmar, Nicolas; Bosch-Traberg, Heidrun; Busch, Robert; Charytan, David M.; Hadjadj, Samy; Gillard, Pieter; Górriz, José Luis; Idorn, Thomas; Ji, Linong; et al. (Nature Medicine, 2024)
People with type 2 diabetes and chronic kidney disease have a high risk for kidney failure and cardiovascular (CV) complications. Glucagon-like peptide-1 receptor agonists and sodium-glucose cotransporter-2 inhibitors (SGLT2i) independently reduce CV and kidney events. The effect of combining both is unclear. FLOW trial participants with type 2 diabetes and chronic kidney disease were stratified by baseline SGLT2i use (N = 550) or no use (N = 2,983) and randomized to semaglutide/placebo. The primary outcome was a composite of kidney failure, ≥50% estimated glomerular filtration rate reduction, kidney death or CV death. The risk of the primary outcome was 24% lower in all participants treated with semaglutide versus placebo (95% confidence interval: 34%, 12%). The primary outcome occurred in 41/277 (semaglutide) versus 38/273 (placebo) participants on SGLT2i at baseline (hazard ratio 1.07; 95% confidence interval: 0.69, 1.67; P = 0.755) and in 290/1,490 versus 372/1,493 participants not taking SGLT2i at baseline (hazard ratio 0.73; 0.63, 0.85; P < 0.001; P interaction 0.109). Three confirmatory secondary outcomes were predefined. Treatment differences favoring semaglutide for total estimated glomerular filtration rate slope (ml min−1/1.73 m2/year) were 0.75 (−0.01, 1.5) in the SGLT2i subgroup and 1.25 (0.91, 1.58) in the non-SGLT2i subgroup, P interaction 0.237. Semaglutide benefits on major CV events and all-cause death were similar regardless of SGLT2i use (P interaction 0.741 and 0.901, respectively). The benefits of semaglutide in reducing kidney outcomes were consistent in participants with/without baseline SGLT2i use; power was limited to detect smaller but clinically relevant effects. ClinicalTrials.gov identifier: NCT03819153.
CRIS-Team Scopus Importer:2024-07-26

Effects of Single Pill Combinations Compared to Identical Multi Pill Therapy on Outcomes in Hypertension, Dyslipidemia and Secondary Cardiovascular Prevention: The START-Study - Wilke, Thomas; Weisser, Burkhard; Predel, Hans Georg; Schmieder, Roland; Wassmann, Sven; Gillessen, Anton; Blettenberg, Jörg; Maywald, Ulf; Randerath, Olaf; Mueller, Sabrina; Böhm, Michael (Integrated Blood Pressure Control, 2022)
Aim: Current guidelines for the treatment of arterial hypertension (AH) or cardiovascular (CV) prevention recommend combination drug treatments with single pill combinations (SPC) to improve adherence to treatment. We aimed to assess whether the SPC concept is clinically superior to multi pill combination (MPC) with identical drugs. Methods and Results: In an explorative study, we analyzed anonymized claims data sets of patients treated with CV drugs for hypertension and/or CV disorders who were insured by the German AOK PLUS statutory health fund covering 01/07/2012-30/06/2018. Patients at age ≥18 years who received either a SPC or MPC with identical drugs were followed for up to one year. A one to one propensity score matching (PSM) was applied within patient groups who started identical drug combinations, and results were reported as incidence rate ratios (IRRs) as well as hazard ratios (HRs). After PSM, data from 59,336 patients were analyzed. In 30 out of 56 IRR analyses, superiority of SPC over MPC was shown. In 5 out of 7 comparisons, the HR for the composite outcome of all-cause death and all-cause hospitalizations was in favor of the SPC regimen (SPC versus MPC): valsartan/amlodipine: HR=0.87 (95% CI: 0.84–0.91, p ≤ 0.001); candesartan/amlodipine: 0.77 (95% CI: 0.65– 0.90, p = 0.001); valsartan/amlodipine/hydrochlorothiazide: HR=0.68 (95% CI: 0.61–0.74, p ≤ 0.001); ramipril/amlodipine: HR=0.80 (95% CI: 0.77–0.83, p ≤ 0.001); acetylsalicylic acid (ASA)/atorvastatin/ramipril: HR=0.64 (95% CI: 0.47–0.88, p = 0.005). Conclusion: SPC regimens are associated with a lower incidence of CV events and lower all-cause mortality in clinical practice. SPC regimens should generally be preferred to improve patient’s prognosis.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Adherence; Cardiovascular outcomes; Clinical practice; Mortality; Prognosis; Single pill

Effects of the nitric oxide synthase inhibitor ronopterin (VAS203) on renal function in healthy volunteers - Ott, Christian; Bosch, Agnes; Winzer, Nicole; Friedrich, Stephanie; Schinzel, Reinhard; Tegtmeier, Frank; Schmieder, Roland (British Journal of Clinical Pharmacology, 2019)
Aims: Reduced nitric oxide (NO) availability may adversely affect renal perfusion and glomerular filtration. The aim of the present study was to characterize in detail the pharmacological effects of VAS203, an inhibitor of NO synthase, on renal haemodynamics in humans. Methods: This double-blind, randomized, placebo-controlled, cross-over phase-I-study comprised 18 healthy men. Renal haemodynamics were assessed with constant-infusion input-clearance technique with p-aminohippurate and inulin for renal plasma flow (RPF) and glomerular filtration rate (GFR), respectively. After baseline measurement, a constant infusion of the tetrahydrobiopterin analogue ronopterin (VAS203, total 10 mg/kg body weight) or placebo was administered at random order for 6 hours additionally. After a wash-out phase of 28 days, the second course was applied. In parallel, markers of early kidney injury and renal function were assessed repeatedly up to 48 hours after starting VAS203/placebo-infusion. Results: VAS203-infusion resulted in a significant decrease of RPF (P <.0001) and GFR (P <.001) compared to placebo, but magnitude was within the physiological range. RPF and GFR recovered partly 2 hours after end of VAS203-infusion and was normal at beginning of the second infusion period. Compared to placebo, preglomerular resistance (P <.0001), and to lesser extent postglomerular resistance (P <.0001) increased, resulting in a decrease of intraglomerular pressure (P <.01). No treatment related effect on markers of early kidney injury, and on renal function (P for all >.20) have been observed. Conclusions: Our phase-I-study in healthy humans indicates that VAS203 (10 mg/kg body weight) reduces renal perfusion and glomerular function within the physiological range mainly due to vasoconstriction at the preglomerular site.
CRIS-Team Scopus Importer:2019-05-03
Keywords: glomerular filtration rate; nitric oxide synthase; renal haemodynamics; renal plasma flow; VAS203

EFFECTS OF THE NO SYNTHASE INHIBITOR RONOPTERIN (VAS203) ON MICRO- AND MACROCIRCULATION IN HEALTHY VOLUNTEERS - Ott, Christian; Bosch, Agnes; Jung, Susan; Kannenkeril, Dennis; Schinzel, R.; Tegtmeier, F.; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-20

Effects of the Selective Sodium-Glucose Cotransporter 2 Inhibitor Empagliflozin on Vascular Function and Central Hemodynamics in Patients With Type 2 Diabetes Mellitus - Striepe, Kristina; Jumar, Agnes; Ott, Christian; Karg, Margarete; Schneider, Markus; Kannenkeril, Dennis; Schmieder, Roland (Circulation, 2017)
EVALuna2:4021

EFFECTS OF THE SGLT2 INHIBITOR EMPAGLIFLOZIN ON VASCULAR FUNCTION IN PATIENTS WITH CHRONIC HEART FAILURE - Kolwelter, Julie; Bosch, Agnes; Jung, Susanne; Linz, Peter; Kannenkeril, Dennis; Nagel, Armin Michael; Ott, Christian; Bramlage, Peter; Uder, Michael; Achenbach, Stephan; Schmieder, Roland (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2021)
CRIS-Team WoS Importer:2021-06-04

Effects of the sodium-glucose cotransporter 2 inhibitor empagliflozin on vascular function in patients with chronic heart failure - Kolwelter, Julie; Bosch, Agnes; Jung, Susanne; Stabel, Lena; Kannenkeril, Dennis; Ott, Christian; Bramlage, Peter; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (ESC Heart Failure, 2021)
Aims Impairment of vascular function contributes to the progression of chronic heart failure (HF) by increasing the afterload. Treatment with selective sodium-glucose cotransporter 2 (SGLT2) inhibitors improves the prognosis of HF, but the precise mechanisms remain unclear. The aim of this study was to analyse the effect of empagliflozin on vascular function in patients with HF.
CRIS-Team WoS Importer:2021-10-01

Effects of treatment with SGLT-2 inhibitors on arginine-related cardiovascular and renal biomarkers - Geßner, Arne; Gemeinhardt, Anna; Bosch, Agnes; Kannenkeril, Dennis; Staerk, Christian; Mayr, Andreas; Fromm, Martin; Schmieder, Roland; Maas, Renke (Cardiovascular Diabetology, 2022)
Background: In patients with type 2 diabetes (T2D) sodium-glucose cotransporter 2 (SGLT-2) inhibitors improve glycaemic control as well as cardiovascular and renal outcomes. Their effects on L-arginine (Arg) related risk markers asymmetric and symmetric dimethylarginine (ADMA and SDMA) and the protective biomarker L-homoarginine (hArg) linking T2D to cardiovascular and renal disease have not yet been reported.
CRIS-Team WoS Importer:2022-01-14

Einfluss neuer Techniken in der Bildgebung der Niere - Uder, Michael; Heinrich, Marc Christopher; Jäger, Florian; Hornegger, Joachim; Schmieder, Roland; Janka, Rolf Matthias (Nephrologe, 2009)
Computed tomography and magnetic resonance imaging have developed very rapidly in recent years. Today these methods are capable not only of morphological assessment of the kidneys but also provide data of a functional nature. Urography by MRI and CT have long been established in clinical routine. Other techniques such as blood level oxygenation-dependent (BOLD), diffusion-weighted, and renal perfusion imaging using MRI or CT are used almost exclusively for research purposes, but they also have many possibilities for renal applications under study conditions in diagnostics and for monitoring vascular and parenchymatous disorders. © 2009 Springer-Verlag.

Elevated VEGF-plasma levels in young patients with mild essential hypertension - Stumpf, Christian; Jukic, Jelena; Yilmaz, A.; Raaz, Dorette; Schmieder, Roland; Daniel, Werner; Garlichs, Christoph (European Journal of Clinical Investigation, 2009)
Background: Growing evidence shows that inflammation plays a pivotal role in the pathophysiology of essential hypertension (EH). Vascular endothelial cell growth factor (VEGF) is currently discussed as a possible mediator of inflammation. To investigate the hypothesis that VEGF plays a role as an inflammatory mediator in EH we performed the present pilot study of young patients in a very early stage of EH. Materials and methods: 15 young patients with mild EH [33.8 ± 7.3 years, systolic blood pressure (SBP): 143.8 ± 10.5 mmHg, diastolic blood pressure (DBP): 88.2 ± 11.1 mmHg, mean arterial pressure (MAP) 106.6 ± 10.4 mmHg] and 15 healthy controls (31.7 ± 10.6 years) were examined. Blood was drawn from a peripheral vein and serum levels of VEGF, monocyte-chemoattractant-protein (MCP)-1, high-sensitivity C-reactive protein (hsCRP), interleukin (IL)-6, and tumour-necrosis-factor (TNF)-α were measured via commercially available enzyme-linked immunoassays. Results: Hypertensives showed increased plasma levels of VEGF (P < 0.05) and MCP-1 (P < 0.05). VEGF positively correlated with MAP (r = 0.46, P < 0.05) and MCP-1 (r = 0.63, P < 0.01). Multivariate analysis demonstrated VEGF to be an independent predictor of MCP-1 levels. Furthermore, hypertensives had higher levels of hsCRP (P < 0.01), IL-6 (P < 0.001) and TNF-α (P < 0.05). IL-6 levels correlated with SBP (r = 0.59, P < 0.001), DBP (r = 0.67, P < 0.001) and MAP (r = 0.46, P < 0.001). A significant positive correlation was also found between hsCRP levels and SBP (r = 0.39, P < 0.05). Conclusions: This pilot study demonstrates that in an early state of EH, inflammatory pathways have already been activated. Besides classical pro-inflammatory cytokines, VEGF serum levels are significantly elevated. The positive correlation of VEGF with MCP-1 is suggestive for the already described induction of MCP-1 via VEGF. © 2008 The Authors.
CRIS-Team Scopus Importer:2024-12-04
Keywords: Cytokines; Hypertension; Inflammation; VEGF

Endovascular ultrasound renal denervation to treat hypertension (RADIANCE-HTN SOLO): a multicentre, international, single-blind, randomised, sham-controlled trial - Azizi, Michel; Schmieder, Roland; Mahfoud, Felix; Weber, Michael A.; Daemen, Joost; Davies, Justin; Basile, Jan; Kirtane, Ajay J.; Wang, Yale; Lobo, Melvin D.; Saxena, Manish; Feyz, Lida; et al. (Lancet, 2018)
BACKGROUND: Early studies suggest that radiofrequency-based renal denervation reduces blood pressure in patients with moderate hypertension. We investigated whether an alternative technology using endovascular ultrasound renal denervation reduces ambulatory blood pressure in patients with hypertension in the absence of antihypertensive medications. METHODS: RADIANCE-HTN SOLO was a multicentre, international, single-blind, randomised, sham-controlled trial done at 21 centres in the USA and 18 in Europe. Patients with combined systolic-diastolic hypertension aged 18-75 years were eligible if they had ambulatory blood pressure greater than or equal to 135/85 mm Hg and less than 170/105 mm Hg after a 4-week discontinuation of up to two antihypertensive medications and had suitable renal artery anatomy. Patients were randomised (1:1) to undergo renal denervation with the Paradise system (ReCor Medical, Palo Alto, CA, USA) or a sham procedure consisting of renal angiography only. The randomisation sequence was computer generated and stratified by centres with randomised blocks of four or six and permutation of treatments within each block. Patients and outcome assessors were blinded to randomisation. The primary effectiveness endpoint was the change in daytime ambulatory systolic blood pressure at 2 months in the intention-to-treat population. Patients were to remain off antihypertensive medications throughout the 2 months of follow-up unless specified blood pressure criteria were exceeded. Major adverse events included all-cause mortality, renal failure, an embolic event with end-organ damage, renal artery or other major vascular complications requiring intervention, or admission to hospital for hypertensive crisis within 30 days and new renal artery stenosis within 6 months. This study is registered with ClinicalTrials.gov, number NCT02649426. FINDINGS: Between March 28, 2016, and Dec 28, 2017, 803 patients were screened for eligibility and 146 were randomised to undergo renal denervation (n=74) or a sham procedure (n=72). The reduction in daytime ambulatory systolic blood pressure was greater with renal denervation (-8·5 mm Hg, SD 9·3) than with the sham procedure (-2·2 mm Hg, SD 10·0; baseline-adjusted difference between groups: -6·3 mm Hg, 95% CI -9·4 to -3·1, p=0·0001). No major adverse events were reported in either group. INTERPRETATION: Compared with a sham procedure, endovascular ultrasound renal denervation reduced ambulatory blood pressure at 2 months in patients with combined systolic-diastolic hypertension in the absence of medications. FUNDING: ReCor Medical.
EVALuna2:34233

Endovascular Ultrasound Renal Denervation to Treat Hypertension: The RADIANCE II Randomized Clinical Trial - Azizi, Michel; Saxena, Manish; Wang, Yale; Jenkins, J. Stephen; Devireddy, Chandan; Rader, Florian; Fisher, Naomi D.L.; Schmieder, Roland; Mahfoud, Felix; Lindsey, Jason; Sanghvi, Kintur; Todoran, Thomas M.; et al. (Journal of the American Medical Association, 2023)
Importance: Two initial sham-controlled trials demonstrated that ultrasound renal denervation decreases blood pressure (BP) in patients with mild to moderate hypertension and hypertension that is resistant to treatment. Objective: To study the efficacy and safety of ultrasound renal denervation without the confounding influence of antihypertensive medications in patients with hypertension. Design, Setting, and Participants: Sham-controlled, randomized clinical trial with patients and outcome assessors blinded to treatment assignment that was conducted between January 14, 2019, and March 25, 2022, at 37 centers in the US and 24 centers in Europe, with randomization stratified by center. Patients aged 18 years to 75 years with hypertension (seated office systolic BP [SBP] ≥140 mm Hg and diastolic BP [DBP] ≥90 mm Hg despite taking up to 2 antihypertensive medications) were eligible if they had an ambulatory SBP/DBP of 135/85 mm Hg or greater and an SBP/DBP less than 170/105 mm Hg after a 4-week washout of their medications. Patients with an estimated glomerular filtration rate of 40 mL/min/1.73 m2or greater and with suitable renal artery anatomy were randomized 2:1 to undergo ultrasound renal denervation or a sham procedure. Patients were to abstain from antihypertensive medications until the 2-month follow-up unless prespecified BP criteria were exceeded and were associated with clinical symptoms. Interventions: Ultrasound renal denervation vs a sham procedure. Main Outcomes and Measures: The primary efficacy outcome was the mean change in daytime ambulatory SBP at 2 months. The primary safety composite outcome of major adverse events included death, kidney failure, and major embolic, vascular, cardiovascular, cerebrovascular, and hypertensive events at 30 days and renal artery stenosis greater than 70% detected at 6 months. The secondary outcomes included mean change in 24-hour ambulatory SBP, home SBP, office SBP, and all DBP parameters at 2 months. Results: Among 1038 eligible patients, 150 were randomized to ultrasound renal denervation and 74 to a sham procedure (mean age, 55 years [SD, 9.3 years]; 28.6% female; and 16.1% self-identified as Black or African American). The reduction in daytime ambulatory SBP was greater with ultrasound renal denervation (mean, -7.9 mm Hg [SD, 11.6 mm Hg]) vs the sham procedure (mean, -1.8 mm Hg [SD, 9.5 mm Hg]) (baseline-adjusted between-group difference, -6.3 mm Hg [95% CI, -9.3 to -3.2 mm Hg], P <.001), with a consistent effect of ultrasound renal denervation throughout the 24-hour circadian cycle. Among 7 secondary BP outcomes, 6 were significantly improved with ultrasound renal denervation vs the sham procedure. No major adverse events were reported in either group. Conclusions and Relevance: In patients with hypertension, ultrasound renal denervation reduced daytime ambulatory SBP at 2 months in the absence of antihypertensive medications vs a sham procedure without postprocedural major adverse events. Trial Registration: ClinicalTrials.gov Identifier: NCT03614260.
CRIS-Team Scopus Importer:2023-03-10

European guidelines for the management of arterial hypertension 2018-what has changed? - Jung, Susan; Schmieder, Roland (Internist, 2019)
BackgroundIn November 2017, the latest American guidelines for the management of arterial hypertension were published. With these guidelines lowering the threshold for hypertension to 130/80mmHg, the latest European guidelines were expected with excitement.ObjectivesThis article gives an overview on the European Society of Cardiology (ESC) and European Society of Hypertension (ESH) 2018 guidelines for the management of arterial hypertension, thereby identifying the most relevant changes in comparison to previous guidelines.Current dataThe latest 2018 ESC/ESH guidelines adhere to the previous definition of hypertension, in which ablood pressure of 140/90mmHg is considered as threshold for diagnosis. In contrast, there was achange in blood pressure treatment target from below 140/90 to between 120-129/70-79mmHg in patients<65years if well tolerated. Among patients65years, asystolic blood pressure between 130 and 139mmHg is recommended, whereas adiastolic blood pressure between 70 and 79mmHg should be targeted. Additionally the guidelines recommend the use of fixed dose combinations as first choice instead of monotherapy to improve adherence. Interventional treatment strategies should only be applied in carefully selected patients at experienced centers and are not recommended outside of clinical studies and registers. Furthermore, the chapters regarding initiation of blood pressure-lowering therapy and clinical evaluation as well as management of hypertension emergencies have been outlined.ConclusionsThe latest European guidelines for the management of hypertension include several changes. One of the most important aspects is thatin contrast to the American guidelinesthe threshold for diagnosis remains at 140/90mmHg, whereas treatment target range has been lowered by roughly 10mmHg and single pill fixed dose combinations are recommended.
CRIS-Team WoS Importer:2019-02-21

European Society of Hypertension position paper on renal denervation 2018 - Schmieder, Roland; Mahfoud, Felix; Azizi, Michel; Pathak, Atul; Dimitriadis, Kyriakos; Kroon, Abraham A.; Ott, Christian; Scalise, Filippo; Mancia, Giuseppe; Tsioufis, Costas (Journal of Hypertension, 2018)
: This ESH update was deemed necessary with the publication of new results of sham-controlled randomized blinded prospective trials with renal denervation (RDN). Proof of concept studies and first randomized trials (some were sham-controlled) displayed discrepant results about the efficacy of RDN. Three sham-controlled randomized trials of the 2.0 generation yielded now similarity in the average blood pressure decrease following RDN. Reduction of ambulatory blood pressure was approximately 5 to 7 mmHg and of office blood pressure 10 mmHg. Such a decrease in blood pressure by pharmacologic therapy has been found to be associated with lower incidence of cardiovascular events in particular with respect to heart failure and stroke by roughly 25%. Nevertheless, some questions about renal denervation are unanswered. The heterogeneity of the blood pressure-lowering response point to the clinical need to identify predictors for efficacy, and questions on long-term safety could not have been answered due to the short duration of the sham-controlled randomized clinical trials.
EVALuna2:34507

European Society of Hypertension position paper on renal denervation 2021 - Schmieder, Roland; Mahfoud, Felix; Mancia, Giuseppe; Azizi, Michael; Boehm, Michael; Dimitriadis, Kyriakos; Kario, Kazuomi; Kroon, Abraham A.; Lobo, Melvin D.; Ott, Christian; Pathak, Atul; Persu, Alexandre; et al. (Journal of Hypertension, 2021)
This ESH Position Paper 2021 with updated proposed recommendations was deemed necessary after the publication of a set of new pivotal sham-controlled randomized clinical trials (RCTs), which provided important information about the efficacy and safety of endovascular device-based renal denervation (RDN) for hypertension treatment. RDN is effective in reducing or interrupting the sympathetic signals to the kidneys and decreasing whole body sympathetic activity. Five independent, fully completed, sham-controlled RCTs provide conclusive evidence that RDN lowers ambulatory and office blood pressure (BP) to a significantly greater extent than sham treatment. BP-lowering efficacy is evident both in patients with and without concomitant antihypertensive medication. The average decrease of 10mmHg in office BP is estimated to lower the incidence of cardiovascular events by 25-30%, based on meta-analyses of RCTs using pharmacological treatment. Neither peri-procedural, nor short-term or long-term adverse events or safety signals (available up to 3 years) have been observed. Implementing RDN as an innovative third option in the armamentarium of antihypertensive treatment requires a structured process that ensures the appropriate performance of the endovascular RDN procedure and adequate selection of hypertensive patients. The latter should also incorporate patients' perspective and preference that needs to be respected in a shared decision-making process.
CRIS-Team WoS Importer:2021-08-20

Evidence of neurodegeneration in individuals with only mildly elevated blood pressure - Jung, Susanne; Bosch, Agnes; Kohler, Nikolas; Ott, Christian; Kannenkeril, Dennis; Dienemann, Thomas; Harazny, Joanna M.; Michelson, Georg; Schmieder, Roland (Journal of Hypertension, 2019)
OBJECTIVE: Initiation of antihypertensive drug treatment in low-risk individuals with grade 1 hypertension is under debate. The aim of this study was to examine the impact of mildly elevated blood pressure (BP) on early neurodegenerative processes independent of ageing. METHODS: Sixty-two individuals were included in this study: 25 young (aged <40 years) and 37 older (aged ≥40 years) individuals at low cardiovascular risk and grade 1 hypertension at most. Macular retinal layer volumes of both eyes were determined by SD-OCT. Total retinal volume but also each inner retinal layer volume separately including retinal nerve fiber layer (RNFL), ganglion cell layer (GCL), inner plexiform layer (IPL), and GCL-IPL were measured in each individual. RESULTS: Retinal layer volumes were lower among older individuals compared with young individuals (RNFL right eye: P = 0.037/left eye: P = 0.021; GCL and GCL-IPL: both eyes P < 0.001; IPL right eye: P = 0.005/left eye: P = 0.002; total retinal volume: both eyes P = 0.002) and there was an inverse correlation between retinal layer volumes and age. Partial correlation analysis, excluding age as a cofactor, revealed an inverse association between retinal layer volumes and DBP. In multiple regression analysis, DBP was identified as a determinant of retinal neurodegenerative processes. CONCLUSION: In the current study, we observed an inverse association between retinal neurodegenerative processes and DBP, suggesting that BP-lowering therapy by early antihypertensive drug-treatment might be beneficial to avoid early neurodegeneration.
EVALuna2:203883

Executive Summary of the Joint Position Paper on Renal Denervation of the Cardiovascular and Interventional Radiological Society of Europe (CIRSE) and the European Society of Hypertension (ESH) - Moss, Jonathan G.; Belli, Anna-Maria; Coca, Antonio; Lee, Michael; Mancia, Giuseppe; Peregrin, Jan H.; Redon, Josep; Reekers, Jim A.; Tsioufis, Costas; Vorwerk, Dierk; Schmieder, Roland (Cardiovascular and Interventional Radiology, 2016)
EVALuna2:3904

Expertise: no longer a sine qua non for guideline authors? - Messerli, Franz H.; Hofstetter, Louis; Agabiti-Rosei, Enrico; Burnier, Michel; Elliott, William J.; Franklin, Stanley S.; Grodzicki, Tomasz; Kario, Kazuomi; Kjeldsen, Sverre E.; Kostis, John B.; Laurent, Stephane; Leenen, Frans H.; et al. (Journal of Hypertension, 2017)
: Several sets of guidelines have been published recently and more are in the works. The very recent American College of Physicians/American Academy of Family Practitioners guidelines were put together by a set of authors and consultants without any expertise in the topic under discussion, that is, hypertension. Although we are not maintaining that all guidelines should be written exclusively by experts, complete lack of expertise among guideline authors is not acceptable.
EVALuna2:3962

Externally Delivered Focused Ultrasound for Renal Denervation - Neuzil, Petr; Ormiston, John; Brinton, Todd J.; Starek, Zdenek; Esler, Murray; Dawood, Omar; Anderson, Thomas L.; Gertner, Michael; Whitbourne, Rob; Schmieder, Roland (Jacc-Cardiovascular Interventions, 2016)
The aim of this study was to assess clinical safety and efficacy outcomes of renal denervation executed by an externally delivered, completely noninvasive focused therapeutic ultrasound device.Renal denervation has emerged as a potential treatment approach for resistant hypertension.Sixty-nine subjects received renal denervation with externally delivered focused ultrasound via the Kona Medical Surround Sound System. This approach was investigated across 3 consecutive studies to optimize targeting, tracking, and dosing. In the third study, treatments were performed in a completely noninvasive way using duplex ultrasound image guidance to target the therapy. Short- and long-term safety and efficacy were evaluated through use of clinical assessments, magnetic resonance imaging scans prior to and 3 and 24 weeks after renal denervation, and, in cases in which a targeting catheter was used to facilitate targeting, fluoroscopic angiography with contrast.All patients tolerated renal denervation using externally delivered focused ultrasound. Office blood pressure (BP) decreased by 24.6 ± 27.6/9.0 ± 15.0 mm Hg (from baseline BP of 180.0 ± 18.5/97.7 ± 13.7 mm Hg) in 69 patients after 6 months and 23.8 ± 24.1/10.3 ± 13.1 mm Hg in 64 patients with complete 1-year follow-up. The response rate (BP decrease >10 mm Hg) was 75% after 6 months and 77% after 1 year. The most common adverse event was post-treatment back pain, which was reported in 32 of 69 patients and resolved within 72 h in most cases. No intervention-related adverse events involving motor or sensory deficits were reported. Renal function was not altered, and vascular safety was established by magnetic resonance imaging (all patients), fluoroscopic angiography (n = 48), and optical coherence tomography (n = 5).Using externally delivered focused ultrasound and noninvasive duplex ultrasound, image-guided targeting was associated with substantial BP reduction without any major safety signals. Further randomized, sham-controlled trials will be needed to validate this unique approach.
EVALuna2:3868

Facing the Challenge of Lowering Blood Pressure and Cholesterol in the Same Patient: Report of a Symposium at the European Society of Hypertension - Williams, Bryan; Masi, Stefano; Wolf, Jacek; Schmieder, Roland (Cardiology and Therapy, 2020)
A symposium held at the 29th European Meeting on Hypertension and Cardiovascular Protection in Milan, Italy, discussed the potential impact and long-term benefits of early active management of cardiovascular disease (CVD) risk in patients with hypertension, and potential barriers to this strategy. Hypertension often aggregates with other cardiovascular risk factors, exponentially increasing morbidity and mortality. While effective therapies to treat hypertension exist, a substantial number of patients still experience major cardiovascular events. Two major issues account for these disappointing results: interventions initiated too late in the disease trajectory and lack of effective translation of the research findings into daily clinical practice. Results from genetic studies suggest that lifetime exposure to lower blood pressure (BP) and cholesterol levels due to protective gene mutations, can provide greater cardiovascular benefits than middle-/late-age interventions. Clinical guidelines suggest adding statins to BP-lowering therapies for further cardiovascular benefits in most hypertensive patients; however, real-world data show that physicians' compliance with these recommendations and patients' adherence to BP- and lipid-lowering treatments remain poor, resulting in poor risk factor control and an increased risk of adverse outcomes. The use of single-pill combinations (SPC) can partially mitigate these issues, as they are associated with increased patient adherence and improved BP control. Treatment with SPC has been recommended in the European Hypertension Guidelines, but optimization of the total CVD risk may need adoption of more ambitious treatment strategies aimed to deliver single pills that control multiple CVD risk factors. Amlodipine, perindopril and atorvastatin have been shown to improve BP and lipid levels to a great extent when given separately, and this combination has also been shown to improve cardiovascular outcomes. Overall, early intervention in patients with hypertension with use of an effective, high-intensity cardiovascular risk reduction regimen and attention to medication adherence through reducing pill burden are likely to result in optimal outcomes.
CRIS-Team WoS Importer:2020-05-29

First experience in analysing pulsatile retinal capillary flow and arteriolar structural parameters measured noninvasively in hypertensive patients - Harazny, Joanna M.; Ott, Christian; Raff, Ulrike; Welzenbach, Juergen; Kwella, Norbert; Michelson, Georg; Schmieder, Roland (Journal of Hypertension, 2014)
Increased pulsatile pressure induces as well as aggravates microvascular damage. Scanning laser Doppler flowmetry allows the noninvasive assessment of both retinal capillary flow (RCF) and arteriolar structural parameters of the retinal circulation. Moreover, pulsatile characteristics of the retinal arterioles can be assessed.In study 1, reliability of pulsatile RCF and structural parameters were examined in randomly selected patients. In study 2, pulsatile RCF as well as the structural parameters of retinal arterioles were assessed in hypertension grade 1-2 (HT1-2; n = 20) and treatment-resistant hypertension (TRH; n = 19).In study 1, test-retest, interobserver and intraobserver reliability of all parameters showed coefficients of variation of less than 10%. In study 2, it was shown that patients with TRH had higher pulse pressure (P = 0.003) and pulsed RCF values (P < 0.001) as patients with HT1-2. Patients with HT1-2 had no change in the vessel diameter, but a significant difference in lumen diameter, resulting in an altered wall thickness (P = 0.001) between systole and diastole. In contrast, patients with TRH showed differences in vessel diameter (P = 0.005) as well as lumen diameter (P = 0.001), resulting in an unaltered wall thickness between systole and diastole. Hence, wall thickness change as a result of pulsed flow regulation observed in HT1-2 was missing in TRH.We suggest a new reliable tool for evaluating the pulsatility in the retinal circulation in humans, and found significant differences in pulsatile RCF and structural parameters between patients with HT1-2 and those with TRH.
EVALuna2:3718

First report of the Global SYMPLICITY Registry on the effect of renal artery denervation in patients with uncontrolled hypertension - Boehm, Michael; Mahfoud, Felix; Ukena, Christian; Hoppe, Uta C.; Narkiewicz, Krzysztof; Negoita, Manuela; Ruilope, Luis; Schlaich, Markus P.; Schmieder, Roland; Whitbourn, Robert; Williams, Bryan; Zeymer, Uwe; et al. (Hypertension, 2015)
This study aimed to assess the safety and effectiveness of renal denervation using the Symplicity system in real-world patients with uncontrolled hypertension (NCT01534299). The Global SYMPLICITY Registry is a prospective, open-label, multicenter registry. Office and 24-hour ambulatory blood pressures (BPs) were measured. Change from baseline to 6 months was analyzed for all patients and for subgroups based on baseline office systolic BP, diabetic status, and renal function; a cohort with severe hypertension (office systolic pressure, >=160 mm Hg; 24-hour systolic pressure, >=135 mm Hg; and >=3 antihypertensive medication classes) was also included. The analysis included protocol-defined safety events. Six-month outcomes for 998 patients, including 323 in the severe hypertension cohort, are reported. Mean baseline office systolic BP was 163.5±24.0 mm Hg for all patients and 179.3±16.5 mm Hg for the severe cohort; the corresponding baseline 24-hour mean systolic BPs were 151.5±17.0 and 159.0±15.6 mm Hg. At 6 months, the changes in office and 24-hour systolic BPs were -11.6±25.3 and -6.6±18.0 mm Hg for all patients (P<0.001 for both) and -20.3±22.8 and -8.9±16.9 mm Hg for those with severe hypertension (P<0.001 for both). Renal denervation was associated with low rates of adverse events. After the procedure through 6 months, there was 1 new renal artery stenosis >70% and 5 cases of hospitalization for a hypertensive emergency. In clinical practice, renal denervation resulted in significant reductions in office and 24-hour BPs with a favorable safety profile. Greater BP-lowering effects occurred in patients with higher baseline pressures.URL: www.clinicaltrials.gov. Unique identifier: NCT01534299.
EVALuna2:3765

FLOW MEDIATED VASODILATION/VASOCONSTRICTION IN DIFFERENT DISEASE POPULATIONS - Kannenkeril, Dennis; Dienemann, T.; Jung, Susan; Striepe, Kristina; Kopp, C.; Schneider, M.; Ott, Christian; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-20

Frailty as clinically relevant Parameters in elderly Patients with arterial Hypertension - the FOHYP Study: Rationale and Study Design - Ritt, M.; Schwarz, C.; Bollheimer, Cornelius; Schmieder, Roland; Gaßmann, Karl-Günter; Sieber, Cornel (Zeitschrift für Gerontologie und Geriatrie, 2013)

From SYMPLICITY HTN-3 to the Renal Denervation Global Registry: where do we stand and where should we go? - Pathak, Atul; Ewen, Sebastian; Fajadet, Jean; Honton, Benjamin; Mahfoud, Felix; Marco, Jean; Schlaich, Markus; Schmieder, Roland; Tsioufis, Konstantinos; Ukena, Christian; Zeller, Thomas (EuroIntervention, 2014)
EVALuna2:3706

Haemoglobin and vascular function in the human retinal vascular bed - Ritt, Martin; Harazny, Joanna M.; Schmidt, Stefan; Raff, Ulrike; Ott, Christian; Michelson, Georg; Schmieder, Roland (Journal of Hypertension, 2013)
: Haemoglobin is a potential nitric oxide (NO) scavenger. Haemoglobin is associated with blood viscosity and the red blood cell free layer width of microvessels that impact on shear stress in the microcirculation. We hypothesized that haemoglobin modulates retinal vascular function.: In 139 nondiabetic male patients with haemoglobin levels within the normal range, the vasodilatatory response of retinal capillary blood flow (RCF) to flicker light exposure and the vasoconstrictor response of RCF to infusion of NO synthase inhibitor N-monomethyl-L-arginine (L-NMMA) were assessed. The latter, because of the selective nature of L-NMMA, reflects a parameter of basal NO activity of retinal vasculature. Examinations of retinal parameters were performed noninvasively and in vivo using scanning laser Doppler flowmetry.: Patients with haemoglobin greater or equal the median revealed reduced increase of RCF to flicker light exposure (2.83 ± 12 vs. 9.52 ± 14 (%), P adjusted = 0.002), and greater decrease of RCF to L-NMMA infusion (-7.35 ± 13 vs. -0.92 ± 14 (%), P adjusted = 0.008), compared with patients with haemoglobin below the median. Haemoglobin was negatively related to the percentage change of RCF to flicker light exposure (r = -0.249, P = 0.004) and to L-NMMA infusion (r = -0.201, P = 0.018). In multiple linear regression analysis haemoglobin was an independent determinant of the percentage change of RCF to flicker light exposure (model 1: ß = -0.278, P = 0.003 and model 2: ß = -0.283, P = 0.002) and to L-NMMA infusion (model 1: ß = -0.256, P = 0.005 and model 2: ß = -0.269, P = 0.004).: Haemoglobin emerged as an independent determinant of vascular function in the human retinal vascular bed.
EVALuna2:3613

Heart rate and blood pressure interactions in the development of erectile dysfunction in high-risk cardiovascular patients - Kratz, Mario T.; Schumacher, Helmut; Sliwa, Karen; Schmieder, Roland; Poess, Janine; Mahfoud, Felix; Unger, Thomas; Lonn, Eva; Koon, Teo; Mancia, Guiseppe; Sleight, Peter; Yusuf, Salim; et al. (European Journal of Preventive Cardiology, 2014)
Erectile dysfunction (ED) is associated with cardiovascular risk factors as elevated systolic blood pressure (SBP), resting high heart rate (HR), and endothelial dysfunction and predicts cardiovascular events. However, the interaction between high HR and SBP and the development of ED remains unclear.We evaluated 1015 male patients enrolled in the ED substudy of ONTARGET and TRANSCEND, examining the influence of mean HR and mean SBP obtained over all study visits (mean 10.9±1.4 study visits) and their interaction with ED. In patients without pre-existing ED, new onset ED was detected in 29% of patients below, and 41% of patients above, the median of mean HR (OR 1.72, 95% CI 1.8-2.5, p = 0.0047). In patients with pre-existing ED, high HR had no add-on effect. With or without pre-existing ED, high SBP had no influence after adjustment for covariates (OR 1.03, 95% CI 0.66-1.59, p = 0.91). In a continuous model, it was shown that effects of high HR were prominent at low Kölner (Cologne) Evaluation of Erectile Function (KEED) score baseline values and in the presence of SBP above the median.In patients at risk for cardiovascular events, high HR is associated with ED, whereas the effect of high SBP was not significant. High resting HR might represent a cardiovascular risk indicator. Whether HR represents a potential treatment target to improve ED in high-risk individuals must be scrutinized in prospective trials.
EVALuna2:3655

High cholesterol absorption is associated with increased cardiovascular risk in haemodialysis patients: insights from the AURORA study - Silbernagel, Gunther; Duarte, Kevin; Sadiku, Samir; Fauler, Gunter; Maerz, Winfried; Schmieder, Roland; Jardine, Alan G.; Massy, Ziad A.; Girerd, Nicolas; Fellstrom, Bengt; Rossignol, Patrick; Scharnagl, Hubert; et al. (European Journal of Preventive Cardiology, 2022)
Aims Statin treatment did not reduce the risk of cardiovascular events in haemodialysis patients in the 4D and AURORA trials. Post hoc analyses in the 4D study suggested that high cholesterol absorption was associated with increased cardiovascular risk and that atorvastatin would reduce cardiovascular risk in haemodialysis patients with low cholesterol absorption but not in those with high cholesterol absorption. Methods and results AURORA is a randomized, double-blind, placebo-controlled, multi-centre trial in haemodialysis patients. The participants were randomly assigned to receive either rosuvastatin, 10 mg daily, or a matching placebo. There was a follow-up for cardiovascular death with a median duration of 3.9 years. The cholestanol and lathosterol to cholesterol ratios were used to estimate cholesterol absorption and synthesis, respectively. Measurement of non-cholesterol sterols was available in 2332 participants of the 2733 patients included in the primary analysis of the AURORA study. A total of 598 participants died from cardiovascular diseases. The 3rd vs. the 1st tertile of the cholestanol-to-cholesterol ratio was significantly associated with increased risk of cardiovascular death [hazard ratio, HR (95% confidence interval, CI) = 1.36 (1.11-1.65)] in univariate (P = 0.002) and multivariate models (P = 0.034). In contrast, the 3rd vs. the 1st tertile of the lathosterol-to-cholesterol ratio was significantly associated with decreased risk of cardiovascular death [HR (95% CI) = 0.81 (0.67-0.99)] in univariate (P = 0.041) and multivariate (P = 0.019) models. There was no significant interaction between the cholestanol and lathosterol to cholesterol tertiles and treatment group in predicting cardiovascular death. Conclusion The present data from the AURORA study confirm that high cholesterol absorption is associated with increased cardiovascular risk in haemodialysis patients. Assessment of the individual cholesterol absorption rate to guide initiation of statin treatment is not supported by the findings in the AURORA study.
CRIS-Team WoS Importer:2022-05-20

HIGH CHOLESTEROL ABSORPTION IS ASSOCIATED WITH INCREASED CARDIOVASCULAR RISK IN HEMODIALYSIS PATIENTS: INSIGHTS FROM THE AURORA STUDY - Silbernagel, G.; Duarte, K.; Sadiku, S.; Fauler, G.; Maerz, W.; Schmieder, Roland; Jardine, A. G.; Massy, Z. A.; Girerd, N.; Fellstrom, B.; Scharnagl, H.; Zannad, F. (ATHEROSCLEROSIS, 2022)
CRIS-Team WoS Importer:2022-10-14

High Sodium Diet - Role in Renal Sympathodepression - Rodionova, Kristina; Ditting, Tilmann; Fahrmeier, Franziska; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland (FASEB JOURNAL, 2020)
CRIS-Team WoS Importer:2020-10-16

How does empagliflozin improve arterial stiffness in patients with type 2 diabetes mellitus? - Bosch, A.; Ott, Christian; Jung, Susan; Striepe, Kristina; Karg, M. V.; Kannenkeril, Dennis; Dienemann, T.; Schmieder, Roland (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

How does empagliflozin improve arterial stiffness in patients with type 2 diabetes mellitus? Sub analysis of a clinical trial - Bosch, Agnes; Ott, Christian; Jung, Susan; Striepe, Kristina; Karg, Marina V.; Kannenkeril, Dennis; Dienemann, Thomas; Schmieder, Roland (Cardiovascular Diabetology, 2019)
BackgroundEmpagliflozin has been shown to reduce cardiovascular mortality, but the underlying pathogenetic mechanisms are poorly understood. It was previously demonstrated that empagliflozin improved arterial stiffness.MethodsOur analysis comprising 58 patients with type 2 diabetes mellitus identifies factors triggering the improvement of arterial stiffness. All patients participated in an investigator-initiated, prospective, double-blind, randomized, placebo-controlled, interventional clinical trial (http://www.ClinicalTrials.gov: NCT02471963, registered 15th June 2015, retrospectively registered) and received either 6-weeks treatment with 25mg empagliflozin orally once daily or placebo (crossover). Central systolic pressure and central pulse pressure were recorded by the SphygmoCor System (AtCor Medical). Now, we investigated the impact of parameters of glucose metabolism, volume status, sympathetic activation, lipids, uric acid, blood pressure and inflammation on vascular parameters of arterial stiffness using multivariate regression analysis.ResultsAs previously reported, therapy with empagliflozin improved arterial stiffness as indicated by reduced central systolic blood pressure (113.612.1 vs 118.612.9mmHg, p<0.001), central pulse pressure (39.1 +/- 10.2 vs 41.9 +/- 10.7mmHg, p=0.027) forward (27.1 +/- 5.69 vs 28.7 +/- 6.23mmHg, p=0.031) as well as reflected wave amplitude (18.9 +/- 5.98 vs 20.3 +/- 5.97mmHg, p=0.045) compared to placebo. The multivariate regression analysis included age, sex and change between empagliflozin and placebo therapy of the following parameters: HbA1c, copeptin, hematocrit, heart rate, LDL-cholesterol, uric acid, systolic 24-h ambulatory blood pressure and high sensitive CRP (hsCRP). Besides the influence of age (beta=-0.259, p=0.054), sex (beta=0.292, p=0.040) and change in systolic 24-h ambulatory blood pressure (beta=0.364, p=0.019), the change of hsCRP (beta=0.305, p=0.033) emerged as a significant determinant of the empagliflozin induced reduction in arterial stiffness (placebo corrected). When replacing HbA1c with fasting plasma glucose in the multivariate regression analysis, a similar effect of the change in hsCRP (beta=0.347, p=0.017) on arterial stiffness parameters was found.Conclusion Besides age and sex, change in systolic 24-h ambulatory blood pressure and change in hsCRP were determinants of the empagliflozin induced improvement of vascular parameters of arterial stiffness, whereas parameters of change in glucose metabolism and volume status had no significant influence. Our analysis suggests that empagliflozin exerts, at least to some extent, its beneficial vascular effects via anti-inflammatory mechanisms.
CRIS-Team WoS Importer:2019-04-18

How to measure retinal microperfusion in patients with arterial hypertension - Szulc, Urszula; Dąbrowska, Edyta; Pieczyński, Janusz; Białkowski, Paweł; Narkiewicz, Krzysztof; Schmieder, Roland; Harazny, Joanna (Blood Pressure, 2020)
Purpose: Assessment and monitoring of changes in microcirculatory perfusion, perfusion dynamic, vessel structure and oxygenation is crucial in management of arterial hypertension. Constant search for non-invasive methods has led the clinical focus towards the vasculature of the retina, which offers a large opportunity to detect the early phase of the functional and structural changes in the arterial hypertension and can reflect changes in brain vasculature. We review all the available methods of retinal microcirculation measurements including angiography, oximetry, retinal vasculature assessment software, Optical Coherence Tomography Angiography, Adaptive Optics and Scanning Laser Doppler Flowmetry and their application in clinical research. Materials and methods: To further analyse the applicability of described methods in hypertension research we performed a systematic search of the PubMed electronic database (April 2020). In our analysis, we included 111 articles in which at least one of described methods was used for assessment of microcirculation of the retina in hypertensive individuals. Results: Up to this point, the methods most commonly published in studies of retinal microcirculation in arterial hypertension were Scanning Laser Doppler Flowmetry followed shortly by Optical Coherence Tomography Angiography and retinal vasculature assessment software. Conclusions: While none of described methods enables the simultaneous measurement of all microcirculatory parameters, certain techniques are widely used in arterial hypertension research, while others gain popularity in screening.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Arterial hypertension; microperfusion; retinal microvasculature

Hypertension and kidney disease Bluthochdruck und Nierenerkrankungen - Striepe, Kristina; Schmieder, Roland (Tägliche Praxis, 2020)
The association between kidney disease and hypertension is bidirectional and complex. The kidney could be actor and victim of arterial hypertension. Autoregulatory processes protect the kidney in subjects with mild to moderate arterial hypertension. Above a certain threshold autoregulatory processes fail and glomerular pressure increases, resulting in kidney damage. In contrast, renal disease could cause arterial hypertension via diverse mechanisms, for example increased activity of the sympathetic system, impaired vascular/endothelial function, extracellular sodium overload, extracellular volume overload, increased activity of the renin angiotensin system and vascular stiffening of large arteries. Since arterial hypertension is the most predominant factor for progression of chronic kidney failure, in subjects with arterial hypertension and kidney disease an office blood pressure value of 130-140/70-80 mmHg is advocated. In cases of overt proteinuria the recommended value is lower (systolic 120-130 mmHg). A blood pressure lower than 120/70 mmHg should be avoided because of an increasing cardiovascular mortality. Subjects with comorbid kidney disease and hypertension should be treated with a renin-angiotensin system inhibitor (RAS-inhibitor), this is recommended worldwide in several guidelines. The RAS-inhibitor should be combined with a diuretic or calcium antagonist or both. For patients with still uncontrolled hypertension, there is the option to get an interventional treatment, in particular renal denervation.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Blood pressure; Blood pressure targets; Kidney disease; Renal denervation; Renin-angiotensin system

Hypertension: How should data from SYMPLICITY HTN-3 be interpreted? - Schmieder, Roland (Nature Reviews Cardiology, 2014)
EVALuna:26730

Hypertension urgencies in the SPYRAL HTN-OFF MED Pivotal trial - Weber, Michael A.; Schmieder, Roland; Kandzari, David E.; Townsend, Raymond R.; Mahfoud, Felix; Tsioufis, Konstantinos; Kario, Kazuomi; Pocock, Stuart; Tatakis, Fotis; Ewen, Sebastian; Choi, James W.; East, Cara; et al. (Clinical Research in Cardiology, 2022)
The SPYRAL HTN-OFF MED Pivotal trial (https://clinicaltrials.gov/ct2/show/NCT02439749) demonstrated significant reductions in blood pressure (BP) after renal denervation (RDN) compared to sham control in the absence of anti-hypertensive medications. Prior to the 3-month primary endpoint, medications were immediately reinstated for patients who met escape criteria defined as office systolic BP (SBP) >= 180 mmHg or other safety concerns. Our objective was to compare the rate of hypertensive urgencies in RDN vs. sham control patients. Patients were enrolled with office SBP >= 150 and < 180 mmHg, office diastolic BP (DBP) >= 90 mmHg and mean 24 h SBP >= 140 and < 170 mmHg. Patients had been required to discontinue any anti-hypertensive medications and were randomized 1:1 to RDN or sham control. In this post-hoc analysis, cumulative incidence curves with Kaplan-Meier estimates of rate of patients meeting escape criteria were generated for RDN and sham control patients. There were 16 RDN (9.6%) and 28 sham control patients (17.0%) who met escape criteria between baseline and 3 months. There was a significantly higher rate of sham control patients meeting escape criteria compared to RDN for all escape patients (p = 0.032), as well as for patients with a hypertensive urgency with office SBP >= 180 mmHg (p = 0.046). Rate of escape was similar between RDN and sham control for patients without a measured BP exceeding 180 mmHg (p = 0.32). In the SPYRAL HTN-OFF MED Pivotal trial, RDN patients were less likely to experience hypertensive urgencies that required immediate use of anti-hypertensive medications compared to sham control.
CRIS-Team WoS Importer:2022-07-29

Hypertrophic remodelling of retinal arterioles in patients with congestive heart failure - Jung, Susanne; Kolwelter, Julie; Bosch, Agnes; Cífková, Renata; Harazny, Joanna M.; Ott, Christian; Achenbach, Stephan; Schmieder, Roland (ESC Heart Failure, 2021)
Aims: Analysis of microvascular parameters in the retinal circulation—known to reflect those in the systemic circulation—allows us to differentiate between eutrophic and hypertrophic remodelling of small arteries. This study aimed to examine microvascular changes in patients with congestive heart failure (CHF) and reduced as well as mid-range ejection fraction. Methods and results: Forty subjects with CHF underwent measurement of retinal capillary flow (RCF), wall-to-lumen ratio (WLR), vessel and lumen diameter, wall thickness, and wall cross-sectional area (WCSA) of retinal arterioles of the right eye by scanning laser Doppler flowmetry (SLDF). Applying a matched pair approach, we compared this group with reference values of age-matched controls from a random sample in the population of Pilsen, Czech Republic. There was no significant difference in RCF and WLR between the groups (RCF: P = 0.513; WLR: P = 0.106). In contrast, wall thickness and WCSA, indicators of hypertrophic remodelling, were higher in CHF subjects (WT: 15.0 ± 4.2 vs. 12.7 ± 4.2 μm, P = 0.021; WCSA: 4437.6 ± 1314.5 vs. 3615.9 ± 1567.8 μm2, P = 0.014). Similarly, vessel (109.4 ± 11.1 vs. 100.5 ± 14.4 μm, P = 0.002) and lumen diameter (79.0 ± 7.9 vs. 75.2 ± 8.5 μm, P = 0.009) were increased in CHF. Conclusions: In CHF subjects, we observed hypertrophic remodelling of retinal arterioles indicative of similar changes of small resistance arteries in the systemic circulation. Microvascular structure and function assessed by SLDF may thereby represent a useful, non-invasive method for monitoring of microvascular damage in patients with CHF and may offer innovative treatment targets for new CHF therapies.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Heart failure; Hypertrophic remodelling; Microvasculature; Retina

Identifying Isolated Systolic Hypertension From Upper-Arm Cuff Blood Pressure Compared With Invasive Measurements - Picone, Dean S.; Schultz, Martin G.; Armstrong, Matthew K.; Black, J. Andrew; Bos, Willem Jan W.; Chen, Chen Huan; Cheng, Hao Min; Cremer, Antoine; Dwyer, Nathan; Hughes, Alun D.; Kim, Hack Lyoung; Lacy, Peter S.; et al. (Hypertension, 2021)
Isolated systolic hypertension (ISH) is the most common form of hypertension and is highly prevalent in older people. We recently showed differences between upper-arm cuff and invasive blood pressure (BP) become greater with increasing age, which could influence correct identification of ISH. This study sought to determine the difference between identification of ISH by cuff BP compared with invasive BP. Cuff BP and invasive aortic BP were measured in 1695 subjects (median 64 years, interquartile range [55-72], 68% male) from the INSPECT (Invasive Blood Pressure Consortium) database. Data were recorded during coronary angiography among 29 studies, using 21 different cuff BP devices. ISH was defined as ≥130/<80 mm Hg using cuff BP compared with invasive aortic BP as the reference. The prevalence of ISH was 24% (n=407) according to cuff BP but 38% (n=642) according to invasive aortic BP. There was fair agreement (Cohen κ, 0.36) and 72% concordance between cuff and invasive aortic BP for identifying ISH. Among the 28% of subjects (n=471) with misclassification of ISH status by cuff BP, 20% (n=96) of the difference was due to lower cuff systolic BP compared with invasive aortic systolic BP (mean, -16.4 mm Hg [95% CI, -18.7 to -14.1]), whereas 49% (n=231) was from higher cuff diastolic BP compared with invasive aortic diastolic BP (+14.2 mm Hg [95% CI, 11.5-16.9]). In conclusion, compared with invasive BP, cuff BP fails to identify ISH in a sizeable portion of older people and demonstrates the need to improve cuff BP measurements.
CRIS-Team Scopus Importer:2021-02-05
Keywords: aorta; blood pressure; coronary angiography; hypertension; prevalence

Impact of Antihypertensive Medication Changes after Renal Denervation among Different Patient Groups: SPYRAL HTN-ON MED - Townsend, Raymond R.; Ferdinand, Keith C.; Kandzari, David E.; Kario, Kazuomi; Mahfoud, Felix; Weber, Michael A.; Schmieder, Roland; Pocock, Stuart; Tsioufis, Konstantinos; David, Shukri; Steigerwalt, Susan; Walton, Antony; et al. (Hypertension, 2024)
BACKGROUND: The SPYRAL HTN-ON MED (Global Clinical Study of Renal Denervation With the Symplicity Spyral Multi-electrode Renal Denervation System in Patients With Uncontrolled Hypertension in the Absence of Antihypertensive Medications)trial showed significant office and nighttime systolic blood pressure (BP) reductions in patients with hypertension following renal denervation (RDN) compared with sham-control patients, despite similar 24-hour BP reductions. We compared antihypertensive medication and BP changes among prespecified subpopulations. METHODS: The multicenter, randomized, sham-controlled, blinded SPYRAL HTN-ON MED trial (n=337) evaluated BP changes after RDN compared with a sham procedure in patients with hypertension prescribed 1 to 3 antihypertensive drugs. Most patients (n=187; 54%) were enrolled outside the United States, while 156 (46%) US patients were enrolled, including 60 (18%) Black Americans. RESULTS: Changes in detected antihypertensive drugs were similar between RDN and sham group patients in the outside US cohort, while drug increases were significantly more common in the US sham group compared with the RDN group. Patients from outside the United States showed significant reductions in office and 24-hour mean systolic BP at 6 months compared with the sham group, whereas BP changes were similar between RDN and sham in the US cohort. Within the US patient cohort, Black Americans in the sham control group had significant increases in medication burden from baseline through 6 months (P=0.003) but not in the RDN group (P=0.44). CONCLUSIONS: Patients enrolled outside the United States had minimal antihypertensive medication changes between treatment groups and had significant office and 24-hour BP reductions compared with the sham group. Increased antihypertensive drug burden in the US sham cohort, especially among Black Americans, may have diluted the treatment effect in the combined trial population. REGISTRATION: URL: https://www.clinicaltrials.gov; Unique identifier: NCT02439775.
CRIS-Team Scopus Importer:2024-05-03
Keywords: antihypertensive agents; Black or African American; blood pressure; hypertension; renal denervation

IMPACT OF BLOOD PRESSURE AND AGEING ON RETINAL NEURODEGENERATION ASSESSED BY SPECTRAL-DOMAIN OPTICAL COHERENCE TOMOGRAPHY - Jung, Susan; Bosch, Agnes; Kohler, N.; Ott, Christian; Kannenkeril, Dennis; Dienemann, T.; Harazny, J. M.; Michelson, Georg; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-20

Impact of Renal Denervation on Plasma Renin Activity and Relationship of Baseline Plasma Renin Activity to Blood Pressure Lowering Response to Renal Denervation in the SPYRAL HTN-OFF MED Pivotal trial - Mahfoud, Felix; Townsend, Raymond; Kandzari, David; Kario, Kazuomi; Schmieder, Roland; Tsioufis, Konstantinos; Boehm, Michael; Pocock, Stuart; Cohen, Sidney; Fahy, Martin; Weber, Michael (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2020)
CRIS-Team WoS Importer:2020-12-25

Impact of renal denervation on tissue Na(+) content in treatment-resistant hypertension - Ott, Christian; Kopp, Christoph; Dahlmann, Anke; Schmid, Andrea; Linz, Peter; Hammon, Matthias; Ditting, Tilmann; Veelken, Roland; Uder, Michael; Titze, Jens; Schmieder, Roland; Cavallaro, Alexander Josef (Clinical Research in Cardiology, 2017)
Renal denervation (RDN) has been introduced for reducing blood pressure (BP) in treatment-resistant hypertension (TRH). The precise mechanism how RDN exerts its BP-lowering effects are not yet fully understood. It is widely accepted that sodium (Na(+)) plays a crucial role in the pathogenesis of hypertensive disease. However, there is increasing evidence of osmotically inactive Na(+) storage. We investigated the impact of RDN on Na(+) homeostasis using estimation of salt intake, and measurement of tissue Na(+) content.In a study 41 patients with TRH (office BP >=140/90 mmHg and diagnosis confirmed by 24-h ambulatory BP monitoring) underwent RDN. Tissue Na(+) content was assessed non-invasively with 3.0 T magnetic resonance imaging before and 6 months after RDN. In addition, 24-h urinary Na(+) excretion as an estimate of salt intake and spot urine Na(+)/K(+) excretion were assessed. The study was registered at http://www.clinicaltrials.gov (ID: NCT01687725).There was a significant fall in BP (office: -17 ± 20/-10 ± 12 mmHg; 24-h: -11 ± 13/-6 ± 9 mmHg, all p < 0.001) 6 months after RDN. In contrast, tissue Na(+) content of the muscle (20.1 ± 3.9 vs. 20.7 ± 4.0 mmol/L, p = 0.229) and skin (24.4 ± 6.5 vs. 24.8 ± 6.6 mmol/L, p = 0.695) did not change after RDN. Moreover, there was also no change in salt intake after RDN, whereas Na(+)/K(+) ratio only acutely increased.Although RDN resulted in a substantial reduction of BP, tissue Na(+) content of the muscle and skin was not mobilized and reduced. These data indicate that the BP reduction after RDN is unrelated to Na(+) homeostasis.
EVALuna2:3743

Impact of telmisartan on cardiovascular outcome in hypertensive patients at high risk: a Telmisartan Randomised AssessmeNt Study in ACE iNtolerant subjects with cardiovascular Disease subanalysis - Foulquier, Sebastien; Boehm, Michael; Schmieder, Roland; Sleight, Peter; Teo, Koon; Yusuf, Salim; Schumacher, Helmut; Unger, Thomas (Journal of Hypertension, 2014)
In the Telmisartan Randomised AssessmeNt Study in ACE iNtolerant subjects with cardiovascular Disease, all patients were at high cardiovascular risk, and a substantial proportion were hypertensive. We performed a post-hoc analysis to explore the hypothesis that telmisartan has a differential action in hypertensive vs. nonhypertensive patients.The primary four-fold endpoint (composite of cardiovascular death, myocardial infarction (MI), stroke, or hospitalization for heart failure), the secondary three-fold endpoint (cardiovascular death, MI, and stroke), the individual components, new onset of left ventricular hypertrophy (LVH), and new onset of albuminuria were analyzed.There was no evidence for a significantly differential treatment effect of telmisartan in hypertensive and nonhypertensive patients for any endpoints, although the occurrence of the secondary three-fold endpoint was significantly lower in the telmisartan group (13.0%) compared with placebo (15.0%, P < 0.05) only in hypertensive patients. Moreover, data from this post-hoc analysis suggest that MI may be less frequent in hypertensive patients treated with telmisartan (3.8 vs. 5.1%; P < 0.05). Telmisartan may also reduce new onset of LVH (nonhypertensive patients P < 0.05; hypertensive patients P < 0.001) in both subgroups, and new onset of microalbuminuria and macroalbuminuria in hypertensive patients (P < 0.001 and P < 0.01, respectively).The effect of telmisartan in hypertensive and nonhypertensive patients at high cardiovascular risk was not different. This post-hoc analysis suggests that MI may be further reduced by telmisartan in hypertensive patients. Further investigations are needed to study the hypotheses raised by this explanatory analysis.
EVALuna2:3708

Impact of type 1 diabetes and its duration on wall-to-lumen ratio and blood flow in retinal arterioles - Stefański, Adrian; Wolf, Jacek; Harazny, Joanna M.; Miszkowska-Nagórna, Eliza; Wolnik, Bogumił; Murawska, Joanna; Narkiewicz, Krzysztof; Schmieder, Roland (Microvascular Research, 2023)
Background: Subclinical damage to both the small and large vessels may contribute to the development and progression of cardiovascular disease. Scanning laser Doppler flowmetry (SLDF), an established method used to measure retinal microcirculation, has been successfully applied in hypertensive and post-stroke patients. Methods: Retinal microcirculation was assessed in 158 patients with type 1 diabetes and 38 age-matched healthy controls. The diabetics were divided into 3 groups: group A with diabetes duration <12 months, group B with diabetes with 1–10 years, and group C >10 years of diabetes. Retinal capillary structure and perfusion were evaluated using a Heidelberg retina flowmeter and automatically analyzed with full-field perfusion imaging. Results: Age and BMI were comparable in all the diabetic patients and the controls (mean age 24.8 ± 4.7 years, mean BMI 22.9 ± 4.1). In the univariate analyses, RCF (retinal capillary flow) was significantly higher in group A (297 ± 121 arbitrary units [AU]) vs group B (236 ± 52 AU; p = 0.007) and group C (236 ± 70 AU; p = 0.008) and comparable to that of the controls (p = 0.46). Additionally, the WLR (Wall-to-Lumen Ratio) was highest in group C compared to the other diabetic subgroups and controls (p = 0.001). Multivariate regression analyses including age, BMI, sex, HbA1c, smoking, systolic blood pressure, and diabetes duration as covariates, showed, that only diabetes duration was significantly associated with WLR variations, whereas HbA1c was significantly linked to retinal capillary flow levels. Conclusions: New-onset diabetes is associated with an increase in RCF, which then gradually decreased with the duration of the disease. Structural changes of the retinal arterioles estimated via WLR are evident later in the course of diabetes, especially when the disease duration exceeded 10 years.
CRIS-Team Scopus Importer:2023-02-17
Keywords: Arterioles remodeling; Cardiovascular disease; Retinal microcirculation; Scanning laser Doppler Flowmetry; SLDF; Subclinical organ damage; Type 1 diabetes; Wall-to-lumen ratio

Impaired excitability of renal afferent innervation after exposure to the inflammatory chemokine CXCL1 - Ditting, Tilmann; Freisinger, Wolfgang; Rodionova, Kristina; Schatz, Johannes; Lale, Nena; Heinlein, Sonja; Linz, Peter; Ott, Christian; Schmieder, Roland; Scrogin, Karie E.; Veelken, Roland (American Journal of Physiology-Renal Physiology, 2016)
Recently, we showed that renal afferent neurons exhibit a unique firing pattern, i.e., predominantly sustained firing, upon stimulation. Pathological conditions such as renal inflammation likely alter excitability of renal afferent neurons. Here, we tested whether the proinflammatory chemokine CXCL1 alters the firing pattern of renal afferent neurons. Rat dorsal root ganglion neurons (Th11-L2), retrogradely labeled with dicarbocyanine dye, were incubated with CXCL1 (20 h) or vehicle before patch-clamp recording. The firing pattern of neurons was characterized as tonic, i.e., sustained action potential (AP) firing, or phasic, i.e., <5 APs following current injection. Of the labeled renal afferents treated with vehicle, 58.9% exhibited a tonic firing pattern vs. 7.8%, in unlabeled, nonrenal neurons (P < 0.05). However, after exposure to CXCL1, significantly more phasic neurons were found among labeled renal neurons; hence the occurrence of tonic neurons with sustained firing upon electrical stimulation decreased (35.6 vs. 58.9%, P < 0.05). The firing frequency among tonic neurons was not statistically different between control and CXCL1-treated neurons. However, the lower firing frequency of phasic neurons was even further decreased with CXCL1 exposure [control: 1 AP/600 ms (1-2) vs. CXCL1: 1 AP/600 ms (1-1); P < 0.05; median (25th-75th percentile)]. Hence, CXCL1 shifted the firing pattern of renal afferents from a predominantly tonic to a more phasic firing pattern, suggesting that CXCL1 reduced the sensitivity of renal afferent units upon stimulation.
EVALuna2:3740

Impaired increase of retinal capillary blood flow to flicker light exposure in arterial hypertension - Ritt, Martin; Harazny, Joanna M.; Ott, Christian; Raff, Ulrike; Bauernschubert, Philipp; Lehmann, Marina; Michelson, Georg; Schmieder, Roland (Hypertension, 2012)
We hypothesized that the increase of retinal capillary blood flow (RCF) to flicker light exposure is impaired in subjects with arterial hypertension. In 146 nondiabetic untreated male subjects with (n=50) or without (n=96) arterial hypertension, RCF was measured before and after flicker light exposure noninvasively and in vivo using scanning laser Doppler flowmetry. In addition, in a subgroup of 28 subjects, the change of RCF to flicker light exposure was again assessed during parallel infusion of nitric oxide synthase inhibitor N-monomethyl-l-arginine (L-NMMA). The increase of RCF to flicker light exposure was lower in patients with untreated hypertension compared with normotensive subjects when expressed in absolute terms (7.69±54 versus 27.2±44 AU; P adjusted=0.013) or percent changes (2.95±14 versus 8.33±12%; P adjusted=0.023). Systolic (?=-0.216; P=0.023) but not diastolic blood pressure (?=-0.117; P=0.243) or mean arterial pressure (?=-0.178; P=0.073) was negatively related to the percent change of RCF to flicker light exposure, independently of other cardiovascular risk factors. In the subgroup of 28 subjects, the increase of RCF to flicker light exposure was similar at baseline and during parallel infusion of L-NMMA when expressed in absolute terms (20.0±51 versus 22.6±56 AU; P=0.731) or percent changes (7.12±16 versus 8.29±18%; P=0.607). The increase of RCF to flicker light exposure is impaired in arterial hypertension. In the subgroup of the total study cohort, nitric oxide was not a major determinant of the increase of RCF to flicker light exposure.
EVALuna2:3575

Implementation of Bayesian Study Design in the SPYRAL HTN-OFF MED Pivotal Trial - Boehm, Michael; Townsend, Raymond; Weber, Michael; Kandzari, David; Mahfoud, Felix; Kario, Kazuomi; Schmieder, Roland; Tsioufis, Konstantinos; Debruin, Vanessa; Hickey, Graeme; Fahy, Martin; Pocock, Stuart (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Improved blood pressure control via a novel chronic disease management model of care in sub-Saharan Africa: Real-world program implementation results - Otieno, Harun A.; Miezah, Charles; Yonga, Gerald; Kueffer, Fred; Guy, Molly; Lang'At, Chemuttaai; Hettrick, Douglas A.; Schmieder, Roland (Journal of Clinical Hypertension, 2021)
A chronic disease management model of care (Empower Health) was launched in rural and urban areas of Ghana and Kenya in 2018. The goal was to improve disease awareness, reduce the burden of disease, and improve the clinical effectiveness and efficiency of managing hypertension. Leveraging the model, clinicians provide patients with tailored management plans. Patients accessed regular blood pressure checks at home, at the clinic, or at community-partner locations where they received real-time feedback. On the mobile application, clinicians viewed patient data, provided direct patient feedback, and wrote electronic prescriptions accessible through participating pharmacies. To date, 1266 patients had been enrolled in the "real-world" implementation cohort and followed for an average of 351 +/- 133 days across 5 facilities. Average baseline systolic blood pressure (SBP) was 145 +/- 21 mmHg in the overall cohort and 159 +/- 16 mmHg in the subgroup with uncontrolled hypertension (n = 743) as defined by baseline SBP >= 140 mmHg. SBP decreased significantly through 12 months in both the overall cohort (-9.4 mmHg, p < .001) and in the uncontrolled subgroup (-17.6 mmHg, p < .001). The proportion patients with controlled pressure increased from 46% at baseline to 77% at 12 months (p < .001). In summary, a new chronic disease management model of care improved and sustained blood pressure control to 12 months, especially in those with elevated blood pressure at enrollment.
CRIS-Team WoS Importer:2021-02-12

Improved cardiovascular risk prediction in patients with end-stage renal disease on hemodialysis using machine learning modeling and circulating microribonucleic acids - De Gonzalo-Calvo, David; Martinez-Camblor, Pablo; Baer, Christian; Duarte, Kevin; Girerd, Nicolas; Fellstrom, Bengt; Schmieder, Roland; Jardine, Alan G.; Massy, Ziad A.; Holdaas, Hallvard; Rossignol, Patrick; Zannad, Faiez; et al. (Theranostics, 2020)
Rationale: To test whether novel biomarkers, such as microribonucleic acids (miRNAs), and nonstandard predictive models, such as decision tree learning, provide useful information for medical decision-making in patients on hemodialysis (HD).
CRIS-Team WoS Importer:2020-07-31

Improved Persistence to Medication, Decreased Cardiovascular Events and Reduced All-Cause Mortality in Hypertensive Patients with Use of Single-Pill Combinations: Results from the START-Study - Schmieder, Roland; Wassmann, Sven; Predel, Hans Georg; Weisser, Burkhard; Blettenberg, Jörg; Gillessen, Anton; Randerath, Olaf; Mevius, Antje; Wilke, Thomas; Böhm, Michael (Hypertension, 2023)
Background: Single-pill combination improves adherence and persistence to medication in hypertension. It remains unclear whether this also reduces cardiovascular outcomes and all-cause mortality. We analyzed whether single-pill combinations are superior to identical multiple pills on persistence to medication, cardiovascular outcomes, and all-cause mortality. Methods: This was a retrospective claims data (German AOK PLUS) analysis. Data from hypertensive patients ≥18 years treated with renin-angiotensin system combinations given as single pill or identical multipills covering the years 2012 to 2018 were analyzed and followed up to at least 1 year. After 1:1 propensity score matching, persistence to medication, cardiovascular events, and all-cause mortality were compared using non-parametric tests. Results were reported as incidence rate ratios and hazard ratios. Results: After propensity score matching data from 57 998 patients were analyzed: 10 801 patients received valsartan/amlodipine, 1026 candesartan/amlodipine, 15 349 ramipril/amlodipine, and 1823 amlodipine/valsartan/hydrochlorothiazide as single pill or identical multipill. No relevant differences in patient characteristics were observed within the 4 groups. In all groups, a significant lower all-cause mortality, a significant a higher persistence to medication, a significant lower event rate in 15 out of 20 comparisons, and a tendency in the remaining 5 comparisons was observed under single pills compared with multipill combinations. Conclusions: Antihypertensive combination therapy reduces all-cause mortality and cardiovascular when provided as single pill compared to identical drugs as multipills. This strongly supports the European Society of Cardiology/European Society of Hypertension and International Society of Hypertension guidelines recommending the use of a single-pill combination and thus should be more rigorously implemented into daily clinical practice.
CRIS-Team Scopus Importer:2023-05-05
Keywords: antihypertensive agents; cardiovascular diseases; hypertension; medication adherence; mortality; prognosis; risk factors

Improvement in Retinal Capillary Rarefaction After Valsartan Treatment in Hypertensive Patients - Jumar, Agnes; Harazny, Joanna M.; Ott, Christian; Kistner, Iris; Friedrich, Stefanie; Schmieder, Roland (Journal of Clinical Hypertension, 2016)
Decreased capillary density influences vascular resistance and perfusion. The authors aimed to investigate the influence of the renin-angiotensin receptor blocker valsartan on retinal capillary rarefaction in hypertensive patients. Retinal vascular parameters were measured noninvasively and in vivo by scanning laser Doppler flowmetry before and after 4 weeks of treatment with valsartan in 95 patients with hypertension stage 1 or 2 and compared with 55 healthy individuals. Retinal capillary rarefaction was determined with the parameters intercapillary distance (ICD) and capillary area (CapA). In hypertensive patients, ICD decreased (23.4±5.5 ?m vs 21.5±5.6 ?m, P<.001) and CapA increased (1564±621 vs 1776±795, P=.001) after valsartan treatment compared with baseline. Compared with healthy normotensive controls (ICD 20.2±4.2 ?m, CapA 1821±652), untreated hypertensive patients showed greater ICD (P<.001) and smaller CapA (P=.019), whereas treated hypertensive patients showed no difference in ICD (P=.126) and CapA (P=.728). Therapy with valsartan for 4 weeks diminished capillary rarefaction in hypertensive patients.
EVALuna2:3866

Improvement of albuminuria after renal denervation - Ott, Christian; Mahfoud, Felix; Schmid, Axel; Ditting, Tilmann; Veelken, Roland; Ewen, Sebastian; Ukena, Christian; Uder, Michael; Boehm, Michael; Schmieder, Roland (International Journal of Cardiology, 2014)
The primary objective of this study was the effect of renal denervation (RDN) on elevated urinary albumin-to-creatinine ratio (UACR) in treatment-resistant hypertensive patients. In addition, patients were stratified according their UACR at baseline into micro- (30-300 mg/g, n=37) and macroalbuminuria (>= 300 mg/g, <2,200 mg/g, n=22).Increased albuminuria indicates cardiovascular and renal damage in hypertension. RDN emerged as an innovative interventional approach to reduce blood pressure (BP) and may thus reduce albumin urinary excretion.Fifty-nine treatment-resistant hypertensive patients with elevated UACR at baseline underwent catheter-based RDN using the Symplicity Flex(TM) catheter (Medtronic Inc., Santa Rosa, CA).In the whole and pre-specified subgroups both office and 24-h ambulatory BP were significantly reduced 6 months after RDN. In parallel, a significant reduction in UACR occurred in all patients (160 (65-496) versus 89 (29-319) mg/g creatinine, p<0.001) and in both subgroups (microalbuminuria: 83 (49-153) versus 58 (17-113) mg/g creatinine, p=0.001; macroalbuminuria: (536 (434-1483) versus 478 (109-1080) mg/g creatinine, p<0.001). In accordance, the prevalence of micro- and macroalbuminuria decreased significantly. Regression analysis revealed a modest positive relationship between the decrease of UACR and the fall of systolic BP (?=0.340, p=0.039) independent of renal function. Renal function remained unchanged after RDN.In summary, following RDN, the magnitude of albuminuria as well as the prevalence of micro- and macroalbuminuria decreased in treatment-resistant hypertensive patients. Since albuminuria is an independent renal and cardiovascular risk factor, our findings suggest a reduction of renal and cardiovascular risk in these patients.
EVALuna2:3681

Increased Aldosterone Release During Head-Up Tilt in Early Primary Hypertension - Reinold, Annemarie; Schneider, Andreas; Kalizki, Tatjana; Raff, Ulrike; Schneider, Markus P.; Schmieder, Roland; Schmidt, Bernhard M. W. (American Journal of Hypertension, 2017)
EVALuna2:3924

Individualised treatment targets in patients with type-2 diabetes and hypertension - Schmieder, Roland; Tschoepe, Diethelm; Koch, Cornelia; Ouarrak, Taoufik; Gitt, Anselm K. (Cardiovascular Diabetology, 2018)
AIM: Patients with type-2 diabetes mellitus (T2DM) are at high risk of cardiovascular events, accentuated in the presence of hypertension. At present, it is unclear to what extent the guidelines for the management of T2DM, advocating reduction in HbA1c levels to below target levels, are being adhered to in clinical practice. METHODS: DIALOGUE was a prospective, observational, non-interventional registry performed across multiple centres in Germany. Patients aged 18 years or older who had T2DM and hypertension for whom the treating physician considered blood glucose lowering medication as inadequate and/or not safe/tolerable and chose to add a further oral drug or switch drug treatment were included. Patients were assigned a treatment target HbA1c value (≤ 6.5% [strict]; > 6.5 to ≤ 7.0% [intermediate]; > 7.0 to ≤ 7.5% [lenient]). RESULTS: 8568 patients with T2DM and hypertension were enrolled. 6691 (78.1%) had 12-month follow-up. Patients who were assigned a strict HbA1c treatment target (n = 2644) were younger, had shorter diabetes duration, and less comorbidity in comparison to those with intermediate (n = 2912) or lenient targets (n = 1135). Only 53.1% of patients achieved their HbA1c treatment target (46.2% [strict], 56.8% [intermediate], 59.4% [lenient]). There was little sign of treatment intensification for patients that had not achieved their HbA1c target. CONCLUSIONS: Achievement of treatment targets was poor, leaving many patients with sub-optimal blood glucose levels. The apparent reluctance of physicians to intensify antidiabetic drug therapy is alarming, especially considering the evidence pointing to an association of hyperglycaemia and microvascular complications in patients with T2DM.
EVALuna2:33737

Influence of Age on Upper Arm Cuff Blood Pressure Measurement - Picone, Dean S.; Schultz, Martin G.; Otahal, Petr; Black, J. Andrew; Bos, Willem J.; Chen, Chen Huan; Cheng, Hao Min; Cremer, Antoine; Dwyer, Nathan; Fonseca, Ricardo; Hughes, Alun D.; Kim, Hack Lyoung; et al. (Hypertension, 2020)
Blood pressure (BP) is a leading global risk factor. Increasing age is related to changes in cardiovascular physiology that could influence cuff BP measurement, but this has never been examined systematically and was the aim of this study. Cuff BP was compared with invasive aortic BP across decades of age (from 40 to 89 years) using individual-level data from 31 studies (1674 patients undergoing coronary angiography) and 22 different cuff BP devices (19 oscillometric, 1 automated auscultation, 2 mercury sphygmomanometry) from the Invasive Blood Pressure Consortium. Subjects were aged 64±11 years, and 32% female. Cuff systolic BP overestimated invasive aortic systolic BP in those aged 40 to 49 years, but with each older decade of age, there was a progressive shift toward increasing underestimation of aortic systolic BP (P<0.0001). Conversely, cuff diastolic BP overestimated invasive aortic diastolic BP, and this progressively increased with increasing age (P<0.0001). Thus, there was a progressive increase in cuff pulse pressure underestimation of invasive aortic PP with increasing decades of age (P<0.0001). These age-related trends were observed across all categories of BP control. We conclude that cuff BP as an estimate of aortic BP was substantially influenced by increasing age, thus potentially exposing older people to greater chance for misdiagnosis of the true risk related to BP.
CRIS-Team Scopus Importer:2020-03-17
Keywords: aging; cardiovascular disease; coronary angiography; risk factor; sphygmomanometers

Influence of blood flow on arteriolar wall-to-lumen ratio in the human retinal circulation in vivo - Ritt, Martin; Harazny, Joanna M.; Ott, Christian; Raff, Ulrike; Lehmann, Marina; Michelson, Georg; Schmieder, Roland (Microvascular Research, 2012)
We hypothesized that blood flow impacts on arteriolar wall-to-lumen ratio and that vasodilatory capacity is negatively related to arteriolar wall-to-lumen ratio in the human retinal vascular bed.The study cohort comprised 141 non-diabetic untreated male patients with (n=52) or without (n=89) arterial hypertension but without evidence for cardiovascular disease. Retinal capillary blood flow (RCF) before and after exposure to flicker light and to infusion of nitric oxide (NO) synthase inhibitor N-monomethyl-l-arginine (L-NMMA), and parameters of retinal arteriolar morphology, e.g. wall-to-lumen ratio, were assessed non-invasively and in vivo by scanning laser Doppler flowmetry.The study cohort was grouped according to the median RCF into two groups. Patients with RCF above the median revealed lower wall-to-lumen ratio (0.30±0.1 vs 0.34±0.1 (-), P adjusted=0.023) compared to patients with RCF equal or below the median. In addition, RCF was negatively related to wall-to-lumen ratio independently of cardiovascular risk factors (ß=-0.224, P=0.026). In parallel, the decrease of RCF to L-NMMA infusion was greater in patients with RCF above the median compared to the counter group (-8.95±11 vs. 0.35±15 (%), P adjusted <0.001). The increase in RCF to flicker light exposure was negatively related to wall-to-lumen ratio in hypertensive but not in normotensive or all patients (r=-0.292, P=0.047, r=-0.035, P=0.746 and r=-0.126, P=0.144, respectively).In the retinal circulation blood flow impacts on arteriolar wall-to-lumen ratio. Basal NO activity might modulate blood flow and arteriolar morphological changes. In hypertensive, but not in normotensive patients, the vasodilatory capacity is negatively related to arteriolar wall-to-lumen ratio in the human retinal vascular bed.
EVALuna2:3527

Influence of Gender on Blood Pressure Reduction After Renal Denervation in GSR DEFINE - Weil, Joachim; Mahfoud, Felix; Schmieder, Roland; Narkiewicz, Krzysztof; Williams, Bryan; Fahy, Martin; Mancia, Giuseppe (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Interpretation of noninvasive retinal microvascular studies: the individual source of the automatic full field imaging analysis program has to be taken into account - Harazny, Joanna M.; Schmieder, Roland (Journal of Hypertension, 2018)
EVALuna2:35228

INTRARENAL HIGH SALT ADMINISTRATION CAUSES TONIC INHIBITION OF RENAL SYMPATHETIC NERVE ACTIVITY (RSNA) - Hindermann, Martin; Rodionova, Kristina; Dietz, Amelie; Ditting, Tilmann; Ott, Christian; Schmieder, Roland; Amann, Kerstin Ute; Veelken, Roland (2018)
EVALuna2:204842

Invasive treatment of resistant hypertension: present and future - Ott, Christian; Schmieder, Roland (Current Hypertension Reports, 2014)
The underlying pathophysiologic concept of diverse invasive devices to treat resistant hypertension (e.g., sympathetic denervation, carotid sinus nerve stimulation) is known for a long time. Since the pioneering work in the 1940s in humans, innovative techniques have been developed resulting in less invasive treatment procedures and, hence, overcoming serious side effects, which in turn improved safety and lead to more widespread use. Recently, new experimental technologies have been or are under evaluation in experiments and first-in-man studies have been conducted. Data with interventional techniques are rapidly expanding and have to be interpreted with caution. Additional data from randomized potentially sham-controlled studies are urgently needed. This article focuses on the increasing work of different invasive approaches for the treatment of resistant hypertension.
EVALuna2:3692

Is Azilsartan More Effective in Younger Than in Older Patients? An Explorative Analysis of the Prospective EARLY Registry - Schmieder, Roland; Bramlage, Peter (Journal of Clinical Hypertension, 2016)
EVALuna2:3843

IS BASAL NITRIC OXIDE ACTIVITY OF THE RENAL VASCULATURE ALTERED? ANALYSIS OF A RANDOMIZED CONTROLLED TRIAL COMPARING TWO COMBINATION THERAPIES - Kannenkeril, Dennis; Ott, Christian; Bosch, Agnes; Striepe, Kristina; Pietschner, Robert; Schiffer, Mario; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2022)
CRIS-Team WoS Importer:2023-02-17

IS BASAL NITRIC OXIDE ACTIVITY OF THE RENAL VASCULATURE ALTERED? ANALYSIS OF A RANDOMIZED CONTROLLED TRIAL COMPARING TWO COMBINATION THERAPIES - Kannenkeril, Dennis; Ott, Christian; Bosch, Agnes; Striepe, Kristina; Pietschner, Robert; Schiffer, Mario; Schmieder, Roland (Journal of Hypertension, 2022)
OBJECTIVE: Recently we demonstrated that a combination therapy with empagliflozin and linagliptin in patients with type 2 diabetes mellitus (T2DM) induce changes in renal hemodynamics. The purpose of this study was to analyze the influence of basal nitric oxide (NO) activity of the renal vasculature on the described changes of the renal hemodynamic profile. DESIGN AND METHOD: In this study patients with T2DM were nalysing to receive either empagliflozin and linagliptin (E+L group, n = 50) or metformin and insulin glargine (M+I group, n = 46), for 3 months. Renal hemodynamics were assessed with constant-infusion input-clearance technique with p-aminohippuric acid for renal plasma flow (RPF) and inulin for glomerular filtration rate (GFR) at baseline and after treatment. Due to withdrawal of inulin from the market during the study, GFR and filtration fraction (FF) were measured only in a sub-group of patients (E+L: n = 34; M+I: n = 31). Intraglomerular hemodynamics were calculated according the model established by Gomez. The basal NO activity in the renal circulation has been assessed by nalysing change in RPF in response to intravenously administrated NG-monomethyl-l-arginine (NO inhibitor). RESULTS: After 3 months of treatment, we did not observe any change in basal NO activity compared to baseline in either of the groups. In the E+L group, we found a correlation between basal NO activity of the renal vasculature after 3 months of treatment and change in RPF (r = -0.535, p < 0.001), renal blood flow (r = -0.468, p = 0.001) and renal vascular resistance (r = 0.377, p = 0.007) induced by treatment. Similar correlations with change in FF (r = 0.639, p < 0.001), preglomerular (r = 0.350, p = 0.046) and postglomerular resistance (r = 0.588, p < 0.001) have been found. No such relationships were found in the M+I group after 3 months and with basal NO activity at baseline in both treatment groups. CONCLUSIONS: Basal NO emerged as a determinant of the renal hemodynamic response in the combination therapy of empagliflozin and linagliptin, but not in the combination therapy of insulin and metformin.
CRIS-Team Scopus Importer:2022-09-09

Is GFR decline induced by SGLT2 inhibitor of clinical importance? - Günes-Altan, Merve; Bosch, Agnes; Striepe, Kristina; Bramlage, Peter; Schiffer, Mario; Schmieder, Roland; Kannenkeril, Dennis (Cardiovascular Diabetology, 2024)
Background: Use of sodium-glucose-cotransporter-2 (SGLT2) inhibitors often causes an initial decline in glomerular filtration rate (GFR). This study addresses the question whether the initial decline of renal function with SGLT2 inhibitor treatment is related to vascular changes in the systemic circulation. Methods: We measured GFR (mGFR) and estimated GFR (eGFR) in 65 patients with type 2 diabetes (T2D) at baseline and after 12 weeks of treatment randomized either to a combination of empagliflozin and linagliptin (SGLT2 inhibitor based treatment group) (n = 34) or metformin and insulin (non-SGLT2 inhibitor based treatment group) (n = 31). mGFR was measured using the gold standard clearance technique by constant infusion of inulin. In addition to blood pressure (BP), we measured pulse wave velocity (PWV) under standardized conditions reflecting vascular compliance of large arteries, as PWV is considered to be one of the most reliable vascular parameter of cardiovascular (CV) prognosis. Results: Both mGFR and eGFR decreased significantly after initiating treatment, but no correlation was found between change in mGFR and change in eGFR in either treatment group (SGLT2 inhibitor based treatment group: r=-0.148, p = 0.404; non-SGLT2 inhibitor based treatment group: r = 0.138, p = 0.460). Noticeably, change in mGFR correlated with change in PWV (r = 0.476, p = 0.005) in the SGLT2 inhibitor based treatment group only and remained significant after adjustment for the change in systolic BP and the change in heart rate (r = 0.422, p = 0.018). No such correlation was observed between the change in eGFR and the change in PWV in either treatment group. Conclusions: Our main finding is that after initiating a SGLT2 inhibitor based therapy an exaggerated decline in mGFR was related with improved vascular compliance of large arteries reflecting the pharmacologic effects of SGLT2 inhibitor in the renal and systemic vascular bed. Second, in a single patient with T2D, eGFR may not be an appropriate parameter to assess the true change of renal function after receiving SGLT2 inhibitor based therapy. Trial registration: clinicaltrials.gov (NCT02752113).
CRIS-Team Scopus Importer:2024-06-14
Keywords: GFR decline; PWV; SGLT2 inhibitors

Is vascular remodelling in patients with chronic heart failure exaggerated? - Pietschner, Robert; Bosch, Agnes; Kannenkeril, Dennis; Striepe, Kristina; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland; Kolwelter, Julie (ESC Heart Failure, 2022)
Background Vascular remodelling of large arteries increases afterload of the left ventricle. The aim of this study was to analyse whether vascular remodelling and function under laboratory and 24-hour ambulatory conditions is impaired in patients with chronic heart failure (CHF) independently of cardiovascular risk factors.
CRIS-Team WoS Importer:2022-10-21

Kidney hemodynamic effects of sodium-glucose cotransporter 2 inhibitors in diabetes: physiology and clinical implications - León-Jiménez, David; Sridhar, Vikas S.; López-Mendoza, Manuel; Scholtes, Rosalie A.; Schmieder, Roland; Cherney, David Z.I.; van Raalte, Daniël H.; Toro-Prieto, Francisco J.; Miramontes-González, José Pablo; van Bommel, Erik J.M. (Clinical Kidney Journal, 2025)
The progressive loss of kidney function in diabetes mellitus is partly attributable to the occurrence of glomerular hyperfiltration. Consequently, therapeutic interventions that lower intra-glomerular pressure are a cornerstone of treatment in diabetic kidney disease. Sodium-glucose cotransporter 2 (SGLT2) inhibitors consistently reduce glomerular filtration rate (GFR) and calculated intraglomerular pressures across studies. However, the net effect on arteriolar tone that leads to acute GFR declines may differ between cohorts. While pre-glomerular vasoconstriction appears to be the dominant mechanism responsible for GFR dipping in patients with type 1 diabetes (T1D) and glomerular hyperfiltration, other factors, including post-glomerular vasodilation, may contribute to the acute GFR decline in normofilterering individuals with T1D and type 2 diabetes. Regardless of the responsible mechanisms, acute changes in GFR are associated with long-term kidney function preservation—a relationship that may reflect an underlying protective decline in glomerular hypertension.
CRIS-Team Scopus Importer:2025-01-31
Keywords: albuminuria; CKD; diabetic kidney disease; proteinuria; renin–angiotensin system

Left Ventricular Structure in Patients With Mild-to-Moderate CKD-a Magnetic Resonance Imaging Study - Schneider, Markus; Scheppach, Johannes B.; Raff, Ulrike; Toncar, Sebastian; Ritter, Christian; Klink, Thorsten; Stoerk, Stefan; Wanner, Christoph; Schlieper, Georg; Saritas, Turgay; Reinartz, Sebastian D.; Floege, Juergen; et al. (Kidney International Reports, 2019)
Introduction: The high burden of left ventricular (LV) abnormalities in patients with advanced chronic kidney disease (CKD) is well established. However, less is known about the prevalence, patterns, and determinants of LV abnormalities in patients with early CKD.
CRIS-Team WoS Importer:2019-02-21

Local application of tropicamide 0.5% reduces retinal capillary blood flow - Harazny, Joanna M.; Schmieder, Roland; Welzenbach, Juergen; Michelson, Georg (Blood Pressure, 2013)
Abstract Introduction. Scanning laser Doppler flowmetry (SLDF) plays an important role in the study of arterial hypertension, diabetes and stroke. The technology enables non-invasive measurement of the retinal capillary perfusion (RCF), retinal haemodynamics and arteriolar morphology in human. The values can be measured in mydriasis or in non-mydriatic eyes. It is not clear whether the using of vasoactive mydriatica for pupil dilation affects the measured parameters in retina. Acetylcholine, a vasoactive neurotransmitter in human retina, affects the contractility of pericytes using muscarinic receptors and stimulates endothelial synthesis of nitric oxide (NO). We examined whether blockade of the retinal cholinergic receptors by tropicamide affects the RCF. Methods. We measured RCF in both eyes of 13 healthy subjects before and 30 min after the local application of one drop of 0.5% tropicamide to the right eye. The mean age of the group was 44 ± 14 years. The left eye was used as control. RCF was measured by Heidelberg retina flowmetry. Results. Thirty minutes after local application of one drop of 0.5% tropicamide to the right eye RCF decreased significantly (p = 0.001) by 31.9 ± 13% but did not change in the control eye. The maximal decrease was observed 20 min after application of the tropicamide. Conclusion. Locally administered tropicamide profoundly affects the RCF. Thus pupil dilatation impairs any assessment of retinal microcirculation.
EVALuna2:3619

Long-term efficacy and safety of renal denervation: an update from registries and randomised trials - Dimitriadis, Kyriakos; Schmieder, Roland; Iliakis, Panagiotis; Nickel, Laura; Tsioufis, Konstantinos; Weil, Joachim (Blood Pressure, 2023)
CRIS-Team Scopus Importer:2023-10-20

Long-term efficacy and safety of renal denervation in the presence of antihypertensive drugs (SPYRAL HTN-ON MED): a randomised, sham-controlled trial - Mahfoud, Felix; Kandzari, David E.; Kario, Kazuomi; Townsend, Raymond R.; Weber, Michael A.; Schmieder, Roland; Tsioufis, Konstantinos; Pocock, Stuart; Dimitriadis, Kyriakos; Choi, James W.; East, Cara; D'Souza, Richard; et al. (Lancet, 2022)
Background: Renal denervation has been shown to lower blood pressure in the presence of antihypertensive medications; however, long-term safety and efficacy data from randomised trials of renal denervation are lacking. In this pre-specified analysis of the SPYRAL HTN-ON MED study, we compared changes in blood pressure, antihypertensive drug use, and safety up to 36 months in renal denervation versus a sham control group. Methods: This randomised, single-blind, sham-controlled trial enrolled patients from 25 clinical centres in the USA, Germany, Japan, the UK, Australia, Austria, and Greece, with uncontrolled hypertension and office systolic blood pressure between 150 mm Hg and 180 mm Hg and diastolic blood pressure of 90 mm Hg or higher. Eligible patients had to have 24-h ambulatory systolic blood pressure between 140 mm Hg and less than 170 mm Hg, while taking one to three antihypertensive drugs with stable doses for at least 6 weeks. Patients underwent renal angiography and were randomly assigned (1:1) to radiofrequency renal denervation or a sham control procedure. Patients and physicians were unmasked after 12-month follow-up and sham control patients could cross over after 12-month follow-up completion. The primary endpoint was the treatment difference in mean 24-h systolic blood pressure at 6 months between the renal denervation group and the sham control group. Statistical analyses were done on the intention-to-treat population. Long-term efficacy was assessed using ambulatory and office blood pressure measurements up to 36 months. Drug surveillance was used to assess medication use. Safety events were assessed up to 36 months. This trial is registered with ClinicalTrials.gov, NCT02439775; prospectively, an additional 260 patients are currently being randomly assigned as part of the SPYRAL HTN-ON MED Expansion trial. Findings: Between July 22, 2015, and June 14, 2017, among 467 enrolled patients, 80 patients fulfilled the qualifying criteria and were randomly assigned to undergo renal denervation (n=38) or a sham control procedure (n=42). Mean ambulatory systolic and diastolic blood pressure were significantly reduced from baseline in the renal denervation group, and were significantly lower than the sham control group at 24 and 36 months, despite a similar treatment intensity of antihypertensive drugs. The medication burden at 36 months was 2·13 medications (SD 1·15) in the renal denervation group and 2·55 medications (2·19) in the sham control group (p=0·26). 24 (77%) of 31 patients in the renal denervation group and 25 (93%) of 27 patients in the sham control group adhered to medication at 36 months. At 36 months, the ambulatory systolic blood pressure reduction was −18·7 mm Hg (SD 12·4) for the renal denervation group (n=30) and −8·6 mm Hg (14·6) for the sham control group (n=32; adjusted treatment difference −10·0 mm Hg, 95% CI −16·6 to −3·3; p=0·0039). Treatment differences between the renal denervation group and sham control group at 36 months were −5·9 mm Hg (95% CI −10·1 to −1·8; p=0·0055) for mean ambulatory diastolic blood pressure, −11·0 mm Hg (−19·8 to −2·1; p=0·016) for morning systolic blood pressure, and −11·8 mm Hg (−19·0 to −4·7; p=0·0017) for night-time systolic blood pressure. There were no short-term or long-term safety issues associated with renal denervation. Interpretation: Radiofrequency renal denervation compared with sham control produced a clinically meaningful and lasting blood pressure reduction up to 36 months of follow-up, independent of concomitant antihypertensive medications and without major safety events. Renal denervation could provide an adjunctive treatment modality in the management of patients with hypertension. Funding: Medtronic.
CRIS-Team Scopus Importer:2022-04-15

Long-Term, Patient-Level Analysis of Radiofrequency Renal Denervation in the SYMPLICITY Clinical Trial Program - Mahfoud, Felix; Townsend, Raymond R.; Kandzari, David E.; Mancia, Giuseppe; Whitbourn, Robert; Lauder, Lucas; Bhatt, Deepak L.; Kario, Kazuomi; Schmieder, Roland; Schlaich, Markus; Fahy, Martin; Böhm, Michael (JACC: Advances, 2025)
Background: Renal denervation (RDN) lowers blood pressure (BP) in patients with uncontrolled hypertension. Current guidelines recommend RDN for patients with uncontrolled BP despite the use of antihypertensive (AH) medications. Durability of BP reductions and assessment of which patient baseline characteristics correlate with subsequent BP reductions are scarce. Objectives: The authors leveraged patient data from the entire SYMPLICITY Clinical program to model long-term BP reductions and assess patient characteristics associated with future BP reductions. Methods: Repeated BP measurements from each patient were analyzed using linear mixed models. Models were fitted with office systolic BP (SBP), 24-h ambulatory SBP, office diastolic BP (DBP), and 24-h ambulatory DBP as outcome variables. Baseline BP, baseline number of AH medications, AH medications over time, and other variables were included as fixed effects. Results: The mixed model included data from 4,155 patients treated with the Symplicity RDN system. The mean age was 60 ± 12 years, 40.4% of whom were female. Estimated, longitudinal office and 24-h ambulatory SBP changes through 36 months, after adjusting for AH medication effects, were biphasic, with a steep reduction after RDN through the first 6 months followed by continuous and steady reductions in office and 24-h SBP and DBP afterward through 36 months. Higher baseline office systolic or 24-h ambulatory SBP were correlated with greater reductions through follow-up in office and 24-h SBP, respectively. Patient characteristics consistent with high sympathetic nerve activity, such as atrial fibrillation and type 2 diabetes, emerged as statistically significant covariates associated with greater office systolic and office and 24-h diastolic BP reductions, respectively. Conclusions: Modeling suggested patients have durable BP reductions following RDN, with a steep immediate reduction followed by a steady reduction through 3 years.
CRIS-Team Scopus Importer:2025-02-28
Keywords: hypertension; linear regression model; renal denervation

LONG-TERM REDUCTION IN MORNING AND NIGHTTIME BLOOD PRESSURE AFTER RENAL DENERVATION: 36-MONTH RESULTS FROM SPYRAL HTN-ON MED PILOT TRIAL - Kario, Kazuomi; Mahfoud, Felix; Kandzari, David E.; Townsend, Raymond R.; Weber, Michael A.; Schmieder, Roland; Tsioufis, Konstantinos; Pocock, Stuart; Fahy, Martin; Boehm, Michael (JOURNAL OF HYPERTENSION, 2023)
CRIS-Team WoS Importer:2023-03-17

Long-term reduction in morning and nighttime blood pressure after renal denervation: 36-month results from SPYRAL HTN-ON MED trial - Kario, Kazuomi; Mahfoud, Felix; Kandzari, David E.; Townsend, Raymond R.; Weber, Michael A.; Schmieder, Roland; Tsioufis, Konstantinos; Pocock, Stuart; Brar, Sandeep; Hettrick, Douglas A.; Fahy, Martin; Boehm, Michael (Hypertension Research, 2022)
Elevated morning and nighttime blood pressures (BP) are associated with increased risk of cardiovascular events such as stroke and myocardial infarction. We compared the long-term changes in morning and nighttime BP in patients with uncontrolled hypertension (office systolic BP between 150 and <180 mmHg/diastolic BP ≥ 90 mmHg; mean ambulatory systolic BP (SBP) between 140 and <170 mmHg; 1–3 prescribed antihypertensive medications). Eighty patients were randomized to RDN or sham control. In patients taking at least 3 antihypertensive medications at 36 months (N = 23 RDN group; N = 23 sham group), the 24 h ambulatory SBP as well as morning (7:00–9:00AM) and nighttime (1:00–6:00AM) ambulatory SBP were significantly lower for the RDN group compared to sham control (24 h SBP: −20.2 vs. −10.2, p = 0.0087; morning SBP: −23.9 vs. −8.0 mmHg, p = 0.029; nighttime SBP: −20.8 vs. −7.2 mmHg, p = 0.0011). At 36 months, 24 h SBP was controlled to <130 mmHg in 40% of RDN patients in the morning compared to 6% for the sham group; P = 0.021 and in 80% of the RDN patients at night compared to 39% in the sham group; P = 0.019. Major adverse events through 36 months were rare in both groups, and there were no renal artery re-interventions or vascular complications. Morning and nighttime SBP were significantly lower in patients prescribed at least 3 antihypertensive medications at 36 months in the SPYRAL HTN-ON MED trial for RDN compared with sham control. The results suggest RDN has significant benefit when the risk of cardiovascular events is highest.
CRIS-Team Scopus Importer:2022-10-28
Keywords: Cardiovascular prognosis; Randomized controlled trial; Renal denervation; Resistant hypertension

LONG-TERM RESULTS FROM THE SPYRAL HTN-ON MED TRIAL: RENAL DENERVATION INCREASES TIME IN BLOOD PRESSURE TARGET RANGE OVER 36 MONTHS - Tsioufis, Konstantinos; Kandzari, David; Kario, Kazuomi; Townsend, Raymond; Mahfoud, Felix; Weber, Michael; Schmieder, Roland; Pocock, Stuart; Fahy, Martin; Bohm, Michael (JOURNAL OF HYPERTENSION, 2022)
CRIS-Team WoS Importer:2023-02-17

LONG-TERM RESULTS FROM THE SPYRAL HTN-ON MED TRIAL: RENAL DENERVATION INCREASES TIME IN BLOOD PRESSURE TARGET RANGE OVER 36 MONTHS - Tsioufis, Konstantinos; Kandzari, David; Kario, Kazuomi; Townsend, Raymond; Mahfoud, Felix; Weber, Michael; Schmieder, Roland; Pocock, Stuart; Fahy, Martin; Bohm, Michael (Journal of Hypertension, 2022)
OBJECTIVE: Six-month results from the SPYRAL HTN-ON MED pilot trial showed that patients with antihypertensive medications that underwent renal denervation (RDN) had a significantly greater reduction in 24-hr ambulatory and office systolic blood pressure (BP) from baseline compared to sham control. However, the effect of RDN on BP burden over time has not been established. Time in target range (TTR) analysis estimates the percent of time since procedure spent in a preferred systolic BP range as an indicator of BP control. An increase in TTR is associated with significantly lower risk of major cardiovascular events. In this analysis, we evaluate the long-term safety and efficacy of RDN in the SPYRAL HTN-ON MED pilot trial. DESIGN AND METHOD: Eligible patients were enrolled in SPYRAL HTN-ON MED with an office systolic BP (OSBP) of 150 to < 180 mmHg, office diastolic BP > = 90 mm Hg, and a 24-hr mean ambulatory systolic BP (ASBP) of 140 to < 170 mmHg. Successive follow-up BP measures over 36 months were linearly interpolated to estimate TTR over time. BP target range was defined as 24-hr ASBP < = 140 mmHg and OSBP < = 140 mmHg. TTR was calculated for each patient as the proportion of time spent in the target BP range since the procedure, including the baseline BP measurement. At 24 months (RDN, n = 34; control, n = 17) there were fewer patients with follow-up measures in the control group due to protocol requirements and the option for patients to crossover. For sham control patients who later crossed over to RDN before their 36-month follow-up (n = 13), the last measure prior to RDN was imputed at 36 months. RESULTS: Long-term, 36-month safety and efficacy outcomes of the first 80 patients andomised 1:1 into the RDN (n = 38) and sham control arms (n = 42) will be presented at ESH 2022, in addition to a time in blood pressure target range analysis. CONCLUSIONS: Thirty-six month results evaluating the long-term efficacy and durability of RDN compared to a sham control in SPYRAL HTN-ON MED for patients with uncontrolled hypertension will be presented at ESH 2022.
CRIS-Team Scopus Importer:2022-09-16

Long-Term Results up to 12 Months After Catheter-Based Alcohol-Mediated Renal Denervation for Treatment of Resistant Hypertension - Mahfoud, Felix; Sievert, Horst; Bertog, Stefan; Lauder, Lucas; Ewen, Sebastian; Lengele, Jean-Philippe; Wojakowski, Wojciech; Schmieder, Roland; Van Der Giet, Markus; Weber, Michael A.; Kandzari, David E.; Parise, Helen; et al. (Circulation: Cardiovascular Interventions, 2021)
BACKGROUND: Primary results of this prospective, open-label, multicenter trial suggested that alcohol-mediated renal denervation with perivascular injection of dehydrated alcohol using the Peregrine System Infusion Catheter safely reduces blood pressure (BP) in patients with resistant hypertension. To date, maintenance of the BP-lowering effect beyond 6 months using this novel technology has not been reported. This article describes the final, 12-month follow-up data on the safety and efficacy of alcohol-mediated renal denervation in these patients.
CRIS-Team WoS Importer:2021-10-01

Low-dose eplerenone decreases left ventricular mass in treatment-resistant hypertension - Schneider, Andreas; Schwab, Johannes; Karg, Margarete; Kalizki, Tatjana; Reinold, Annemarie; Schneider, Markus; Schmieder, Roland; Schmidt, Bernhard M. W. (Journal of Hypertension, 2017)
Mineralocorticoid receptor antagonists are increasingly used in patients with treatment-resistant hypertension (TRH). There is experimental evidence for blood pressure (BP) independent effects of mineralocorticoid receptor blockade on cardiovascular target organ damage. We hypothesized that low-dose eplerenone (50 mg) will reduce left ventricular mass (LVM) beyond its BP-lowering effects.We performed a randomized, double-blind, placebo-controlled, parallel group study in 51 patients with TRH. Patients were allocated to receive either eplerenone 50 mg or placebo for 6 months, while other antihypertensive agents could be added in both groups to achieve a BP target of less than 140/90 mmHg. LVM was assessed by MRI before and after treatment.Baseline office BP was similar in the eplerenone and the placebo group (166 ± 21/91 ± 15 versus 159 ± 19/94 ± 8 mmHg, n.s.). BP was similarly reduced in the eplerenone versus the placebo group (-35 ± 20/-15 ± 11 versus -30 ± 19/-13 ± 7 mmHg, n.s.). However, LVM was reduced only in the eplerenone group (from 155 ± 33 to 136 ± 33 g, P < 0.001), but not in the placebo group (152 ± 32 versus 148 ± 38 g, P = 0.45).Despite similar BP-lowering, only patients with TRH who were allocated to eplerenone experienced a reduction of LVM. Thus, our data suggest that in patients with TRH, mineralocorticoid receptor antagonists should be used preferentially in order to achieve an effective reduction of LVM along with the improvement of BP control.
EVALuna2:3937

LOW DOSE-EPLERENONE TREATMENT DECREASES AORTIC STIFFNESS IN PATIENTS WITH METABOLIC SYNDROME - Kannenkeril, Dennis; Bosch, Agnes; Kolwelter, Julie; Striepe, Kristina; Ott, Christian; Schiffer, Mario; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Low dose-eplerenone treatment decreases aortic stiffness in patients with resistant hypertension - Kalizki, Tatjana; Schmidt, Bernhard Magnus Wilhelm; Raff, Ulrike; Reinold, Annemarie; Schwarz, Thomas K.; Schneider, Markus P.; Schmieder, Roland; Schneider, Andreas (Journal of Clinical Hypertension, 2017)
Vascular damage is aggravated in animal models of hypertension with mineralocorticoid (MR) excess and in hypertensive patients with primary hyperaldosteronism. MR antagonism has shown to provide effective blood pressure (BP)-control in patients with treatment resistant hypertension (TRH), but the concurrent effects on the vasculature have not been examined. In a randomized, double-blinded, placebo-controlled parallel-group study, 51 patients with TRH received either eplerenone 50 mg or placebo for 6 months together with additional antihypertensives titrated to achieve a BP target of <140/90 mm Hg. Pulse wave velocity (PWV), augmentation index (AIx), augmentation pressure (AP), AP normalized to a heart rate of 75/min (AP@HR75), renal resistive index (RRI), intima-media thickness (IMT) and urinary albumin excretion rate (UAER) were assessed before and after treatment. PWV was reduced only with eplerenone (from 11.3±3.6 to 9.8±2.6 m/s, P?.001), but not with placebo (10.3±2.0 to 10.1±1.8 m/s, P=.60), despite similar reductions in BP (-35±20/-15±11 mm Hg vs -30±19/-13±7 mm Hg, n.s.). Further, reductions in AP and AP@HR75 were greater with eplerenone, while changes in AIx, RRI, IMT and UAER were similar. Our data show that eplerenone beneficially affects markers of arterial stiffness and wave reflection in patients with TRH, independently of BP lowering. These data add to the evidence that MR antagonism should be the preferred treatment option in TRH.
EVALuna2:3944

Low resting heart rates are associated with new-onset atrial fibrillation in patients with vascular disease: results of the ONTARGET/TRANSCEND studies - Boehm, M.; Schumacher, H.; Linz, D.; Reil, J. -C.; Ukena, C.; Lonn, E.; Teo, K.; Sliwa, K.; Schmieder, Roland; Sleight, P.; Yusuf, S. (Journal of Internal Medicine, 2015)
Elevated systolic blood pressure (SBP) and high resting heart rate (HR) are associated with cardiovascular end-points. Although the association between atrial fibrillation (AF) and SBP is well established, the relation between AF and HR remains unclear.In patients from the ONTARGET and TRANSCEND studies with high cardiovascular disease risk (n = 27 064), new-onset AF was evaluated in relation to mean SBP, visit-to-visit variation in SBP (SBP-CV; i.e. SD/mean × 100%), mean HR and visit-to-visit variation in HR (HR-CV).Low mean HR (P < 0.0001) and high SBP (P = 0.0021) were associated with incident AF. High SBP-CV (P = 0.031) and HR-CV (P < 0.0001) were also associated with incident AF. After adjustment for confounders, SBP and SBP-CV were no longer significantly associated with AF. The detrimental effect of low HR was particularly evident in subjects who were not receiving treatment with beta-blockers (P = 0.014 for interaction between beta-blocker use and mean HR). In addition to low HR, high HR-CV and high SBP had additive effects on incident AF.Low mean HR (<60 beats min(-1) ) is independently associated with incident AF, and low HR-CV and high SBP further increase the incidence of new-onset AF in patients at high risk of cardiovascular disease.
EVALuna2:3768

Lumen narrowing and increased wall to lumen ratio of retinal microcirculation are valuable biomarkers of hypertension-mediated cardiac damage - Dąbrowska, Edyta; Harazny, Joanna M.; Miszkowska-Nagórna, Eliza; Stefański, Adrian; Graff, Beata; Kunicka, Katarzyna; Świerblewska, Ewa; Rojek, Agnieszka; Szyndler, Anna; Wolf, Jacek; Gruchała, Marcin; Schmieder, Roland; et al. (Blood Pressure, 2019)
Purpose: In the course of hypertension, left ventricular hypertrophy and diastolic dysfunction develop very often and may progress toward heart failure. The aim of the study was to analyze the relationship between abnormalities of retinal microcirculation and cardiac damage defined as left ventricular hypertrophy and/or diastolic dysfunction. Materials and methods: The study comprised 88 patients with essential hypertension. The group was divided into two subgroups: hypertensives without cardiac damage (n = 55) and with cardiac damage (n = 33). Control group comprised 32 normotensive subjects. Scanning laser Doppler flowmetry was used to evaluate retinal microcirculation. Echocardiography was used to assess cardiac damage. Results: Lumen diameter of retinal arterioles was significantly smaller in patients with cardiac damage vs. controls (77 vs. 84 µm, p = 0.02). Additionally, there was an evident trend with respect to lumen diameter (LD) across all three studied subgroups; i.e.: the smallest dimeters were present in cardiac damage patients, moderate size in hypertensives’ without cardiac damage, and the largest diameters in healthy controls (pfor trend < 0.01). Lumen diameter was inversely correlated with cardiac intraventricular septum diameter (R = –0.25, p = 0.02), left ventricular mass (R = –0.24, p = 0.02), and left atrial volume (R = –0.22, p = 0.04). Wall to lumen ratio was associated with intraventricular septum diameter (R = 0.21, p = 0.044) and left atrial volume (R = 0.21, p = 0.045). In multivariable regression analysis, lumen diameter was independently associated with intraventricular septum diameter (β = –0.05, p = 0.03), left ventricular mass (β = –1.15, p = 0.04), and left atrial volume (β = –0.42, p = 0.047); wall to lumen ratio was independently associated with intraventricular septum diameter (β = 3.67, p = 0.02) and left atrial volume (β = 30.0, p = 0.04). Conclusions: In conclusion, retinal arterioles lumen diameter and wall to lumen ratio were independent biomarkers of cardiac damage. Retinal examination performed by means of scanning laser Doppler flowmetry might be a valuable tool to improve cardiovascular risk stratification of hypertensive patients.
CRIS-Team Scopus Importer:2019-09-17
Keywords: cardiac damage; diastolic dysfunction; left ventricular hypertrophy; Microcirculation

LUMEN NARROWING OF RETINAL ARTERIOLES IS A VALUABLE BIOMARKER OF CARDIAC DAMAGE - Dabrowska, E.; Harazny, J. M.; Miszkowska-Nagorna, E.; Stefanski, A.; Graff, B.; Szyndler, A.; Kunicka, K.; Swierblewska, E.; Rojek, A.; Schmieder, Roland; Laurent, S.; Narkiewicz, K. (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-20

Management of patients with hypertension and chronic kidney disease referred to Hypertension Excellence Centres among 27 countries. On behalf of the European Society of Hypertension Working Group on Hypertension and the Kidney - Halimi, Jean Michel; Sarafidis, Pantelis; Azizi, Michel; Bilo, Grzegorz; Burkard, Thilo; Bursztyn, Michael; Camafort, Miguel; Chapman, Neil; Cottone, Santina; de Backer, Tine; Deinum, Jaap; Delmotte, Philippe; et al. (Blood Pressure, 2024)
Objective Real-life management of patients with hypertension and chronic kidney disease (CKD) among European Society of Hypertension Excellence Centres (ESH-ECs) is unclear : we aimed to investigate it. Methods A survey was conducted in 2023. The questionnaire contained 64 questions asking ESH-ECs representatives to estimate how patients with CKD are managed. Results Overall, 88 ESH-ECS representatives from 27 countries participated. According to the responders, renin-angiotensin system (RAS) blockers, calcium-channel blockers and thiazides were often added when these medications were lacking in CKD patients, but physicians were more prone to initiate RAS blockers (90% [interquartile range: 70–95%]) than MRA (20% [10–30%]), SGLT2i (30% [20–50%]) or (GLP1-RA (10% [5–15%]). Despite treatment optimisation, 30% of responders indicated that hypertension remained uncontrolled (30% (15–40%) vs 18% [10%–25%]) in CKD and CKD patients, respectively). Hyperkalemia was the most frequent barrier to initiate RAS blockers, and dosage reduction was considered in 45% of responders when kalaemia was 5.5–5.9 mmol/L. Conclusions RAS blockers are initiated in most ESH-ECS in CKD patients, but MRA and SGLT2i initiations are less frequent. Hyperkalemia was the main barrier for initiation or adequate dosing of RAS blockade, and RAS blockers’ dosage reduction was the usual management.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Chronic kidney disease; guidelines; hyperkalaemia; hypertension; management; mineralocorticoid receptor antagonists; RAS blockers; SGLT2 inhibitors

Managing Treatment-Resistant Patients - Schmieder, Roland (High Blood Pressure and Cardiovascular Prevention, 2015)
Treatment-resistant hypertension (TRH) has a prevalence of approximately 10-20 %, and up to 5 % of patients with TRH experience a major cardiovascular or cerebrovascular event each year. Effective management of real TRH is important but can present a significant clinical challenge. Utilisation of treatment options that maximise treatment compliance is recommended, particularly combinations that have supporting data from clinical studies. Renal denervation can be considered for a subset of truly resistant patients.
EVALuna2:3785

Measurement of kidney perfusion by magnetic resonance imaging: Comparison of MRI with arterial spin labeling to para-aminohippuric acid plasma clearance in male subjects with metabolic syndrome - Ritt, Martin; Janka, Rolf Matthias; Schneider, Markus P.; Martirosian, Petros; Hornegger, Joachim; Bautz, Werner; Uder, Michael; Schmieder, Roland (Nephrology Dialysis Transplantation, 2010)
Background. Magnetic resonance imaging with arterial spin labeling (MRI-ASL) is a non-invasive approach to measure organ perfusion. We aimed to examine whether MRI-ASL kidney perfusion measurements are related to measurements of renal plasma flow (RPF) by para-aminohippuric acid (PAH) plasma clearance and whether changes of kidney perfusion in response to treatment with telmisartan can be detected by MRI-ASL.Methods. Twenty-four patients with metabolic syndrome and an estimated creatinine clearance according to Cockroft and Gault of ≥60ml/min were included in the study. Kidney perfusion was assessed by MRI-ASL measurements of a single coronal kidney slice (with flow-sensitive alternating inversion recovery and true fast imaging with steady-state processing sequence) and by measurements of RPF using PAH plasma clearance before and after 2 weeks of treatment with the angiotensin receptor blocker telmisartan. All MRI-ASL examinations were performed on a 1.5 T scanner.Results. Two weeks of therapy with telmisartan led to a significant increase of RPF (from 313 ± 47 to 348 ± 69ml/min/m, P = 0.007) and MRI-ASL kidney perfusion measurements (from 253 ± 20 to 268 ± 25ml/min/100g, P = 0.020). RPF measurements were related with MRI-ASL kidney perfusion measurements (r = 0.575, P < 0.001). Changes of RPF measurements and changes of MRI-ASL kidney perfusion measurements in response to treatment with telmisartan revealed a close relationship when expressed in absolute terms (r = 0.548, P = 0.015) and in percentage changes (r = 0.514, P = 0.025).Conclusions. Perfusion measurement of a single coronal kidney slice by MRI-ASL is able to approximate kidney perfusion and to approximate changes in kidney perfusion due to pharmacological intervention. © 2009 The Author.

Medication adherence in hypertension - Poulter, Neil R.; Borghi, Claudio; Parati, Gianfranco; Pathak, Atul; Toli, Diana; Williams, Bryan; Schmieder, Roland (Journal of Hypertension, 2020)
: Suboptimal adherence to antihypertensive medication is a major contributor to poor blood pressure control. Several methods, direct or indirect, are available for measuring adherence, including the recently developed biochemical screening, although there is no gold-standard method routinely used in clinical practice to accurately assess the different facets of adherence. Adherence to treatment is a complex phenomenon and several of the barriers to adherence will need to be addressed at the healthcare system level; however, when looking at adherence from a more practical side and from the practitioner's perspective, the patient-practitioner relationship is a key element both in detecting adherence and in attempting to choose interventions tailored to the patient's profile. The use of single-pill combinations enabling simplification of treatment regimen, the implementation of a collaborative team-based approach and the development of electronic health tools also hold promise for improving adherence, and thus impacting cardiovascular outcomes and healthcare costs.
CRIS-Team Scopus Importer:2020-03-17

Metabolic effects and cardiovascular safety of an oral triple therapy of type 2 diabetes: The metformin, empagliflozin, linagliptin example - Gallwitz, Baptist; Schmieder, Roland (Diabetologie und Stoffwechsel, 2020)
Based on new evidence and guidelines we discuss the triple therapy of type 2 diabetes using the example of a combination of metformin, empagliflozin and linagliptin. The SGLT-2 inhibitor empagliflozin improves the combined endpoint of cardiovascular death, non-fatal myocardial infarction and stroke (MACE-3) compared to placebo and reduces the incident probability of hospitalization due to heart failure as well as overall mortality. A newly occurring or deteriorating nephropathy is also observed less frequently. The DPP-4 inhibitor linagliptin lowers blood glucose and HbA 1c and has no effects on the cardiovascular endpoint MACE-3, but reduces the progression of albuminuria as compared to placebo. In comparison to the sulfonylurea glimepiride cardiovascular outcomes are similar, but hypoglycemia is much less frequent. The combination of the insulinotropic linagliptin and the insulin-independent, glucosuric empagliflozin improves the metabolic function as compared to placebo in patients who are insufficiently treated with metformin. In such patients the fixed combination of empagliflozin and linagliptin is the first for which three long-term outcome studies have demonstrated metabolic, cardiovascular and renal effects.
CRIS-Team Scopus Importer:2020-09-11
Keywords: cardiovascular outcome study; empagliflozin; hypoglycemia; linagliptin; metformin; renal function

Mid-Term Vascular Safety of Renal Denervation Assessed by Follow-up MR Imaging. - Schmid, Axel; Schmieder, Raphael; Lell, Michael; Janka, Rolf Matthias; Veelken, Roland; Schmieder, Roland; Uder, Michael; Ott, Christian (Cardiovascular and Interventional Radiology, 2016)
Renal denervation (RDN) emerged as a treatment option for reducing blood pressure (BP) in patients with treatment-resistant hypertension (TRH). However, concerns have been raised regarding the incidence of late renal artery stenosis or thromboembolism after RDN. The goal of the current study was, therefore, to conduct a prospective clinical trial on the mid-term vascular integrity of the renal arteries and the perfusion of the renal parenchyma assessed by magnetic resonance imaging (MRI) in the follow-up after catheter-based RDN.In our single-centre investigator initiated study, 51 patients with true TRH underwent catheter-based RDN using the Symplicity Flex(TM) catheter (Medtronic Inc., Palo Alto, CA). Follow-up MRI was performed at a median of 11 months (interquartile range 6-18 months) after RDN on a 1.5T MR unit. High-resolution MR angiography (MRA) and MRI results were compared to the baseline digital angiography of renal arteries obtained at time of RDN. In case of uncertainties (N = 2) catheter angiography was repeated.Both office and 24-h ambulatory BP were significantly reduced 6 and 12 months after RDN. Renal function remained unchanged 6 and 12 months after RDN. In all patients, MRA excluded new or progression of pre-existing low grade renal artery stenosis as well as focal aneurysms at the sites of radiofrequency ablation. In none of the patients new segmental perfusion deficits in either kidney were detected on MRI.No vascular or parenchymal complications after radiofrequency-based RDN were detected in 51 patients followed up by MRI.
EVALuna2:3794

Mineralocorticoid receptor antagonists for nephroprotection and cardioprotection in patients with diabetes mellitus and chronic kidney disease - Ortiz, Alberto; Ferro, Charles J.; Balafa, Olga; Burnier, Michel; Ekart, Robert; Halimi, Jean-Michel; Kreutz, Reinhold; Mark, Patrick B.; Persu, Alexandre; Rossignol, Patrick; Ruilope, Luis M.; Schmieder, Roland; et al. (Nephrology Dialysis Transplantation, 2021)
Diabetic kidney disease (DKD) develops in similar to 40% of patients with diabetes and is the most common cause of chronic kidney disease (CKD) worldwide. Patients with CKD, especially those with diabetes mellitus, are at high risk of both developing kidney failure and cardiovascular (CV) death. The use of renin-angiotensin system (RAS) blockers to reduce the incidence of kidney failure in patients with DKD dates back to studies that are now >= 20 years old. During the last few years, sodium-glucose co-transporter-2 inhibitors (SGLT2is) have shown beneficial renal effects in randomized trials. However, even in response to combined treatment with RAS blockers and SGLT2is, the renal residual risk remains high with kidney failure only deferred, but not avoided. The risk of CV death also remains high even with optimal current treatment. Steroidal mineralocorticoid receptor antagonists (MRAs) reduce albuminuria and surrogate markers of CV disease in patients already on optimal therapy. However, their use has been curtailed by the significant risk of hyperkalaemia. In the FInerenone in reducing kiDnEy faiLure and dIsease prOgression in DKD (FIDELIO-DKD) study comparing the actions of the non-steroidal MRA finerenone with placebo, finerenone reduced the progression of DKD and the incidence of CV events, with a relatively safe adverse event profile. This document presents in detail the available evidence on the cardioprotective and nephroprotective effects of MRAs, analyses the potential mechanisms involved and discusses their potential future place in the treatment of patients with diabetic CKD.
CRIS-Team WoS Importer:2022-03-18

Mortality and morbidity in relation to changes in albuminuria, glucose status and systolic blood pressure: an analysis of the ONTARGET and TRANSCEND studies - Schmieder, Roland; Schutte, Rudolph; Schumacher, Helmut; Boehm, Michael; Mancia, Giuseppe; Weber, Michael A.; Mcqueen, Matthew; Teo, Koon; Yusuf, Salim (Diabetologia, 2014)
Urinary albumin excretion is a strong predictor of cardiovascular disease. It is uncertain whether improvement from microalbuminuria or deterioration from normoalbuminuria over time in patients with differing changes in glucose and BP change their cardiovascular risk.Data on mortality, cardiovascular and renal outcomes were analysed in 22,984 patients from two large parallel randomised clinical trials followed for 56 months. A central laboratory analysed first morning spot urine samples at baseline and after 24 months, and events were recorded over the subsequent 32 months. Patients were stratified by changes in albuminuria, glucose status and mean systolic BP over 2 years.There was a strong association between albuminuria status and all-cause and cardiovascular mortality and combined cardiovascular and renal endpoints (all p < 0.0001). Changes in systolic BP control had no effect on mortality, whereas glucose status was significantly associated with all outcomes. Irrespective of BP control or glucose status, patients showing an improvement from microalbuminuria to normoalbuminuria after 2 years were at a lower risk of all outcome measures than patients showing deterioration from normoalbuminuria to microalbuminuria (HR for all-cause mortality 0.65 [0.52-0.83], p = 0.0004).Patients who showed improvement to normoalbuminuria over 2 years were at lower risk of all-cause and cardiovascular mortality and of cardiovascular and renal events than those who deteriorated to microalbuminuria over time. Albuminuria over time was significantly better than glucose status and BP control in predicting mortality and both cardiovascular and renal outcomes in patients at a high cardiovascular risk.
EVALuna2:3720

Myocardial infarction with a preserved ejection fraction—the impaired function of the cardio-renal baroreflex - Pickny, Lisa; Hindermann, Martin; Ditting, Tilmann; Hilgers, Karl Friedrich; Linz, Peter; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Rodionova, Kristina (Frontiers in Physiology, 2023)
Introduction: In experimental myocardial infarction with reduced ejection fraction causing overt congestive heart failure, the control of renal sympathetic nerve activity (RSNA) by the cardio-renal baroreflex was impaired. The afferent vagal nerve activity under these experimental conditions had a lower frequency at saturation than that in controls. Hence, by investigating respective first neurons in the nodose ganglion (NG), we wanted to test the hypothesis that after myocardial infarction with still-preserved ejection fraction, the cardiac afferent nerve pathway is also already impaired. Material and methods: A myocardial infarction was induced by coronary artery ligature. After 21 days, nodose ganglion neurons with cardiac afferents from rats with myocardial infarction were cultured. A current clamp was used to characterize neurons as “tonic,” i.e., sustained action potential (AP) firing, or “phasic,” i.e., <5 APs upon current injection. Cardiac ejection fraction was measured using echocardiography; RSNA was recorded to evaluate the sensitivity of the cardiopulmonary baroreflex. Renal and cardiac histology was studied for inflammation and fibrosis markers. Results: A total of 192 neurons were investigated. In rats, after myocardial infarction, the number of neurons with a tonic response pattern increased compared to that in the controls (infarction vs. control: 78.6% vs. 48.5%; z-test, *p < 0.05), with augmented production of APs (23.7 ± 2.86 vs. 15.5 ± 1.86 APs/600 ms; mean ± SEM, t-test, *p < 0.05). The baseline activity of RSNA was subtly increased, and its control by the cardiopulmonary baroreflex was impaired following myocardial infarction: the fibrosis marker collagen I augmented in the renal interstitium. Discussion: After myocardial infarction with still-preserved ejection fraction, a complex impairment of the afferent limb of the cardio-renal baroreflex caused dysregulation of renal sympathetic nerve activity with signs of renal fibrosis.
CRIS-Team Scopus Importer:2023-05-05
Keywords: cardiac afferent neurons after myocardial infarction cardiac afferent innervation; congestive heart failure; myocardial infarction; neuronal cell culture; preserved ejection fraction; renal innervation

Neurogenic substance P-influences on action potential production in afferent neurons of the kidney? - Rodionova, Kristina; Hilgers, Karl Friedrich; Linz, Peter; Schaetzl, Johannes; Raschke, Giulia; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Ditting, Tilmann (Pflügers Archiv: European Journal of Physiology, 2021)
We recently showed that a substance P (SP)-dependent sympatho-inhibitory mechanism via afferent renal nerves is impaired in mesangioproliferative nephritis. Therefore, we tested the hypothesis that SP released from renal afferents inhibits the action potential (AP) production in their dorsal root ganglion (DRG) neurons. Cultured DRG neurons (Th11-L2) were investigated in current clamp mode to assess AP generation during both TRPV1 stimulation by protons (pH 6) and current injections with and without exposure to SP (0.5 mu mol) or CGRP (0.5 mu mol). Neurons were classified as tonic (sustained AP generation) or phasic (<= 4 APs) upon current injection; voltage clamp experiments were performed for the investigation of TRPV1-mediated inward currents due to proton stimulation. Superfusion of renal neurons with protons and SP increased the number of action potentials in tonic neurons (9.6 +/- 5 APs/10 s vs. 16.9 +/- 6.1 APs/10 s, P < 0.05, mean +/- SD, n = 7), while current injections with SP decreased it (15.2 +/- 6 APs/600 ms vs. 10.2 +/- 8 APs/600 ms, P < 0.05, mean +/- SD, n = 29). Addition of SP significantly reduced acid-induced TRPV1-mediated currents in renal tonic neurons (- 518 +/- 743 pA due to pH 6 superfusion vs. - 82 +/- 50 pA due to pH 6 with SP superfusion). In conclusion, SP increased action potential production via a TRPV1-dependent mechanism in acid-sensitive renal neurons. On the other hand, current injection in the presence of SP led to decreased action potential production. Thus, the peptide SP modulates signaling pathways in renal neurons in an unexpected manner leading to both stimulation and inhibition of renal neuronal activity in different (e.g., acidic) environmental contexts.
CRIS-Team WoS Importer:2021-04-16

Neurogenic tachykinin mechanisms in experimental nephritis of rats - Rodionova, Kristina; Hilgers, Karl Friedrich; Paulus, Eva-Maria; Tiegs, Gisa; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Ditting, Tilmann (Pflügers Archiv: European Journal of Physiology, 2020)
We demonstrated earlier that renal afferent pathways combine very likely "classical" neural signal transduction to the central nervous system and a substance P (SP)-dependent mechanism to control sympathetic activity. SP content of afferent sensory neurons is known to mediate neurogenic inflammation upon release. We tested the hypothesis that alterations in SP-dependent mechanisms of renal innervation contribute to experimental nephritis. Nephritis was induced by OX-7 antibodies in rats, 6 days later instrumented for recording of blood pressure (BP), heart rate (HR), drug administration, and intrarenal administration (IRA) of the TRPV1 agonist capsaicin to stimulate afferent renal nerve pathways containing SP and electrodes for renal sympathetic nerve activity (RSNA). The presence of the SP receptor NK-1 on renal immune cells was assessed by FACS. IRA capsaicin decreased RSNA from 62.4 +/- 5.1 to 21.6 +/- 1.5 mV s (*p < 0.05) in controls, a response impaired in nephritis. Suppressed RSNA transiently but completely recovered after systemic administration of a neurokinin 1 (NK1-R) blocker. NK-1 receptors occurred mainly on CD11(+)dendritic cells (DCs). An enhanced frequency of CD11c(+)NK1R(+)cell, NK-1 receptor(+)macrophages, and DCs was assessed in nephritis. Administration of the NK-1R antagonist aprepitant during nephritis reduced CD11c(+)NK1R(+)cells, macrophage infiltration, renal expression of chemokines, and markers of sclerosis. Hence, SP promoted renal inflammation by weakening sympathoinhibitory mechanisms, while at the same time, substance SP released intrarenally from afferent nerve fibers aggravated immunological processes i.e. by the recruitment of DCs.
CRIS-Team WoS Importer:2020-11-06

Neurovascular compression in arterial hypertension: Correlation of clinical data to 3d-visualizations of mri-findings - Manava, Panagiota; Hastreiter, Peter; Schmieder, Roland; Jung, Susanne; Fahlbusch, Rudolf; Dörfler, Arnd; Lell, Michael; Buchfelder, Michael; Naraghi, Ramin (Open Neuroimaging Journal, 2021)
Aims: In this study, we attempted to identify clinical parameters predicting the absence or presence of Neurovascular Compression (NVC) at the Ventrolateral Medulla (VLM) in arterial hypertension (HTN) in MRI findings. Background: Cardiovascular and pulmonary afferences are transmitted through the left vagus and glossopharyngeal nerve to the brain stem and vasoactive centers. Evidence supports the association between HTN and NVC at the left VLM. Several independent studies indicate a reduction of HTN after Microvascular Decompression (MVD) of the left. Several independent studies indicate a reduction of HTN after Microvascular Decompression (MVD) of the left VLM. Image processing of MRI provides comprehensible detection of NVC. HTN affects hemodynamic parameters and organs. Objective: This study analyzes and correlates clinical data and MRI findings in patients with and without NVC at the VLM in treatment resistant HTN to obtain possible selection criteria for neurogenic hypertension. Methods: In 44 patients with treatment resistant HTN, we compared MRI findings of neurovascular imaging to demographic, clinical and lifestyle data, office and 24-hour ambulatory Blood Pressure (BP), and cardiovascular imaging and parameters. Results: Twenty-nine (66%) patients had evidence of NVC at the VLM in MRI. Sixteen patients (36%) had unilateral NVC on the left side, 7 (16%) unilateral right and 6 (14%) bilateral NVC. Fifteen (34%) had no evidence of NVC at the VLM. Patients with left sided NVC were significantly younger, than those without NVC (p=0.034). They showed a statistically significant variance in daytime (p=0.020) and nighttime diastolic BP (p<0.001) as the mean arterial pressure (p=0.020). Other measured parameters did not show significant differences between the two groups. Conclusion: We suggest to examine young adults with treatment resistant HTN for the presence of NVC at VLM, before signs of permanent organ damage appear. Clinical and hemodynamic parameters did not emerge as selection criteria to predict NVC. MVD as a surgical treatment of NVC in HTN is not routine yet as a surgical treatment of NVC in HTN is not routine yet. Detection of NVC by imaging and image processing remains the only criteria to suggest MVD, which should be indicated on an individual decision.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Hypertension; Image fusion; MRI; Neuroimaging; Neurovascular compression; Ventrolateral medulla

New approaches in the treatment of hypertension - Oparil, Suzanne; Schmieder, Roland (Circulation Research, 2015)
Hypertension is the most common modifiable risk factor for cardiovascular disease and death, and lowering blood pressure with antihypertensive drugs reduces target organ damage and prevents cardiovascular disease outcomes. Despite a plethora of available treatment options, a substantial portion of the hypertensive population has uncontrolled blood pressure. The unmet need of controlling blood pressure in this population may be addressed, in part, by developing new drugs and devices/procedures to treat hypertension and its comorbidities. In this Compendium Review, we discuss new drugs and interventional treatments that are undergoing preclinical or clinical testing for hypertension treatment. New drug classes, eg, inhibitors of vasopeptidases, aldosterone synthase and soluble epoxide hydrolase, agonists of natriuretic peptide A and vasoactive intestinal peptide receptor 2, and a novel mineralocorticoid receptor antagonist are in phase II/III of development, while inhibitors of aminopeptidase A, dopamine ?-hydroxylase, and the intestinal Na(+)/H(+) exchanger 3, agonists of components of the angiotensin-converting enzyme 2/angiotensin(1-7)/Mas receptor axis and vaccines directed toward angiotensin II and its type 1 receptor are in phase I or preclinical development. The two main interventional approaches, transcatheter renal denervation and baroreflex activation therapy, are used in clinical practice for severe treatment resistant hypertension in some countries. Renal denervation is also being evaluated for treatment of various comorbidities, eg, chronic heart failure, cardiac arrhythmias and chronic renal failure. Novel interventional approaches in early development include carotid body ablation and arteriovenous fistula placement. Importantly, none of these novel drug or device treatments has been shown to prevent cardiovascular disease outcomes or death in hypertensive patients.
EVALuna2:3760

New data, new studies, new hopes for renal denervation in patients with uncontrolled hypertension - Papademetriou, Vasilios; Stavropoulos, Konstantinos; Imprialos, Kostas; Doumas, Michael; Schmieder, Roland; Pathak, Atul; Tsioufis, Costas (International Journal of Cardiology: Hypertension, 2019)
Background: following the publication of SYMPLICITY HTN-3 the field of renal of denervation was put on hold. Although SYMPLICITY HTN-3 was well-designed and sham-controlled trial it failed to show any meaningful reduction in office or 24 h ambulatory blood pressure. The procedure was however safe and allowed research to continue. Although several pitfalls of the study have been pointed out, incomplete renal denervation was also implicated. Since then, a great deal of basic and clinical research took place and will be briefly commented on in this article. Methods and results: Before and after SYMPLICITY-HTN-3, numerous uncontrolled, single or unblinded studies have shown substantial office BP reduction ranging from −7.7 to −32 mmHg and ambulatory BP ranging from −2.2 to 10.2 mmHg. Average weighted office systolic BP reduction was −20.8 mmHg and weighted average 24 h ambulatory BPM reduction was −7.8 mmHg. National and international registries have shown similar BP reductions, but results remained unconvincing due to lack of reliable sham controls. In recent years, 5 well-designed sham – controlled studies (beyond, SYMPLICITY-HTN-3) have been published. Of those studies two were single center and three were multicenter international studies. Four studies used single tip or multi-electrode, radiofrequency catheters and one used focused ultrasound. The three multicenter studies reported positive-placebo subtracted results and established BP reductions measured both in the office and by ambulatory monitoring. No serious adverse events were reported. Conclusions: It can therefore be concluded that the latest sham controlled studies established efficacy and safety of renal denervation.
CRIS-Team Scopus Importer:2019-12-27
Keywords: Denervation; Hypertension; Renal artery; Sympathetic nervous system

New software analyses increase the reliability of measurements of retinal arterioles morphology by scanning laser Doppler flowmetry in humans - Harazny, Joanna M.; Raff, Ulrike; Welzenbach, Juergen; Ott, Christian; Ritt, Martin; Lehmann, Maria; Michelson, Georg; Schmieder, Roland; Lehmann, Maria (Journal of Hypertension, 2011)
The investigation of the retinal arterioles offers the unique opportunity to analyze in vivo arteriolar remodeling in arterial hypertension in humans. We analyzed the reliability of assessing retinal arteriolar morphology with our new version of the software analyses for scanning laser Doppler flowmetry.In the test-retest reliability study, 10 eyes of 10 healthy persons were measured during 5 days under routine laboratory conditions with the Heidelberg Retinal Flowmetry. In a second study, interobserver and intraobserver reliability was analyzed from retinal images of 18 patients with three types of arterial hypertension by three readers and the most experienced reader analyzed all images twice on two different days. Images were analyzed by the old and the newly developed software versions. To characterize the reliability, the coefficients of variation were calculated.The test-retest study analyzed with the new program showed that the variation coefficients of vessel and lumen diameter, wall thickness, wall/lumen ratio and new calculated parameter: lumen/vessel diameter ratio of retinal arterioles were significantly less than 10%, with the exception of the wall cross-sectional area (12.5%). The interobserver and intraobserver reliability showed in nearly all circumstances coefficients of variations of less than 10% and did not differ across various readers and patient groups.The new software 'SLDF version 4.0' clearly improved the reliability of assessing the structural parameters of the retinal arterioles. The application delivers reliable measurements of the retinal arteriolar structure in vivo in human
EVALuna2:3487

New strategies to improve clinical outcomes for diabetic kidney disease - Forst, Thomas; Mathieu, Chantal; Giorgino, Francesco; Wheeler, David C.; Papanas, Nikolaos; Schmieder, Roland; Halabi, Atef; Schnell, Oliver; Streckbein, Marina; Tuttle, Katherine R. (BMC Medicine, 2022)
Background: Diabetic kidney disease (DKD), the most common cause of kidney failure and end-stage kidney disease worldwide, will develop in almost half of all people with type 2 diabetes. With the incidence of type 2 diabetes continuing to increase, early detection and management of DKD is of great clinical importance. Main body: This review provides a comprehensive clinical update for DKD in people with type 2 diabetes, with a special focus on new treatment modalities. The traditional strategies for prevention and treatment of DKD, i.e., glycemic control and blood pressure management, have only modest effects on minimizing glomerular filtration rate decline or progression to end-stage kidney disease. While cardiovascular outcome trials of SGLT-2i show a positive effect of SGLT-2i on several kidney disease-related endpoints, the effect of GLP-1 RA on kidney-disease endpoints other than reduced albuminuria remain to be established. Non-steroidal mineralocorticoid receptor antagonists also evoke cardiovascular and kidney protective effects. Conclusion: With these new agents and the promise of additional agents under clinical development, clinicians will be more able to personalize treatment of DKD in patients with type 2 diabetes.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Diabetic kidney disease; Kidney protective agents; Type 2 diabetes

Non-invasive cardiovascular imaging for evaluating subclinical target organ damage in hypertensive patients: A consensus paper from the European Association of Cardiovascular Imaging (EACVI), the European Society of Cardiology Council on Hypertension, and - Perrone-Filardi, Pasquale; Coca, Antonio; Galderisi, Maurizio; Paolillo, Stefania; Alpendurada, Francisco; De Simone, Giovanni; Donal, Erwan; Kahan, Thomas; Mancia, Giuseppe; Redon, Josep; Schmieder, Roland; Williams, Bryan; et al. (European Heart Journal - Cardiovascular Imaging, 2017)
Arterial hypertension (HTN) accounts for the largest amount of attributable cardiovascular (CV) mortality worldwide, and risk stratification in hypertensive patients is of crucial importance to manage treatment and prevent adverse events. Asymptomatic involvement of different organs in patients affected by HTN represents an independent determinant of CV risk and the identification of target organ damage (TOD) is recommended to further reclassify patients' risk. Non-invasive CV imaging is progressively being used and continues to provide new technological opportunities to TOD evaluation at early stage. The aim of this article is to provide the community of cardiology with an update on appropriate and justified use of non-invasive imaging tests in the growing population of hypertensive patients.
EVALuna2:4039

Non-invasive Renal Denervation: Update on External Ultrasound Approaches - Schmieder, Roland; Ott, Christian; Bramlage, Peter (Current Hypertension Reports, 2016)
In the last decade, intravenous renal denervation (RDN) has emerged as an alternative to pharmacological treatment in patients with resistant hypertension, but currently involves an invasive and technically challenging procedure. The Surround Sound(TM) system utilises externally delivered ultrasound to achieve RDN using a completely non-invasive, automated real-time tracking system coupled with a therapeutic delivery module thereby addressing these limitations. A brief history, technical overview and summary of preclinical and clinical studies of the KonaMedical Surround Sound(TM) system are presented. A literature search using the terms "renal denervation", "resistant hypertension" and "external ultrasound" was performed using PubMed, and references retrieved were selected based on relevancy and year of publication (date range 1991-2015). The Surround Sound(TM) system appears to be a promising approach to RDN which eliminates several of the factors currently limiting the intravenous approach. So far, it has demonstrated efficacy for reducing blood pressure in resistant hypertension patients with minimal adverse effects. Several double-blind, sham-controlled clinical trials are currently underway to confirm the validity of these findings.
EVALuna2:3851

Non-steroidal mineralocorticoid receptor antagonism for the treatment of cardiovascular and renal disease - Bramlage, Peter; Swift, Stephanie L.; Thoenes, Martin; Minguet, Joan; Ferrero, Carmen; Schmieder, Roland (European Journal of Heart Failure, 2016)
Pharmaceutical antagonism of the mineralocorticoid receptor (MR) can protect against organ damage caused by elevated aldosterone levels in patients experiencing heart failure (HF), chronic kidney disease (CKD), primary aldosteronism, and hypertension. While traditional steroid-based MR antagonists effectively reduce mortality rates and extend patient survival, their broad application has been limited by significant side effects, most notably hyperkalaemia. Recently, finerenone (BAY 94-8862) has emerged as a next-generation non-steroidal dihydropyridine-based MR antagonist designed to minimize off-target effects while maintaining potent efficacy. In this review, the outcomes of finerenone therapy in several diseases associated with MR activity are explored. The (pre-) clinical efficacy of finerenone is compared with that of traditional steroid-based MR antagonists. Finally, recent and ongoing clinical trials using finerenone to treat chronic HF, CKD, and diabetic nephropathy are discussed. Taken together, pre-clinical and clinical evidence suggests that finerenone may achieve equivalent organ-protective effects with reduced levels of electrolyte disturbance compared with traditional steroid-based MR antagonists. This supports further clinical development of finerenone for the treatment of cardiovascular and renal disease.
EVALuna2:3822

Novel approaches to define responders to interventional treatment in hypertension: insights from the SPYRAL HTN-OFF and HTN-ON MED trials - Schmieder, Roland; Hettrick, Douglas A.; Böhm, Michael; Kandzari, David E.; Kario, Kazuomi; Mahfoud, Felix; Tsioufis, Konstantinos; Weber, Michael A.; Esler, Murray D.; Townsend, Raymond R. (Hypertension Research, 2025)
Multiple sham-controlled clinical trials have demonstrated significant reductions in both office and 24-h blood pressure (BP) following radiofrequency renal denervation (RDN) in the uncontrolled hypertension population. Notably, the blood pressure response varies widely within individual participants, thus showing a clinical need to identify potential RDN “responders” prior to the procedure. Despite multiple analytic efforts, no single parameter, aside from baseline blood pressure, has been consistently associated with BP reduction following RDN. However, this failure may be due to limitations in empiric definitions of responders. Indeed, commonly applied responder definitions based on the difference between two point-in-time BP measurements are fraught due to visit-to-visit variability in office and 24-h blood pressure endpoints. Several factors should be considered to develop a more clinically useful operational definition of procedural response including relative changes in office and 24-h BP, consideration of the temporal response to RDN, as well as adjustment for baseline BP. The current evidence may provide incentives for future expert consensus to precisely define responders to hypertension treatments. (Figure presented.)
CRIS-Team Scopus Importer:2024-11-22
Keywords: Blood pressure variability; Renal denervation; Responders

Novel approaches to management of hypertension - Bosch, Agnes; Schmieder, Roland (Current Opinion in Nephrology and Hypertension, 2021)
Purpose of review Of the roughly 1.4 billion people with hypertension worldwide, only about one in seven has their blood pressure (BP) successfully treated and adequately controlled. This review will focus on new therapeutic approaches of hypertension. Recent findings Several recent clinical studies and guidelines have favoured the assessment of target organ damage and cardiovascular risk scores for the diagnosis and treatment approach of hypertension. Paradigm shifts recommended in the guidelines are the initiation of antihypertensive treatment with combination (not mono) therapy and the recommendation of single-pill combinations (SPC), which improve adherence and result in rapid and effective BP control. In clinical trials with optimized design and renal denervation (RDN) technology, the biological proof of concept has been established. Consistent, durable ambulatory and office BP reductions without procedure associated serious adverse events have been documented. The challenges are now to identify patients who respond best to interventional treatment. Major key points in the treatment strategy for hypertension are: individualization of the therapy according to total cardiovascular risk, combination therapy as initial step, recommendation of SPC and RDN as promising interventional therapy.
CRIS-Team WoS Importer:2021-01-15

NT-proBNP and stem cell factor plasma concentrations are independently associated with cardiovascular outcomes in end-stage renal disease hemodialysis patients. - Rossignol, P.; Duarte, K.; Bresso, E.; Åsberg, A.; Devignes, M. D.; Eriksson, N.; Girerd, N.; Glerup, R.; Jardine, A. G.; Holdaas, H.; Lamiral, Z.; Leroy, C.; et al. (European Heart Journal Open, 2022)
AIMS: End-stage renal disease (ESRD) treated by chronic hemodialysis (HD) is associated with poor cardiovascular (CV) outcomes, with no available evidence-based therapeutics. A multiplexed proteomic approach may identify new pathophysiological pathways associated with CV outcomes, potentially actionable for precision medicine. METHODS AND RESULTS: The AURORA trial was an international, multicentre, randomized, double-blind trial involving 2776 patients undergoing maintenance HD. Rosuvastatin vs. placebo had no significant effect on the composite primary endpoint of death from CV causes, nonfatal myocardial infarction or nonfatal stroke. We first compared CV risk-matched cases and controls (n = 410) to identify novel biomarkers using a multiplex proximity extension immunoassay (276 proteomic biomarkers assessed with OlinkTM). We replicated our findings in 200 unmatched cases and 200 controls. External validation was conducted from a multicentre real-life Danish cohort [Aarhus-Aalborg (AA), n = 331 patients] in which 92 OlinkTM biomarkers were assessed. In AURORA, only N-terminal pro-brain natriuretic peptide (NT-proBNP, positive association) and stem cell factor (SCF) (negative association) were found consistently associated with the trial's primary outcome across exploration and replication phases, independently from the baseline characteristics. Stem cell factor displayed a lower added predictive ability compared with NT-ProBNP. In the AA cohort, in multivariable analyses, BNP was found significantly associated with major CV events, while higher SCF was associated with less frequent CV deaths. CONCLUSIONS: Our findings suggest that NT-proBNP and SCF may help identify ESRD patients with respectively high and low CV risk, beyond classical clinical predictors and also point at novel pathways for prevention and treatment.
EVALuna2:555781

Olmesartan improves pulse wave velocity and lowers central systolic blood pressure and ambulatory blood pressure in patients with metabolic syndrome - Raff, Ulrike; Walker, Stefanie Elke; Ott, Christian; Schneider, Markus P.; Schmieder, Roland (Journal of Clinical Hypertension, 2015)
Ambulatory blood pressure (BP) and central systolic BP (cSBP) are superior to brachial office BP measurements in predicting cardiovascular end organ damage. The authors aimed to analyze the effect of olmesartan 80 mg (OLM 80) vs 20 mg (OLM 20) vs amlodipine 5 mg (AML 5) on central hemodymamics and ambulatory BP in patients with metabolic syndrome (MetS).In a double-blind, three-phase crossover study comprising 69 untreated patients with MetS defined by the Third Report of the Expert Panel on Detection, Evaluation, and Treatment of High Blood Cholesterol in Adults guidelines, the effects of OLM 80 on central hemodynamics (cSBP), central pulse pressure), pulse wave velocity (PWV), and 24-hour ambulatory BP were compared with OLM 20 and AML 5, given for 6 weeks each. In 69 patients (47 men, 22 women) (51.5±9.75 years), reduction in cSBP was the highest with OLM 80 and significantly greater than the reduction with AML 5 (-14.1 mm Hg vs -9.7 mm Hg, P=.0117). All three substances significantly reduced 24-hour ambulatory systolic (OLM 80 and OLM 20 P<.0001; AML 5 P=.0105). BP and 24-hour diastolic BP (OLM 80 and OLM 20 P<.0001; AML 5 P=.0126). PWV was significantly reduced by OLM 80 (-0.58 m/s, P=.0088) and by OLM 20 (-0.48 m/s, P=.0362) but not by AML 5 (-0.28 m/s, P=.2065). For PWV, no significant differences were detected between the three groups. OLM significantly improves arterial stiffness as demonstrated by the reduction in PWV and in cSBP. In addition, 24-hour ambulatory BP was reduced to a greater extent with OLM 80 than with AML 5.
EVALuna2:3748

OS 12-03 SGLT-2-INHIBITION WITH DAPAGLIFLOZIN REDUCES TISSUE SODIUM CONTENT - Schmieder, Roland; Ott, Christian; Linz, Peter; Jumar, Agnes; Friedrich, Stefanie; Titze, Jens; Hammon, Matthias; Uder, Michael; Kistner, Iris (Journal of Hypertension, 2016)
Sodium tissue content by Na magnetic resonance imaging (Na-MRI) has been validated in experimental and human studies. SGLT-2 inhibition blocks the reabsorption of glucose and, in parallel, of sodium in the proximal tubular cells in a 1:1 fashion. We hypothesized that SGLT-2 inhibition in patients with type 2 diabetes leads to decreased tissue sodium content due to its pharmacological action.In a prospective, double blind, placebo controlled, cross-over trial 59 patients (61 ± 7.6 years) with type 2 diabetes were randomized to dapagliflozin 10 mg o.d. and placebo for 6 weeks each. In addition to metabolic parameters and ambulatory blood pressure (BP) we analyzed the sodium content in the skin and muscles of the lower leg by the Na-MRI at baseline, after the first and second treatment phase of 6 weeks.Compared to baseline 6 weeks treatment with the SGLT-2 inhibitor dapagliflozin decreased fasting (132 ± 28 vs. 114 ± 19 mg/dl, p < 0.001), postprandial blood glucose (178 ± 66 mg/dl vs. 153 ± 46 mg/dl, p < 0.001), body weight (87.6 vs. 86.6 kg, p < 0.001) and systolic (129 ± 12 vs. 126 ± 11, p = 0.010) and diastolic (77.4 ± 9 vs. 75.6 ± 8 mmHg, p = 0.024) 24-hour ambulatory BP. Tissue sodium content in the skin was reduced after 6 weeks treatment with dapagliflozin compared to baseline (24.1 ± 6.6 vs.22.7 ± 6.4 mmol/L; p = 0.013). No significant reduction of tissue sodium content was observed in the muscle (M. triceps surae: 20.5 ± 3.5 vs. 20.4 ± 3.7 mmol/L, p = 0.801). No clear significant difference in tissue water content of muscle and skin was observed after 6 weeks of treatment with dapagliflozin, compared to baseline.SGLT-2 inhibition with dapagliflozin resulted in a significant decrease in sodium tissue content of the skin after 6 weeks. This observation point to a decrease of total sodium content in patients with type 2 diabetes known to be salt sensitive and prone to cardiovascular complications, that might be mitigated by SGLT-2 inhibition.
EVALuna2:14604

OS 28-03 SECRETORY CAPACITY OF PANCREATIC BETA CELLS IS ENHANCED 6 MONTHS AFTER RENAL DENERVATION IN TREATMENT RESISTANT HYPERTENSIVE PATIENTS - Ott, Christian; Kistner, Iris; Schmid, Axel; Friedrich, Stefanie; Ditting, Tilmann; Veelken, Roland; Mahfoud, Felix; Boehm, Michael; Uder, Michael; Schmieder, Roland (Journal of Hypertension, 2016)
Renal denervation (RDN) lowers blood pressure (BP) by interruption of sympathetic nerve activity. A high sympathetic tone increases not only BP but also decreases pancreatic beta cell insulin secretion. Hence, the objective of the study was to analyze whether RDN improves secretory capacity of beta cells.In 40 patients (7 diabetics, 19 prediabetics, 14 non diabetics) with treatment resistant hypertension (defined by office BP >= 140/90 mmHg and diagnosis confirmed with 24-h ambulatory BP >= 130/80 mmHg), insulin secretion was measured before and 6 months after RDN (Simplicity flex catheter, Medtronic) by glucagon test. At each time point blood was sampled prior to glucagon administration and 6 minutes after intravenous injection of 1 ml glucagon for measurement of C-peptide, insulin and proinsulin (by ELISA).In these 40 patients (mean age 58 ± 12 years, mean office BP 154 ± 22 mmHg / 89 ± 14 mmHg while on 5.2 ± 1.4 antihypertensive drugs) office systolic and diastolic BP was significantly reduced 6 months after RDN (both p < 0.01). Fasting plasma glucose and HbA1c level was significantly reduced 6 month after RDN (both p < 0.01). Six months after RDN, the increase of C-peptide concentration and insulin concentration after glucagon injection was significantly higher compared to before RDN (both p < 0.05).Thus, our data indicate an improved pancreatic beta cell function after RDN in patients with treatment resistant hypertension.
EVALuna2:14605

Outcomes Following Radiofrequency Renal Denervation According to Antihypertensive Medications: Subgroup Analysis of the Global SYMPLICITY Registry DEFINE - Mahfoud, Felix; Mancia, Giuseppe; Schmieder, Roland; Ruilope, Luis; Narkiewicz, Krzysztof; Schlaich, Markus; Williams, Bryan; Ribichini, Flavio; Weil, Joachim; Almerri, Khaled; Sharif, Faisal; Lauder, Lucas; et al. (Hypertension, 2023)
BACKGROUND: The Global SYMPLICITY Registry DEFINE (Denervation Findings in Real World) investigates radiofrequency renal denervation (RDN) in a broad range of patients with hypertension. We evaluated whether the number or type of antihypertensive medications were associated with increased long-term blood pressure (BP) reductions and cardiovascular outcomes following radiofrequency RDN. METHODS: Patients underwent radiofrequency RDN and were categorized by baseline number (0-3 and ≥4) and different combinations of medication classes. BP changes were compared between groups through 36 months. Individual and composite major adverse cardiovascular events were analyzed. RESULTS: Of 2746 evaluable patients, 18% were prescribed 0 to 3 and 82% prescribed ≥4 classes. At 36 months, office systolic BP significantly decreased (P<0.0001) by -19.0±28.3 and -16.2±28.6 mm Hg in the 0 to 3 and ≥4 class groups, respectively. Twenty-four-hour mean systolic BP significantly decreased (P<0.0001) by -10.7±19.7 and -8.9±20.5 mm Hg, respectively. BP reduction was similar between the medication subgroups. Antihypertensive medication classes decreased from 4.6±1.4 to 4.3±1.5 (P<0.0001). Most decreased (31%) or had no changes (47%) to the number of medications, while 22% increased. The number of baseline antihypertensive medication classes was inversely related to the change in prescribed classes at 36 months (P<0.001). Cardiovascular event rates were generally low. More patients in the ≥4 compared with 0 to 3 medication classes had myocardial infarction at 36 months (2.8% versus 0.3%; P=0.009). CONCLUSIONS: Radiofrequency RDN reduced BP safely through 36 months, independent of the number and type of baseline antihypertensive medication classes. More patients decreased than increased their number of medications. Radiofrequency RDN is a safe and effective adjunctive therapy regardless of antihypertensive medication regimen. REGISTRATION: URL: https://www. CLINICALTRIALS: gov; Unique identifier: NCT01534299.
CRIS-Team Scopus Importer:2023-08-04
Keywords: humans; hypertension; myocardial infarction; risk reduction behavior; stroke

Oxidized LDL, statin use, morbidity, and mortality in patients receiving maintenance hemodialysis - Wagner, Sandra; Apetrii, Mugurel; Massy, Ziad A.; Kleber, Marcus E.; Delgado, Graciela E.; Scharnagel, Hubert; Maerz, Winfried; Metzger, Marie; Rossignol, Patrick; Jardine, Alan; Holdaas, Hallvard; Fellstroem, Bengt; et al. (Free Radical Research, 2017)
Statin treatment reduces the risk of cardiovascular mortality in the general population, but it has little or no benefit in hemodialyzed (HD) patients. This may reflect different underlying pathophysiology of cardiovascular disease (CVD) in patients treated with HD, maybe involving the oxidative stress. Our aim was to assess the association of oxidized low-density lipoprotein (oxLDL), determined by Mercodia oxLDL enzyme-linked immunosorbent assay (ELISA) kit, with major adverse cardiac events (MACE) and all-cause mortality in HD patients based on the AURORA trial (rosuvastatin vs placebo), and patients not on HD from the Ludwigshafen Risk and Cardiovascular Health (LURIC) study. We also assessed whether its decrease due to statin use improves these outcomes using Cox proportional hazard models. Baseline oxLDL level was 34.2 ± 13.8 U/L in AURORA and did not differ between treatment groups, and 74.6 ± 28.1 U/L in LURIC. Lower baseline oxLDL levels were associated with higher hazard ratios (HRs) for outcomes, but not anymore after adjusting for apolipoprotein B level in AURORA and was not related to mortality in LURIC. OxLDL levels decreased by 30.9% between baseline and 3 months in the statin-treated group and increased by 10.5% between 3 and 12 months. Nevertheless, oxLDL reduction was not significantly associated with adjusted HRs for MACE and for all-cause mortality. These results showed no association between oxLDL and MACE after adjustment on apolipoprotein B, which may relate to the properties of the method used for oxLDL. Our results also showed no benefit for oxLDL reduction by rosuvastatin on outcomes. Future clinical trials are needed to define the relative CVD risks and benefits of other modalities of oxidative stress modification in this population.
EVALuna2:4040

Patient-Level Pooled Analysis of Endovascular Ultrasound Renal Denervation or a Sham Procedure 6 Months After Medication Escalation: The RADIANCE Clinical Trial Program - Azizi, Michel; Sharp, Andrew S.P.; Fisher, Naomi D.L.; Weber, Michael A.; Lobo, Melvin D.; Daemen, Joost; Lurz, Philipp; Mahfoud, Felix; Schmieder, Roland; Basile, Jan; Bloch, Michael J.; Saxena, Manish; et al. (Circulation, 2024)
BACKGROUND: The randomized, sham-controlled RADIANCE-HTN (A Study of the Recor Medical Paradise System in Clinical Hypertension) SOLO, RADIANCE-HTN TRIO, and RADIANCE II (A Study of the Recor Medical Paradise System in Stage II Hypertension) trials independently met their primary end point of a greater reduction in daytime ambulatory systolic blood pressure (SBP) 2 months after ultrasound renal denervation (uRDN) in patients with hypertension. To characterize the longer-term effectiveness and safety of uRDN versus sham at 6 months, after the blinded addition of antihypertensive treatments (AHTs), we pooled individual patient data across these 3 similarly designed trials. METHODS: Patients with mild to moderate hypertension who were not on AHT or with hypertension resistant to a standardized combination triple AHT were randomized to uRDN (n=293) versus sham (n=213); they were to remain off of added AHT throughout 2 months of follow-up unless specified blood pressure (BP) criteria were exceeded. In each trial, if monthly home BP was ≥135/85 mm Hg from 2 to 5 months, standardized AHT was sequentially added to target home BP <135/85 mm Hg under blinding to initial treatment assignment. Six-month outcomes included baseline- and AHT-adjusted change in daytime ambulatory, home, and office SBP; change in AHT; and safety. Linear mixed regression models using all BP measurements and change in AHT from baseline through 6 months were used. RESULTS: Patients (70% men) were 54.1±9.3 years of age with a baseline daytime ambulatory/home/office SBP of 150.5±9.8/151.0±12.4/155.5±14.4 mm Hg, respectively. From 2 to 6 months, BP decreased in both groups with AHT titration, but fewer uRDN patients were prescribed AHT (P=0.004), and fewer additional AHT were prescribed to uRDN patients versus sham patients (P=0.001). Whereas the unadjusted between-group difference in daytime ambulatory SBP was similar at 6 months, the baseline and medication-adjusted between-group difference at 6 months was -3.0 mm Hg (95% CI, -5.7, -0.2; P=0.033), in favor of uRDN+AHT. For home and office SBP, the adjusted between-group differences in favor of uRDN+AHT over 6 months were -5.4 mm Hg (.6.8, -4.0; P<0.001) and -5.2 mm Hg (.7.1, -3.3; P<0.001), respectively. There was no heterogeneity between trials. Safety outcomes were few and did not differ between groups. CONCLUSIONS: This individual patient-data analysis of 506 patients included in the RADIANCE trials demonstrates the maintenance of BP-lowering efficacy of uRDN versus sham at 6 months, with fewer added AHTs.
CRIS-Team Scopus Importer:2024-03-15
Keywords: ablation; catheter; antihypertensive drugs; blood pressure; denervation; hypertension; hypertension; renal

Patient preference for therapies in hypertension: a cross-sectional survey of German patients - Schmieder, Roland; Högerl, Karin; Jung, Susan; Bramlage, Peter; Veelken, Roland; Ott, Christian (Clinical Research in Cardiology, 2019)
BACKGROUND: Hypertension is poorly controlled in numerous patients despite effective medication being available. Catheter-based renal denervation (RDN) has emerged as an alternative treatment option. We aimed to assess how likely patients with elevated blood pressure (BP) are to accept RDN as treatment option. METHODS: A questionnaire-based cross-sectional survey was performed in patients with elevated BP in Germany. Data on patient demographics, clinical characteristics and treatment preferences were collected, anonymized and analyzed. RESULTS: One thousand and eleven patients completed the survey. Mean age was 66 years (55% male). If not already on medication (n = 172), 38.2% of patients would prefer RDN. Of those already on drug therapy (n = 839), 28.2% would opt for RDN. Patients who were pro-RDN were younger (p < 0.0001) and more often male (p < 0.0001). Nineteen percent would choose RDN if it lowered systolic BP by at least 20 mmHg, more than 40% if they did not have to take any more pills thereafter, and 30% if it would lower BP by at least 10 mmHg. Experiences of side effects and drug adherence were identified as determinants of patient preference. Physicians were the main source of information regarding medical problems (95.5%) and influence patients' decision regarding therapies (98%). CONCLUSIONS: This survey found that a significant proportion of patients would choose catheter-based RDN over lifelong pharmacotherapy. These patients were younger and more likely to be male but their expectation of the extent of BP decrease with RDN was high. Physicians are key mediators for treatment selection. They need to incorporate patient preferences into shared decision making.
EVALuna2:118640

Patients With Newly Diagnosed Hypertension Treated With the Renin Angiotensin Receptor Blocker Azilsartan Medoxomil vs Angiotensin-Converting Enzyme Inhibitors: The Prospective EARLY Registry - Schmieder, Roland; Potthoff, Sebastian A; Bramlage, Peter; Baumgart, Peter; Mahfoud, Felix; Buhck, Hartmut; Ouarrak, Taoufik; Ehmen, Martina; Senges, Jochen; Gitt, Anselm K; EARLY Registry Group (Journal of Clinical Hypertension, 2015)
For patients with newly diagnosed hypertension, angiotensin-converting enzyme (ACE) inhibitors or angiotensin receptor blockers (ARBs) are usually the first-line therapies. There is, however, no real-life data regarding the relative clinical effectiveness and tolerability of either drug class. The prospective registry, Treatment With Azilsartan Compared to ACE Inhibitors in Antihypertensive Therapy (EARLY), was conducted to evaluate the effectiveness of the ARB azilsartan medoxomil (AZL-M) vs ACE inhibitors in real-world patients. Of the 1153 patients with newly diagnosed hypertension who were included in the registry, 789 were prescribed AZL-M and 364 were prescribed an ACE inhibitor. After multivariate adjustment, AZL-M was found to provide superior blood pressure reduction and better target blood pressure (<140/90 mm Hg) achievement. The proportion of patients with adverse events was not statistically different between groups. The authors conclude that in newly diagnosed hypertensive patients, AZL-M provides superior blood pressure control with a similar safety profile compared with ACE inhibitors.
EVALuna2:3815

Patients With Resistant Hypertension in the Global SYMPLICITY Registry: Antihypertensive Medication Burden and Changes in Blood Pressure out to 3 Years - Schlaich, Markus; Boehm, Michael; Mancia, Giuseppe; Schmieder, Roland; Narkiewicz, Krzysztof; Ruilope, Luis; Williams, Bryan; Shen, Cheryl; Mahfoud, Felix (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2020)
CRIS-Team WoS Importer:2020-12-25

PCSK-9-inhibitor therapy improves endothelial function in high-risk patients with cardiovascular disease - Kannenkeril, Dennis; Bosch, Agnes; Kolwelter, Julie; Striepe, Kristina; Pietschner, Robert; Ott, Christian; Schiffer, Mario; Achenbach, Susanne; Schmieder, Roland (EUROPEAN HEART JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

PCSK-9-inhibitor therapy improves endothelial function in high-risk patients with cardiovascular disease - Kannenkeril, Dennis; Bosch, Agnes; Kolwelter, Julie; Striepe, Kristina; Berner, Laura; Pietschner, Robert; Ott, Christian; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (Clinical Research in Cardiology, 2024)
Background: Impaired endothelial function predicts cardiovascular events. The aim of this study was to analyze the effect of evolocumab on endothelial function in patients with cardiovascular disease. Methods: This was a prospective, double-blinded, randomized, controlled, single center study including patients with cardiovascular disease and treated with statins. Patients were consecutively randomized (1:1) to either evolocumab treatment or placebo. All patients underwent examination of endothelial function at baseline, and after 1, 4 and 8 weeks of treatment by a semi-automatic high-resolution ultrasound system (UNEX EF 18G). Parameters of endothelial function were flow-mediated vasodilation (FMD), low flow-mediated vasoconstriction (L-FMC) and vasoactive range (VAR). Results: Hundred three patients with a mean age of 66.2 ± 7.7 years and a mean LDL-cholesterol of 98 ± 19.1 mg/dl completed the study. The change in VAR from baseline to week 8 was significantly different with evolocumab compared to placebo (p = 0.045). Moreover, VAR increased after 8 weeks of treatment with evolocumab compared to baseline (p = 0.034). No change has been noticed in FMD and L-FMC after 8 weeks of treatment with evolocumab. In subgroup analyses, VAR improved in patients with age ≤ 67 years, lower systolic blood pressure (≤ 125 mmHg) and higher baseline LDL-cholesterol (> 95 mg/dl), (p = 0.006, p = 0.049 and p = 0.042, respectively) after 8 weeks of evolocumab treatment. No serious adverse event related to study medication occurred during the study. Conclusion: Our data indicate that endothelial function improved with evolocumab treatment in high-risk patients on statin therapy with preexisting cardiovascular disease. Our results contribute to the mechanistic explanation why lower incidence of the cardiovascular composite endpoint has been demonstrated in the FOURIER study. Graphical abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-11-29
Keywords: Endothelial function; Evolocumab; Flow-mediated vasodilation; PCSK-9 inhibitor; Vasoactive range

Percutaneous Creation of a Central Iliac Arteriovenous Anastomosis for the Treatment of Arterial Hypertension - Bertog, S. C.; Sobotka, Nathan A.; Sobotka, P. A.; Lobo, M. D.; Sievert, K.; Vaskelyte, L.; Sievert, H.; Schmieder, Roland (Current Hypertension Reports, 2018)
PURPOSE OF REVIEW: Provision of a summary on the physiologic effects of arteriovenous fistula creation and description of previously published human data on the efficacy of a percutaneously implanted device creating an arteriovenous fistula. Though antihypertensive therapy is effective, some patient's blood pressure remains poorly controlled despite adherence to optimal medical therapy. Moreover, some patients are not compliant with recommended medical therapy due to side effects or personal decision. This has prompted exploration of alternative, device-based antihypertensive therapies including, among others, the percutaneous creation of an arteriovenous fistula. An arteriovenous fistula is accompanied by a number of favorable physiologic changes that may lower blood pressure. These physiologic changes, conduction of the procedure, and previously published human experience are summarized in this review article. RECENT FINDINGS: The results of a recently published trial comparing arteriovenous fistula creation and standard antihypertensive therapy versus standard antihypertensive therapy alone are summarized. Creation of an arteriovenous fistula is accompanied by a significant blood pressure reduction likely related to a reduction in total arterial resistance, perhaps blood volume reduction, inhibition of the baroreceptor reflex, and release of natriuretic peptides. These findings foster further interest in studying the impact of an arteriovenous fistula and arterial blood pressure. The design of a large randomized trial comparing arteriovenous fistula creation to sham control is outlined.
EVALuna2:34238

Persistence and cardiovascular outcomes with ramipril, atorvastatin, ASA as a single pill compared to the multi pill combination. A subanalysis of the START study, a claims data analysis - Predel, H. G.; Weisser, B.; Wassmann, S.; Schmieder, Roland; Blettenberg, J.; Gillessen, A.; Fournier; Noetel, A.; Randerath, O.; Boehm, M. (EUROPEAN HEART JOURNAL, 2020)
CRIS-Team WoS Importer:2021-02-12

Phase II randomized sham-controlled study of renal denervation for individuals with uncontrolled hypertension - WAVE IV - Schmieder, Roland; Ott, Christian; Toennes, Stefan W.; Bramlage, Peter; Gertner, Michael; Dawood, Omar; Baumgart, Peter; O'Brien, Benjamin; Dasgupta, Indranil; Nickenig, Georg; Ormiston, John; Saxena, Manish; et al. (Journal of Hypertension, 2017)
The aim of this double-blind, randomized, sham-controlled study was to verify the blood pressure (BP)-lowering efficacy of externally delivered focused ultrasound for renal denervation (RDN).Nonrandomized, first proof-of-concept study and experimental evidence suggested that noninvasive techniques of RDN emerged as an alternative approach of RDN to invasive technologies.WAVE IV, an international, randomized (1 : 1) sham-controlled, double-blind prospective clinical study, was prematurely stopped. Patients were enrolled if office BP was at least 160 mmHg and 24-h ambulatory BP was at least 135 mmHg, while taking three or more antihypertensive medications. The treatment consisted of bilateral RDN using therapeutic levels of ultrasound energy and the sham consisted of bilateral application of diagnostic levels of ultrasound energy.In the 81 treated patients neither changes in office BP at 12 and 24 weeks, nor changes in 24-h ambulatory BP at 24-week follow-up visit differed between the two groups significantly. Of note, no safety signal was observed. Adherence analysis disclosed full adherence in 77% at baseline and 82% at 6 months' follow-up visit. Post hoc analysis revealed that stricter criteria for stabilization of BP at baseline were associated with a numerically greater change in 24-h ambulatory BP in the RDN group than in the sham group.Our data did not prove that antihypertensive efficacy of the externally delivered focused ultrasound for RDN was greater than the sham effect. Stabilization of BP at baseline was identified as an important determinant of BP changes.
EVALuna2:4028

Physician Preferences for Recommending Renal Denervation to Hypertensive Patients Is Influenced by Patients' Antihypertensive Medication Nonadherence Due to Medication Side Effects - Wang, Tzung-Dau; Schmieder, Roland; Kandzari, David E.; Lee, Ying-Hsiang; Haro, Carlos F.; Pathak, Atul (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2022)
CRIS-Team WoS Importer:2022-05-13

Plasma renin and aldosterone concentrations related to endovascular ultrasound renal denervation in the RADIANCE-HTN SOLO trial - Fisher, Naomi D.L.; Kirtane, Ajay J.; Daemen, Joost; Rader, Florian; Lobo, Melvin D.; Saxena, Manish; Abraham, Josephine; Schmieder, Roland; Sharp, Andrew S.P.; Gosse, Philippe; Claude, Lisa; Song, Yang; et al. (Journal of Hypertension, 2022)
Objective: The RADIANCE-HTN SOLO trial demonstrated a greater reduction in daytime ambulatory SBP at 2 months by endovascular ultrasound renal denervation than sham procedure. We hypothesized that plasma renin and aldosterone concentrations would be associated with the SBP response to renal denervation. Methods: Hypertensive patients were randomized to renal denervation (n=74) or sham (n=72) after a 4-week washout of antihypertensive medications. In a 53-patient subset, 2-month and 6-month plasma renin and aldosterone concentration were measured. Dietary sodium was not controlled. Results: Mean age of the 29 treatment and 24 sham patients was 54years; 62% were men; 17% black. Daytime ambulatory SBP fell in the denervation but not the sham group at 2 months (-7.8=10.7 vs. -0.1=10.1mmHg; P=0.048). Baseline plasma renin and aldosterone concentrations were in the low-normal range, did not change significantly at 2 months in either group and did not predict response to renal denervation. At 6 months, after the addition of antihypertensive medications, there was a significant rise in renin in the sham but not the denervation group. Conclusion: Although renal denervation but not sham resulted in a decrease in daytime ambulatory SBP at 2 months, renin and aldosterone concentrations did neither predict the BP response to renal denervation; nor did they fall after denervation. A rise in renin at 6 months in the sham group likely represents confounding from antihypertensive medications. Whether the BP-lowering effect of renal denervation depends on reducing local intrarenal renin release requires further study.
CRIS-Team Scopus Importer:2022-02-04
Keywords: Aldosterone; Hypertension; Renal denervation; Renin

Platelet CD40 contributes to enhanced monocyte chemoattractant protein 1 levels in patients with resistant hypertension - Stumpf, Christian; Raaz, Dorette; Klinghammer, Lutz; Schneider, Markus; Schmieder, Roland; Garlichs, Christoph D.; Achenbach, Stephan (European Journal of Clinical Investigation, 2016)
Growing evidence shows that inflammation plays a pivotal role in the pathophysiology of essential hypertension (EH). Although it is acknowledged that target organ damage involves an inflammatory response, most work has focused on the role of macrophages. However, recently, platelets were identified as inducing inflammation partly by releasing cytokines. The goal of our study was to evaluate the role of platelets as inflammatory cells in the pathogenesis of EH.Thirty-nine patients with EH and 30 healthy normotensive controls have been examined. Expression of platelet CD40 was measured by flow cytometry. Serum levels of monocyte chemoattractant protein 1 (MCP-1) and sCD40L were measured via a multiplexing assay. In in vitro experiments, activated platelets were cocultured with human umbilical vein endothelial cells (HUVEC) in the presence and absence of anti-CD154 antibodies. MCP-1 in the supernatants was measured by EIA.Essential hypertension patients showed significantly enhanced MCP-1 levels with highest levels in EH patients with microalbuminuria. EH patients showed increased expression of platelet CD40. In the cell coculture model, activated platelets were able to significantly induce MCP-1 release from HUVEC in a CD40L-dependent manner. EH patients showed elevated sCD40L levels with a positive correlation with MCP-1 levels.Platelets can contribute to enhanced MCP-1 levels in EH. MCP-1 is markedly elevated in serum of EH patients with highest levels in patients with microalbuminuria, one early sign of renal target organ damage. Further studies are required to test whether MCP-1 blocking or antiplatelet strategies may represent new therapeutic options in preventing hypertensive target organ damage.
EVALuna2:3852

Pleiotropic effects under combined therapy with empagliflozin and linagliptin compared to metformin and insulin glargine in patients with type 2 diabetes - Jung, Susan; Ott, Christian; Kannenkeril, Dennis; Bosch, Agnes; Karg, M.; Striepe, Kristina; Bramlage, P.; Schmieder, Roland (DIABETOLOGIA, 2019)
CRIS-Team WoS Importer:2019-10-11

Predicting blood pressure response to renal denervation based on a new approach - Bytyqi, Venera; Kannenkeril, Dennis; Striepe, Kristina; Bosch, Agnes; Karg, Marina V.; Schmid, Axel; Schiffer, Mario; Uder, Michael; Schmieder, Roland (Journal of Hypertension, 2024)
Background: Identifying predictors of blood pressure (BP) response to renal denervation (RDN) is crucial for patient selection. According to Wilder's principle, baseline BP predicts BP change after any antihypertensive intervention. Thus, any observed BP change after RDN is the sum of the BP change depending on the baseline BP and the specific BP reduction due to RDN. Based on this concept, we propose a new definition of BP responders. Methods: In our center, 148 patients with uncontrolled hypertension underwent RDN, and 24-h ambulatory BP (ABP) was measured at baseline, and 6 months after the procedure. The decrease in 24-h systolic BP (SBP) correlated with baseline SBP (P = <0.001, r = -0.374). We determined the RDN-specific effect by subtracting the predicted SBP decrease from the observed SBP decrease. The cohort was divided into RDN responders, neutral responders, and nonresponders. Results: Our study population had a mean age of 59 ± 10.4 years and was 74% male. The RDN-specific (residual) 24-h ABP decreased by -14.9 ± 6.3/-8.2 ± 3.8 mmHg (responder group), 1.0 ± 3.2/0.2 ± 1.9 mmHg (neutral group), and 14.2 ± 10.4/8.3 ± 3.9 mmHg (nonresponder group) 6 months after RDN. Responders had fewer antihypertensive medications (P = 0.018), higher baseline office heart rate (HR) (P = 0.019), higher 24-h ambulatory HR (P = 0.003), lower BMI (P < 0.038), and absence of type 2 diabetes (T2D) (P = 0.020). Conclusion: Our definition of BP responders to RDN separates baseline BP-related changes from RDN-specific changes. Positive predictors for BP response to RDN include low BMI, fewer antihypertensive medications, high baseline office HR, high 24-h ambulatory HR, and absence of T2D.
CRIS-Team Scopus Importer:2024-11-29
Keywords: clinical predictors; renal denervation; renal denervation responders

Predictors of blood pressure response after renal denervation beyond pretreatment blood pressure - Schmieder, Roland; Delles, C.; Lauder, L.; Ott, Christian; Boehm, M.; Mahfoud, F. (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Predictors of blood pressure response to ultrasound renal denervation in the RADIANCE-HTN SOLO study - Saxena, Manish; Schmieder, Roland; Kirtane, Ajay J.; Mahfoud, Felix; Daemen, Joost; Basile, Jan; Lurz, Philipp; Gosse, Philippe; Sanghvi, Kintur; Fisher, Naomi D. L.; Rump, Lars C.; Pathak, Atul; et al. (Journal of Human Hypertension, 2021)
The blood pressure (BP) lowering response to renal denervation (RDN) remains variable with about one-third of patients not responding to ultrasound or radiofrequency RDN. Identification of predictors of the BP response to RDN is needed to optimize patient selection for this therapy. This is a post-hoc analysis of the RADIANCE-HTN SOLO study. BP response to RDN was measured by the change in daytime ambulatory systolic blood pressure (dASBP) at 2 months post procedure. Univariate regression was used initially to assess potential predictors of outcome followed by multivariate regression analysis. In the univariate analysis, predictors of response to RDN were higher baseline daytime ambulatory diastolic blood pressure (dADBP), the use of antihypertensive medications at screening, and presence of orthostatic hypertension (OHTN) whilst the presence of untreated accessory arteries was a negative predictor of response. Multivariate analysis determined that dADBP and use of antihypertensive medications were predictors of response to RDN with a trend for OHTN to predict response. Obese females also appeared to be better responders to RDN in an interaction model. RDN is more effective in patients with elevated baseline dADBP and those with OHTN, suggesting increased peripheral vascular resistance secondary to heightened sympathetic tone. These assessments are easy to perform in clinical setting and may help in phenotyping patients who will respond better to RDN.
CRIS-Team Scopus Importer:2021-06-04

Prevention of electrocardiographic left ventricular remodeling by the angiotensin receptor blocker olmesartan in patients with type 2 diabetes - Raff, Ulrike; Ott, Christian; Ruilope, Luis M.; Menne, Jan; Haller, Hermann; Schmieder, Roland (Journal of Hypertension, 2014)
To assess the ability of olmesartan (OLM) to prevent or delay left ventricular remodeling and hypertrophy in patients with type 2 diabetes.This prespecified ECG substudy of Randomised OlmesArtan and Diabetes MicroAlbuminuria Prevention (ROADMAP), which compared OLM with placebo, assessed the signs of left ventricular remodeling in patients with a 12-lead ECG at baseline and after at least 2 years. Cornell voltage QRS duration product (primary objective), Cornell voltage index and Sokolow-Lyon index were assessed.In total, 9418 ECG recordings and 1513 patients from ROADMAP were analyzed (placebo, n = 736; OLM, n = 777). Quartiles defined by baseline Cornell voltage QRS duration product were assessed and the proportion of patients in the highest quartile (>=200 mVms) increased from 24.0 to 26.5% in the placebo group and decreased from 25.5 to 22.3% in the OLM group [odds ratio (OR) 0.598 (95% confidence interval [CI] 0.440-0.813); P = 0.0011]. The OR did not change after adjustment for baseline parameters. By the end of study, 38.7% of patients in the placebo group and 34.7% in the OLM group shifted from a lower to a higher quartile or remained in the highest quartile of Cornell voltage QRS duration product [OR 0.797 (95% CI 0.637-0.996); P = 0.0465]. This translated into a 20.3% risk reduction with OLM and suggested OLM attenuated the progression of left ventricular remodeling versus placebo.OLM substantially delayed the development of left ventricular remodeling in type 2 diabetes. This effect was not explained by the differences in blood pressure control. Thus, OLM delayed the onset of microalbuminuria, as well as the ECG signs of cardiac structural adaptation in type 2 diabetes.
EVALuna2:3738

Proceedings from the 2nd European Clinical Consensus Conference for device-based therapies for hypertension: state of the art and considerations for the future - Mahfoud, Felix; Schmieder, Roland; Azizi, Michel; Pathak, Atul; Sievert, Horst; Tsioufis, Costas; Zeller, Thomas; Bertog, Stefan; Blankestijn, Peter J.; Boehm, Michael; Burnier, Michel; Chatellier, Gilles; et al. (European Heart Journal, 2017)
EVALuna2:3951

Proceedings from the 3rd European Clinical Consensus Conference for clinical trials in device-based hypertension therapies - Mahfoud, Felix; Azizi, Michel; Ewen, Sebastian; Pathak, Atul; Ukena, Christian; Blankestijn, Peter J.; Böhm, Michael; Burnier, Michel; Chatellier, Gilles; Durand Zaleski, Isabelle; Grassi, Guido; Joner, Michael; et al. (European Heart Journal, 2020)
CRIS-Team Scopus Importer:2020-05-15

Proceedings from the European clinical consensus conference for renal denervation: considerations on future clinical trial design - Mahfoud, Felix; Boehm, Michael; Azizi, Michel; Pathak, Atul; Zaleski, Isabelle Durand; Ewen, Sebastian; Tsioufis, Kostantinos; Andersson, Bert; Blankestijn, Peter J.; Burnier, Michel; Chatellier, Gilles; Gafoor, Sameer; et al. (European Heart Journal, 2015)
EVALuna2:3763

Progressive Kidney Failure by Angiotensinogen Inactivation in the Germline - Wopperer, Florian; Olinger, Eric; Wiesener, Antje; Broeker, Katharina A.E.; Knaup, Karl; Schaefer, Jan Thomas; Galiano, Matthias; Schneider, Karen; Schiffer, Mario; Büttner-Herold, Maike; Reis, André; Schmieder, Roland; et al. (Hypertension, 2024)
BACKGROUND: Autosomal recessive renal tubular dysgenesis is a rare, usually fatal inherited disorder of the REN (renin)angiotensin system. Herein, we report an adolescent individual experiencing an unknown chronic kidney disease and aim to provide novel insights into disease mechanisms. METHODS: Exome sequencing for a gene panel associated with renal disease was performed. The REN-angiotensin system was assessed by comprehensive biochemical analysis in blood. REN expression was determined in primary tubular cells by quantitative polymerase chain reaction and in situ hybridization on kidney biopsy samples. Allele frequencies of heterozygous and biallelic deleterious variants were determined by analysis of the Genomics England 100,000 Genomes Project. RESULTS: The patient was delivered prematurely after oligohydramnios was detected during pregnancy. Postnatally, he recovered from third-degree acute kidney injury but developed chronic kidney disease stage G3b over time. Exome sequencing revealed a previously reported pathogenic homozygous missense variant, p.(Arg375Gln), in the AGT (angiotensinogen) gene. Blood AGT concentrations were low, but plasma REN concentration and gene expression in kidney biopsy, vascular, and tubular cells revealed strong upregulation of REN. Angiotensin II and aldosterone in blood were not abnormally elevated. CONCLUSIONS: Renal tubular dysgenesis may present as chronic kidney disease with a variable phenotype, necessitating broad genetic analysis for diagnosis. Functional analysis of the renin-angiotensin system in a patient with AGT mutation revealed novel insights regarding compensatory upregulation of REN in vascular and tubular cells of the kidney and in plasma in response to depletion of AGT substrate as a source of Ang II (similarly observed with hepatic AGT silencing for the treatment of hypertension).
CRIS-Team Scopus Importer:2024-07-26
Keywords: angiotensinogen; exome; mass spectrometry; mutation; renin-angiotensin system

Quality Of Life And Emotional Impact Of A Fixed Dose Combination Of Antihypertensive Drugs In Patients With Uncontrolled Hypertension - Schmieder, Roland; Fronk, Eva-Maria; Alexandre, A. F.; Bramlage, Peter (Value in Health, 2015)
EVALuna2:3802

Quality of life and emotional impact of a fixed-dose combination of antihypertensive drugs in patients with uncontrolled hypertension - Schmieder, Roland; Jumar, Agnes; Fronk, Eva-Maria; Alexandre, Ana-Filipa; Bramlage, Peter (Journal of Clinical Hypertension, 2017)
Often considered to be a symptomless condition, hypertension can be associated with a significant emotional burden. To analyze changes of health-related quality of life as well as the emotional burden questions regarding the impact of hypertension were incorporated into the noninterventional SeviTarget study. Comparisons were made between baseline and follow-up findings, and between patients with treatment target achievement and those without. A total of 5831 patients were recruited. At baseline, only 33.3% of patients described their current state of health as good or excellent, while at follow-up this value had risen to 75.8%. Responses regarding symptoms and limitations in activities and mental factors such as anxiety associated with treatment all improved during antihypertensive treatment. Changes to more optimistic responses were more likely for patients who achieved a target BP of <140/90 mm Hg. The study demonstrates that improvements in quality of life and the perceived emotional burden related to hypertension can be achieved with effective management of hypertension.
EVALuna2:3906

RADIANCE-HTN SOLO: A MULTICENTER, RANDOMIZED, SHAM-CONTROLLED STUDY OF RENAL DENERVATION IN PATIENTS WITH UNCONTROLLED HYPERTENSION IN THE ABSENCE OF ANTIHYPERTENSIVE MEDICATIONS - Azizi, M.; Schmieder, Roland; Mahfoud, F.; Weber, M.; Daemen, J.; Davies, J.; Basile, J.; Kirtane, A.; Wang, Y.; Mauri, L. (2018)
EVALuna2:202961

Rationale and design of two randomized sham-controlled trials of catheter-based renal denervation in subjects with uncontrolled hypertension in the absence (SPYRAL HTN-OFF MED Pivotal) and presence (SPYRAL HTN-ON MED Expansion) of antihypertensive medications: a novel approach using Bayesian design - Böhm, Michael; Townsend, Raymond R.; Kario, Kazuomi; Kandzari, David; Mahfoud, Felix; Weber, Michael A.; Schmieder, Roland; Tsioufis, Konstantinos; Hickey, Graeme L.; Fahy, Martin; DeBruin, Vanessa; Brar, Sandeep; et al. (Clinical Research in Cardiology, 2020)
Background: The SPYRAL HTN clinical trial program was initiated with two 80-patient pilot studies, SPYRAL HTN-OFF MED and SPYRAL HTN-ON MED, which provided biological proof of principle that renal denervation has a blood pressure-lowering effect versus sham controls for subjects with uncontrolled hypertension in the absence or presence of antihypertensive medications, respectively. Trial design: Two multicenter, prospective, randomized, sham-controlled trials have been designed to evaluate the safety and efficacy of catheter-based renal denervation for the reduction of blood pressure in subjects with hypertension in the absence (SPYRAL HTN-OFF MED Pivotal) or presence (SPYRAL HTN-ON MED Expansion) of antihypertensive medications. The primary efficacy endpoint is baseline-adjusted change from baseline in 24-h ambulatory systolic blood pressure. The primary safety endpoint is incidence of major adverse events at 1 month after randomization (or 6 months in cases of new renal artery stenosis). Both trials utilize a Bayesian design to allow for prespecified interim analyses to take place, and thus, the final sample sizes are dependent on whether enrollment is stopped at the first or second interim analysis. SPYRAL HTN-OFF MED Pivotal will enroll up to 300 subjects and SPYRAL HTN-ON MED Expansion will enroll up to 221 subjects. A novel Bayesian power prior approach will leverage historical information from the pilot studies, with a degree of discounting determined by the level of agreement with data from the prospectively powered studies. Conclusions: The Bayesian paradigm represents a novel and promising approach in device-based hypertension trials. Clinical trial registration: URL: https://www.clinicaltrials.gov. Unique identifier: NCT02439749 (SPYRAL HTN-OFF MED Pivotal) and NCT02439775 (SPYRAL HTN-ON MED Expansion).
CRIS-Team Scopus Importer:2020-02-18
Keywords: Blood pressure; Device-based statistics; Renal sympathetic nervous system; Sham; Trial design

Rationale, design, and baseline characteristics of ARTS-DN: a randomized study to assess the safety and efficacy of finerenone in patients with type 2 diabetes mellitus and a clinical diagnosis of diabetic nephropathy - Ruilope, Luis M.; Agarwal, Rajiv; Chan, Juliana C.; Cooper, Mark E.; Gansevoort, Ron T.; Haller, Hermann; Remuzzi, Giuseppe; Rossing, Peter; Schmieder, Roland; Nowack, Christina; Ferreira, Anna C.; Pieper, Alexander; et al. (American Journal of Nephrology, 2014)
Finerenone decreases albuminuria in patients having heart failure with reduced ejection fraction and mild-to-moderate (stage 2-3) chronic kidney disease. The MinerAlocorticoid Receptor Antagonist Tolerability Study-Diabetic Nephropathy (ARTS-DN; NCT01874431) is a multicenter, randomized, double-blind, placebo-controlled, parallel-group, phase 2b study. ARTS-DN investigated whether the mineralocorticoid receptor antagonist finerenone reduces albuminuria without causing major alterations in serum potassium levels in patients with type 2 diabetes mellitus and a clinical diagnosis of DN who were receiving a renin-angiotensin-system (RAS) inhibitor.Patients were randomized to oral finerenone 1.25-20 mg or placebo once daily. The primary objectives were to assess the ratio of the urinary albumin-to-creatinine ratio at day 90 to that at baseline in patients receiving finerenone, and to compare it with that in the placebo group. Additional exploratory analyses included evaluating changes from baseline in serum potassium levels, efficacy and safety biomarkers, and health-related quality of life.Of 1,501 patients screened, 821 (the sample population) received at least one dose of finerenone/placebo. Baseline characteristics included: male, 77.8%; white, 84.2%; very high albuminuria (formerly macroalbuminuria), 38.4%; high albuminuria (formerly microalbuminuria), 60.3%; median (range) estimated glomerular filtration rate, 66.3 (24.5-130.7) ml/min/1.73 m(2); and systolic blood pressure (mean ± standard deviation), 138.1 ± 14.4 mm Hg. There was a history of cardiovascular disease in 39.6%, diabetic neuropathy in 20.0%, and diabetic retinopathy in 19.9% of patients.ARTS-DN is the first phase 2b trial of finerenone in combination with a RAS inhibitor in patients with type 2 diabetes mellitus and a clinical diagnosis of DN.
EVALuna2:3938

Reasons for antihypertensive medication nonadherence influence physician preferences for hypertension management - Schmieder, Roland; Kandzari, D. E.; Wang, T. -D.; Lee, Y. -H.; Haro, C.; Pathak, A. (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Reduced effect of percutaneous renal denervation on blood pressure in patients with isolated systolic hypertension - Ewen, Sebastian; Ukena, Christian; Linz, Dominik; Kindermann, Ingrid; Cremers, Bodo; Laufs, Ulrich; Wagenpfeil, Stefan; Schmieder, Roland; Boehm, Michael; Mahfoud, Felix (Hypertension, 2015)
Renal denervation can reduce blood pressure in certain patients with resistant hypertension. The effect in patients with isolated systolic hypertension (ISH, >=140/<90 mm Hg) is unknown. This study investigated the effects of renal denervation in 126 patients divided into 63 patients with ISH and 63 patients with combined hypertension (CH, >=140/>=90 mm Hg) defined as baseline office systolic blood pressure (SBP) >=140 mm Hg despite treatment with >=3 antihypertensive agents. Renal denervation significantly reduced office SBP and diastolic blood pressure (DBP) at 3, 6, and 12 months by 17/18/17 and 5/4/4 mm Hg in ISH and by 28/27/30 and 13/16/18 mm Hg in CH, respectively. The reduction in SBP and DBP in ISH was lower compared with patients with CH at all observed time points (P<0.05 for SBP/DBP intergroup comparison). The nonresponder rate (change in office SBP <10 mm Hg) after 6 months was 37% in ISH and 21% in CH (P<0.001). Mean 24-hour ambulatory SBP and DBP after 3, 6, and 12 months were significantly reduced by 10/13/15 and 6/6/9 mm Hg in CH, respectively. In patients with ISH the reduction in systolic ambulatory blood pressure was 4/8/7 mm Hg (P=0.032/P<0.001/P=0.009) and 3/4/2 mm Hg (P=0.08/P<0.001/P=0.130) in diastolic ambulatory blood pressure after 3, 6, and 12 months, respectively. The ambulatory blood pressure reduction was significantly lower after 3 and 12 months in SBP and after 12 months in ambulatory DBP, respectively. In conclusion, renal denervation reduces office and ambulatory blood pressure in patients with ISH. However, this reduction is less pronounced compared with patients with CH.
EVALuna2:3734

Reduced tissue sodium content is related to improvement of vascular function in patients with chronic heart failure treated with the SGLT2 inhibitor empagliflozin - Kolwelter, Julie; Kannenkeril, Dennis; Linz, Peter; Jung, Susanne; Nagel, Armin Michael; Bosch, Agnes; Ott, Christian; Bramlage, P.; Uder, Michael; Achenbach, Stephan; Schmieder, Roland (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Reduction in blood pressure following renal denervation for patients with differing baseline cardiovascular risk - Mahfoud, F.; Mancia, G.; Schmieder, Roland; Narkiewicz, K.; Ruilope, L.; Schlaich, M.; Williams, B.; Fahy, M.; Bohm, M. (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Reduction of Clinical Events in High-Risk Hypertension Patients Treated With Renal Denervation: A Modeled Estimate From 36-Month Global SYMPLICTY Registry Data - Schlaich, Markus; Pietzsch, Jan Benjamin; Mahfoud, Felix; Wiliams, Bryan; Mancia, Giuseppe; Narkiewicz, Krzystzof; Ruilope, Luis; Hettrick, Doug; Bohm, Michael; Schmieder, Roland (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2022)
CRIS-Team WoS Importer:2022-05-13

Reduction of tissue sodium content by SGLT-2-inhibition with dapagliflozin - Karg, M. V.; Ott, Christian; Linz, Peter; Jumar, A.; Kannenkeril, Dennis; Titze, J.; Hammon, Matthias; Uder, Michael; Schmieder, Roland (2017)
EVALuna2:36268

Reference values of retinal microcirculation parameters derived from a population random sample - Cífková, Renata; Harazny, Joanna M.; Bruthans, Jan; Wohlfahrt, Peter; Krajčoviechová, Alena; Lánská, Věra; Gelžinský, Július; Mateřánková, Markéta; Mareš, Štěpán; Filipovský, Jan; Mayer, Otto; Schmieder, Roland (Microvascular Research, 2021)
Retinal microcirculation reflects retinal perfusion abnormalities and retinal arterial structural changes at relatively early stages of various cardiovascular diseases. Our objective has been to establish reference values for major functional and structural parameters of retinal microcirculation in a randomly selected urban population sample. A total of 398 randomly selected individuals from an urban population aged 25 to 65 years, resident in Pilsen, Czech Republic, were screened for major cardiovascular risk factors. Retinal microcirculation was assessed using scanning laser Doppler flowmetry (SLDF), with data evaluable in 343 patients. Of this number, complete data were available for 256 individuals free from manifest cardiovascular disease, diabetes and drug treatment for hypertension and/or dyslipidemia, constituting the reference value population. Juxtapapillary retinal capillary blood flow has increased significantly with age whereas vessel and luminal diameters have decreased. No sex differences in retinal microcirculation parameters have been found. Therefore, reference values for retinal microcirculation parameters have been established by age groups. Unattended automated office systolic BP, after adjusting for age, correlated significantly with wall-to-lumen ratio (WLR) and wall thickness (WT). Moreover, after adjusting for age and mean BP, a positive relationship has been found between carotid femoral pulse wave velocity and WT, WLR and wall cross-sectional area, indicating the interaction between micro- and macro-vasculature. In conclusion, our study is the first to provide reference values of retinal microcirculation parameters in a random Caucasian population sample. Our results have shown that, at the population level, the first structural changes in retinal microcirculation are those in lumen diameters. Of note, a close relationship between BP and vascular remodeling of retinal arterioles and between aortic stiffness and WLR of retinal arterioles suggests an interaction between micro- and macro-vasculature.
CRIS-Team Scopus Importer:2020-12-11
Keywords: Czech post-MONICA study; Juxtapapillary retinal capillary blood flow; Luminal diameter; Retinal vascular resistance; Scanning laser Doppler flowmetry; Vessel diameter; Wall cross-sectional area; Wall thickness; Wall-to-lumen ratio

REFERENCE VALUES OF RETINAL MICROCIRCULATION PARAMETERS IN A WHITE POPULATION RANDOM SAMPLE. CZECH POST-MONICA STUDY - Cifkova, R.; Harazny, J. M.; Bruthans, J.; Wohlfahrt, P.; Krajcoviechova, A.; Lanska, V.; Gelzinsky, J.; Materankova, M.; Mares, S.; Filipovsky, J.; Mayer, O.; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-20

RELATION BETWEEN NOISE ANNOYANCE, STRESS HORMONES AND THE RENAL HEMODYNAMIC - Bosch, Agnes; Kannenkeril, Dennis; Rauh, Manfred; Ott, Christian; Striepe, Kristina; Jung, Susanne; Kolwelter, Julie; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Relation between waist circumference and the renal hemodynamic in healthy individuals - Bosch, Agnes; Kannenkeril, Dennis; Ott, Christian; Striepe, Kristina; Schiffer, Mario; Schmieder, Roland (Nutrition Metabolism and Cardiovascular Diseases, 2024)
Background and aims: Obesity has been shown to be an independent risk factor for the development of CKD. Little is known about pathways of interaction of visceral fat mass estimated by waist circumference (WC) and metabolic factors with the renal and intraglomerular hemodynamic profile in healthy, non-obese individuals. Methods and results: The study population of this post-hoc analysis in 80 healthy individuals, who participated in a randomized, controlled clinical trial (www.clinicaltrials.gov: NCT02783456) was divided into two groups based on median of WC (high WC and low WC group). Renal hemodynamic profiles were analyzed using steady state input clearance (infusion of para-amino-hippuric acid and inulin). Intraglomerular pressure (IGP) and resistances of the afferent (RA) and efferent (RE) arterioles were calculated (Gomez equation). The analysis included healthy, non-smoking individuals, aged 27 ± 9 years with median WC of 84.75 ± 9 cm. Glomerular filtration rate (GFR) (110 ± 15 vs. 127 ± 16 ml/min/m2, p < 0.001), renal plasma flow (RPF) (620 ± 109 vs. 700 ± 104 ml/min, p = 0.001) and IGP (36.7 ± 2.3 vs. 38.5 ± 3.1 mmHg, p = 0.003) were lower in the high WC compared to the low WC group. Patients in the high WC group showed higher renal vascular resistance (RVR) (85 ± 19 vs. 70 ± 12 mmHg/(ml/min), p < 0.001), higher RA (4034 ± 1177 vs. 3069 ± 786 dyn∗s/cm5, p < 0.001) and higher RE (2283 ± 339 vs. 2118 ± 280 dyn∗s/cm5, p = 0.021) compared to the low WC group. Individuals in the high WC group showed higher leptin levels (p = 0.003) and higher HOMA-IR (p = 0.024) compared to the low WC group. Conclusion: Increased WC in healthy young individuals was associated with reduced GFR and RPF likely mediated by increased RVR.
CRIS-Team Scopus Importer:2024-03-08
Keywords: Clearance analysis; Obesity; Renal hemodynamic; Waist circumference

Relationship Between Ubiquitin-Specific Peptidase 18 and Hypertension in Polish Adult Male Subjects: A Cross-Sectional Pilot Study - Dziamałek-Macioszczyk, Paulina; Harazny, Joanna M.; Kwella, Norbert; Wojtacha, Paweł; Jung, Susanne; Dienemann, Thomas; Schmieder, Roland; Stompór, Tomasz (Medical Science Monitor, 2020)
BACKGROUND Arterial hypertension (HT) is a leading cause of cardiac hypertrophy and heart failure. Ubiquitin-specific peptidase 18 (USP18) has been recently described as a factor that prevents myocardial dysfunction. The present study measured serum USP18 levels in normotensive (n=29), isolated diastolic hypertensive (n=20), and systolic-diastolic hypertensive (n=30) male participants and correlated these results with biochemical parameters that are included in routine assessments of patients with hypertension. MATERIAL AND METHODS Seventy-nine men, aged 24 to 82 years (mean=50.8±11.4 years), were included in the study. None of the participants had ever been treated for HT. Blood and urine parameters were assessed using routine techniques. Serum USP18 levels were measured by enzyme-linked immunosorbent assay. RESULTS The means and 95% confidence intervals (CIs) of USP18 levels in the HT(-), iDHT(+), and HT(+) groups were 69.3 (22.1-116.5) pg/ml, 90.1 (29.0-151.3) pg/ml, and 426.7 (163.1-690.3) pg/ml, respectively. In the HT(+) group, the mean serum USP18 level was 6.2-times higher than in the HT(-) group (p=0.014) and 4.7-times higher than in the iDHT(+) group (p=0.19). The partial correlation analysis that was adjusted for risk factors of arteriosclerosis indicated that USP18 levels were correlated with systolic blood pressure, pulse pressure, and heart rate. CONCLUSIONS This preliminary study found that serum USP18 levels were significantly higher in drug-naive male participants with arterial hypertension compared with normotensive controls. USP18 exerts cardiovascular-protective effects. Elevations of USP18 levels may indicate a counterregulatory process that is engaged during increases in pressure in the left ventricle.
CRIS-Team Scopus Importer:2020-06-23

Relative and Combined Prognostic Importance of On-Treatment Mean and Visit-to-Visit Blood Pressure Variability in ONTARGET and TRANSCEND Patients - Mancia, Giuseppe; Schumacher, Helmut; Boehm, Michael; Redon, Josep; Schmieder, Roland; Verdecchia, Paolo; Sleight, Peter; Teo, Koon; Yusuf, Salim (Hypertension, 2017)
In 28 790 patients recruited for the ONTARGET (Ongoing Treatment Alone and in Combination With Ramipril Global End Point Trials) and TRANSCEND (Telmisartan Randomized Assessment Study in ACE Intolerant Subjects With Cardiovascular Disease) trials, we investigated the prognostic value for cardiovascular events (primary outcome) of (1)on-treatment visit-to-visit systolic blood pressure (SBP) variability versus mean SBP and (2) the 2 measures together. SBP variability was measured by the coefficient of variation (CV) of mean SBP to which it was unrelated. Confounders such as variable time and number of visits from which to calculate SBP-CV were avoided by using the same number of visits at identical times in all patients. The covariate-adjusted risk of the primary outcome (Cox models) increased as SBP-CV or mean on-treatment quintile SBP increased, but only for mean on-treatment SBP, the relationship achieved statistical significance: global test for trend, P=0.12 versus P<0.0001. SBP-CV showed a relationship with fatal events, but it was unrelated to the risk of myocardial infarction and stroke, which were predicted by on-treatment mean SBP. Prediction of the primary outcome improved by the combined use of both measures: global test for trend, P<0.0001; hazard ratio for combined fifth versus first quintile, 1.42 (1.20-1.68) compared with 1.13 (1.01-1.27) for SBP-CV and 1.24 (1.11-1.40) for mean SBP. Thus, in the present study, on-treatment mean SBP provided an overall better prediction of cardiovascular risk than visit-to-visit SBP-CV. Prediction improved by their combined use, which may thus offer a more precise estimate of the protective effect of treatment.URL: http//www.clinicaltrial.gov. Unique identifier: NCT153.101.
EVALuna2:4023

Renal adaptation in pre-obesity patients with hypertension - Bosch, Agnes; Rauh, Manfred; Striepe, Kristina; Schiffer, Mario; Schmieder, Roland; Kannenkeril, Dennis (Journal of Hypertension, 2024)
Background and hypothesis: Obesity aggravates the risk to develop chronic kidney disease in hypertensive patients. Whether pre-obesity already impairs renal function, renal perfusion and intraglomerular hemodynamics in hypertensive patients is unknown. Methods: Renal hemodynamic profiles were measured using steady state input clearance (infusion of para-amino-hippuric acid and inulin) in 36 patients with primary arterial hypertension stage 1-2 without antihypertensive medication. Intraglomerular pressure (IGP) and resistances of the afferent (RA) and efferent (RE) arterioles were calculated. The study population was divided into two groups based on median of waist circumference (WC) (96 cm) (pre-obesity and non-obesity group1) and median of body mass index (BMI) (26.5 kg/m2) (pre-obesity and non-obesity group2), respectively. Results: All patients were males, non-smoking, aged 36 ± 10 years, with an office blood pressure of 145 ± 8.6/89 ± 11.8 mmHg. None of the patients had cardiovascular disease. Patients from the pre-obese group 1 showed lower glomerular filtration rate (GFR), lower renal plasma flow (RPF) and lower IGP compared to the non-obese group1. Renal vascular resistance (RVR) and RA were higher in the pre-obese group1 compared to the non-obese group1. Similar differences in the hemodynamic profile were found for patients in the pre-obesity group2 compared to the non-obesity group2. Conclusion: The renal hemodynamic profile in hypertensive patients with pre-obesity, irrespective whether defined by WC or BMI, was characterized by a reduced GFR and RPF and by an increased RVR preferentially at the preglomerular site. Our results suggest that hypofiltration is the first phase of renal adaptation in pre-obesity hypertension.
CRIS-Team Scopus Importer:2024-09-20
Keywords: body mass index; clearance analysis; pre-obesity; renal hemodynamic; waist circumference

Renal and intraglomerular haemodynamics in chronic heart failure with preserved and reduced ejection fraction - Jung, Susanne; Bosch, Agnes; Kolwelter, Julie; Striepe, Kristina; Kannenkeril, Dennis; Schuster, Tizia; Ott, Christian; Achenbach, Stephan; Schmieder, Roland (ESC Heart Failure, 2021)
Aims: Congestive heart failure (CHF) and impaired renal function are two often co-existing medical conditions and associated with adverse cardiovascular outcome. The aim of the current study was to assess renal and intraglomerular haemodynamics by constant infusion input clearance technique in subjects with CHF. Methods and results: The group of subjects with CHF consisted of 27 individuals with HFpEF and 27 individuals with HFrEF and were compared with 31 healthy controls. Subjects underwent renal clearance examination to measure glomerular filtration rate (GFR) and renal blood and plasma flow (RBF and RPF) and to calculate intraglomerular haemodynamics such as resistances of the afferent (RA) and efferent arterioles (RE) as well as intraglomerular pressure (Pglom). Measured GFR was lower in CHF subjects (68.1 ± 10.1 mL/min/1.73 m2) compared with controls (83.6 ± 13.4 mL/min/1.73 m2, Padj < 0.001) as was Pglom (Padj < 0.001). Total renal vascular resistance (RVR) was higher in CHF subjects (87.3 ± 20.1 vs. 73.8 ± 17.1 dyn × s/cm5, Padj < 0.001) mediated by an increased resistance at the afferent site (3201 ± 1084 vs. 2181 ± 796 dyn × s/cm5, Padj < 0.001). Comparing HFpEF and HFrEF subjects, RA was higher in HFrEF subjects. The severity of CHF assessed by NT-proBNP revealed an inverse association with renal perfusion (RPF r = −0.421, P = 0.002, RBF r = −0.414, P = 0.002) and a positive relation with RVR (r = 0.346, P = 0.012) at the post-glomerular site (RE: r = 0.318, P = 0.022). Conclusions: Renal function assessed by measured GFR is reduced and renal vascular resistance at the preglomerular, afferent site is increased in HFpEF and, to greater extent, in HFrEF. Our data indicate a close cardiorenal interaction in CHF.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Cardiorenal interaction; Heart failure; Preserved ejection fraction; Reduced ejection fraction; Renal haemodynamics

Renal artery denervation for treatment of patients with self-reported obstructive sleep apnea and resistant hypertension: results from the Global SYMPLICITY Registry - Linz, Dominik; Mancia, Giuseppe; Mahfoud, Felix; Narkiewicz, Krzysztof; Ruilope, Luis; Schlaich, Markus; Kindermann, Ingrid; Schmieder, Roland; Ewen, Sebastian; Williams, Bryan; Boehm, Michael (Journal of Hypertension, 2017)
Sleep-disordered breathing, predominantly obstructive sleep apnea (OSA), is highly prevalent in patients with hypertension. OSA may underlie the progression to resistant hypertension, partly due to increased activation of the sympathetic nervous system. This analysis of patients with and without OSA evaluated the blood pressure (BP)-lowering effect of sympathetic modulation by renal denervation (RDN) in a real-world setting.The Global SYMPLICITY Registry (NCT01534299) is a prospective, open-label, multicenter registry conducted worldwide to evaluate the safety and effectiveness of RDN in patients with uncontrolled hypertension. Office and 24-h ambulatory BP were reported for all patients, based on the presence of OSA.Among 1868 patients, self-reported OSA occurred in 205 patients, who were more likely to be men (76 vs 57%, P < 0.001), have a higher BMI (34 ± 6 vs 30 ± 5 kg/m, P < 0.001), chronic kidney disease (30 vs 21%, P = 0.003), left ventricular hypertrophy (25 vs 15%, P < 0.001), and type 2 diabetes (50 vs 36%, P < 0.001). Among OSA patients, the baseline office SBP (166 ± 26 mmHg) was reduced by 14.0 ± 25.3 mmHg at 6 months (P < 0.001). Ambulatory 24-h SBP was reduced by 4.9 ± 18.0 mmHg (n = 115, P = 0.005) from 155 ± 19 mmHg at baseline. The 6-month change in SBP from baseline was not statistically different between OSA and non-OSA patients. BP reduction after RDN was also similar in OSA patients already treated with and not treated with continuous positive airway pressure.RDN resulted in significant BP reductions at 6 months in hypertensive patients with and without OSA, and regardless of continuous positive airway pressure usage in OSA patients.
EVALuna2:3936

Renal Denervation: A Practical Guide for Health Professionals Managing Hypertension - Schmieder, Roland; Burnier, Michel; East, Cara; Tsioufis, Konstantinos; Delaney, Sean (Interventional Cardiology (London), 2023)
Growing evidence demonstrates the suitability of renal denervation in a broad population of patients; however, questions remain over its suitability and practical implementation. Given the rapidity of emerging data, this has been a challenging field for potential adopters to navigate. The purpose of this article is twofold: to provide navigation through emerging clinical data and evolving guidance; and to provide physicians with practical, evidence-based advice for identifying eligible patients and providing appropriate management in the pre- and postintervention settings. Although many of these recommendations are based on existing published guidance documents, we reflect equally on our own experiences of using this technology.
CRIS-Team Scopus Importer:2023-04-07
Keywords: antihypertensive; blood pressure control; cardiovascular risk; Hypertension; recommendations; renal denervation

Renal denervation-a valid treatment option despite SYMPLICITY HTN-3 - Schmieder, Roland (Nature Reviews Cardiology, 2014)
EVALuna2:3739

Renal Denervation for Resistant Hypertension: Past, Present, and Future - Ott, Christian; Schmieder, Roland (Current Hypertension Reports, 2015)
Renal denervation (RDN) for treatment of resistant hypertension was introduced only 5 years ago. A clear pathophysiological role of renal sympathetic activity for the initiation and maintenance of hypertension and promising data showing a substantial and sustained blood pressure (BP) reduction after RDN has promoted the widespread use of the method at least in Europe. However, in a pivotal trial that included a sham-control group, no significant BP lowering effects was observed. Afterwards, it became clear that methodological issues and poor performance and execution of the intervention have hampered the results of Symplicity HTN-3 study, thereby limiting its validity profoundly. Now, in 2015, the renaissance of RDN has begun and new randomized prospective clinical trials have or will be started soon. In the meantime, it may be wise not to ignore all previous findings, as a rescue therapy for treatment resistant hypertension. A new science era emerged, with changes of the interventional approach and selection of patients potentially profiting most from RDN.
EVALuna2:3795

Renal Denervation for Treating Hypertension: Current Scientific and Clinical Evidence - Weber, Michael A.; Mahfoud, Felix; Schmieder, Roland; Kandzari, David E.; Tsioufis, Konstantinos P.; Townsend, Raymond R.; Kario, Kazuomi; Böhm, Michael; Sharp, Andrew S.P.; Davies, Justin E.; Osborn, John W.; Fink, Greg D.; et al. (Jacc-Cardiovascular Interventions, 2019)
Initial studies of catheter-based renal denervation (RDN) for uncontrolled HTN using radiofrequency ablation in the main renal arteries showed that RDN was effective in lowering office blood pressure (BP). However, the first randomized sham-controlled trial, SYMPLICITY-HTN-3, did not show significantly lower office or 24-h ambulatory systolic BP compared with sham treatment. Subsequent studies in both animals and humans demonstrated the potential importance of more distal and branch renal artery radiofrequency ablation, and a second-generation multielectrode system became available. Two recent randomized sham-controlled trials in patients not taking antihypertensive drugs (SPYRAL HTN-OFF MED) or continuing to take drugs (SPYRAL HTN-ON MED) performed RDN with the second-generation radiofrequency ablation system using an ablation protocol that included treatment of the distal renal artery as well as the branch renal arteries. These studies showed that RDN significantly reduced office and 24-h ambulatory BP compared with sham treatment. Another recent randomized sham-controlled trial in patients not receiving medications showed that RDN with catheter-based ultrasound (RADIANCE-HTN SOLO) applied in just the main renal arteries significantly lowered daytime ambulatory and office BP compared with sham treatment. These trials have renewed clinical and scientific interest in defining the appropriate role of RDN in hypertension treatment. In addition, other important issues will need to be addressed in the future such as the development of tests to determine the extent of RDN at the time of the procedure and the potential of renal nerve fibers to regain their patency at some later stage following the ablation procedure.
CRIS-Team Scopus Importer:2019-06-21
Keywords: ambulatory blood pressure; hypertension; radiofrequency; renal denervation; ultrasound

Renal denervation for uncontrolled hypertension: A systematic review and meta-analysis examining multiple subgroups - Sharp, Andrew S.P.; Sanderson, Alice; Hansell, Neil; Reddish, Katie; Miller, Paul; Moss, Joe; Schmieder, Roland; McCool, Rachael (Journal of Hypertension, 2024)
This systematic review and meta-analysis was conducted to assess the randomized controlled trial (RCT) evidence available for renal denervation (RDN) in uncontrolled arterial hypertension. Twenty-five RCTs met the eligibility criteria for the systematic review, and 16 RCTs were included in the meta-analysis. The results of the random effects meta-analysis estimated a mean difference of -8.5 mmHg [95% confidence interval (CI) -13.5 to -3.6] for office SBP, -3.6 mmHg (95% CI -5.2 to -2.0) for 24 h SBP and -3.9 mmHg (95% CI -5.6 to -2.2) for ambulatory daytime SBP in favour of RDN compared with control (medication and/or sham-only) at primary follow-up. Similarly favourable results were observed across a range of prespecified subgroup analyses, including treatment-resistant hypertension. This meta-analysis suggests that the use of RDN in uncontrolled hypertension leads to consistent reductions in blood pressure. Reductions appear to be statistically consistent in the presence or absence of medications and in populations resistant to the use of three medications.
CRIS-Team Scopus Importer:2024-06-14
Keywords: meta-analysis; renal denervation; systematic review; treatment-resistant hypertension; uncontrolled hypertension

Renal denervation-implications for chronic kidney disease - Veelken, Roland; Schmieder, Roland (Nature Reviews Nephrology, 2014)
Catheter-based renal denervation to treat patients with resistant hypertension and chronic kidney disease (CKD) has generated considerable interest. Data from the majority of, but not all, observational studies and randomized controlled trials suggest that the procedure does not impair renal function and can effectively reduce office and ambulatory blood pressure in patients with primary hypertension. The putative beneficial effects of renal denervation seem to result from the interruption of renal efferent and afferent nerves. In patients with resistant hypertension and CKD, interruption of afferent reflexes might lead to a reduction in global sympathetic tone. The subsequent sustained reduction in blood pressure is expected to slow the progression of renal disease. However, renal denervation might also improve glucose metabolism, increase insulin sensitivity and reduce renal inflammation, with renoprotective effects in patients with CKD. Additional large randomized controlled trials of renal denervation in hypertensive and normotensive patients with CKD are required to precisely define the clinical value of the procedure in this population.
EVALuna2:3684

Renal denervation improves 24-hour central and peripheral blood pressures, arterial stiffness, and peripheral resistance - Ott, Christian; Franzen, Klaas F.; Graf, Tobias; Weil, Joachim; Schmieder, Roland; Reppel, Michael; Mortensen, Kai (Journal of Clinical Hypertension, 2018)
Ambulatory blood pressure (BP) and central BP are better predictors for overall cardiovascular risk and mortality than brachial BP. Renal denervation (RDN) has been shown to reduce office brachial and central BP as well as brachial ambulatory BP, but data on central ambulatory BP are limited. Patients (N = 94) with treatment resistant hypertension (TRH) who underwent RDN were included. Ambulatory BP, including central pressures, hemodynamics, and arterial stiffness were measured at baseline and 3, 6, 12 months after RDN by an oscillometric device (MobiloGraph™). At 3, 6, and 12-month follow-ups, brachial ambulatory BP was reduced (P for all < .001). Consistently, central ambulatory BP was reduced (P for all < .001). Ambulatory assessed averaged daytime pulse wave velocity improved after RDN (P < .05). Total vascular resistance decreased (P for all < .01). In patients with TRH, RDN improves brachial and central ambulatory BP, arterial stiffness, and total vascular resistance, indicating an improvement of cardiovascular outcome.
EVALuna2:33738

Renal Denervation in High-Risk Patients With Hypertension - Mahfoud, Felix; Mancia, Giuseppe; Schmieder, Roland; Narkiewicz, Krzysztof; Ruilope, Luis; Schlaich, Markus; Whitbourn, Robert; Zirlik, Andreas; Zeller, Thomas; Stawowy, Philipp; Cohen, Sidney A.; Fahy, Martin; et al. (Journal of the American College of Cardiology, 2020)
Background: Renal denervation (RDN) is under investigation for treatment of uncontrolled hypertension and might represent an attractive treatment for patients with high cardiovascular (CV) risk. It is important to determine whether baseline CV risk affects the efficacy of RDN. Objectives: The purpose of this study was to assess blood pressure (BP) reduction and event rates after RDN in patients with various comorbidities, testing the hypothesis that RDN is effective and durable in these high-risk populations. Methods: BP reduction and adverse events over 3 years were evaluated for several high-risk subgroups in the GSR (Global proSpective registrY for syMPathetic renaL denervatIon in seleCted IndicatIons Through 3 Years Registry), an international registry of RDN in patients with uncontrolled hypertension (n = 2,652). Comparisons were made for patients age ≥65 years versus age <65 years, with versus without isolated systolic hypertension, with versus without atrial fibrillation, and with versus without diabetes mellitus. Baseline cardiovascular risk was estimated using the American Heart Association (AHA)/American College of Cardiology (ACC) atherosclerosis cardiovascular disease (ASCVD) risk score. Results: Reduction in 24-h systolic BP at 3 years was −8.9 ± 20.1 mm Hg for the overall cohort, and for high-risk subgroups, BP reduction was −10.4 ± 21.0 mm Hg for resistant hypertension, −8.7 ± 17.4 mm Hg in patients age ≥65 years, −10.2 ± 17.9 mm Hg in patients with diabetes, −8.6 ± 18.7 mm Hg in isolated systolic hypertension, −10.1 ± 20.3 mm Hg in chronic kidney disease, and −10.0 ± 19.1 mm Hg in atrial fibrillation (p < 0.0001 compared with baseline for all). BP reduction in patients with measurements at 6, 12, 24, and 36 months showed similar reductions in office and 24-h BP for patients with varying baseline ASCVD risk scores, which was sustained to 3 years. Adverse event rates at 3 years were higher for patients with higher baseline CV risk. Conclusions: BP reduction after RDN was similar for patients with varying high-risk comorbidities and across the range of ASCVD risk scores. The impact of baseline risk on clinical event reduction by RDN-induced BP changes could be evaluated in further studies. (Global proSpective registrY for syMPathetic renaL denervatIon in seleCted IndicatIons Through 3 Years Registry; NCT01534299)
CRIS-Team Scopus Importer:2020-06-09
Keywords: blood pressure; cardiovascular risk; device-based hypertension therapy; hypertension; renal denervation

Renal denervation in hypertensive patients not on blood pressure lowering drugs - De Jager, Rosa L.; Sanders, Margreet F.; Bots, Michiel L.; Lobo, Melvin D.; Ewen, Sebastian; Beeftink, Martine M. A.; Boehm, Michael; Daemen, Joost; Doerr, Oliver; Hering, Dagmara; Mahfoud, Felix; Nef, Holger; et al. (Clinical Research in Cardiology, 2016)
Studies on the blood pressure lowering effect of renal denervation (RDN) in resistant hypertensive patients have produced conflicting results. Change in medication usage during the studies may be responsible for this inconsistency. To eliminate the effect of medication usage on blood pressure we focused on unmedicated hypertensive patients who underwent RDN.Our study reports on a cohort of patients, who were not on blood pressure lowering drugs at baseline and during follow-up, from eight tertiary centers. Data of patients were used when they were treated with RDN and had a baseline office systolic blood pressure (SBP) >=140 mmHg and/or 24-h ambulatory SBP >=130 mmHg. Our primary outcome was defined as change in office and 24-h SBP at 12 months after RDN, compared to baseline. Fifty-three patients were included. There were three different reasons for not using blood pressure lowering drugs: (1) documented intolerance or allergic reaction (57 %); (2) temporary cessation of medication for study purposes (28 %); and (3) reluctance to take antihypertensive drugs (15 %). Mean change in 24-h SBP was -5.7 mmHg [95 % confidence interval (CI) -11.0 to -0.4; p = 0.04]. Mean change in office SBP was -13.1 mmHg (95 % CI -20.4 to -5.7; p = 0.001). No changes were observed in other variables, such as eGFR, body-mass-index and urinary sodium excretion.This explorative study in hypertensive patients, who are not on blood pressure lowering drugs, suggests that at least in some patients RDN lowers blood pressure.
EVALuna2:3850

Renal denervation in moderate treatment-resistant hypertension - Ott, Christian; Mahfoud, Felix; Schmid, Axel; Ditting, Tilmann; Sobotka, Paul A.; Veelken, Roland; Spies, Aline; Ukena, Christian; Laufs, Ulrich; Uder, Michael; Boehm, Michael; Schmieder, Roland (Journal of the American College of Cardiology, 2013)
Objectives This study sought to investigate the effect of renal denervation (RDN) in patients with treatment-resistant hypertension according to the established definition (Joint National Committee VII and European Society of Hypertension/European Society of Cardiology guidelines), that is, office blood pressure (BP) ≥140/90 mm Hg (with at least three antihypertensive drugs, including a diuretic, in adequate doses) and confirmed by 24-h ambulatory BP monitoring (ABPM). Background RDN emerged as an innovative interventional antihypertensive therapy. However, so far, only patients with severe hypertension (systolic BP ≥160 mm Hg or ≥150 mm Hg for patients with type 2 diabetes) have been investigated. Methods In this study, there were 54 patients with moderate treatment-resistant hypertension (office BP ≥140/90 mm Hg and <160/100 mm Hg and diagnosis confirmed by 24-h ABPM of ≥130/80 mm Hg) who underwent catheter-based RDN using the Symplicity catheter (Medtronic Inc., Mountain View, California). Results Patients were treated with 5.1 ± 1.4 antihypertensive drugs on average. Office BP was significantly reduced by 13/7 mm Hg 6 months after RDN (systolic: 151 ± 6 mm Hg vs. 138 ± 21 mm Hg, p < 0.001; diastolic: 83 ± 11 mm Hg vs. 75 ± 11 mm Hg, p < 0.001). In patients (n = 36) who underwent ABPM 6 months after treatment, there was a reduction in average 24-h ABPM by 14/7 mm Hg (systolic: 150 ± 16 mm Hg vs. 136 ± 16 mm Hg, p < 0.001; diastolic: 83 ± 10 mm Hg vs. 76 ± 10 mm Hg, p < 0.001). In 51% of patients, office BP was controlled below 140/90 mm Hg after RDN. In addition, heart rate decreased from 67 ± 11 to 63 ± 10 beats/min (p = 0.006). Conclusions Our data indicate that RDN may reduce office and 24-h ambulatory BP substantially in patients with moderate treatment-resistant hypertension. (Renal Denervation in Treatment Resistant Hypertension; NCT01687725). © 2013 by the American College of Cardiology Foundation.
CRIS-Team Scopus Importer:2023-03-08
Keywords: 24-h ambulatory blood pressure; renal denervation; treatment-resistant hypertension

Renal denervation in patients with chronic kidney disease: current evidence and future perspectives - Schmieder, Roland (Nephrology Dialysis Transplantation, 2022)
Supported by several high-quality randomized controlled trials and registry analyses, catheter-based renal denervation is becoming an important adjunctive treatment modality for the safe and efficacious treatment of hypertension besides lifestyle modifications and antihypertensive medication. Renal denervation is of particular interest to nephrologists as the intervention may provide additional benefits to hypertensive people with chronic kidney disease (CKD), a condition typically characterized by sympathetic hyperactivity. A growing body of clinical evidence supports the safety and efficacy of renal denervation in this difficult-to-control population. In addition, preclinical and clinical research works indicate potential nephroprotective effects in CKD patients. The current review examines recent research on renal denervation with a focus on renal disease and assesses the latest findings and their implications from a nephrologist's perspective.
CRIS-Team WoS Importer:2022-07-29

Renal denervation in patients with versus without chronic kidney disease: results from the Global SYMPLICITY Registry with follow-up data of 3 years - Ott, Christian; Mahfoud, Felix; Mancia, Giuseppe; Narkiewicz, Krzysztof; Ruilope, Luis M.; Fahy, Martin; Schlaich, Markus P.; Böhm, Michael; Schmieder, Roland (Nephrology Dialysis Transplantation, 2022)
BACKGROUND: Activity of the sympathetic nervous system is increased in patients with hypertension and chronic kidney disease (CKD). Here we compare short- and long-term blood pressure (BP)-lowering effects of renal denervation (RDN) between hypertensive patients with or without CKD in the Global SYMPLICITY Registry. METHODS: Office and 24-h ambulatory BP (ABP) were assessed at prespecified time points after RDN. The presence of CKD was defined according to the estimated glomerular filtration rate (eGFR) and enrolled patients were stratified based on the presence (n = 475, eGFR <60 mL/min/1.73 m2) or absence (n = 1505, eGFR ≥60mL/min/1.73 m2) of CKD. RESULTS: Patients with CKD were older (P < 0.001) and were prescribed more antihypertensive medications (P < 0.001). eGFR decline per year was not significantly different between groups after the first year. Office and 24-h ABP were significantly reduced from baseline at all time points after RDN in both groups (all P < 0.001). After adjusting for baseline data, patients without CKD had a greater reduction in office systolic BP (-17.3 ± 28.3 versus -11.7 ± 29.9 mmHg; P = 0.009) but not diastolic BP at 36 months compared with those with CKD. Similar BP and eGFR results were found when the analysis was limited to patients with both baseline and 36-month BP data available. There was no difference in the safety profile of the RDN procedure between groups. CONCLUSIONS: After adjusting for baseline data, 24-h systolic and diastolic ABP reduction were similar in patients with and without CKD after RDN, whereas office systolic but not diastolic BP was reduced less in patients with CKD. We conclude that RDN is an effective antihypertensive treatment option in CKD patients.
CRIS-Team Scopus Importer:2022-02-11
Keywords: blood pressure; hypertension; renal function

Renal denervation in refractory hypertension: joint statement of the German hypertension league DHL eV and the German societies of cardiology, angiology, nephrology and radiology - Vonend, Oliver; Boehm, Michael; Eckert, Siegfried; Hausberg, Martin; Rittger, Harald; Rump, Lars-Christian; Schmieder, Roland; Schulte, Karl-Ludwig; Schunkert, Heribert; Uder, Michael; Veelken, Roland; Vorwerk, Dierk; et al. (Deutsche Medizinische Wochenschrift, 2015)
Arterial hypertension is a major risk factor for cardiovascular mortality and remains insufficiently controlled in Germany. The sham controlled Symplicity HTN-3 trial did meet its primary safety endpoint but failed to meet its primary efficacy endpoint. Renal denervation can not replace established, well-proven therapies. It can only be used in selected truly resistant hypertensive patients as an additive approach and should be performed by specialized centers only. Randomized controlled trials are needed to further evaluate renal denervation.
EVALuna2:3770

Renal denervation in the management of hypertension in adults. A clinical consensus statement of the ESC Council on Hypertension and the European Association of Percutaneous Cardiovascular Interventions (EAPCI). - Barbato, Emanuele; Azizi, Michel; Schmieder, Roland; Lauder, Lucas; Böhm, Michael; Brouwers, Sofie; Bruno, Rosa Maria; Dudek, Dariusz; Kahan, Thomas; Kandzari, David E.; Lüscher, Thomas F.; Parati, Gianfranco; et al. (EuroIntervention, 2023)
Since the publication of the 2018 European Society of Cardiology/European Society of Hypertension (ESC/ESH) Guidelines for the Management of Arterial Hypertension, several high-quality studies, including randomised, sham-controlled trials on catheter-based renal denervation (RDN) were published, confirming both the blood pressure (BP)-lowering efficacy and safety of radiofrequency and ultrasound RDN in a broad range of patients with hypertension, including resistant hypertension. A clinical consensus document by the ESC Council on Hypertension and the European Association of Percutaneous Cardiovascular Interventions (EAPCI) on RDN in the management of hypertension was considered necessary to inform clinical practice. This expert group proposes that RDN is an adjunct treatment option in uncontrolled resistant hypertension, confirmed by ambulatory BP measurements, despite best efforts at lifestyle and pharmacological interventions. RDN may also be used in patients who are unable to tolerate antihypertensive medications in the long term. A shared decision-making process is a key feature and preferably includes a patient who is well informed on the benefits and limitations of the procedure. The decision-making process should take (i) the patient's global cardiovascular (CV) risk and/or (ii) the presence of hypertension-mediated organ damage or CV complications into account. Multidisciplinary hypertension teams involving hypertension experts and interventionalists evaluate the indication and facilitate the RDN procedure. Interventionalists require expertise in renal interventions and specific training in RDN procedures. Centres performing these procedures require the skills and resources to deal with potential complications. Future research is needed to address open questions and investigate the impact of BP-lowering with RDN on clinical outcomes and potential clinical indications beyond hypertension.
EVALuna2:525513

Renal denervation in the management of hypertension in adults. A clinical consensus statement of the ESC Council on Hypertension and the European Association of Percutaneous Cardiovascular Interventions (EAPCI). - Barbato, Emanuele; Azizi, Michel; Schmieder, Roland; Lauder, Lucas; Boehm, Michael; Brouwers, Sofie; Bruno, Rosa Maria; Dudek, Dariusz; Kahan, Thomas; Kandzari, David E.; Luscher, Thomas F.; Parati, Gianfranco; et al. (European Heart Journal, 2023)
Since the publication of the 2018 European Society of Cardiology/European Society of Hypertension (ESC/ESH) Guidelines for the Management of Arterial Hypertension, several high-quality studies, including randomised, sham-controlled trials on catheter-based renal denervation (RDN) were published, confirming both the blood pressure (BP)-lowering efficacy and safety of radiofrequency and ultrasound RDN in a broad range of patients with hypertension, including resistant hypertension. A clinical consensus document by the ESC Council on Hypertension and the European Association of Percutaneous Cardiovascular Interventions (EAPCI) on RDN in the management of hypertension was considered necessary to inform clinical practice. This expert group proposes that RDN is an adjunct treatment option in uncontrolled resistant hypertension, confirmed by ambulatory BP measurements, despite best efforts at lifestyle and pharmacological interventions. RDN may also be used in patients who are unable to tolerate antihypertensive medications in the long term. A shared decision-making process is a key feature and preferably includes a patient who is well informed on the benefits and limitations of the procedure. The decision-making process should take (i) the patient's global cardiovascular (CV) risk and/or (ii) the presence of hypertension-mediated organ damage or CV complications into account. Multidisciplinary hypertension teams involving hypertension experts and interventionalists evaluate the indication and facilitate the RDN procedure. Interventionalists require expertise in renal interventions and specific training in RDN procedures. Centres performing these procedures require the skills and resources to deal with potential complications. Future research is needed to address open questions and investigate the impact of BP-lowering with RDN on clinical outcomes and potential clinical indications beyond hypertension.
EVALuna2:525512

Renal Denervation Lowers Nighttime Blood Pressure in True Resistant Hypertension - Kario, Kazuomi; Kandzari, David E.; Mahfoud, Felix; Weber, Michael A.; Schmieder, Roland; Tsioufis, Konstantinos; Liu, Minglei; Böhm, Michael; Townsend, Raymond R. (Hypertension, 2024)
CRIS-Team Scopus Importer:2024-12-06
Keywords: blood pressure; catheters; denervation; hypertension; life style

Renal denervation preserves renal function in patients with chronic kidney disease and resistant hypertension - Ott, Christian; Mahfoud, Felix; Schmid, Axel; Toennes, Stefan W.; Ewen, Sebastian; Ditting, Tilmann; Veelken, Roland; Ukena, Christian; Uder, Michael; Boehm, Michael; Schmieder, Roland (Journal of Hypertension, 2015)
Arterial hypertension and increased sympathetic activity are underlying pathogenetic mechanisms of the progressive loss of renal function in patients with chronic kidney disease (CKD). Meta-analyses have shown that impaired renal function is an independent cardiovascular risk factor. We hypothesized that renal denervation (RDN) decreases the decline of renal function in patients with CKD stages 3 and 4 and treatment-resistant hypertension.We performed an observational study of 27 patients with CKD stages 3 and 4, office blood pressure (BP) >= 140/90 mmHg, while on at least three antihypertensive drug classes including diuretic, and diagnosis confirmed by 24-h ambulatory BP measurement >= 130/80 mmHg. All patients underwent catheter-based RDN using the Symplicity Flex RDN System (Medtronic Inc., Santa Rosa, California, USA). Renal function was evaluated for up to 3 years prior and 1 year after RDN. The change in estimated glomerular filtration rate (eGFR) was calculated by regression slope individually for each patient before and after RDN. The study was registered at http://www.clinicaltrials.gov (ID: NCT01442883).Mean baseline BP was 156 ± 12/82 ± 13 mmHg, despite treatment with 6.2 ± 1.1 antihypertensive drugs. One year after RDN, office BP was reduced by 20 ± 20 (P < 0.001)/8 ± 14 mmHg (P = 0.005) and average 24-h ambulatory BP by 9 ± 14 (P = 0.009)/4 ± 7 mmHg (P = 0.019). Before RDN, eGFR declined by -4.8 ± 3.8 ml/min per 1.73 m per year, and after RDN eGFR improved by +1.5 ± 10 ml/min per 1.73 m at 12 months (P = 0.009).Our observational pilot study in patients with CKD stages 3 and 4 indicates that treatment of hypertension with RDN decreases BP and slows or even halts the decline of renal function.
EVALuna2:3767

Renal denervation Really an alternative to reducing blood pressure? - Striepe, Kristina; Schiffer, Mario; Schmieder, Roland (Internist, 2022)
Since the current guidelines were published in 2018, a total of 5 sham-controlled high-quality studies evaluating renal denervation have been conducted and the results were published. These five studies clearly confirmed the efficacy and safety of renal denervation, which correspond to the knowledge of the Clinical Consensus Conference. Thus, an update of the guidelines for the treatment of arterial hypertension regarding the clinical significance of renal denervation is urgently necessary. For this reason, the position paper of the working group of the European Society of Hypertension on the current state of renal denervation was reviewed. An approval of this procedure can soon be expected. In Germany there is a diagnosis-related group (DRG) for the reimbursement of renal denervation, which was suspended due to the erroneous Symplicity 3 study. This DRG should be revived in practice by a structured process of the implementation of renal denervation. It will then be a joint task of treating physicians and specialists in certified centers to identify eligible patients. In the future, antihypertensive treatment will consist of three pillars: lifestyle measures, pharmacotherapy and interventional treatment. These three treatment options should not be regarded as competitive (which is better) but alternative (patient preference) and additive (the aim is blood pressure control). It is the task of the treating physician to provide the patient with the ideal treatment concept. Clearly, renal denervation will not replace antihypertensive pharmacotherapy; however, it can lead to a reduction of the drug burden and increase of patient adherence to medication. It represents an option of modern antihypertensive treatment and will also become increasingly more important in special patient groups.
CRIS-Team WoS Importer:2022-01-21

Renal Denervation Update From the International Sympathetic Nervous System Summit: JACC State-of-the-Art Review - Kiuchi, Márcio G.; Esler, Murray D.; Fink, Gregory D.; Osborn, John W.; Banek, Christopher T.; Böhm, Michael; Denton, Kate M.; DiBona, Gerald F.; Everett, Thomas H.; Grassi, Guido; Katholi, Richard E.; Knuepfer, Mark M.; et al. (Journal of the American College of Cardiology, 2019)
Three recent renal denervation studies in both drug-naïve and drug-treated hypertensive patients demonstrated a significant reduction of ambulatory blood pressure compared with respective sham control groups. Improved trial design, selection of relevant patient cohorts, and optimized interventional procedures have likely contributed to these positive findings. However, substantial variability in the blood pressure response to renal denervation can still be observed and remains a challenging and important problem. The International Sympathetic Nervous System Summit was convened to bring together experts in both experimental and clinical medicine to discuss the current evidence base, novel developments in our understanding of neural interplay, procedural aspects, monitoring of technical success, and others. Identification of relevant trends in the field and initiation of tailored and combined experimental and clinical research efforts will help to address remaining questions and provide much-needed evidence to guide clinical use of renal denervation for hypertension treatment and other potential indications.
CRIS-Team Scopus Importer:2019-06-18
Keywords: blood pressure; cardiovascular disease; hypertension; renal denervation; sympathetic nervous system

Renal denervation: where do we stand and what is the relevance to the nephrologist? - Schmieder, Roland (Nephrology Dialysis Transplantation, 2022)
Catheter-based renal denervation to reduce high blood pressure (BP) has received well-deserved attention after a recent series of sham-controlled trials reported significant antihypertensive efficacy and very favourable tolerability and safety of the intervention. This emerging treatment option is of high relevance to nephrologists. Patients with chronic kidney disease (CKD) are at elevated risk of cardiovascular adverse events and often present with hypertension, which is very difficult to control with medication. Renal denervation promises a new tool to reduce BP and to prevent loss of renal function in this population. The current review considers the role of the kidney and neurohormonal activation in the development of hypertension and the rationale for renal denervation. The current state of the evidence for the effectiveness and tolerability of the procedure is considered from the nephrologists' perspective, with a focus on the potential future role of renal denervation in the management of CKD patients with hypertension.
CRIS-Team WoS Importer:2022-04-08

RENAL HEMODYNAMIC CHANGES AFTER RENAL DENERVATION - Schmieder, R. S.; Schmid, Axel; Janka, Rolf Matthias; Ditting, T.; Veelken, Roland; Uder, Michael; Schmieder, Roland; Ott, Christian (2016)
EVALuna2:34706

Renal hemodynamic effects differ between antidiabetic combination strategies: randomized controlled clinical trial comparing empagliflozin/linagliptin with metformin/insulin glargine - Ott, Christian; Jung, Susanne; Korn, Manuel; Kannenkeril, Dennis; Bosch, Agnes; Kolwelter, Julie; Striepe, Kristina; Bramlage, Peter; Schiffer, Mario; Schmieder, Roland (Cardiovascular Diabetology, 2021)
Background: Type 2 diabetes causes cardio-renal complications and is treated with different combination therapies. The renal hemodynamics profile of such combination therapies has not been evaluated in detail. Methods: Patients (N = 97) with type 2 diabetes were randomized to receive either empagliflozin and linagliptin (E+L group) or metformin and insulin glargine (M+I group) for 3 months. Renal hemodynamics were assessed with para-aminohippuric acid and inulin for renal plasma flow (RPF) and glomerular filtration rate (GFR). Intraglomerular hemodynamics were calculated according the Gomez´ model. Results: Treatment with E+L reduced GFR (p = 0.003), but RPF remained unchanged (p = 0.536). In contrast, M+I not only reduced GFR (p = 0.001), but also resulted in a significant reduction of RPF (p < 0.001). Renal vascular resistance (RVR) decreased with E+L treatment (p = 0.001) but increased with M+I treatment (p = 0.001). The changes in RPF and RVR were different between the two groups (both padjust < 0.001). Analysis of intraglomerular hemodynamics revealed that E+L did not change resistance of afferent arteriole (RA) (p = 0.116), but diminished resistance of efferent arterioles (RE) (p = 0.001). In M+I group RA was increased (p = 0.006) and RE remained unchanged (p = 0.538). The effects on RA (padjust < 0.05) and on RE (padjust < 0.05) differed between the groups. Conclusions: In patients with type 2 diabetes and preserved renal function treatment with M+I resulted in reduction of renal perfusion and increase in vascular resistance, in contrast to treatment with E+I that preserved renal perfusion and reduced vascular resistance. Moreover, different underlying effects on the resistance vessels have been estimated according to the Gomez model, with M+I increasing RA and E+L predominantly decreasing RE, which is in contrast to the proposed sodium-glucose cotransporter 2 inhibitor effects. Trial registration: The study was registered at www.clinicaltrials.gov (NCT02752113) on April 26, 2016
CRIS-Team Scopus Importer:2021-09-17
Keywords: Hemodynamics; Intraglomerular; Renal; Type 2 diabetes

RENAL IMAGING IN HYPERTENSION - Schmieder, Roland (JOURNAL OF HYPERTENSION, 2023)
CRIS-Team WoS Importer:2023-03-17

Renal impairment and worsening of renal function in acute heart failure: can new therapies help? The potential role of serelaxin - Schmieder, Roland; Mitrovic, Veselin; Hengstenberg, Christian (Clinical Research in Cardiology, 2015)
Renal dysfunction is a frequent finding in patients with acute heart failure (AHF) and an important prognostic factor for adverse outcomes. Worsening of renal function occurs in 30-50 % of patients hospitalised for AHF, and is associated with increased mortality, prolonged hospital stay and increased risk of readmission. Likely mechanisms involved in the decrease in renal function include impaired haemodynamics and activation of neurohormonal factors, such as the renin-angiotensin-aldosterone system, the sympathetic nervous system and the arginine-vasopressin system. Additionally, many drugs currently used to treat AHF have a detrimental effect on renal function. Therefore, pharmacotherapy for AHF should carefully take into account any potential complications related to renal function. Serelaxin, currently in clinical development for the treatment of AHF is a recombinant form of human relaxin-2, identical in structure to the naturally occurring human relaxin-2 peptide hormone that mediates cardiac and renal adaptations during pregnancy. Data from both pre-clinical and clinical studies indicate a potentially beneficial effect of serelaxin on kidney function. In this review, we discuss the mechanisms and impact of impairment of renal function in AHF, and the potential benefits of new therapies, such as serelaxin, in this context.
EVALuna2:3787

Renal outcomes and blood pressure patterns in diabetic and nondiabetic individuals at high cardiovascular risk - Böhm, Michael; Schumacher, Helmut; Teo, Koon K.; Lonn, Eva M.; Mahfoud, Felix; Emrich, Insa; Mancia, Giuseppe; Redon, Josep; Schmieder, Roland; Sliwa, Karen; Lehrke, Michael; Marx, Nikolaus; et al. (Journal of Hypertension, 2021)
BACKGROUND: Diabetes and hypertension are risk factors for renal and cardiovascular outcomes. Data on the association of achieved blood pressure (BP) with renal outcomes in patients with and without diabetes are sparse. We investigated the association of achieved SBP, DBP with renal outcomes and urinary albumin excretion (UAE) in people with vascular disease. METHODS: In this pooled analysis, we assessed renal outcome data from high-risk patients aged 55 years or older with a history of cardiovascular disease, 70% of whom had hypertension, randomized to The Ongoing Telmisartan Alone and in Combination with Ramipril Global Endpoint Trial and to Telmisartan Randomized Assessment Study in ACE Intolerant Subjects with Cardiovascular Disease trials investigating telmisartan, ramipril and their combination with a median follow-up of 56 months. Standardized office BP was measured every 6 months, estimated glomerular filtration rate (eGFR) and UAE at baseline, 2 years and study end. Associations of mean achieved BP on treatment were investigated on major renal outcomes including end-stage renal disease (ESRD), decline of eGFR by at least 40%, doubling of creatinine and the composites thereof and on UAE. Analyses were by Cox regression analysis, analysis of variance and Chi2-test. Of 30 937 patients with complete data, 19 450 patients without and 11 487 with diabetes were enrolled between 1 December 2001 and 31 July 2003 and followed until 31 July 2008. Data were pooled as the outcomes for telmisartan 80 mg/day (n = 2903) or placebo (n = 2907) for Telmisartan Randomized Assessment Study in ACE Intolerant Subjects with Cardiovascular Disease and ramipril 10 mg/day (n = 8407), telmisartan 80 mg/day (n = 8386) or the combination of both (n = 8334) were similar. RESULTS: For both those with and without diabetes, the hazard ratios for the composites ESRD or doubling of serum creatinine (707 events overall) and ESRD or 40% eGFR loss (2371 events overall) reached a nadir at achieved SBP of 120 to less than 140 mmHg, and increased with higher and lower SBP with similar relative risk with or without diabetes. For example, risk for the former composite reached a hazard ratios 3.06 (confidence interval 1.90-4.92) with a mean achieved SBP more than 160 mmHg compared with 120 to less than 130 mmHg with diabetes and hazard ratios 2.14 (1.09-4.26) without diabetes. In contrast, the development of new microalbuminuria and macroalbuminuria (3002 and 846 events overall) associated linearly over the whole range of achieved SBP (apart from a slight increase in risk at SBP less than 120 mmHg only in those without diabetes). Absolute risks for the composite and albuminuria outcomes were consistently greater in those with diabetes as compared with without diabetes with high event rates over the whole SBP spectrum. The increased renal risk at low SBP was not related to a meaningful reduction of mandated study drugs or open label renin-angiotensin-aldosterone system inhibition. CONCLUSION: In patients at high cardiovascular risk, SBP levels more than 140 mmHg and less than 120 are associated with increased risk for renal outcomes. Renal risk was greater in diabetes across the whole range of achieved SBP and DBP. These data suggest similar target BP range in patients with and without diabetes to prevent renal outcomes, a frequent complication in high-risk vascular patients. CLINICAL TRIAL REGISTRATION: Clinical Trial registration: http://clinicaltrials.gov.Unique identifier: NCT00153101.
CRIS-Team Scopus Importer:2021-04-19

Renin Uptake by the Endothelium Mediates Vascular Angiotensin Formation - Hilgers, Karl Friedrich; Veelken, Roland; Müller, Dominik N.; Kohler, Hans; Hartner, Andrea; Botki, Suzanne R.; Stumpf, Christian; Schmieder, Roland; Gomez, Ariel (Hypertension, 2001)
We investigated the role of the vascular endothelium in the local production of angiotensin. Angiotensin release from isolated rat hindquarters perfused with an artificial medium was measured by high-performance liquid chromatography and radioimmunoassay. Perfused hindquarters with endothelium released angiotensin I spontaneously, indicating ongoing renin-angiotensinogen reaction. Endothelium denudation (by a detergent, validated by electron microscopy and by the absence of a vasodilator response to acetylcholine) reduced angiotensin I release by >90%, whereas bilateral nephrectomy 24 hours before perfusion abolished the release completely. Infusion of renin into perfused hindquarters induced sustained local angiotensin I release in the presence of an intact endothelium but not after endothelium denudation. The conversion of angiotensin I to angiotensin II was abrogated by endothelium denudation, whereas the disappearance of angiotensin II was unchanged. Endothelium denudation diminished the pressor response to angiotensin II but abolished the response to renin and angiotensin I. Expression of renin messenger RNA, investigated by reverse-transcription polymerase chain reaction using 4 different primer combinations, was not detected in up to 5 μg vascular RNA, whereas a renin signal was readily detected with 5 ng kidney RNA. The effects of endothelium destruction on Ang I formation support the notion that the endothelium mediates vascular angiotensin formation by taking up reni
Keywords: renin; angiotensin; angiotensinogen; mRNA; vessels; perfusion; endothelium

Reply - Schmieder, Roland; Mahfoud, Felix (Journal of Hypertension, 2019)
EVALuna2:118641

Reply to comment on Cost of poor adherence to anti-hypertensive therapy in five European country - Mennini, F S; Marcellusi, Andrea; von der Schulenburg, J M Graf; Gray, A; Levy, P; Sciattella, P; Soro, M; Staffiero, G; Zeidler, J; Maggioni, A; Schmieder, Roland (European Journal of Health Economics, 2015)
EVALuna:29545

Reproducibility of Kidney Perfusion Measurements With Arterial Spin Labeling at 1.5 Tesla MRI Combined With Semiautomatic Segmentation for Differential Cortical and Medullary Assessment - Hammon, Matthias; Janka, Rolf Matthias; Siegl, Christian; Seuß, Hannes; Grosso, Roberto; Martirosian, Petros; Schmieder, Roland; Uder, Michael; Kistner, Iris (Medicine, 2016)
Magnetic resonance imaging with arterial spin labeling (ASL) is a noninvasive approach to measure organ perfusion. The purpose of this study was to evaluate the reproducibility of ASL kidney perfusion measurements with semiautomatic segmentation, which allows separate quantification of cortical and medullary perfusion.The right kidneys of 14 healthy volunteers were examined 6 times on 2 occasions (3 times at each occasion). There was a 10-minute pause between each examination and a 14-day interval between the 2 occasions. Cortical, medullary, and whole kidney parenchymal perfusion was determined with customized semiautomatic segmentation software. Coefficient of variances (CVs) and intraclass correlations (ICCs) were calculated.Mean whole, cortical, and medullary kidney perfusion was 307.26 ± 25.65, 337.10 ± 34.83, and 279.61 ± 26.73 mL/min/100 g, respectively. On session 1, mean perfusion for the whole kidney, cortex, and medulla was 307.08 ± 26.91, 336.79 ± 36.54, and 279.60 ± 27.81 mL/min/100 g, respectively, and on session 2, 307.45 ± 24.65, 337.41 ± 33.48, and 279.61 ± 25.94 mL/min/100 g, respectively (P > 0.05; R = 0.60/0.59/0.54). For whole, cortical, and medullary kidney perfusion, the total ICC/CV were 0.97/3.43 ± 0.86%, 0.97/4.19 ± 1.33%, and 0.96/4.12 ± 1.36%, respectively. Measurements did not differ significantly and showed a very good correlation (P > 0.05; R = 0.75/0.76/0.65).ASL kidney measurements combined with operator-independent semiautomatic segmentation revealed high correlation and low variance of cortical, medullary, and whole kidney perfusion.
EVALuna2:3854

Response of Blood Pressure to Renal Denervation Is Not Associated with Genetic Variants - Delles, Christian; Schmieder, Roland; Daly, Rónán; Kannenkeril, Dennis; Bosch, Agnes; Lauder, Lucas; Kunz, Michael; Böhm, Michael; Hamilton, Graham; Schmieder, Raphael; Schmid, Axel; Herzyk, Pawel; et al. (Hypertension, 2024)
BACKGROUND: Renal denervation lowers blood pressure (BP) in patients with uncontrolled hypertension. We conducted an unbiased genomic screen to identify genetic variants that may associate with BP response to renal denervation (RDN). METHODS: Patients (n=268) with uncontrolled resistant hypertension (baseline BP, 166±21/90±15 mm Hg) who underwent endovascular RDN using the Symplicity catheter (Medtronic, Inc, Santa Rosa, CA) were included. Reduction in 24-hour ambulatory systolic BP was assessed at 6 months and divided into 2 groups: above and below the median response of 6.0 mm Hg, taking preintervention 24-hour ambulatory BP and regression to the mean into account. Whole exome sequencing assessing 249 669 variants, was conducted using Illumina NovaSeq technology read on a NovaSeq S4 Flow Cell device. RESULTS: We did not identify individual gene variants associated with BP response following RDN. These findings were confirmed after adjustment for sex and in a sensitivity analysis looking at tertiles of BP response. We also explored specific variants in AGT, ADD1, ADRB1, ADRB2, and SCNN1A that have been proposed as potential candidate genes for response and found no association (all P>0.13). Gene ontology analysis of variants across the 2 responder groups highlighted differences in biologic processes such as cell adhesion and molecular function such as protein tyrosine kinase activity. CONCLUSIONS: The response to RDN, in terms of 24-hour BP reduction, was not associated with the genetic profile of patients with resistant hypertension. These data do not support the use of a genetic score to identify potential responders to RDN.
CRIS-Team Scopus Importer:2024-12-06
Keywords: blood pressure; catheters; genetic profile; genomics; hypertension

Response to: Cavagna et al The importance of considering cultural and environmental elements in an interventional model of care to fight hypertension in Africa - Otieno, Harun A.; Miezah, Charles; Yonga, Gerald; Kueffer, Fred; Guy, Molly; Lang’at, Chemuttaai; Hettrick, Douglas A.; Schmieder, Roland (Journal of Clinical Hypertension, 2021)
CRIS-Team Scopus Importer:2021-04-09

Response to letter regarding article, "ambulatory blood pressure changes after renal sympathetic denervation in patients with resistant hypertension" - Mahfoud, Felix; Ukena, Christian; Schmieder, Roland; Cremers, Bodo; Rump, Lars C.; Vonend, Oliver; Weil, Joachim; Schmidt, Martin; Hoppe, Uta C.; Zeller, Thomas; Bauer, Axel; Ott, Christian; et al. (Circulation, 2014)
EVALuna2:3677

Response to ‘Why the lack of enthusiasm for renal denervation?’ - Sharp, Andrew S.P.; Sanderson, Alice; Hansell, Neil; Reddish, Katie; Miller, Paul; Moss, Joe; Schmieder, Roland; McCool, Rachael (Journal of Hypertension, 2024)
CRIS-Team Scopus Importer:2024-11-15

Responsiveness of afferent renal nerve units in renovascular hypertension in rats - Rodionova, Kristina; Hilgers, Karl Friedrich; Rafii-Tabrizi, Salman; Doellner, Johannes; Cordasic, Nada; Linz, Peter; Karl, Annalena; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; et al. (Pflügers Archiv: European Journal of Physiology, 2021)
Previous data suggest that renal afferent nerve activity is increased in hypertension exerting sympathoexcitatory effects. Hence, we wanted to test the hypothesis that in renovascular hypertension, the activity of dorsal root ganglion (DRG) neurons with afferent projections from the kidneys is augmented depending on the degree of intrarenal inflammation. For comparison, a nonhypertensive model of mesangioproliferative nephritis was investigated. Renovascular hypertension (2-kidney, 1-clip [2K1C]) was induced by unilateral clipping of the left renal artery and mesangioproliferative glomerulonephritis (anti-Thy1.1) by IV injection of a 1.75-mg/kg BW OX-7 antibody. Neuronal labeling (dicarbocyanine dye [DiI]) in all rats allowed identification of renal afferent dorsal root ganglion (DRG) neurons. A current clamp was used to characterize neurons as tonic (sustained action potential [AP] firing) or phasic (1-4 AP) upon stimulation by current injection. All kidneys were investigated using standard morphological techniques. DRG neurons exhibited less often tonic response if in vivo axonal input from clipped kidneys was received (30.4% vs. 61.2% control, p < 0.05). However, if the nerves to the left clipped kidneys were cut 7 days prior to investigation, the number of tonic renal neurons completely recovered to well above control levels. Interestingly, electrophysiological properties of neurons that had in vivo axons from the right non-clipped kidneys were not distinguishable from controls. Renal DRG neurons from nephritic rats also showed less often tonic activity upon current injection (43.4% vs. 64.8% control, p < 0.05). Putative sympathoexcitatory and impaired sympathoinhibitory renal afferent nerve fibers probably contribute to increased sympathetic activity in 2K1C hypertension.
CRIS-Team WoS Importer:2021-07-23

Resting heart rate is associated with renal disease outcomes in patients with vascular disease: results of the ONTARGET and TRANSCEND studies - Boehm, M.; Schumacher, H.; Schmieder, Roland; Mann, J. F. E.; Teo, K.; Lonn, E.; Sleight, P.; Mancia, G.; Linz, D.; Mahfoud, F.; Ukena, C.; Sliwa, K.; et al. (Journal of Internal Medicine, 2015)
Resting heart rate (RHR) is associated with cardiovascular disease outcomes in high-risk patients. It is not known whether RHR is predictive of renal outcomes such as albuminuria, end-stage renal disease (ESRD) or doubling of creatinine. We evaluated whether RHR could predict renal endpoints in patients at a high risk of cardiovascular disease. We also tested the effects of RHR at different levels of systolic blood pressure (SBP).We analysed data from 28 757 patients in the ONTARGET and TRANSCEND trials. RHR and SBP were available for a mean of 4.9 ± 0.4 visits (range 3-5) within the first 2 years of the studies. Albuminuria was determined at baseline, at 2 years and at study end.Mean RHR was predictive of incident micro-albuminuria [hazard ratio (HR) for RHR >=80 vs. <60 beats min(-1) 1.49, 95% confidence interval (CI) 1.29-1.71, P < 0.0001], incident macro-albuminuria (HR 1.84, 95% CI 1.39-2.42, P < 0.0001), doubling of creatinine (HR 1.47, 95% CI 1.00-2.17, P = 0.050) and ESRD (HR 1.78, 95% CI 1.00-3.16, P = 0.050), and the combined renal end-point (HR 1.51, 95% CI 1.32-1.74, P < 0.0001). Associations were robust at SBPs from <120 to >=150 mmHg, with the lowest risk at a SBP of 130-140 mmHg.Resting heart rate is a potent predictor of these renal outcomes, as well as their combination, in patients with cardiovascular disease. RHR at all SBP levels should be considered as a possible renal disease risk predictor and should be investigated as a treatment target with RHR-reducing agents.
EVALuna2:3749

Retinal arterial remodeling in patients with pheochromocytoma or paraganglioma and its reversibility following surgical treatment - Gosk-Przybylek, Maria; Doroszko, Adrian; Dobrowolski, Piotr; Warchol-Celinska, Ewa; Harazny, Joanna; Binczyk, Ewelina; Szymanek, Katarzyna; Peczkowska, Mariola; Kabat, Marek; Toutounchi, Sadegh; Galazka, Zbigniew; Gornicka, Barbara; et al. (Journal of Hypertension, 2020)
OBJECTIVE: Structural abnormalities in resistance arteries are a hallmark of patients with hypertension. In hypertensive patients with pheochromocytoma or paraganglioma (PPGL), it is still a matter of debate whether structural vascular changes are because of elevated blood pressure (BP) or to toxic effects of elevated circulating catecholamines. Hence, the aim of our study was to assess whether catecholamine excess and/or elevated BP affect the structure of small retinal arteries in patients with catecholamine-producing tumors. METHODS: The study included 27 patients with PPGL and 27 hypertensive patients. All patients underwent biochemical tests for catecholamine excess, echocardiography and analyses of scanning-laser-Doppler-flowmetry (SLDF) both at baseline and 12 months following surgical resection of PPGL. RESULTS: Baseline retinal arterial diameter, arterial wall thickness and wall cross sectional area (WCSA) were higher in patients with PPGL as compared with subjects without PPGL (arterial diameter: 110 ± 16.5 vs. 99.5 ± 10.8 μm, wall thickness: 16.3 ± 6.0 vs. 13.5 ± 4.0 μm, WCSA: 4953.9 ± 2472.8 vs. 3784.1 ± 1446.3 μm, P < 0.05). Significant correlations were noted between wall thickness and WCSA and echocardiographic parameters assessing diastolic and systolic function of left ventricle. No correlations between retinal parameters, BP level and plasma concentrations of metanephrines were observed. In patients with PPGL, there were postoperative decreases in wall thickness (16.4 ± 15.8 vs. 14.8 ± 4.7 μm; P = 0.011) and WLR (0.42 ± 0.13 vs. 0.37 ± 0.10; P = 0.003) at 12 months after surgical removal of tumors. CONCLUSION: This is the first study to demonstrate that catecholamine excess is related to thickening of retinal arteries independent of BP and reversible after surgical cure. These data support a role of catecholamines in vascular remodeling in PPGL patients.
CRIS-Team Scopus Importer:2020-07-31

Retinal capillary and arteriolar changes in patients with chronic kidney disease - Bosch, Agnes; Scheppach, Johannes B.; Harazny, Joanna M.; Raff, Ulrike; Schmieder, Roland; Schneider, Markus; Eckardt, Kai-Uwe (Microvascular Research, 2018)
RATIONALE: Premature cardiovascular disease is a leading cause of death in patients with chronic kidney disease (CKD). In animal models CKD has been shown to cause renal and extrarenal vascular remodeling and capillary rarefaction, but data in humans with CKD are sparse. Retinal arteriolar wall-to-lumen ratio (WLR) is an established marker of early end-organ damage and there is evidence that arteriolar and capillary changes in the retinal circulation mirror those in the general and in particular the cerebrovascular microcirculation. OBJECTIVE: The aim of this study was to compare retinal capillary density and arteriolar structure between patients with CKD and healthy individuals. METHODS: We compared 76 patients with CKD stage 3+ or proteinuria >500 mg/g creatinine in the presence of a normal GFR from the German Chronic Kidney Disease cohort to 53 healthy control subjects, who participated in clinical trials during 2007 and 2015 in our Clinical Research Center. Retinal vascular parameters were measured non-invasively in vivo by scanning laser Doppler Flowmetry (SLDF, Heidelberg Engineering, Germany). Capillary rarefaction was assessed by intercapillary distance. RESULTS: Patients with CKD showed greater WLR (0.403 ± 0.11 vs 0.351 ± 0.11, p = 0.010) and greater wall thickness (WT) (15.1 ± 4.1 vs 13.5 ± 3.8, p = 0.026) compared to healthy individuals. Intercapillary distance (ICD) (22.4 ± 5.7 vs 20.2 ± 4.1, p = 0.008) was greater in the CKD group compared to the healthy control group. After adjustment for differences in clinical characteristics of the groups (age, gender, BMI, serum cholesterol) WLR (p = 0.046), WT (p = 0.025) and ICD (p = 0.003) remained significantly different between the two groups. There was a correlation between serum phosphate level and WLR in the CKD group (r = 0.288, p = 0.013). CONCLUSION: Patients with moderately severe CKD show retinal signs of end-organ damage indicated by an increased wall-to-lumen ratio and capillary rarefaction.
EVALuna2:34237

Retinal Capillary Rarefaction in Patients with Type 2 Diabetes Mellitus - Jumar, Agnes; Harazny, Joanna M.; Ott, Christian; Friedrich, Stefanie; Kistner, Iris; Striepe, Kristina; Schmieder, Roland (PLoS ONE, 2016)
In diabetes mellitus type 2, capillary rarefaction plays a pivotal role in the pathogenesis of end-organ damage. We investigated retinal capillary density in patients with early disease.This cross-sectional study compares retinal capillary rarefaction determined by intercapillary distance (ICD) and capillary area (CapA), measured non-invasively and in vivo by scanning laser Doppler flowmetry, in 73 patients with type 2 diabetes, 55 healthy controls and 134 individuals with hypertension stage 1 or 2.In diabetic patients, ICD was greater (23.2±5.5 vs 20.2±4.2, p = 0.013) and CapA smaller (1592±595 vs 1821±652, p = 0.019) than in healthy controls after adjustment for differences in cardiovascular risk factors between the groups. Compared to hypertensive patients, diabetic individuals showed no difference in ICD (23.1±5.8, p = 0.781) and CapA (1556±649, p = 0.768).In the early stage of diabetes type 2, patients showed capillary rarefaction compared to healthy individuals.
EVALuna2:3920

Retinal capillary rarefaction in patients with untreated mild-moderate hypertension - Bosch, Agnes J.; Harazny, Joanna M.; Kistner, Iris; Friedrich, Stefanie; Wojtkiewicz, Joanna; Schmieder, Roland (Bmc Cardiovascular Disorders, 2017)
Microvascular rarefaction influences peripheral vascular resistance, perfusion and metabolism by affecting blood pressure and flow pattern. In hypertension microvascular rarefaction has been described in experimental animal studies as well as in capillaroscopy of skin and biopsies of muscle tissue in patients. Retinal circulation mirrors cerebral microcirculation and allows non-invasive investigations. We compared capillary rarefaction of retinal vessels in hypertensive versus normotensive subjects.In this study retinal capillary rarefaction in 70 patients with long time (more than 67 month of disease duration) and 64 patients with short time hypertension stage 1 or 2 has been compared to 55 healthy control subjects, who participated in clinical trials in our Clinical Research Center ( www.clinicaltrials.gov : NCT01318395, NCT00627952, NCT00152698, NCT01319344). Retinal vascular parameters have been measured non-invasively and in vivo in perfusion image by scanning laser Doppler flowmetry (Heidelberg Engineering, Germany). Capillary rarefaction was assessed by capillary area (CapA) (in pixel-number) and intercapillary distance (ICD) (in ?m). Additionally retinal capillary flow (RCF) was measured.ICD was greater in the long time hypertensive group compared to healthy individuals (24.2 ± 6.3 ?m vs 20.1 ± 4.2 ?m, p = 0.001) and compared to short time hypertensive patients (22.2 ± 5.2 ?m, p = 0.020). Long time hypertensive patients showed less CapA compared to healthy people (1462 ± 690 vs 1821 ± 652, p = 0.005). Accordingly, RCF was significantly lower in the long time hypertensive group compared to the healthy control group (282 ± 70 AU vs 314 ± 60 AU, p = 0.032). Our data indicate a lower level of retinal capillary density in hypertensive patients, especially in those with long time hypertension.Patients with hypertension stage 1 or 2 showed retinal capillary rarefaction in comparison to healthy normotensive subjects. Retinal capillary rarefaction was intensified with duration of disease.
EVALuna2:4038

Retinal microperfusion after renal denervation in treatment-resistant hypertensive patients - Ott, Christian; Harazny, Joanna M.; Schmid, Axel; Ditting, Tilmann; Veelken, Roland; Bladowski, Marek; Michelson, Georg; Uder, Michael; Schmieder, Roland (Clinical Research in Cardiology, 2015)
High pulsatile pressure and flow in the arteries causes microvascular damage, and hence increased cardio-, and cerebrovascular complications. With advanced stages of hypertensive disease, an exaggerated pulsatile retinal capillary flow (RCF) has been shown, but data about interventional effect are missing.Fifty-one patients with true treatment-resistant hypertension (TRH) underwent renal denervation (RDN) using the Symplicity Flex(TM) catheter and were followed for 12 months. RCF was assessed non-invasively using Scanning laser Doppler flowmetry (SLDF) before, 6 (6 M), and 12 (12 M) months after RDN. RCF was measured in systole and diastole and pulsed RCF (difference of RCF in systole minus diastole) was calculated. In addition, flicker light-induced vasodilation (representing vasodilatory capacity) was assessed.Systolic and diastolic office blood pressure (BP) as well as 24-h ABPM decreased significantly 6 M and 12 M after RDN, compared to baseline values (all p < 0.001). There was a significant reduction of pulsed RCF 6 M (231 ± 81 versus 208 ± 68 AU, p = 0.046) and 12 M (194 ± 72 AU, p = 0.001) after RDN, whereas the mean RCF was unchanged. Moreover, there was a significant increase of flicker light-induced vasodilation after RDN (p = 0.043).In hypertensive patients with TRH, we observed a decrease of pulsed RCF 6 M and 12 M after RDN and an increase of vasodilatory capacity, in parallel to decreases in BP and heart rate. The reduction of pulsed RCF after RDN implies a decrease of shear stress on the vascular wall by the pulsed blood flow. This and the increment of vasodilatory capacity suggest an improvement of retinal (and potentially cerebral) microcirculation.
EVALuna2:3762

Retinal neurodegeneration in patients with end-stage renal disease assessed by spectral-domain optical coherence tomography - Jung, Susanne; Bosch, Agnes; Ott, Christian; Kannenkeril, Dennis; Dienemann, Thomas; Harazny, Joanna M.; Michelson, Georg; Schmieder, Roland (Scientific Reports, 2020)
Spectral-domain optical coherence tomography (SD-OCT) represents a reliable tool for retinal layer volume and thickness measurement. The aim of this study was to evaluate retinal changes indicating neurodegenerative processes in patients with end-stage renal disease (ESRD) compared to healthy controls. This was a cross-sectional, single-center study comprising 32 ESRD patients and 38 controls. Sectoral retinal nerve fiber layer (RNFL) thickness and retinal layer volumes were obtained by SD-OCT. Age- and gender-adjusted retinal layer volumes such as total retinal volume (p = 0.037), ganglion cell layer volume (GCL, p = 0.003), ganglion cell layer – inner plexiform layer volume (GCL-IPL, p = 0.005) and inner retinal layer volume (IRL, p = 0.042) of the right eye were lower in ESRD patients. Inner plexiform layer volume of both eyes (IPL, right eye: p = 0.017; left eye: 0.044) was reduced, as was RNFL thickness in the temporal superior sector (right eye: p = 0.016). A subgroup analysis excluding patients with diabetes revealed that GCL (p = 0.014) and GCL-IPL volume of the right eye (p = 0.024) and temporal superior sector of the RNFL scan (p = 0.021) in ESRD patients were still significantly thinner. We observed a decrease in several retinal layer volumes and temporal RNFL thickness indicative of retinal neurodegenerative processes in patients with ESRD.
CRIS-Team Scopus Importer:2020-04-03

Retinal vascular resistance in arterial hypertension - Kannenkeril, Dennis; Harazny, Joanna M.; Bosch, Agnes; Ott, Christian; Michelson, Georg; Schmieder, Roland; Friedrich, Stefanie (Blood Pressure, 2017)
Retinal microcirculation represents an easily accessible, non-invasive, in-vivo possibility to assess early microvascular changes. In addition to the assessment of functional (e.g. retinal capillary flow, RCF) and retinal arteriolar structural parameters (e.g. wall-to-lumen-ratio, WLR) we now suggest a new parameter reflecting the resistance in small retinal arterioles (RVR).In 45 normotensive (NT) subjects and 123 patients with hypertension stage 1 (HT) we assessed RCF, WLR, arteriolar diameter, lumen diameter and wall cross section area in the retinal circulation by using scanning laser Doppler flowmetry (SLDF). Mean arterial pressure (MAP) was measured immediately before the SLDF measurement and retinal vascular resistance was calculated (RVR = MAP/RCF). In a separate study the test-retest reliability was determined in 6 volunteers from our clinical staff by assessing RVR three times within six weeks.The analysis of the volunteers revealed a coefficient of variation for RVR of 7.75 ± 2.11% and Cronbach´s alpha was 0.90. WLR, a marker of vascular remodeling did not differ between NT and HT. In contrast, RCF and inner diameter of the retinal arterioles (ID) were significantly lower (RCF: p = .045 and ID: p = .001) in the HT group than in the NT group and RVR was significantly higher in the HT group than in the NT group (p < .001). In both groups we found no correlation of RVR with age, but a significant correlation of RVR with WLR (NT: r = 0.34, p = .006; HT: r = 0.25, p = .01), indicating that the RVR reflects vascular remodeling in the retinal circulation.Our data showed an increased retinal vascular resistance in hypertensive patients compared to non-hypertensive patients prior to the occurrence of structural retinal vascular remodeling. The correlation between RVR and WLR indicates that RVR is a reliable, non-invasive and early-sensitive marker of vascular remodeling in early hypertension.
EVALuna2:4030

S2k guidelines for the diagnosis and treatment of type B aortic dissection - Torsello, G.; Czerny, M.; Grundmann, R. T.; Krankenberg, H.; Nikol, S.; Puls, R.; Raddatz, A.; Schelzig, H.; Schmieder, Roland; Zahn, R. (Gefässchirurgie, 2019)
Type B aortic dissection is a relatively rare clinical picture that involves many fields of medicine and requires a multidisciplinary approach. In this report, the disciplines involved constitute the most important aspects of the new S2k guidelines for the diagnosis and treatment of type B aortic dissection. More specifically, the definition and epidemiology, the clinical and technical diagnostic methods, in addition to the imaging methods, are presented, and recommendations for the individual topics based on scientific studies and expert opinion are given. In the guidelines, the various procedures related to the main conservative and surgical treatment regimes in the acute, subacute, and chronic phases of the condition are dealt with.
CRIS-Team WoS Importer:2019-02-27

Safety and effectiveness of a fixed-dose combination of olmesartan, amlodipine, and hydrochlorothiazide in clinical practice - Bramlage, Peter; Fronk, Eva Maria; Wolf, Wolf Peter; Smolnik, RüDiger; Sutton, Gemma; Schmieder, Roland (Vascular Health and Risk Management, 2015)
Clinical trials indicate that the use of fixed-dose combinations (FDCs) is associated with a higher level of treatment adherence and prolonged blood pressure (BP) control. The aim of this study was to document the safety and effectiveness of the FDC olmesartan/amlodipine/hydrochlorothiazide in patients with essential hypertension in clinical practice.This multicenter, prospective, 24-week, noninterventional study enrolled 5,831 patients from primary care offices in Germany and Austria. Inclusion criteria were a diagnosis of essential hypertension and newly initiated treatment with the FDC.The mean age of patients was 63.5 years, almost 50% of patients had a time since diagnosis of essential hypertension of over 5 years, and approximately 70% of patients had at least one cardiovascular risk factor, including 29.4% of patients with diabetes mellitus. Following approximately 24 weeks of treatment, the mean reduction in systolic/diastolic BP was 29.0/14.0 mmHg, a BP response was observed by 94.2% of patients, and a target BP of <140/90 mmHg was attained in 67.5% of patients. At least one adverse drug reaction (ADR) was experienced by 1.2% of patients, with the most common being peripheral edema. Subanalyses demonstrated that the following factors did not have a significant influence on the ADR rate: age (<65 years versus >=65 years), diabetes mellitus (no/yes), cardiovascular risk (low/high), and concomitant medication (no/yes).This study demonstrates that in clinical practice, treatment with the three-drug combination as an FDC tablet resulted in a very high proportion of patients with a BP response and control, accompanied by a very low rate of ADRs.
EVALuna2:3750

Salt intake determines retinal arteriolar structure in treatment resistant hypertension independent of blood pressure - Raff, Ulrike; Harazny, Joanna M.; Titze, Stephanie; Schmidt, Bernhard Magnus Wilhelm; Michelson, Georg; Schmieder, Roland (Atherosclerosis, 2012)
Patients with treatment resistant hypertension are at increased risk of developing cardiovascular end organ damage. The role of sodium in end organ damage is gaining interest and an independent association of sodium and cardiovascular morbidity and mortality has been described.In an observational study including 40 patients with treatment resistant hypertension, we analysed retinal arteriolar structure in vivo as a determinant of remodelling of small resistant vessels (wall/lumen ratio, wall thickness, wall cross section area) using scanning laser Doppler flowmetry and automatic full-field perfusion imaging analysis. Urinary sodium excretion was determined by 24h urine sample and, in parallel 24h ambulatory blood pressure was measured. We analysed the association of the retinal arterial structure with urinary sodium excretion and blood pressure.Wall to lumen ratio, wall thickness and wall cross section area were strongly associated with urinary sodium excretion but not with 24h blood pressure. In a multiple regression analysis including urinary sodium excretion, BMI, age and 24h blood pressure, urinary sodium excretion emerged as the only independent determinant of wall thickness (?=0.432, p=0.01), and wall cross section area (?=0.439, p=0.008).Our results clearly demonstrate that salt intake influences the structure of retinal arterioles independent of blood pressure in treatment resistant hypertension. Considering the morphologic relation of retinal arteriolar and cerebral vascular structure these results might prove to have important implications on risk stratification in patients with treatment resistant hypertension.
EVALuna2:3574

Scientific Data and Transparency of Conflict of Interest Are Important, Not Biased Editorial Without Facts - Schmieder, Roland; Neuzil, Petr (Jacc-Cardiovascular Interventions, 2016)
EVALuna2:3909

Screening and management of hypertensive patients with chronic kidney disease referred to Hypertension Excellence Centres among 27 countries. A pilot survey based on questionnaire - Halimi, Jean Michel; Sarafidis, Pantelis; Azizi, Michel; Bilo, Grzegorz; Burkard, Thilo; Bursztyn, Michael; Camafort, Miguel; Chapman, Neil; Cottone, Santina; de Backer, Tine; Deinum, Jaap; Delmotte, Philippe; et al. (Journal of Hypertension, 2024)
Objective: Real-life management of hypertensive patients with chronic kidney disease (CKD) is unclear. Methods: A survey was conducted in 2023 by the European Society of Hypertension (ESH) to assess management of CKD patients referred to ESH-Hypertension Excellence Centres (ESH-ECs) at first referral visit. The questionnaire contained 64 questions with which ESH-ECs representatives were asked to estimate preexisting CKD management quality. Results: Overall, 88 ESH-ECs from 27 countries participated (fully completed surveys: 66/88 [75.0%]). ESH-ECs reported that 28% (median, interquartile range: 15–50%) had preexisting CKD, with 10% of them (5–30%) previously referred to a nephrologist, while 30% (15–40%) had resistant hypertension. The reported rate of previous recent (<6months) estimated glomerular filtration rate (eGFR) and urine albumin–creatinine ratio (UACR) testing were 80% (50–95%) and 30% (15–50%), respectively. The reported use of renin-angiotensin system blockers was 80% (70–90%). When a nephrologist was part of the ESH-EC teams the reported rates SGLT2 inhibitors (27.5% [20 – 40%] vs. 15% [10 – 25], P ¼ 0.003), GLP1-RA (10% [10 – 20%] vs. 5% [5 – 10%], P ¼ 0.003) and mineralocorticoid receptor antagonists (20% [10 – 30%] vs. 15% [10 – 20%], P ¼ 0.05) use were greater as compared to ESH-ECs without nephrologist participation. The rate of reported resistant hypertension, recent eGFR and UACR results and management of CKD patients prior to referral varied widely across countries. Conclusions: Our estimation indicates deficits regarding CKD screening, use of nephroprotective drugs and referral to nephrologists before referral to ESH-ECs but results varied widely across countries. This information can be used to build specific programs to improve care in hypertensives with CKD.
CRIS-Team Scopus Importer:2024-08-16
Keywords: albuminuria; chronic kidney disease; glomerular filtration rate; hypertension; management; screening

Secretory Capacity of Pancreatic Beta-Cells Is Enhanced 6 Months After Renal Denervation in Hypertensive Patients - Ott, Christian; Schmid, Axel; Mahfoud, Felix; Akarca, Ertan; Kistner, Iris; Ditting, Tilmann; Veelken, Roland; Boehm, Michael; Uder, Michael; Schmieder, Roland (Journal of the American College of Cardiology, 2018)
EVALuna2:35226

Semaglutide in patients with overweight or obesity and chronic kidney disease without diabetes: a randomized double-blind placebo-controlled clinical trial - Apperloo, Ellen M.; Gorriz, Jose L.; Soler, Maria Jose; Cigarrán Guldris, Secundino; Cruzado, Josep M.; Puchades, Maria Jesús; López-Martínez, Marina; Waanders, Femke; Laverman, Gozewijn D.; van der Aart-van der Beek, Annemarie; Hoogenberg, Klaas; van Beek, André P.; et al. (Nature Medicine, 2024)
Semaglutide reduces albuminuria and the risk of kidney disease progression in patients with type 2 diabetes and chronic kidney disease (CKD). We conducted a randomized placebo-controlled double-blind clinical trial in adults with CKD (estimated glomerular filtration rate (eGFR) ≥25 ml min−1 1.73 m−2 and urine albumin-to-creatinine ratio (UACR) ≥30 and <3,500 mg g−1) and body mass index ≥27 kg m−2. Participants were randomized to semaglutide 2.4 mg per week or placebo. The primary endpoint was percentage change from baseline in UACR at week 24. Safety was monitored throughout. Overall, 125 participants were screened, of whom 101 were randomized to semaglutide (n = 51) or placebo (n = 50). Mean age was 55.8 (s.d. 12) years; 40 participants (39.6%) were female; median UACR was 251 mg g−1 (interquartile range 100, 584); mean eGFR was 65.0 (s.d. 25) ml min−1 1.73 m−2; and mean body mass index was 36.2 (s.d. 5.6) kg m−2. Chronic glomerulonephritis (n = 25) and hypertensive CKD (n = 27) were the most common CKD etiologies. Treatment for 24 weeks with semaglutide compared to placebo reduced UACR by −52.1% (95% confidence interval −65.5, −33.4; P < 0.0001). Gastrointestinal adverse events were more often reported with semaglutide (n = 30) than with placebo (n = 15). Semaglutide treatment for 24 weeks resulted in a clinically meaningful reduction in albuminuria in patients with overweight/obesity and non-diabetic CKD. ClinicalTrials.gov registration: NCT04889183.
CRIS-Team Scopus Importer:2025-02-04

SEMI-AUTOMATIC MEASUREMENT OF INTIMA-MEDIA THICKNESS OF BRACHIAL ARTERY IN PATIENTS WITH CONGESTIVE HEART FAILURE - Kannenkeril, Dennis; Kolwelter, Julie; Pietschner, Robert; Striepe, Kristina; Bosch, Agnes; Achenbach, Stephan; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2022)
CRIS-Team WoS Importer:2023-02-17

SEMI-AUTOMATIC MEASUREMENT OF INTIMA-MEDIA THICKNESS OF BRACHIAL ARTERY IN PATIENTS WITH CONGESTIVE HEART FAILURE - Kannenkeril, Dennis; Kolwelter, Julie; Pietschner, Robert; Striepe, Kristina; Bosch, Agnes; Achenbach, Stephan; Schmieder, Roland (Journal of Hypertension, 2022)
OBJECTIVE: Cardiovascular diseases are associated with an increase in intima-media thickness (IMT). However, the techniques used to measure IMT have limitations. A semi-automatic device called UNEX has been developed, which overcomes the limitation of classic systems (in particular the investigator-dependency of conventional, "hand-held'' measurements). The purpose of this study was to measure the intima-media thickness of the brachial artery (bIMT) with the UNEX device in patients with and without congestive heart failure. DESIGN AND METHOD: The UNEX device is comprised of a 7.5-MHz, H-shaped linear array transducer and a novel stereotactic probe-holding device (UNEX EF 18G; UNEX Co., Nagoya, Japan). Another advantage of this device is the continuous recording of B-mode images and A-mode waves of the brachial artery. Measurement of bIMT was automatically performed on A-mode images of the far wall of the brachial artery. The analysis system automatically detects the measurement point where an image was clearly obtained. The average of mean measurement values obtained from 10 cardiac cycles was defined as bIMT. In a first set of clinical studies, we measured bIMT in patients with reduced left ventricular ejection fraction (HFrEF) and in patients without heart failure. RESULTS: Patients with HFrEF (n = 85, ejection fraction: 38.3 ± 8.4 %, NT-pro-BNP: 713 ± 714.7 pg/ml) compared to patients without heart failure (n = 63) were older (66.4 ± 9.2 vs. 53.8 ± 12.6 years, p < 0.001), with more male subjects (67 vs. 40, p = 0.039). bIMT was higher in patients with HFrEF compared to the other group (0.295 ± 0.083 vs. 0.249 ± 0.083 mm, p < 0.001). After adjustment for age, gender and other cardiovascular risk factors, the result remained significant (p = 0.032). CONCLUSIONS: Our study demonstrate that IMT of large muscular arteries can be automatically (investigator independently) measured. Our data indicate an increased vascular remodeling in patients with HFrEF independent of other confounders.
CRIS-Team Scopus Importer:2022-09-16

Serum levels of the Th1 chemoattractant interferon-gamma-inducible protein (IP) 10 are elevated in patients with essential hypertension - Stumpf, Christian; Auer, Claudia; Yilmaz, Atilla; Lewczuk, Piotr; Klinghammer, Lutz; Schneider, Markus; Daniel, Werner; Schmieder, Roland; Garlichs, Christoph (Hypertension Research, 2011)
Growing evidence shows that inflammation has a pivotal role in the pathophysiology of essential hypertension (EH). Although it has been acknowledged that target organ damage involves an inflammatory response, most work has focused on the role of macrophages, but T lymphocytes have recently become the center of interest. The goal of our study was to evaluate the role of T-cell-specific cytokines in the pathogenesis of EH. The study examined 39 patients with EH (57.7±6.8 years, systolic blood pressure (SBP) 157.5±11.8 mm Hg, diastolic blood pressure 92.2±12.9 mm Hg, mean arterial pressure 113.9±12.6 mm Hg) and 30 healthy, normotensive controls (55.2±4.9 years). Blood was drawn from a peripheral vein, and serum levels of interferon-inducible protein (IP)-10 and interleukins (IL)-4,-7 and-13 were measured by a multiplexing assay. Hypertensive patients had significantly higher levels of IP-10, IL-4, IL-7 and IL-13 than control subjects. When the patients were classified into tertiles according to their serum IP-10 levels (T1: 41.2-9±4.1 pg ml-1; T2: 103.4-1±62.5 pg ml 1; T3: 171.7-443.5 pgml 1), the patients classified into the highest tertile also had the highest blood pressure. In a correlation analysis, plasma IP-10 concentration was significantly associated with SBP (r0.59, P<0.001). Furthermore, hypertensives with microalbuminuria, an early sign of hypertensive target organ damage, had the highest IP-10 levels. A stepwise multivariate regression analysis revealed IP-10 as the strongest independent predictor of SBP (P<0.01). In conclusion, our study provides new insights into the pathophysiological mechanisms in EH linking inflammation and IP-10. However, these preliminary results need to be confirmed in larger trials. © 2011 The Japanese Society of Hypertension All rights reserved.
CRIS-Team Scopus Importer:2023-07-10
Keywords: cytokines; inflammation; IP-10; microalbuminuria; T-cells

Serum markers of fibrosis, cardiovascular and all-cause mortality in hemodialysis patients: the AURORA trial - Salib, Madonna; Girerd, Sophie; Girerd, Nicolas; Marz, Winfried; Scharnagl, Hubert; Massy, Ziad A.; Leroy, Celine; Duarte, Kevin; Holdaas, Hallvard; Jardine, Alan G.; Schmieder, Roland; Fellstrom, Bengt; et al. (Clinical Research in Cardiology, 2021)
Background Biomarkers of fibrosis are associated with outcome in several cardiovascular diseases. However, their relevance to chronic kidney disease and dialysis is uncertain, as it remains unclear how the kidneys and the dialysis procedure itself affect their elimination and degradation. We aimed to investigate the relationship of the blood levels of two markers associated with fibrosis: procollagen type I C-terminal pro-peptide (PICP) and galectin-3 (Gal-3) with mortality in dialysis patients.
CRIS-Team WoS Importer:2021-07-09

Sex Differences in Blood Pressure and Potential Implications for Cardiovascular Risk Management - Picone, Dean S.; Stoneman, Elif; Cremer, Antoine; Schultz, Martin G.; Otahal, Petr; Hughes, Alun D.; Black, J. Andrew; Bos, Willem Jan; Chen, Chen Huan; Cheng, Hao Min; Dwyer, Nathan; Lacy, Peter; et al. (Hypertension, 2023)
BACKGROUND: Accurate blood pressure (BP) measurement is critical for optimal cardiovascular risk management. Age-related trajectories for cuff-measured BP accelerate faster in women compared with men, but whether cuff BP represents the intraarterial (invasive) aortic BP is unknown. This study aimed to determine the sex differences between cuff BP, invasive aortic BP, and the difference between the 2 measurements. METHODS: Upper-arm cuff BP and invasive aortic BP were measured during coronary angiography in 1615 subjects from the Invasive Blood Pressure Consortium Database. This analysis comprised 22 different cuff BP devices from 28 studies. RESULTS: Subjects were 64±11 years (range 40-89) and 32% women. For the same cuff systolic BP (SBP), invasive aortic SBP was 4.4 mm Hg higher in women compared with men. Cuff and invasive aortic SBP were higher in women compared with men, but the sex difference was more pronounced from invasive aortic SBP, was the lowest in younger ages, and the highest in older ages. Cuff diastolic blood pressure overestimated invasive diastolic blood pressure in both sexes. For cuff and invasive diastolic blood pressure separately, there were sex*age interactions in which diastolic blood pressure was higher in younger men and lower in older men, compared with women. Cuff pulse pressure underestimated invasive aortic pulse pressure in excess of 10 mm Hg for both sexes in older age. CONCLUSIONS: For the same cuff SBP, invasive aortic SBP was higher in women compared with men. How this translates to cardiovascular risk prediction needs to be determined, but women may be at higher BP-related risk than estimated by cuff measurements.
CRIS-Team Scopus Importer:2023-01-27
Keywords: diagnostic equipment; hypertension; physiology; pulse wave analysis; sex factors

Sex-specific differences and long-term outcome of patients with coronary artery disease and chronic kidney disease: the Coronary Artery Disease and Renal Failure (CAD-REF) Registry - Engelbertz, Christiane; Pinnschmidt, Hans O.; Freisinger, Eva; Reinecke, Holger; Schmitz, Boris; Fobker, Manfred; Schmieder, Roland; Wegscheider, Karl; Breithardt, Günter; Pavenstädt, Hermann; Brand, Eva (Clinical Research in Cardiology, 2021)
Background: Cardiovascular morbidity and mortality are closely linked to chronic kidney disease (CKD). Sex-specific long-term outcome data of patients with coronary artery disease (CAD) and CKD are scarce. Methods: In the prospective observational multicenter Coronary Artery Disease and REnal F﻿ailure (CAD-REF) Registry, 773 (23.1%) women and 2,579 (76.9%) men with angiographically documented CAD and different stages of CKD were consecutively enrolled and followed for up to 8 years. Long-term outcome was evaluated using survival analysis and multivariable Cox-regression models. Results: At enrollment, women were significantly older than men, and suffered from more comorbidities like CKD, hypertension, diabetes mellitus, and multivessel coronary disease. Regarding long-term mortality, no sex-specific differences were observed (Kaplan–Meier survival estimates: 69% in women vs. 69% in men, plog-rank = 0.7). Survival rates decreased from 89% for patients without CKD at enrollment to 72% for patients with CKD stages 1–2 at enrollment and 49% for patients with CKD stages 3–5 at enrollment (plog-rank < 0.001). Cox-regression analysis revealed that sex or multivessel coronary disease were no independent predictors of long-term mortality, while age, CKD stages 3–5, albumin/creatinine ratio, diabetes, valvular heart disease, peripheral artery disease, and left-ventricular ejection fraction were predictors of long-term mortality. Conclusions: Sex differences in CAD patients mainly exist in the cardiovascular risk profile and the extent of CAD. Long-term mortality was not depended on sex or multivessel disease. More attention should be given to treatment of comorbidities such as CKD and peripheral artery disease being independent predictors of death. Clinical Trail Registration ClinicalTrials.gov Identifier: NCT00679419 Graphic abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2021-06-04
Keywords: Chronic kidney disease; Coronary artery disease; Long-term mortality; Sex; Treatment

SGLT-2-inhibition with dapagliflozin reduces tissue sodium content: a randomised controlled trial - Karg, Margarete; Bosch, A.; Kannenkeril, Dennis; Striepe, Kristina; Ott, Christian; Schneider, M. P.; Boemke-Zelch, Franziska; Linz, Peter; Nagel, Armin Michael; Titze, Jens; Uder, Michael; Schmieder, Roland (Cardiovascular Diabetology, 2018)
Sodium tissue content by 23Na magnetic resonance imaging (Na-MRI) has been validated in experimental and human studies. SGLT-2 inhibition blocks the reabsorption of glucose and of sodium in the proximal tubular cells in a 1:1 fashion. We hypothesized that SGLT-2 inhibition in patients with type 2 diabetes characterized by sodium retention leads to decreased tissue sodium content due to its pharmacological action.In a prospective double blind, placebo controlled, cross-over trial 59 patients (61 ± 7.6 years) with type 2 diabetes were randomized to either dapagliflozin 10 mg or placebo once daily for 6 weeks each. In addition to metabolic parameters and ambulatory blood pressure (BP) we analysed the sodium content in the skin and muscles of the lower leg by Na-MRI.Compared to baseline 6 weeks treatment with the SGLT-2 inhibitor dapagliflozin decreased fasting (132 ± 28 vs. 114 ± 19 mg/dl, p < 0.001), postprandial blood glucose (178 ± 66 mg/dl vs. 153 ± 46 mg/dl, p < 0.001), body weight (87.6 vs. 86.6 kg, p < 0.001) and systolic (129 ± 12 vs. 126 ± 11 mmHg, p = 0.010), and diastolic (77.4 ± 9 vs. 75.6 ± 8 mmHg, p = 0.024), 24-h ambulatory BP. Tissue sodium content in the skin was reduced after 6 weeks treatment with dapagliflozin compared to baseline [24.1 ± 6.6 vs. 22.7 ± 6.4 A.U.(arbitrary unit) p = 0.013]. No significant reduction of tissue sodium content was observed in the muscle (M. triceps surae: 20.5 ± 3.5 vs. 20.4 ± 3.7 A.U. p = 0.801). No clear significant difference in tissue water content of muscle and skin was observed after 6 weeks of treatment with dapagliflozin, compared to baseline.SGLT-2 inhibition with dapagliflozin resulted in a significant decrease in tissue sodium content of the skin after 6 weeks. This observation point to a decrease of total sodium content in patients with type 2 diabetes prone to cardiovascular complications, that might be mitigated by SGLT-2 inhibition. Trial registration The study was registered at http://www.clinicaltrials.gov (NCT02383238) retrospectively registered.
EVALuna2:4043

Single pill regimen improves persistence and leads lo better clinical outcome compared to identical multi pill combination. Results of START, a German claims data analysis - Predel, H. G.; Weisser, B.; Schmieder, Roland; Wassmann, S.; Blettenberg, J.; Gillessen, A.; Fournier; Noetel, A.; Randerath, O.; Boehm, M. (EUROPEAN HEART JOURNAL, 2020)
CRIS-Team WoS Importer:2021-02-12

Single pill treatment in daily practice is associated with improved clinical outcomes and all-cause mortality in cardiovascular diseases: results from the START project - Weisser, B.; Wilke, T.; Predel, H. G.; Schmieder, Roland; Wassmann, S.; Gillessen, A.; Blettenberg, J.; Maywald, U.; Randerath, O.; Mevius, A.; Boehm, M. (EUROPEAN HEART JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

Six-Month Results of Treatment-Blinded Medication Titration for Hypertension Control Following Randomization to Endovascular Ultrasound Renal Denervation or a Sham Procedure in the RADIANCE-HTN SOLO Trial - Azizi, Michel; Schmieder, Roland; Mahfoud, Felix; Weber, Michael A.; Daemen, Joost; Lobo, Melvin D.; Sharp, Andrew S. P.; Bloch, Michael J.; Basile, Jan; Wang, Yale; Saxena, Manish; Lurz, Philipp; et al. (Circulation, 2019)
BACKGROUND: The multicenter, international, randomized, blinded, sham-controlled RADIANCE-HTN SOLO trial demonstrated a 6.3 mmHg greater reduction in daytime ambulatory systolic blood pressure (BP) at 2 months by endovascular ultrasound renal denervation (RDN) compared with a sham procedure among patients not treated with antihypertensive medications. We report 6-month results following the addition of a recommended standardized stepped-care antihypertensive treatment (SSAHT) to the randomized endovascular procedure under continued blinding to initial treatment. METHODS: Patients with a daytime ambulatory BP greater ≥135/85 mmHg and <170/105 mmHg after a 4-week discontinuation of up to 2 antihypertensive medications and a suitable renal artery anatomy, were randomized to RDN (n=74) or sham (n=72). Patients were to remain off antihypertensive medications throughout the first 2 months of follow-up unless safety BP criteria were exceeded. Between 2 and 5 months, if monthly measured home BP was ≥135/85 mmHg, a SSAHT was recommended consisting of the sequential addition of amlodipine 5 mg/day, a standard dose of an angiotensin converting enzyme inhibitor/angiotensin receptor blocker, and hydrochlorothiazide 12.5 mg/day, followed by the sequential uptitration of hydrochlorothiazide (25 mg/day) and amlodipine (10 mg/day). Outcomes included the 6-month (i) change in daytime ambulatory systolic BP adjusted for medications and baseline SBP, (ii) medication burden, and (iii) safety. RESULTS: A total of 69/74 RDN patients and 71/72 sham patients completed the 6-month ambulatory BP measurement. At 6 months, 65.2% of patients in the RDN group were treated with the SSAHT vs. 84.5% in the sham group (p=0.008) and the average number of antihypertensive medications and defined daily dose were less in the RDN group than in the sham group (0.9±0.9 vs. 1.3±0.9, p=0.010 and 1.4±1.5 vs. 2.0±1.8, p=0.018; respectively). Despite less intensive SSAHT, RDN reduced daytime ambulatory systolic BP to a greater extent than sham (-18.1±12.2 vs. -15.6±13.2 mmHg, respectively; difference adjusted for baseline BP and number of medications: -4.3 mmHg, 95% confidence interval, -7.9 to -0.6, p=0.024). There were no major adverse events in either group through 6 months. CONCLUSIONS: The BP lowering effect of endovascular ultrasound RDN was maintained at 6 months with less prescribed antihypertensive medications compared with a sham control. CLINICAL TRIAL REGISTRATION: URL: https://www.clinicaltrials.gov. Unique identifier: NCT02649426.
EVALuna2:118642

Skin Sodium Concentration Correlates with Left Ventricular Hypertrophy in CKD - Schneider, Markus P.; Raff, Ulrike; Kopp, Christoph; Scheppach, Johannes B.; Toncar, Sebastian; Wanner, Christoph; Schlieper, Georg; Saritas, Turgay; Floege, Juergen; Schmid, Matthias; Birukov, Anna; Dahlmann, Anke; et al. (Journal of the American Society of Nephrology, 2017)
The pathogenesis of left ventricular hypertrophy in patients with CKD is incompletely understood. Sodium intake, which is usually assessed by measuring urinary sodium excretion, has been inconsistently linked with left ventricular hypertrophy. However, tissues such as skin and muscle may store sodium. Using (23)sodium-magnetic resonance imaging, a technique recently developed for the assessment of tissue sodium content in humans, we determined skin sodium content at the level of the calf in 99 patients with mild to moderate CKD (42 women; median [range] age, 65 [23-78] years). We also assessed total body overhydration (bioimpedance spectroscopy), 24-hour BP, and left ventricular mass (cardiac magnetic resonance imaging). Skin sodium content, but not total body overhydration, correlated with systolic BP (r=0.33, P=0.002). Moreover, skin sodium content correlated more strongly than total body overhydration did with left ventricular mass (r=0.56, P<0.001 versus r=0.35, P<0.001; P<0.01 between the two correlations). Linear regression analysis demonstrated that skin sodium content is a strong explanatory variable for left ventricular mass, unaffected by BP and total body overhydration. In conclusion, we found skin sodium content to be closely linked to left ventricular mass in patients with CKD. Interventions that reduce skin sodium content might improve cardiovascular outcomes in these patients.
EVALuna2:3863

Skin sodium content as a predictor of blood pressure response to renal denervation - Günes-Altan, Merve; Schmid, Axel; Kannenkeril, Dennis; Linz, Peter; Ott, Christian; Bosch, Agnes; Schiffer, Mario; Uder, Michael; Schmieder, Roland (Hypertension Research, 2023)
Patients with treatment resistant hypertension (TRH) are known to have elevated sodium (Na) content in muscle and skin. Renal denervation (RDN) emerged as an adjacent therapeutic option in this group of patients. This analysis aimed at evaluating whether tissue Na content predicts blood pressure (BP) response after RDN in patients with TRH. Radiofrequency-device based RDN was performed in 58 patients with uncontrolled TRH. Office and 24-h ambulatory BP were measured at baseline and after 6 months. To assess tissue Na content Na magnetic resonance imaging (Na-MRI) was performed at baseline prior to RDN. We splitted the study cohort into responders and non-responders based on the median of systolic 24-h ambulatory blood pressure (ABP) reduction after 6 months and evaluated the association between BP response to RDN and tissue Na content in skin and muscle. The study was registered at http://www.clinicaltrials.gov (NCT01687725). Six months after RDN 24-h ABP decreased by −8.6/−4.7 mmHg. BP-Responders were characterized by the following parameters: low tissue sodium content in the skin (p = 0.040), female gender (p = 0.027), intake of aldosterone antagonists (p = 0.032), high baseline 24-h night-time heart rate (p = 0.045) and high LDL cholesterol (p < 0.001). These results remained significant after adjustment for baseline 24-h systolic BP. Similar results were obtained when the median of day-time and night-time ABP reduction after 6 months were used as cut-off criteria for defining BP response to RDN. We conclude that in addition to clinical factors including baseline 24-h ABP Na-MRI may assist to select patients with uncontrolled TRH for RDN treatment. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-11-03
Keywords: Renal denervation; Sodium MRI; Tissue sodium

Sodium quantification in skeletal muscle: comparison between Cartesian gradient-echo and radial ultra-short echo time 23Na MRI techniques - Gerhalter, Teresa; Schilling, Felix; Zeitouni, Nour; Linz, Peter; Baudin, Pierre Yves; Kannenkeril, Dennis; Kopp, Christoph; Dahlmann, Anke; Schmieder, Roland; Uder, Michael; Nagel, Armin Michael; Gast, Lena (European Radiology Experimental, 2024)
Background: Clinical magnetic resonance imaging (MRI) studies often use Cartesian gradient-echo (GRE) sequences with 2-ms echo times (TEs) to monitor apparent total sodium concentration (aTSC). We compared Cartesian GRE and ultra-short echo time three-dimensional (3D) radial-readout sequences for measuring skeletal muscle aTSC. Methods: We retrospectively evaluated 211 datasets from 112 volunteers aged 62.3 ± 12.1 years (mean ± standard deviation), acquired at 3 T from the lower leg. For 23Na MRI acquisitions, we used a two-dimensional Cartesian GRE sequence and a density-adapted 3D radial readout sequence with cuboid field-of-view (DA-3D-RAD-C). We calibrated the 23Na MR signal using reference tubes either with or without agarose and subsequently performed a relaxation correction. Additionally, we employed a six-echo 1H GRE sequence and a multi-echo spin-echo sequence to calculate proton density fat fraction (PDFF) and water T2. Paired Wilcoxon signed-rank test, Cohen dz for paired samples, and Spearman correlation were used. Results: Relaxation correction effectively reduced the differences in muscle aTSC between the two acquisition and calibration methods (DA-3D-RAD-C using NaCl/agarose references: 20.05 versus 19.14 mM; dz = 0.395; Cartesian GRE using NaCl/agarose references: 19.50 versus 18.82 mM; dz = 0.427). Both aTSC of the DA-3D-RAD-C and Cartesian GRE acquisitions showed a small but significant correlation with PDFF as well as with water T2. Conclusions: Different 23Na MRI acquisition and calibration approaches affect aTSC values. Applying relaxation correction is advised to minimize the impact of sequence parameters on quantification, and considering additional fat correction is advisable for patients with increased fat fractions. Relevance statement: This study highlights relaxation correction’s role in improving sodium MRI accuracy, paving the way for better disease assessment and comparability of measured sodium signal in patients. Key points: • Differences in MRI acquisition methods hamper the comparability of sodium MRI measurements. • Measured sodium values depend on used MRI sequences and calibration method. • Relaxation correction during postprocessing mitigates these discrepancies. • Thus, relaxation correction enhances accuracy of sodium MRI, aiding its clinical use. Graphical Abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-05-31
Keywords: Calibration; Magnetic resonance imaging; Muscle (skeletal); Sodium; Volunteers

SUBGROUP ANALYSIS IN THE GLOBAL SYMPLICITY REGISTRY: 3-YEAR SAFETY AND EFFICACY - Mahfoud, F.; Mancia, G.; Schmieder, Roland; Narkiewicz, K.; Ruilope, L.; Schlaich, M.; Williams, B.; Fahy, M.; Boehm, M. (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-20

Systolic blood pressure variation and mean heart rate is associated with cognitive dysfunction in patients with high cardiovascular risk - Boehm, Michael; Schumacher, Helmut; Leong, Darryl; Mancia, Giuseppe; Unger, Thomas; Schmieder, Roland; Custodis, Florian; Diener, Hans-Christoph; Laufs, Ulrich; Lonn, Eva; Sliwa, Karen; Teo, Koon; et al. (Hypertension, 2015)
Elevated systolic blood pressure (SBP) correlates to cognitive decline and incident dementia. The effects of heart rate (HR), visit to visit HR variation, and visit to visit SBP variation are less well established. Patients without preexisting cognitive dysfunction (N=24 593) were evaluated according to mean SBP, SBP visit to visit variation (coefficient of variation [standard deviation/mean×100%], CV), mean HR, and visit to visit HR variation (HR-CV) in the Ongoing Telmisartan Alone and in Combination with Ramipril Global Endpoint Trial and the Telmisartan Randomized Assessment Study in ACE Intolerant Subjects with Cardiovascular Disease. Cognitive function was assessed with mini mental state examination. Cognitive dysfunction (fall in mini mental state examination <=24 points), important cognitive decline (drop of >=5 points), and cognitive deterioration (drop of >1 point per year or decline to <24 points) were assessed. SBP and HR were measured over 10.7±2.2 (mean±SD) visits. Mean SBP, mean HR, and SBP-CV were associated with cognitive decline, dysfunction, and deterioration (all P<0.01, unadjusted). After adjustment, only SBP-CV (P=0.0030) and mean HR (P=0.0008) remained predictors for cognitive dysfunction (odds ratios [95% confidence intervals], 1.32 [1.10-1.58] for 5th versus 1st quintile of SBP-CV and 1.40 [1.18-1.66] for 5th versus 1st quintile of mean HR). Similar effects were observed for cognitive decline and deterioration. SBP-CV and mean HR showed additive effects. In conclusion, SBP-CV and mean HR are independent predictors of cognitive decline and cognitive dysfunction in patients at high CV risk.http://www.clinicaltrials.gov. Unique identifier: NCT 00153101.
EVALuna2:3771

The authors reply - Ott, Christian; Schmieder, Roland (Kidney International, 2022)
CRIS-Team Scopus Importer:2022-04-01

The effect of renal denervation in moderate treatment-resistant hypertension with confirmed medication adherence - Ott, Christian; Mahfoud, Felix; Schmid, Andrea; Ewen, Sebastian; Toennes, Stefan W.; Meyer, Markus R.; Helfer, Andreas G.; Maurer, Hans H.; Ditting, Tilmann; Veelken, Roland; Zivanovic, Ina; Uder, Michael; et al. (Journal of Hypertension, 2016)
Data on the blood pressure (BP)-lowering effect of renal denervation (RDN) in moderate treatment-resistant hypertension (TRH) are limited. Moreover, change of adherence to medication, as one potential confounder of BP response, has never been analyzed rigorously in this group of patients. We analyzed the effect of RDN on BP in patients with moderate TRH who were retrospectively found to be completely adherent to their antihypertensive medication.Our study cohort comprised 40 patients with moderate TRH [office BP >= 140/90 but <160/100 mmHg and 24-h ambulatory BP monitoring (ABPM) >=130/80 mmHg] who underwent catheter-based RDN. Further major inclusion criterion was complete adherence to their medication (>=80% intake of their prescribed antihypertensive drugs) at baseline (assessed by retrospective toxicological analysis).Six months after RDN, office BP was reduced by -10/-6 mmHg (SBP: 149 ± 6 vs. 139 ± 15 mmHg; DBP: 81 ± 12 vs. 75 ± 10 mmHg; both P < 0.001) and 24-h ABPM by -7/-4 mmHg (SBP: 150 ± 14 vs. 143 ± 16 mmHg, P = 0.005; DBP: 82 ± 10 vs. 78 ± 9 mmHg, P = 0.009). Number of prescribed antihypertensive medication [6.0 (5.0-6.0) vs. 5.5 (5.0-6.0), P = 0.013] and adherence rate (95.2 ± 7.6 vs. 91.7 ± 13.9%, P = 0.065) was slightly reduced 6 months after RDN, both likely to underestimate the true BP reduction.Thus, our data indicate that even after given full respect to drug adherence as potential confounder of BP response after RDN, both office and 24-h ABPM were substantially reduced in patients with moderate TRH.
EVALuna2:3907

The Effect of Resting Heart Rate on the New Onset of Microalbuminuria in Patients With Type 2 Diabetes: A Subanalysis of the ROADMAP Study - Schmieder, Roland; Bramlage, Peter; Haller, Hermann; Ruilope, Luis M.; Boehm, Michael (Medicine, 2016)
The association between resting heart rate and new-onset microalbuminuria in patients with type 2 diabetes is not clear. The objective of the current analysis was to assess the relationship between heart rate and incidence of microalbuminuria in patients with type 2 diabetes.Data from the Randomised Olmesartan and Diabetes Microalbuminuria Prevention (ROADMAP) study were retrospectively analyzed. New-onset microalbuminuria was documented and related to heart rate as recorded at baseline and last assessment, and the mean of the measurements taken during the double-blind part of the ROADMAP trial.Patients (n = 4299) had a mean age of 57.8 ± 8.7 years and 46.3% were male. Characteristics were not different between the olmesartan and the placebo groups, except for a higher systolic blood pressure (136.7 vs 135.7 mm Hg; P = 0.04) and albumin creatinine ratio (5.9 vs 5.5; P = 0.03).Increased risk of microalbuminuria was found with increasing heart rate, independent of whether baseline [highest vs lowest quartile odds ratio (OR) 1.39; 95% confidence interval (95% CI) 1.03-1.87; P = 0.032], last assessment (OR 1.71; 95% CI 1.26-2.31; P = 0.001), or mean heart rate was considered (OR: 1.77; 95% CI: 1.30-2.41; P = 0.0003). The greater risk of new-onset microalbuminuria with a high baseline heart rate was also found when data were adjusted for mean systolic blood pressure (OR: 1.35; 95% CI: 1.00-1.82; P = 0.0496; interaction P < 0.0001). Although there was no risk increase with baseline heart rate in the placebo group (P = 0.8253 for trend), microalbuminuria was less frequent in patients receiving olmesartan in the low heart rate quartiles (P = 0.002 for trend).A low heart rate reduces the risk of patients with type 2 diabetes developing microalbuminuria, independent of blood pressure. The data demonstrate potential benefits of reducing the heart rate of type 2 diabetes patients, and indicate that olmesartan could, in particular, reduce the risk of microalbuminuria in patients with low heart rate.
EVALuna2:3855

The effect of sacubitril/valsartan compared to olmesartan on cardiovascular remodelling in subjects with essential hypertension: the results of a randomized, double-blind, active-controlled study - Schmieder, Roland; Wagner, Frank; Mayr, Michael; Delles, Christian; Ott, Christian; Keicher, Christian; Hrabak-Paar, Maja; Heye, Tobias; Aichner, Solveig; Khder, Yasser; Yates, Denise; Albrecht, Diego; et al. (European Heart Journal, 2017)
Progressive aortic stiffening eventually leads to left ventricular (LV) hypertrophy and heart failure if left untreated. Anti-hypertensive agents have been shown to reverse this to some extent. The effects of sacubitril/valsartan (LCZ696), a dual-action angiotensin receptor blocker (ARB), and neprilysin inhibitor, on arterial stiffness and LV remodelling have not been investigated.This was a randomized, multi-centre, double-blind, double-dummy, active-controlled, parallel group, study to compare the effects on cardiovascular remodelling of sacubitril/valsartan with those of olmesartan in patients with hypertension and elevated pulse pressure. Magnetic resonance imaging scans were used to assess LV mass and local aortic distensibility, at baseline and at 12 and 52 weeks after initiation of treatment. Central pulse and systolic pressure were determined using a SphymoCor® XCEL device at each time point. A total of 114 patients were included, with 57 in each treatment group. The mean age was 59.8 years, and 67.5% were male. Demographic characteristics did not vary between the two sets of patients. Left ventricular mass index decreased to a greater extent in the sacubitril/valsartan group compared to the olmesartan group from baseline to 12 weeks (-6.36 vs. -2.32 g/m2; P = 0.039) and from baseline to 52 weeks (-6.83 vs. -3.55 g/m2; P = 0.029). These differences remained significant after adjustment for systolic blood pressure (SBP) at follow-up (P = 0.036 and 0.019 at 12 and 52 weeks, respectively) and similar signals (though formally non-significant) were observed after adjusting for changes in SBP (P = 0.0612 and P = 0.0529, respectively). There were no significant differences in local distensibility changes from baseline to 12 or 52 weeks between the two groups; however, there was a larger reduction in central pulse pressure for the sacubitril/valsartan group compared to the olmesartan group (P = 0.010).Since LV mass change correlates with cardiovascular prognosis, the greater reductions in LV mass indicate valuable advantages of sacubitril/valsartan compared to olmesartan. The finding that LV mass index decrease might be to some extent independent of SBP suggests that the effect of the dual-acting agent may go beyond those due to its BP-lowering ability.
EVALuna2:3950

The impact of age on the benefits and risks of aliskiren treatment: analyses of the 3A registry - Friedrich, S.; Zeymer, U.; Dechend, R.; Hagedorn, I.; Riemer, T.; Zemmrich, C.; Bramlage, P.; Pittrow, D.; Senges, J.; Schmieder, Roland (Journal of Human Hypertension, 2015)
We aimed to analyze benefits and risks of aliskiren treatment in older adults (?65 years) in clinical practice. Patients (n=14 986) were assigned to either aliskiren (ALIS), an angiotensin-converting-enzyme inhibitor or angiotensin receptor blocker (ACEi/ARB), or an agent not blocking the renin-angiotensin system (non-RAS). Older adults (n=7396) had a longer history of hypertension (8.7 vs 4.7 years; P<0.0001), lower mean diastolic blood pressure (DBP; 87.7±11.0 vs 92.1±11.0 mm Hg) and more renal (12.0 vs 5.6%; P<0.0001) or cardiovascular disease (44.0 vs 18.9%; P<0.0001); 4548 received aliskiren (68.8%), 1215 ACEi/ARBs (18.4%) and 850 non-RAS treatments (12.9%). Office BP at 1 year was reduced by 18.4±21.5/7.2±12.0 mm Hg. BP reductions were greater (19.5±21.7/7.6±12.1 mm Hg) in the aliskiren group than in the ACEi/ARB (15.6±20.9/6.4±11.9) and non-RAS groups (16.1±20.7/6.5±11.7 mm Hg), respectively (P<0.0001 for systolic BP (SBP) and <0.01 for DBP). After multivariable adjustment, differences in SBP reductions were clinically irrelevant and no differences were noted for DBP. Adverse effects were higher in older adults with no differences between treatment groups. In conclusion, the present analysis of a large, unselected cohort of patients in clinical practice from the 3A study, offers real-life evidence of the effectiveness and safety of aliskiren for the treatment of hypertension in older adults.
EVALuna2:3737

The influence of aircraft noise exposure on the systemic and renal haemodynamics - Bosch, Agnes; Kannenkeril, Dennis; Jung, Susanne; Striepe, Kristina; Karg, Marina V.; Ott, Christian; Schmieder, Roland (European Journal of Preventive Cardiology, 2022)
Aims: Epidemiological studies found a link between aircraft noise exposure and increased incidence of arterial hypertension and cardiovascular disease, but the underlying pathophysiological mechanisms are not fully understood. Clinical studies have shown that mental stress affects the systemic and renal haemodynamic, but no such study was performed with noise exposure as stress factor. We analysed systemic and renal effects of 25 min standardized aircraft noise in a sham controlled clinical study including 80 healthy men and 34 male patients with hypertension. Methods and results: Systemic haemodynamic parameters were measured using electrocardiography and impedance cardiography. The renal haemodynamic was assessed using steady state input clearance with infusion of para-aminohippuric acid and inulin for glomerular filtration rate and renal plasma flow, respectively. In the systemic circulation of hypertensive patients, there was an increase in total peripheral resistance (TPR) (1420 ± 387 vs. 1640 ± 516 dyn·s·cm-5, P = 0.001) and a decrease in cardiac index (CI) (2.9 ± 0.8 vs. 2.6 ± 0.8 L/(min·m2, P < 0.001) 25 min after the start of noise exposure, which was not present during sham procedure (P = 0.10, P = 0.86). In healthy individuals a procedure induced increase in TPR and decrease in CI was present after noise (TPR: 995 ± 239 vs. 1106 ± 308 dyn·s·cm-5, P = 0.001, CI: 3.6 ± 0.7 vs. 3.3 ± 0.9 L/(min·m2, P < 0.001) and sham application (TPR: P = 0.002, CI: P < 0.001). However, in healthy individuals changes in TPR (P = 0.450) and CI (P = 0.605) from baseline until 25 min after the start of the intervention did not differ between noise and sham exposure. In the renal circulation of hypertensive patients and healthy individuals the response did not differ between noise and sham procedure. Conclusions: In hypertensive but not healthy men we observed a systemic vasoconstrictive response after aircraft noise exposure accompanied by a decrease in CI. No significant changes were observed in the renal circulation. Our results suggest that male hypertensive patients are more susceptible for noise-induced changes of vascular resistance in the systemic circulation.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Aircraft noise; Clearance; Hypertension; Renal haemodynamic; Systemic haemodynamic

THE INFLUENCE OF ANNOYANCE DUE TO AIRCRAFT NOISE ON RENAL HEMODYNAMIC - Bosch, Agnes; Kannenkeril, Dennis; Ott, Christian; Harazny, J. M.; Striepe, Kristina; Karg, M. V.; Jung, Susan; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-20

THE INFLUENCE OF ANNOYANCE DUE TO NOISE ON RENAL HEMODYNAMIC - Bosch, Agnes; Kannenkeril, Dennis; Ott, C.; Harazny, J. M.; Striepe, Kristina; Karg, M.; Dienemann, T.; Jung, Susan; Schmieder, Roland (2018)
EVALuna2:202962

The International Society of Hypertension and World Hypertension League call on governments, nongovernmental organizations and the food industry to work to reduce dietary sodium - Campbell, Norman R. C.; Lackland, Daniel T.; Chockalingam, Arun; Liu Lisheng; Harrap, Stephen B.; Touyz, Rhian M.; Burrell, Louise M.; Ramirez, Agustin J.; Schmieder, Roland; Schutte, Aletta E.; Prabhakaran, Dorairaj; Schiffrin, Ernesto L. (Journal of Hypertension, 2014)
The International Society of Hypertension and the World Hypertension League have developed a policy statement calling for reducing dietary salt. The policy supports the WHO and the United Nations recommendations, which are based on a comprehensive and up-to-date review of relevant research. The policy statement calls for broad societal action to reduce dietary salt, thus reducing blood pressure and preventing hypertension and its related burden of cardiovascular disease. The hypertension organizations and experts need to become more engaged in the efforts to prevent hypertension and to advocate strongly to have dietary salt reduction policies implemented. The statement is being circulated to national hypertension organizations and to international nongovernmental health organizations for consideration of endorsement. Member organizations of the International Society of Hypertension and the World Hypertension League are urged to support this effort.
EVALuna2:3683

The renin-angiotensin receptor blocker azilsartan medoxomil compared with the angiotensin-converting enzyme inhibitor ramipril in clinical trials versus routine practice: insights from the prospective EARLY registry - Bramlage, Peter; Schmieder, Roland; Gitt, Anselm K.; Baumgart, Peter; Mahfoud, Felix; Buhck, Hartmut; Ouarrak, Taoufik; Ehmen, Martina; Potthoff, Sebastian A. (Trials, 2015)
Patient characteristics and blood pressure-related outcomes in randomized clinical trials (RCTs) differ from clinical practice because of stringent selection criteria. The present study aimed to explore the relationship between clinical trials and clinical practice. We analyzed data from patients enrolled in the "Treatment with Azilsartan Compared to ACE-Inhibitors in Anti-Hypertensive Therapy" (EARLY) registry comparing blood pressure (BP) effects of the angiotensin receptor blocker (ARB) azilsartan medoxomil (AZL-M) with the angiotensin-converting enzyme (ACE) inhibitor ramipril between patients who met the eligibility criteria of a previous RCT and those who did not.Patients with primary arterial hypertension were consecutively enrolled from primary care offices in Germany into the EARLY registry in a 7:3 ratio for treatment with AZL-M or an ACE inhibitor, provided that they met the following criteria at baseline: 1) no antihypertensive treatment prior to inclusion or a non-renin-angiotensin system (RAS) based monotherapy; 2) initiation of treatment with either AZL-M or an ACE inhibitor alone. Analyses were performed to evaluate BP effects for patients in the EARLY registry who met the selection criteria of a prior RCT (RCT+) versus those who did not (RCT-).Out of 3,698 patients considered, 1,644 complied with the RCT criteria (RCT+) while 2,054 did not (RCT-). RCT- patients (55.5 %) displayed a higher risk profile in terms of age and comorbidities, and a wider spectrum of BP values at baseline, as highlighted by the grades of hypertension and mean BP values. The proportion of patients who achieved target blood pressure control in the RCT+ group was significantly higher for AZL-M versus ramipril (64.1 versus 56.1 %; P < 0.01), in accordance with the result of the clinical trial. In the RCT- AZL-M group, the proportion of patients who met BP targets was lower (58.1 %) than in the RCT+ AZL-M group (64.1 %), whereas the proportion of patients with target BP values in the RCT- ramipril and the RCT+ ramipril groups was similar (57.7 versus 56.1 %). Thus, in contrast to results for the RCT+ group, in the RCT- group, the target BP attainment rate for AZL-M was not significantly superior to that for ramipril. However, the tolerability profile of AZL-M and ramipril was comparable in both populations. At the 12-month follow-up, death and stroke rates were low (<=0.5 %) and adverse events did not differ between the AZL-M and ramipril groups, irrespective of RCT eligibility.These data confirm that the EARLY population comprised a broader spectrum of hypertensive patients than RCTs, and the differences in patient characteristics were accompanied by disparate rates of blood pressure goal attainment. Overall, the validity of the RCT was demonstrated and confirmed in clinical practice with a broader range of patients with various comorbidities.
EVALuna2:3821

THE SGLT2 INHIBITOR EMPAGLIFLOZIN REDUCES TISSUE SODIUM CONTENT IN PATIENTS WITH CHRONIC HEART FAILURE - Kolwelter, Julie; Kannenkeril, Dennis; Linz, Peter; Jung, Susanne; Nagel, Armin Michael; Bosch, Agnes; Ott, Christian; Bramlage, Peter; Uder, Michael; Achenbach, Stephan; Schmieder, Roland (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2021)
CRIS-Team WoS Importer:2021-06-04

The SGLT2 inhibitor empagliflozin reduces tissue sodium content in patients with chronic heart failure: results from a placebo-controlled randomised trial - Kolwelter, Julie; Kannenkeril, Dennis; Linz, Peter; Jung, Susanne; Nagel, Armin Michael; Bosch, Agnes; Ott, Christian; Bramlage, Peter; Nöh, Lisa; Schiffer, Mario; Uder, Michael; Achenbach, Stephan; et al. (Clinical Research in Cardiology, 2022)
Introduction: Sodium-glucose co-transporter 2 (SGLT2) inhibitors have cardiovascular protective properties in addition to the metabolic effects and represent a cornerstone of treating patients with chronic heart failure (CHF). We hypothesised that empagliflozin reduces tissue sodium content in patients with CHF. Methods: In a double-blind, randomised (2:1), placebo-controlled, parallel-group, clinical trial, 74 patients with NYHA class II–III CHF and an ejection fraction of 49% or less received empagliflozin 10 mg once daily or placebo for 3 months. In each patient, tissue sodium content of the lower leg was assessed non-invasively by sodium-MRI (23Na-MRI) at baseline, after 1 and 3 months of treatment. Results: After 1 and 3 months treatment with empagliflozin (n = 48), a significant decrease in skin sodium content was observed (1 month: 22.8 ± 6.1 vs. 21.6 ± 6.0 AU, p = 0.039; 3 months: 22.9 ± 6.1 vs. 21.6 ± 6.1 AU, p = 0.013), while there was no change in muscle sodium and muscle water content. In direct comparison, the change in skin sodium content between baseline and 3 months was − 1.3 ± 3.5 AU in the empagliflozin group versus 0.6 ± 3.5 AU in the placebo group (p for between-group difference = 0.022). No significant difference regarding change in muscle sodium and in muscle water content was observed after 3 months treatment between the two groups. Conclusion: This trial showed a significant decrease in skin sodium content after 1 and 3 months of treatment with empagliflozin. The decrease in skin sodium content may reflect a decrease in subclinical micro-oedema or/and in non-osmotic bound tissue sodium, both reported to impair left ventricular function. Trial registration number: NCT03128528 (http://www.clinicaltrials.gov). Trial registration date: 25th April 2017.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Chronic heart failure; Empagliflozin; Magnetic resonance imaging; SGLT2 inhibitor; Sodium; Tissue sodium content

THE SINGLE PILL CONCEPT LEADS TO IMPROVED PERSISTENCE OF MEDICATION, CLINICAL OUTCOMES AND REDUCED ALL-CAUSE MORTALITY IN HYPERTENSIVE PATIENTS - RESULTS FROM THE START PROJECT - Predel, Hans-Georg; Weisser, Burkhard; Wassmann, Sven; Gillessen, Anton; Blettenberg, Joerg; Fournier, Valerie; Noetel, Andrea; Randerath, Olaf; Boehm, Michael; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

The World Hypertension League and International Society of Hypertension call on governments, nongovernmental organizations, and the food industry to work to reduce dietary sodium - Campbell, Norm; Lackland, Daniel; Chockalingam, Arun; Liu Lisheng; Schiffrin, Ernesto L.; Harrap, Stephen; Touyz, Rhian M.; Burrell, Louise; Ramirez, Augustin; Schmieder, Roland; Aletta, Schutte; Prabhakaran, Dorairaj (Journal of Clinical Hypertension, 2014)
EVALuna2:3707

Tissue sodium concentration correlates with hypertrophic vascular remodelling in type 2 diabetes - Kannenkeril, Dennis; Jung, Susan; Harazny, Jeremy; Striepe, Kristina; Ott, Christian; Linz, Peter; Nagel, Armin Michael; Uder, Michael; Schmieder, Roland (DIABETOLOGIA, 2019)
CRIS-Team WoS Importer:2019-10-11

Tissue sodium concentration emerged as a determinant of hypertrophic vascular remodeling in type 2 diabetes - Schmieder, Roland; Jung, Susanne; Kannenkeril, Dennis; Harazny, J. M.; Striepe, Kristina; Ott, Christian; Linz, Peter; Nagel, Angela; Uder, Michael (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Tissue sodium content correlates with hypertrophic vascular remodeling in type 2 diabetes - Kannenkeril, Dennis; Jung, Susanne; Harazny, Joanna; Striepe, Kristina; Ott, Christian; Dahlmann, Anke; Kopp, Christoph; Schiffer, Mario; Linz, Peter; Nagel, Armin Michael; Uder, Michael; Schmieder, Roland (Journal of Diabetes and Its Complications, 2021)
Background: Prospective studies describe a linkage between increased sodium intake and higher incidence of cardiovascular organ damage and end points. We analyzed whether tissue sodium content in the skin and muscles correlate with vascular hypertrophic remodeling, a risk factor for cardiovascular disease.
CRIS-Team WoS Importer:2021-12-03

Tissue sodium content in hypertension and related organ damage - Kolwelter, Julie; Uder, Michael; Schmieder, Roland (Journal of Hypertension, 2020)
Most textbooks state that sodium (Na) accumulation goes hand in hand with fluid retention to maintain the environmental isotonicity. In the last century, several studies found, however, that Na is stored in the extravascular space leading to an activation of the monocyte phagocytic system cells that work as a regulator of the interstitial electrolyte homeostasis. Na-23-MRI was developed to quantify noninvasively, accurately and reliably tissue Na content. In this review, we give an up-to-date overview of clinical studies utilizing this Na-23-MRI technique to elucidate the importance of tissue Na content in patients with cardiovascular risk factors leading to microvascular and macrovascular complications. Na storage leads ultimately to organ damage such as left ventricular hypertrophy or hypertrophic vascular remodeling of resistance vessels. Elevated Na content in muscle and skin has been detected in patients with treatment resistant hypertension, type 2 diabetes mellitus, acute and chronic heart failure, chronic kidney disease and end-stage renal failure. Pharmacological interventions have shown that a mobilization of extracellular accumulated Na is possible and may emerge as a new therapeutic approach in some diseases.
CRIS-Team WoS Importer:2021-01-01

Tissue sodium content in patients with type 2 diabetes mellitus - Kannenkeril, Dennis; Karg, Marina V.; Bosch, Agnes; Ott, Christian; Linz, Peter; Nagel, Armin Michael; Uder, Michael; Schmieder, Roland (Journal of Diabetes and Its Complications, 2019)
Background: Tissue sodium content by 23 Na magnetic resonance imaging (MRI)has been found to be increased in arterial hypertension. We analyzed whether tissue sodium content is increased in patients with type-2 diabetes (T2DM). Methods: Patients with T2DM were compared to those with primary hypertension. Patients with T2DM were off any antidiabetic and hypertensive patients off any antihypertensive therapy for at least 4 weeks. Skin and muscle sodium content was assessed non-invasively with a 3.0 T clinical MRI system (Magnetom Verio, Siemens Health Care, Erlangen, Germany)in each patient. Results: In patients with T2DM (N = 59)we observed significantly greater muscle sodium content (diabetes: 20.6 ± 3.5 vs hypertension: 16.3 ± 2.5 mmol/l, p < 0.001)and skin sodium content (diabetes: 24.5 ± 7.2 vs hypertension: 20.6 ± 5.7 mmol/l, p = 0.01)than in those with primary hypertension (N = 33). When potential confounders (age, body mass index, gender, systolic and diastolic blood pressure, estimated glomerular filtration rate)were entered in a covariance analysis, both skin sodium content (p = 0.037)and muscle sodium content (p < 0.001)were still clearly elevated. Conclusion: Patients with T2DM have greater skin and muscle sodium content. These are the first known data to demonstrate increased tissue sodium content in patients with T2DM, measured by 23 Na magnetic resonance imaging. Since tissue sodium content is related to organ damage, therapeutic intervention should aim at reducing tissue sodium content.
CRIS-Team Scopus Importer:2019-05-21
Keywords: 23Na-MRI; T2DM; Tissue sodium content; Salt; Sodium retention

Triglyceride-glucose index, low-density lipoprotein levels, and cardiovascular outcomes in chronic stable cardiovascular disease: results from the ONTARGET and TRANSCEND trials - Haring, Bernhard; Schumacher, Helmut; Mancia, Giuseppe; Teo, Koon K.; Lonn, Eva M.; Mahfoud, Felix; Schmieder, Roland; Mann, Johannes F.E.; Sliwa, Karen; Yusuf, Salim; Böhm, Michael (European Journal of Preventive Cardiology, 2024)
Aims The triglyceride-glucose index (TyG) has been proposed as an alternative to insulin resistance and as a predictor of cardiovascular outcomes. Little is known on its role in chronic stable cardiovascular disease and its predictive power at controlled low density lipoprotein (LDL) levels. ............................................................................................................................................................................................ Methods Our study population consisted of 29 960 participants in the ONTARGET and TRANSCEND trials that enrolled patients and results with known atherosclerotic disease. Triglycerides and glucose were measured at baseline. TyG was calculated as the logarithmized product of fasting triglycerides and glucose divided by 2. The primary endpoint of both trials was a composite of cardiovascular death, myocardial infarction, stroke, or hospitalization for heart failure. The secondary endpoint was all-cause death and the components of the primary endpoint. Cox proportional hazards models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CI) with extensive covariate adjustment for demographic, medical history, and lifestyle factors. During a mean follow-up of 4.3 years, 4895 primary endpoints and 3571 all-cause deaths occurred. In fully adjusted models, individuals in the highest compared to the lowest quartile of the TyG index were at higher risk for the primary endpoint (HR 1.14; 95% CI 1.05–1.25) and for myocardial infarction (HR 1.30; 95% CI 1.11–1.53). A higher TyG index did not associate with the primary endpoint in individuals with LDL levels < 100 mg/dL. ............................................................................................................................................................................................ Conclusion A higher TyG index is associated with a modestly increased cardiovascular risk in chronic stable cardiovascular disease. This association is largely attenuated when LDL levels are controlled. ............................................................................................................................................................................................ Registration www.clinicaltrials.gov: NCT00153101 - Lay summary• The association of triglyceride-glucose index (TyG) with cardiovascular disease in chronic stable cardiovascular disease and its predictive power at controlled low density lipoprotein (LDL) levels is unclear. Using a study population of 29 960 participants with chronic stable cardiovascular disease, we found that higher TyG levels were associated with a modestly increased risk for incident cardiovascular events and low LDL levels largely attenuated the association of TyG with cardiovascular risk.
CRIS-Team Scopus Importer:2024-03-01
Keywords: Cardiovascular disease; Mortality; Myocardial infarction; Triglyceride-glucose index

Twenty-Four-Hour Pulsatile Hemodynamics Predict Brachial Blood Pressure Response to Renal Denervation in the SPYRAL HTN-OFF MED Trial - Weber, Thomas; Wassertheurer, Siegfried; Mayer, Christopher C.; Hametner, Bernhard; Danninger, Kathrin; Townsend, Raymond R.; Mahfoud, Felix; Kario, Kazuomi; Fahy, Martin; Debruin, Vanessa; Peterson, Nicole; Negoita, Manuela; et al. (Hypertension, 2022)
Background: Renal denervation (RDN) lowers blood pressure (BP), but BP response is variable in individual patients. We investigated whether measures of pulsatile hemodynamics, obtained during 24-hour ambulatory BP monitoring, predict BP drop following RDN. Methods: From the randomized, sham-controlled SPYRAL HTN-OFF MED Pivotal trial, we performed a post hoc analysis of BP waveforms from 111 RDN patients and 111 sham controls, obtained with a brachial cuff-based sphygmomanometer. Waveforms were acquired during ambulatory BP monitoring at diastolic BP level and processed with validated ARCSolver algorithms to derive hemodynamic parameters (augmentation index; augmentation pressure; backward and forward wave amplitude; estimated aortic pulse wave velocity). We investigated the relationship between averaged 24-hour values at baseline and the change in 24-hour BP at 3 months in RDN patients, corrected for observed trends in the sham group. Results: There was a consistent inverse relationship between baseline augmentation index/augmentation pressure/backward wave amplitude/forward wave amplitude/estimated aortic pulse wave velocity and BP response to RDN: the decrease in 24-hour systolic BP/diastolic BP was 7.8/5.9 (augmentation index), 8.0/6.3 (augmentation pressure), 6.7/5.4 (backward wave amplitude), 5.7/4.7 (forward wave amplitude), and 7.8/5.2 (estimated aortic pulse wave velocity) mm Hg greater for patients below versus above the respective median value (P<0.001 for all comparisons, respectively). Taking augmentation index/augmentation pressure/backward wave amplitude/forward wave amplitude/estimated aortic pulse wave velocity into account, a favorable BP response following RDN, defined as a drop in 24-hour systolic blood pressure of >= 5 mm Hg, could be predicted with an area under the curve of 0.70/0.74/0.70/0.65/0.62 (P<0.001 for all, respectively). Conclusions: These results suggest that pulsatile hemodynamics, obtained during 24-hour ambulatory BP monitoring, may predict BP response to RDN.
CRIS-Team WoS Importer:2022-06-24

Twenty-Four Month Results in Patients With Resistant Hypertension After Endovascular Ultrasound Renal Denervation in the RADIANCE-HTN TRIO Trial - Bloch, Michael; Kirtane, Ajay; Mahfoud, Felix; Azizi, Michel; Basile, Jan; Daemen, Joost; Saxena, Manish; Gosse, Philippe; Sanghvi, Kintur; Schmieder, Roland (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Two-year outcome and risk factors for mortality in patients with coronary artery disease and renal failure: The prospective, observational CAD-REF Registry - Engelbertz, Christiane; Reinecke, Holger; Breithardt, Günter; Schmieder, Roland; Fobker, Manfred; Fischer, Dieter; Schmitz, Boris; Pinnschmidt, Hans O.; Wegscheider, Karl; Pavenstädt, Hermann; Brand, Eva (International Journal of Cardiology, 2017)
Chronic kidney disease (CKD) and coronary artery disease (CAD) are strongly associated. CAD is the most frequent cause of cardiovascular death in patients with CKD.The prospective observational nationwide multicenter Coronary Artery Disease and REnal Failure (CAD-REF) Registry enrolled 3352 patients with angiographically documented CAD classified according to their baseline estimated glomerular filtration rate (eGFR) into 5 groups according to the K/DOQI-guidelines. Patients were followed for two years. The aim of this study was the analysis of outcome and the identification of risk factors for two-year mortality in patients with both CKD and CAD.With decreasing renal function, patients had more often diabetes mellitus, hypertension, peripheral artery disease, and previous cardiovascular events and interventions. The amount of diseased vessels increased with decreasing renal function. For the whole cohort, two-year mortality was 6.5%. Kaplan-Meier-curves showed highest mortality in patients with CKD stages 4 and 5 (22.4%). In multivariate Cox-regression analyses, significant risk factors for two-year all-cause mortality were lower eGFR, current smoking, left ventricular ejection fraction, diabetes mellitus treated with oral medication or insulin, age, and peripheral artery disease. Coronary status missed the level of statistical significance as a risk factor for mortality in multivariable regression analysis. An eGFR reduction of 10ml/min/1.73m(2) increased the risk of mortality by 19% regardless of other risk factors.Two-year morbidity and mortality increased with the degree of renal impairment. To improve survival of patients with CAD and CKD, nephroprotection is urgently needed especially for patients with atherosclerotic burden.NCT00679419, http://clinicaltrials.gov/.
EVALuna2:3956

Two-Year Outcomes of Patients Treated With Aliskiren Under Clinical Practice Conditions: Non-Interventional Prospective Study - Zeymer, Uwe; Dechend, Ralf; Riemer, Thomas; Deeg, Evelin; Senges, Jochen; Pittrow, David; Schmieder, Roland (Journal of Clinical Hypertension, 2016)
The authors investigated the long-term effectiveness and safety of aliskiren (ALIS) with particular attention on its association with dual blockade of the renin-angiotensin system (RAS). The open, prospective 3A Registry (N=8723) in Germany assigned patients in a 4:1:1 ratio to ALIS, angiotensin-converting enzyme (ACE) inhibitors or angiotensin receptor blockers (ARBs), or non-RAS drugs. Patients taking ALIS compared with those taking ACE inhibitors/ARBs or non-RAS had more comorbidities and risk factors, were taking more antihypertensive agents, and had higher blood pressure (BP) values at entry. At 2 years, BP reduction from baseline was similar in all groups (mean, -20.5/-9.9 mm Hg). A total of 2.3% of patients died, 0.5% had myocardial infarction, 0.6% had stroke, 2.9% were hospitalized, and 5.5% had any event (not significant between groups). ALIS alone or combined with another RAS inhibitor was well tolerated and effective in lowering BP in typical unselected patients with hypertension. Given the methodical limitations of the design, the study cannot be used to confirm or refute safety concerns for dual RAS blockade as suggested by the Aliskiren Trial in Type 2 Diabetes Using Cardio-Renal Endpoints (ALTITUDE) trial.
EVALuna2:3893

Ultrasound renal denervation for hypertension resistant to a triple medication pill (RADIANCE-HTN TRIO): a randomised, multicentre, single-blind, sham-controlled trial - Azizi, Michel; Sanghvi, Kintur; Saxena, Manish; Gosse, Philippe; Reilly, John P.; Levy, Terry; Rump, Lars C.; Persu, Alexandre; Basile, Jan; Bloch, Michael J.; Daemen, Joost; Lobo, Melvin D.; et al. (Lancet, 2021)
Background Endovascular renal denervation reduces blood pressure in patients with mild-to-moderate hypertension, but its efficacy in patients with true resistant hypertension has not been shown. We aimed to assess the efficacy and safety of endovascular ultrasound renal denervation in patients with hypertension resistant to three or more antihypertensive medications.
CRIS-Team WoS Importer:2021-07-23

Update on Treatment of Hypertension After Renal Transplantation - Chatzikyrkou, Christos; Schmieder, Roland; Schiffer, Mario (Current Hypertension Reports, 2021)
Purpose of Review: To incorporate novel findings on pathophysiology and treatment of posttransplant hypertension. Recent Findings: (1) The sodium retaining effects of CNIs are mediated by stimulation of the thiazide-sensitive sodium chloride co-transporter in the distal convoluted tubule and in this regard chlorthalidone was proven to be an effective antihypertensive drug in renal transplantation. (2) Local and not systemic activation of the renin-angiotensin-aldosterone system plays a crucial role in the pathogenesis of posttransplant hypertension. (3) Recent randomized controlled trials failed to prove the presumed superiority of renin-angiotensin blockers in kidney transplantation. (4) Steroid-free and mammalian target of rapamycin-based immunosuppressive drug combinations did not show favorable effects on blood pressure control. (5) In a recent report the risk of non-melanoma skin cancer was higher with thiazide diuretics. But the increased cancer risk in transplant recipients is mainly attributed to comorbidities, such as diabetes and hypertension and of course to the transplantation condition itself or the obligatory application of immunosuppression, and has little to do with the antihypertensive medication Summary: Actual recommendations about BP targets in adult renal transplant recipients are coming from a post hoc analysis of a large randomized trial with another primary endpoint. Unless convincing studies on treatment of hypertension after renal transplantation are available, the ESC/ESH Guidelines 2018 should apply for these patients.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Antihypertensive drugs; Cardiovascular disease; Guidelines; Hypertension; Kidney transplant; Thiazide diuretics

Urinary albumin excretion from spot urine samples predict all-cause and stroke mortality in africans - Schutte, Rudolph; Schmieder, Roland; Huisman, Hugo W.; Smith, Wayne; Van Rooyen, Johannes M.; Fourie, Carla M. T.; Kruger, Ruan; Uys, Lisa; Ware, Lisa; Mels, Catharina M. C.; Greeff, Minrie; Kruger, Iolanthe M.; et al. (American Journal of Hypertension, 2014)
Increased urinary albumin excretion reflects general vascular damage and predicts adverse cardiovascular and renal outcomes. Albuminuria can be determined from easily collected spot urine samples, especially in low-resource settings. However, no prognostic evidence exists for Africans.We followed clinical outcomes in 1,061 randomly selected non diabetic, human immunodeficiency virus (HIV)-negative Africans (mean age: 51.5 years; 62.0% women). Baseline urinary albumin-to-creatinine ratio was assessed from spot urine samples.Over a median follow-up of 4.52 years, 132 deaths occurred, of which 47 were cardiovascular related. The urinary albumin-to-creatinine ratio averaged 6.1 ?g/mg (5th to 95th percentile interval; 1.2-70.0). In multivariable-adjusted analyses, urinary albumin excretion predicted all-cause mortality (hazard ratio (HR), 1.26; 95% confidence interval (CI), 1.07-1.48; P = 0.006), and a tendency existed for cardiovascular mortality (HR, 1.26; 95% CI, 0.97-1.63; P = 0.087), which seemed to be driven by fatal stroke (HR, 1.72; 95% CI, 1.17-2.54; P = 0.006) rather than cardiac mortality (HR, 0.67; 95% CI, 0.41-1.07; P = 0.094). The predictive value remained in 528 hypertensives for both all-cause (HR, 1.38; 95% CI, 1.13-1.69; P = 0.001) and cardiovascular (HR, 1.45; 95% CI, 1.07-1.96; P = 0.017) mortality, again driven by stroke. Our findings also remained significant after we excluded participants with macroalbuminuria, those on antihypertensive treatment, as well as participants who died within 1 year after enrollment.In nondiabetic HIV-negative Africans, albuminuria predicts all-cause and stroke mortality.
EVALuna2:3675

Variability of MRI Aortic Stiffness Measurements in a Multicenter Clinical Trial Setting: Intraobserver, Interobserver, and Intracenter Variability of Pulse Wave Velocity and Aortic Strain Measurement. - Hrabak-Paar, Maja; Kircher, Achim; Sayari, Saeed Al; Kopp, Sebastien; Santini, Francesco; Schmieder, Roland; Kachenoura, Nadjia; Yates, Denise; Langenickel, Thomas; Bremerich, Jens; Heye, Tobias (Radiology: Cardiothoracic Imaging, 2020)
Purpose: To assess intraobserver, interobserver, and scan-rescan variability of MRI aortic stiffness measurements in a multicenter trial setting. Materials and Methods: This study was a retrospective analysis of prospectively collected data in a multicenter prospective clinical trial (clinicaltrials.gov ID NCT01870739). Forty-five adult patients (31 men; mean age, 58 years ± 12 [standard deviation]; 15 patients per center; three centers) with arterial hypertension underwent standardized 3-T baseline MRI assessments between June and September 2014. Aortic strain was calculated from maximum and minimum aortic area measurements repeated three times by three readers at three aortic levels on three retrospectively gated axial gradient-echo (GRE) data sets. Pulse wave velocity (PWV) was assessed three times by five readers as Δx/Δt: Δx was measured on a parasagittal GRE image of the aortic arch, and Δt was extracted from ascending and descending aortic velocity curves created on three axial phase-contrast acquisitions. Intraobserver, interobserver, and scan-rescan variability was calculated using percentage coefficient of variation (COV). Results: Aortic strain variability was lowest at the level of the distal descending aorta (DDA) with median COVs of 1.6% for intraobserver variability, 4.0% for interobserver variability, and 10.3% for scan-rescan variability. It was highest at the ascending aorta (AA) with COVs of 3.6% for intraobserver variability, 10.7% for interobserver variability, and 19.8% for scan-rescan variability. Variability of PWV was low: 0.7% for intraobserver variability, 1.5% for interobserver variability, and 8.1% for scan-rescan variability. Conclusion: Low variability can be achieved for aortic strain and PWV measurements in a multicenter trial setting using standardized MRI protocols. Although COV was lower when measuring aortic strain at DDA compared with AA, variability was acceptable at both anatomic locations.Supplemental material is available for this article.© RSNA, 2020.
EVALuna2:483433

Vascular and renal hemodynamic changes after renal denervation - Ott, Christian; Janka, Rolf Matthias; Schmid, Axel; Titze, Stephanie; Ditting, Tilmann; Sobotka, Paul A.; Veelken, Roland; Uder, Michael; Schmieder, Roland (Clinical Journal of the American Society of Nephrology, 2013)
Background and objectives Renal denervation (RDN) has been shown to be effective in reducing BP in treatmentresistant hypertension. Measurement of the renal and sympathetic activity revealed a decrease in sympathetic drive to the kidney and small resistance vessels after RDN. However, the consequences on renal perfusion and renal vascular resistance (RVR), as well as central hemodynamics, are unknown. Design, setting, participants, & measurements Nineteen patients with treatment-resistant hypertension (office BP140/90mmHg, despite at least three antihypertensive drugs [including a diuretic], and diagnosis confirmed by 24-hour ambulatory BPmonitoring) underwent RDNbetween January andOctober 2011. Renal perfusion and RVR were noninvasively assessed by magnetic resonance imaging with arterial spin labeling, and renal function was assessed by estimating GFR before (day 21), after (day +1), and again after 3 months of RDN. Central hemodynamics was assessed using pulse wave analysis at day 21 and after 6 months of RDN. Results Peripheral office BP (systolic, 158±26 versus 142±23mmHg, P=0.002; diastolic, 83±13 versus 76±9mmHg, P=0.02) and mean systolic 24-hour ambulatory BP (159±17 versus 152±17 mmHg, P=0.02) were significantly reduced 6 months after RDN. Renal perfusion was not statistically different between day 21 and day +1 (256.8 [interquartile range (IQR), 241-278] versus 263.4 [IQR, 252-277] ml/min per 100 g; P=0.17) as well as after 3 months (256.8 [IQR, 241-278] versus 261.2 [IQR, 240-285] ml/min per 100 g; P=0.27) after RDN. RVR dropped (432.1 [IQR, 359-525] versus 390.6 [IQR, 338-461] AU; P=0.02), whereas renal function was not statistically different at any time point. Central systolic BP (145±31 versus 131628 mmHg; P=0.009), diastolic BP (85±18 versus 80±14 mmHg; P=0.03), and central pulse pressure (61±18 versus 52±18 mmHg; P=0.02) were significantly reduced 6 months after RDN. Central augmentation index (24±8 versus 20±8%; P=0.02) was decreased 6 months after RDN. Conclusion The data indicate that RDN significantly reduced peripheral and central BP. Despite reduced systemic BP, renal perfusion and function did not change after RDN. © 2013 by the American Society of Nephrology.
CRIS-Team Scopus Importer:2023-03-08

VASCULAR REMODELING OF RETINAL VESSELS IN PATIENTS WITH CONGESTIVE HEART FAILURE - Jung, Susan; Kannenkeril, Dennis; Ott, Christian; Cifkova, R.; Harazny, J. M.; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-20

Visit-to-visit blood pressure variability and renal outcomes: results from ONTARGET and TRANSCEND trials - Mancia, Giuseppe; Schumacher, Helmut; Böhm, Michael; Mann, Johannes; Redon, Josep; Facchetti, Rita; Schmieder, Roland; Lonn, Eva M.; Teo, Koon K.; Yusuf, Salim (Journal of Hypertension, 2020)
AIMS: There is conflicting evidence on whether in treated hypertensive patients the risk of renal outcomes is associated with visit-to-visit SBP variability. Furthermore, limited evidence is available on how important is SBP variability for prediction of renal outcomes compared with on-treatment mean SBP. We addressed these issues in 28 790 participants of the Ongoing Treatment Alone and in combination with Ramipril Global End point Trial and Telmisartan Randomized AssessmeNt Study in ACE iNtolerant Subjects with Cardiovascular Disease trials. METHODS AND RESULTS: SBP variability was expressed as the coefficient of variation of the mean with which it showed no relationship. SBP variability and mean values were obtained from five visits during the first 2 years of treatment after the end of the titration phase. Incidence of several renal outcomes (end-stage renal disease, doubling of serum creatinine, new microalbuminuria, new macroalbuminuria and their composite) was calculated from the third year of treatment onward. Patients were divided in quintiles of SBP-coefficient of variation (SBP-CV) or mean SBP, which exhibited superimposable mean blood pressure and SBP-CV values, respectively. A progressive increase of SBP-CV was not accompanied by a parallel increase in a widely adjusted (baseline and on-treatment confounders) risk of most renal outcomes (end-stage renal disease, new macroalbuminuria, new microalbuminuria and their composite) in the subsequent on-treatment years. In contrast, the adjusted risk of most renal outcomes increased progressively from the lowest to the highest quintile of on-treatment mean SBP. Progression from lowest to highest mean on-treatment SBP, but not SBP-CV, was also associated with a less frequent return to normoalbuminuria in patients with initial micro or macroalbuminuria. Renal outcome prediction was slightly improved by the combined use of SBP-CV and mean SBP quintiles. CONCLUSION: Visit-to-visit SBP variability had no major predictive value for the risk of renal outcomes, which, in contrast, was sensitively predicted by mean on-treatment SBP. A further slight increase in prediction of renal outcomes was seen by combining on-treatment mean SBP and variability.
CRIS-Team Scopus Importer:2020-09-18

Why in 2016 are patients with hypertension not 100% controlled? A call to action - Redon, Josep; Mourad, Jean-Jacques; Schmieder, Roland; Volpe, Massimo; Weiss, Thomas W. (Journal of Hypertension, 2016)
The objective is to consider the problem of high blood pressure (BP), a leading global risk factor, associated with substantial morbidity and mortality. Despite the availability of treatment guidelines and a wide range of therapies, BP control is suboptimal in many countries. Recent data indicate that only around 40% of patients manage to achieve an adequate level of BP control. A group of international experts in the field of hypertension met in 2008 to consider this problem. The resulting white paper delivered an urgent call to action and identified six key issues for improving BP control. In 2015, a working group of investigators spontaneously undertook an action with the primary aim of considering the current hypertension management situation in Europe, to discuss whether the situation had changed since 2008 and to determine what can be learnt from the projects in other continents, such as the Canadian Hypertension Education Program, which has shown that higher levels of BP control can be achieved across a general population. The working group identified the main challenges affecting the improvement of BP control today and suggests five key actions: identify the BP treatment target of less than 140/90 mmHg for the majority of patients, simplify treatment strategies and encourage pill reduction, decrease therapeutic inertia, improve patient empowerment, and involve healthcare systems and reduce the prevailing focus on drug costs in many healthcare systems. Implementing key actions identified by the working group may help to improve achievement of better BP control across Europe.
EVALuna2:3869

Wilder's principle: pre-treatment value determines post-treatment response - Messerli, Franz H.; Bangalore, Sripal; Schmieder, Roland (European Heart Journal, 2015)
EVALuna2:3747

Will SPRINT change my practice? SPRINT: a randomised trial of intensive versus standard blood-pressure control - Ewen, Sebastian; Lobo, Melvin D.; Pathak, Atul; Schmieder, Roland; Tsioufis, Costas; Wijns, William; Mahfoud, Felix (EuroIntervention, 2016)
EVALuna2:3899